Testing the limits of lacustrine faecal lipid biomarkers as tools to document human and herbivore presence in Alaskan and Eastern Beringian landscapes - Helen Mackay; Helen L. Whelton; Joshua D. Reuther; Ben A. Potter; Mary E. Edwards; Andrew C.G. Henderson; Ian D. Bull; Elinor A. Baldwin; Charlotte Clarke; Roseanna Mayfield; Kimberley L. Davies; Maarten van Hardenbroek; et al. (Quaternary Science Reviews, 2026)

Gloeotrichia echinulata genomes from the United States are nontoxigenic and likely geosmin producers - Theo W. Dreher; Robin Sleith; Edward W. Davis; Ryan S. Mueller; Peter D. Countway (Harmful Algae, 2026)

Eating escargot: seasonal terrestrial gastropod exploitation by forest foragers in the ethnoarchaeological record of Central Africa - Karen D. Lupo; Nicolette M. Edwards (Archaeological and Anthropological Sciences, 2026)
In the prehistoric record, the presence of small-sized resources including gastropods is often viewed as a marker of increased dietary breadth, declining foraging efficiency and/or flexible subsistence patterns involving diversified foraging activities. However, researchers often find it difficult to distinguish natural gastropod accumulations from those created by anthropogenic processes. Here we report on the context, profitability and methods of the seasonal hand-collecting and processing of terrestrial gastropods based on the observations of contemporary Central African forest foragers. In this context, gastropods were exploited in response to temporary and seasonal reductions in the availability of meat and changes in labor demands that allowed women and children to engage in this activity. Analyses of faunal remains from a wet season encampment presented here shows how different kinds of gastropod processing are reflected in the ethnoarchaeological record. These analyses validate several of the characteristics currently used by archaeologists to identify anthropogenic gastropod assemblages. Overall, the degree of burning, specimen completeness, and spatial distribution of snail shells parallels that of other small-sized fauna. Some characteristics, such as shell completeness and spatial association, can reflect different preparation techniques that, in this case, may be indicators of ethnic identity and site clean-up activities. These data also have implications for how terrestrial gastropod consumption might be reflected in other kinds of archaeological evidence. The example discussed here can serve as a model to help archaeologists distinguish diversified seasonal foraging from larger-scale dietary shifts.

Editorial: Aquaculture-aided approaches for conservation and sustainable fisheries - Matthew D. Taylor; Alistair Becker; Edward V. Camp; Luis Henríquez-Antipa; Neil R. Loneragan; Kai Lorenzen (Fisheries Research, 2026)

Prescribed fire and canopy thinning reverse effects of mesophication in fire-suppressed oak savannas - Aidan C. Edwards; Jack D. Pritchard; Lars A. Brudvig (Forest Ecology and Management, 2026)

Adaptive Variation Amid High Gene Flow Across a Broad Latitudinal Gradient in the Reef‐Building Honeycomb Worm, Sabellaria alveolata - Edward J. Wilson; Antony M. Knights; Louise B. Firth; Charlotte Corporeau; Amelia Curd; Stanislas F. Dubois; Fernando P. Lima; Rui Seabra; Flavia L. D. Nunes (Molecular Ecology, 2026)
Climate change is already altering, and will continue to reshape, the persistence and spatial structure of marine populations. Understanding metapopulation connectivity and local adaptation is therefore critical for identifying both vulnerable populations and those with adaptive resilience. We applied a seascape genomics approach to investigate connectivity patterns and adaptive responses in the honeycomb worm, Sabellaria alveolata —an intertidal ecosystem engineer that supports high biodiversity and provides essential ecological functions. A total of 286 individuals from 17 sites spanning the entire latitudinal range were genotyped to assess population structure and local adaptation. Outlier analyses (BayeScan and OutFlank) identified six adaptive and 2117 neutral SNPs. Neutral SNP analysis revealed low to moderate genetic differentiation, indicating well‐connected populations. Admixture with possible ancestral gene pools in Southern Edge and Biscay populations suggests the persistence of unique genetic diversity. While connectivity is likely driven by natural larval dispersal, human‐mediated transport resulting from support vessels, aquaculture, marine debris and expanding offshore and coastal infrastructure may also facilitate gene flow, shaping observed genetic patterns. Despite this high connectivity, we detected genetic signatures of adaptation to temperature, salinity and net primary productivity, with adaptive SNPs linked to genes involved in molecular and physiological responses to these environmental factors. Our findings suggest that S. alveolata is likely resilient to climate change and other anthropogenic pressures, making it a valuable model for investigating the genetic and physiological underpinnings of marine population resilience.

Neurobehavioral and metabolic consequences of embryonic triphenyl phosphate exposure across the lifespan in zebrafish - Andrew B. Hawkey; Perry Piatos; Zade R. Holloway; Dilanaz Unal; Jonna Boyda; Richard T. Di Giulio; Edward D. Levin (Neurotoxicology and Teratology, 2026)

Volatiles in the mantle below Northern Antarctica: Insights from Deception Island volcano - Antonio Caracausi; Antonio Polo-Sánchez; Antonio M. Álvarez-Valero; Jabrane Labidi; Edward D. Young; Hirochika Sumino; Conxita Ávila; Dario Buttitta; Adelina Geyer; Paolo Randazzo (Gondwana Research, 2026)

Addressing Bias in Non‐Probability Fisheries Surveys Using Multilevel Regression and Poststratification Approaches - Zachary Radford; Wendy Edwards; Samantha Hook; Bridgid Bell; Rebecca Mills; Grace Farrell; Martin J. Genner; Stephen D. Simpson; Kieran Hyder (Fish and Fisheries, 2026)
Quantifying harvest of fish stocks is challenging as census data are often unavailable, so surveys are required. Traditional probability‐based surveys use random sampling to obtain representative data that can be scaled to estimate total impact. However, these surveys are costly, so cheaper, non‐probability, citizen science surveys of self‐selected participants are becoming commonplace. Respondents in these surveys may not be representative and inclusion probabilities are unknown, making weighting difficult. This resembles exit polls, which successfully predict election outcomes using Multi‐level Regression and Post‐stratification (MRP), but this has not been tested in fisheries. This study applied MRP to quantify UK recreational sea angling (RSA) participation and catches using data from the UK Sea Angling Diary Project. This represents a ‘worst‐case’ scenario, as there is no sampling frame and no mandatory reporting. Five Bayesian multi‐level models were fitted to two survey datasets: one quantifying participation and days fished, and another location, numbers, and weight of fish caught. Predictions were post‐stratified using UK census data. Estimates from the traditional reweighting and MRP were compared, and a simulation approach was used to assess the accuracy and precision of the two methods. MRP reduced self‐selection bias and improved estimates in under‐represented groups, producing a 40% and 61% improvement for participation and catch, respectively. Average annual UK RSA participation was estimated to be 688,000 anglers, with 6.1 million days fished. Annual catch estimates were 32.4 million fish, weighing 14,876 t. This study demonstrates the value of MRP for reducing bias when analysing and scaling non‐probabilistically collected survey data.

Simulation modelling as a tool to guide control strategies for foot and mouth disease in an endemic country: Nusa Tenggara Barat, Indonesia 2023–2024 - Y. Yupiana; M.A. Stevenson; M. Edwards; R.V. Ekowati; Ermawanto; I. Permatasari; R. Morita; S. Yulianti; Nurhayati; T.D. Utami; D. Nugroho; H.P. Kurniawan; et al. (Preventive Veterinary Medicine, 2026)

Life Course Dietary Insulinemic and Inflammatory Potential and Risk of Type 2 Diabetes in U.S. Women: A Prospective Cohort Study - Yin Zhang; Mingyang Song; Molin Wang; Emily Riseberg; Dong D. Wang; Deirdre K. Tobias; Fred K. Tabung; A. Heather Eliassen; Stephanie A. Smith-Warner; Qi Sun; Eric B. Rimm; Meir J. Stampfer; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Schwertmannite transformation under strongly-acidic conditions favoring jarosite precipitation: The effect of arsenic(V) and temperature - Neal Bailey; Niloofar Karimian; Scott G. Johnston; Mona Hosseinpour Moghaddam; Dane Lamb; Edward D. Burton (Journal of Hazardous Materials, 2026)

Rewilding reshapes gut microbiomes and parasite exposure in European bison: a 17‑month release from Wilder Blean - William JS Edwards; Yaseen Majid Salman Al-Adilee; Constance Denoyelle; Hannah Mackins; Richard A. Griffiths; Anastasios D. Tsaousis (Journal for Nature Conservation, 2026)

“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Retraction Note: Neurotoxic effects of the HCV core protein are mediated by sustained activation of ERK via TLR2 signaling - Amy D. Paulino; Kiren Ubhi; Edward Rockenstein; Anthony Adame; Leslie Crews; Scott Letendre; Ronald Ellis; Ian P. Everall; Igor Grant; Eliezer Masliah (Journal of NeuroVirology, 2026)

Shoulder Kinematic and Muscle Activity Compensations to Scapular Stabilizer Weakness: An Optimal Control Framework - Matthew S. Russell; Daanish M. Mulla; Peter J. Keir; Edward K. Chadwick; Dimitra Blana; Janessa D. M. Drake; Jaclyn N. Chopp-Hurley (Annals of Biomedical Engineering, 2026)
Purpose Shoulder kinematic and muscular redundancy promotes considerable variability, obscuring possible insights into neuromuscular control and compensation mechanisms for muscle weakness or fatigue. The current study harnessed recent advancements in optimal control formulations for computational musculoskeletal models to determine potential neuromuscular control strategies to compensate for isolated muscle weakness. Methods A computational shoulder model characterized by independent clavicular, scapular, and humeral kinematics and 138 muscle elements was used. Optimal control-predicted thoracohumeral elevation kinematics were validated against published empirical kinematics. Force-generating capacity of the upper trapezius, middle trapezius, and lower trapezius, and serratus anterior were individually limited to 75%, 50%, and 25% maximal capacity to generate subsequent optimal control predictions of scapulothoracic kinematic changes associated with muscle weakness. Combined limited maximal force-generating capacity of lower trapezius and serratus anterior was also explored. Results Model-predicted scapulothoracic kinematics showed good agreement with reference data, yet some significant differences were identified below 55° thoracohumeral elevation. Fatigue-mediated kinematic changes were most apparent during sagittal plane elevation. Serratus anterior weakness displayed the largest scapulothoracic kinematic changes at all thresholds of limited force-generating capacity. It also prompted the largest compensatory muscle activity changes from other shoulder muscles, while upper trapezius weakness prompted very little compensatory changes in muscle activity. Conclusion Optimal control simulations were used to identify potential compensation mechanisms for shoulder muscle weakness and predict their effects on scapular kinematics. Findings suggest that thoracohumeral elevation in the scapular plane displayed less trapezius coactivity, both when ‘weakened’ and ‘unweakened.’ Thus, scapular plane tasks may isolate serratus anterior, while frontal plane tasks may achieve more balanced coactivation.

Ensuring adaptability and applicability of long-term contaminant monitoring initiatives: A discussion of NOAA’s National Mussel Watch Program current practices and future approaches - N. A. Castillo; L. M. Swam-Jaramillo; M. M. Rider; A. Morozova; K. L. Kimbrough; E. D. Davenport; M. A. Edwards; F. Arzayus; D. A. Apeti (Environmental Monitoring and Assessment, 2026)

Multi-fidelity data-driven approach to operational guidance - Samuel J. Edwards; Michael D. Levine (Ocean Engineering, 2026)

Weathering of scorodite by root exudates: Arsenic dissolution and solid-phase speciation - Sepide Abbasi; Dane Lamb; Girish Choppala; Edward D. Burton; Marjana Yeasmin; Edwin L.H. Mayes; Mallavarapu Megharaj (Journal of Hazardous Materials, 2026)

Correction: Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

Aquaculture-aided aquatic restoration and conservation: Highlights, challenges, and key lessons from global case studies - Emilee D. Benjamin; Casey A. Murray; Ricardo Riquelme; Edward Camp; Andrew Jeffs; Joshua Patterson; Aaron Pilnick; Jennifer Gumm; Taylor Lipscomb; Gesica Aroca; Marcela Ávila; Holly Richards; et al. (Fisheries Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Observation of Rockfall in the Thermal Infrared - Edward C. Wellman; Kirk W. Schafer; Chad P. Williams; Greatness H. Ojum; Julia J. Potter; Leonard D. Brown; Benjamin Meyer; Bradley J. Ross; John Kemeny (Rock Mechanics and Rock Engineering, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Oases of endemism: Regional aquifer desert springs serve as biodiversity hotspots preserving vulnerable endemic taxa in the Great Basin and Mojave Desert regions - Matthew J. Forrest; Donald W. Sada; Matthew S. Edwards; Robert K. Burton; Richard D. Norris (Limnology and Oceanography, 2026)
Spring ecosystems in arid regions often serve as crucial biodiversity hotspots by providing some of the only reliable sources of surface water. However, anthropogenic activities and climate change have severely degraded spring ecosystems worldwide, emphasizing the need for large‐scale multidisciplinary studies informing conservation efforts. Here, we analyzed characteristics of 1121 widely dispersed springs within the Great Basin and Mojave Desert regions, USA to assess the distribution of endemic animal taxa relative to hydrological, geochemical, and ecological parameters. To our knowledge this is the largest original dataset of springs that has been examined in this manner. Our results revealed that the three broad classes of springs: regional aquifer thermal springs, local aquifer cold springs, and local aquifer geothermal springs can be distinguished by their environmental and physicochemical parameters, taxa present, persistence, and natural and human perturbations. Notably, regional aquifer thermal springs support disproportionate numbers of endemic taxa, likely reflecting their stability and longevity. These patterns are particularly striking considering that these springs have been subjected to extreme anthropogenic exploitation and modifications for centuries and frequently support non‐native taxa. Conversely, local aquifer cold springs, which are often highly disturbed and less persistent, support proportionately fewer endemic taxa. The high abundance of endemic taxa in regional aquifer thermal springs indicates that they represent critical biodiversity hotspots, and efforts to conserve and restore these important ecosystems should be major priorities.

Why controlling for habitat amount is critical for resolving the fragmentation debate - Lenore Fahrig; Carmen Galán‐Acedo; Brandon P. M. Edwards; Andrew K. Habrich; Amanda E. Martin; Cécile H. Albert; Victor Arroyo‐Rodríguez; Allison D. Binley; Jonathan R. Cole; Jessica K. Lockhart; Scott E. Nielsen; Federico Riva; et al. (Conservation Biology, 2026)

Ecological risks and emergent governance needs in seaweed aquaculture - Isabel R. Gregr; Rebecca G. Martone; John D. Driscoll; Edward J. Gregr (Journal of Applied Phycology, 2026)
Seaweed aquaculture is an expanding industry with potential to benefit the climate, food security, and local economies. However, as the industry expands, there is a need to assess potential negative ecological effects and ensure they are properly mitigated. In this report, we examine the state of knowledge on potential negative ecological effects of seaweed aquaculture, drawing from peer-reviewed literature and global regulatory practices. Using British Columbia (BC), Canada, as a case study, we assess the risks from these effects and the suitability of the existing regulatory framework for avoiding them. To contextualize the BC example, we also considered the adequacy of seaweed aquaculture regulations in Europe, Asia, North and South America, and Africa. This global comparison reveals a lack of seaweed-specific policies, weak biosecurity measures, and limited cross-agency collaboration. In BC and elsewhere, seaweed aquaculture regulation is largely indirect, relying on customised license conditions based on tangential legislation rather than on sector-specific, enforceable regulations. This results in inconsistent data, unclear management objectives, and limited indicators of ecological impact. All jurisdictions we examined would benefit from specific seaweed aquaculture policy, seaweed-specific regulations with clear monitoring requirements, improved regulatory coordination, and stronger biosecurity measures. Baseline environmental assessments and ecosystem monitoring would help ensure healthy, resilient coastal ecosystems as the industry develops. These findings provide globally relevant guidance for managing the potential negative ecological effects of this growing industry. Our case study offers a transferable framework for identifying local regulatory gaps in other jurisdictions and developing policy to support sustainable seaweed aquaculture.

Nitrogen partitioning between plant species and soil microbes in alpine heath - Ellen L. Fry; Jonathan R. De Long; Edward Ayres; René van der Wal; Richard D. Bardgett (Soil Biology and Biochemistry, 2026)

Reflectance spectroscopy (200-4200 nm) of the red-sloped C2 carbonaceous chondrites MET 00432, Tagish Lake, Tarda, and WIS 91600 (“CT” grouplet) - Edward A. Cloutis; Devin L. Schrader; Daniel M. Applin; Tomoki Nakamura; Timothy D. Glotch; Takahiro Hiroi; Moe Matsuoka; Michael E. Zolensky; Joshua P. Emery; Kristi M. Peters (Icarus, 2026)

Minor and rare earth element distribution in the Pennsylvanian (Duckmantian) Amos coal, western Kentucky - James C. Hower; Vivian A. Edwards; Tonya D. Morgan; Shelley D. Hopps; Shifeng Dai; Harold H. Schobert (International Journal of Coal Geology, 2026)

Building a 3D Digital Twin for Geotechnical Monitoring at San Xavier Mine - Nilufer K. B. Akbulut; Angelina Anani; Leonard D. Brown; Edward C. Wellman; Sefiu O. Adewuyi (Rock Mechanics and Rock Engineering, 2026)

Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)
High frequency turbulent data from sonic anemometers and other ancillary information collected at multiple levels on several meteorological flux towers located at two coastal sites are used to study velocity and scalar (temperature and humidity) structure–function parameters over heterogeneous surfaces in an area of complex coastal terrains. Understanding of such parameters has important applications for studies on wave propagation in a turbulent atmosphere. One observational site was located on the Outer Banks near the town of Duck, North Carolina, with data from the CASPER-East Program (October–November 2015). The second site was located near the town of Ferryland, Newfoundland, Canada, with data from the C-FOG (Coastal-Fog) field campaign (September–October 2018). These measurements allowed studies of structure parameters and other statistics for different footprints, including relatively smooth sea surface conditions and aerodynamically rough dry inland areas for both stable and unstable stratifications. The coastal land cover discontinuity for onshore and offshore winds leads to a thin internal boundary layer (IBL) that could often be resolved by the instrumented towers. The drag coefficient, Bowen ratio, and diurnal variation of sensible heat flux were found to be coastal IBL markers. Our study shows that lower values of the dimensional structure parameters are associated with higher altitudes, smooth surfaces (i.e., over water, outside onshore IBL) and stable stratification (e.g., nocturnal boundary layer), ceteris paribus. In particular, observations showed that the structure parameters over land footprint areas (inside the onshore IBL) can be an order of magnitude larger than over the sea surface due to the change of aerodynamic and thermal properties of the surface. This study also discusses the applicability of Monin–Obukhov similarity theory (MOST) for the velocity and scalar structure parameters in the coastal environment for both stable and unstable conditions. While surface inhomogeneities and the complexity of the coastal landforms nominally violate assumptions underlying MOST, our observations show that the nondimensional structure parameters obey MOST reasonably well for all measurement levels, stability condition, and wind direction. In addition, we suggest a new variance-based hybrid scaling for the structure parameters that overcomes some of the shortcomings of the traditional approach (e.g., self-correlation and ambiguity of the dimensionless temperature structure parameter for near-neutral conditions).

Evaluation of siRNA-mediated knockdown of heat shock protein 16.2 in adult Acropora cervicornis - Edward P. Gniffke; Benjamin D. Young; Keir J. Macartney; Michael S. Studivan; Ian C. Enochs; Erin E. Easton (Frontiers in Marine Science, 2026)
Acropora cervicornis is a critically endangered Caribbean coral species facing a precipitous decline due to disease and thermal bleaching. To combat the loss of ecologically important reef-building corals, novel molecular approaches can be used to understand mechanisms of resilience and ultimately provide a means to modulate coral performance. In this study, we tested a recently developed method for gene knockdown in adult corals that utilizes short interfering RNAs (siRNAs) and the RNA interference pathway. The Heat Shock Protein 16.2 (HSP16.2) gene in fragments of adult A. cervicornis was targeted for knockdown using a single siRNA construct. RT-qPCR analysis of HSP16.2 gene expression was performed between filtered seawater, no template control siRNA (NTC), and siRNA targeting HSP16.2 across four genotypes of A. cervicornis with known differences in thermal susceptibility (two heat-tolerant and two heat-susceptible genotypes). There was no significant difference in HSP16.2 gene expression due to the treatment of HSP16.2 siRNAs versus controls, but we did identify a single genotype-driven effect that corroborates evidence that A. cervicornis heat tolerance is driven largely by genotype. No difference in photophysiological performance or mortality was observed between experimental and control treatments. There were, however, some differences in mortality and HSP16.2 expression among genotypes. Our results reveal that siRNA-mediated knockdown was not successful for this species and gene and thus further optimization is needed prior to broader applicability of siRNA-mediated knockdown in corals. We provide an assessment of potential methodological improvements to support the development of future reverse-genetics studies in corals.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Timing and amplitude of hydroclimate changes during the last glacial cycle in southwestern North America - Simon D. Steidle; Yuri Dublyansky; Marco Roman; Gina E. Moseley; Kathleen A. Wendt; R. Lawrence Edwards; Christoph Spötl (Quaternary Science Reviews, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

Hormonal and behavioral variation during release from reproductive suppression in an extreme cooperative breeder - Phoebe D. Edwards; Juweriah Munir; Ilapreet Toor; Bruce D. Goldman; Rudy Boonstra; Rupert Palme; Gabriela F. Mastromonaco; Melissa M. Holmes (Mammalian Biology, 2026)

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Periphyton microbial communities of artificial streams impacted similarly by distinct phosphorus enrichment patterns - Anja Skrobonja; Christine Lundsgaard-Nielsen; Edward M. Krynak; Chris T. Parsons; Josh D. Neufeld; Adam G. Yates (Water Research, 2026)

First record of Cassiopea xamachana ephyrae from the wild in India, with insights into its life history and development - L. Ranjith; Raju Saravanan; K.S. Sobhana; I. Jagadis; S. Ramkumar; C. Kalidas; D. Linga Prabu; M. Kavitha; P. Nevathitha; A. Mathan Babu; D. Sarathapriya; L. Loveson Edward; et al. (Regional Studies in Marine Science, 2026)

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Extracellular enzyme activities under adaptive multi-paddock and conventional grazing in grassland soils of western Canada - Dauren Kaliaskar; Edward W. Bork; Cameron N. Carlyle; Bharat M. Shrestha; Timm F. Döbert; Cole D. Gross; Upama Khatri-Chhetri; Mark S. Boyce; Scott X. Chang (Pedobiologia, 2026)

Performance evaluation and methods comparison of transcriptomic-based approaches for the characterization of wastewater treatment effluent - Adam D. Biales; Morgan S. Hu; David C. Bencic; Mary Jean See; Susan T. Glassmeyer; Edward T. Furlong; Julia M. Stelman; Weichun Huang; Dana W. Kolpin; Marc A. Mills; Laura D. Brunelle; Angela L. Batt; et al. (Environmental Pollution, 2026)

Subduction-driven mantle flow beneath and around the Philippine Sea plate from seismic anisotropy - Jonathan Wolf; Frederik Link; Maureen D. Long; Edward Garnero; John D. West (Earth and Planetary Science Letters, 2026)

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Cardiovascular risk factors and vascular neuropathological findings in primary age-related tauopathy versus Alzheimer’s disease - Lisa Y. Xiong; Myuri Ruthirakuhan; Si Won Ryoo; Che-Yuan Wu; Jodi D. Edwards; Jennifer S. Rabin; Maria Carmela Tartaglia; Sandra E. Black; Julia Keith; Walter Swardfager (GeroScience, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Patterns of plastic occurrence during the pre- and post-Super Typhoon Rai (Odette) event in Olango Island Wildlife Sanctuary (OIWS), Philippines - Apple AJ D. Langcamon; Maria Kristina O. Paler; Emiko Fujita; Yutaka Kameda; Mark Edward M. Walton; Martin W. Skov; Jan G. Hiddink; Evelyn B. Taboada (Marine Pollution Bulletin, 2026)

Goethite as an antimony host-phase: Atomic-scale retention mechanisms and the selectivity of commonly-applied extraction schemes - Mona Hosseinpour Moghaddam; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mohammad Rastegari; Edward D. Burton (Journal of Hazardous Materials, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Revealing the Impact of Polystyrene Nanoplastics on Gill Tissues of the Intertidal Clam, Gafrarium Divaricatum (Gmelin, 1791) using Transcriptomics Approach - Edward Inpent Campal; Ezekiel Targain; M. Harshavarthini; Shubra Singh; Kiran D. Rasal; Arvind Sonwane; Rupam Sharma; Mukunda Goswami; Naresh S. Nagpure; Manoj Pandit Brahmane (Marine Biotechnology, 2026)

Metabolic cost of external work: a novel CPET parameter optimises characterisation of exercise performance in obese individuals - Jennifer J. Rayner; Rebecca R. Chamley; Robert Barker Davies; Oliver O’Sullivan; Peter Ladlow; Alex N. Bennett; Edward D. Nicol; Oliver J. Rider; David A. Holdsworth (European Journal of Applied Physiology, 2026)
Purpose Both obesity and cardiorespiratory fitness are crucial determinants of symptoms and prognosis. However, interpreting the gold-standard cardiopulmonary exercise test (CPET) is complicated by increasing body size and varying body composition. We hypothesised that the ‘metabolic cost of external work’ (or oxygen uptake (ml/min)/workload (Watts); V̇O 2 /W), a body weight-independent determinant of endurance capacity, would reflect metabolic health more accurately than V̇O 2 alone. Methods A test cohort of 160 fit individuals underwent anthropomorphic and metabolic assessment, maximal bicycle ergometer CPET, and six-minute walk test (6MWT). V̇O 2 /W was calculated at VT1 and peak. The performance of V̇O 2 /W was validated in 62 older, less fit individuals, undergoing the same protocol. 24 obese volunteers were assigned a weight loss intervention, and the impact on V̇O 2 /W examined. Results In both test and validation cohort, V̇O 2 /W at VT1 and peak correlated with 6MWT distance, more strongly than standard CPET parameters. Including V̇O 2 /W improved the accuracy of predicting 6MWT distance. V̇O 2 /W correlated with BMI, insulin sensitivity and waist-to-hip ratio. Metabolic cost falls with weight loss, in parallel to metabolic and functional improvements, in contrast to other CPET parameters. Conclusion Metabolic cost is strongly associated with functional capacity and metabolic health across a range of body weight and fitness, outperforming standard CPET metrics. It is a simple measure which may improve our assessment of the extent to which exertional symptoms are determined by metabolic factors in an individual, and thereby target the most appropriate intervention to those who will benefit most. Graphical Abstract

Meal Preparation Strategies and Lack of Food Security Among Unaccompanied Latino Migrant Farmworker Youth in Georgia and Florida: A Mixed-Methods Approach - Fiorella L. Carlos Chavez; Kaleea R. Lewis; Bethany A. Moore; Tracy Tang; Edward D. Vargas; Joan M. Hermsen; Rebecca E. Lee; Youngbin Lee; Irma A. Arteaga; Khushi Bypan; J. Sanford Rikoon; Thomas A. Arcury (Journal of Agromedicine, 2026)

Phosphorus–goethite interactions: A review of mechanisms, environmental implications, and industrial relevance - Niloofar Karimian; Mark I. Pownceby; Edward D. Burton; Andrew J. Frierdich (Science of The Total Environment, 2026)

Pleistocene speciation and isolation-by-distance within North American mud and rainbow snakes - Edward A. Myers; Alexander D. McKelvy; Dirk J. Stevenson; Frank T. Burbrink (Molecular Phylogenetics and Evolution, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Hydroxyl (OH) radical oxidation of surfactant films formed from woodland aerosol particulate material at the air-water interface - Edward J. Stuckey; Rebecca J.L. Welbourn; Tobias W.D. Robson; Connor R. Barker; Matthew Wilkinson; James I.L. Morison; Martin D. King (Atmospheric Environment, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Implications of depensation on oyster recruitment, population collapse, restoration, and sustainable fisheries management - Edward V. Camp; William Pine; William R. Casola; Emilee D. Benjamin; Chad Palmer; Kotryna Klizentyte; Kai Lorenzen (Fisheries Research, 2026)

Corridors and Reservoirs: An Analysis of Inter‐Andean Historical Biogeography - Sophie G. Dauerman; Chase D. Brownstein; Lan Wei; Anri Chomentowska; Patrick W. Sweeney; Erika J. Edwards (Journal of Biogeography, 2026)
Aim The Andes are a global biodiversity hotspot, and the formation of this mountain range is linked to the rapid diversification of many lineages across the Tree of Life. The high species richness of the Andes might also act as a reservoir for lineages to disperse across the South American continent. Recent syntheses of Andean geological history and the accumulation of phylogenetic studies of different Andean clades present an opportunity for a synthesis of the historical biogeography of the Andean biota. Location The Andes. Taxon All taxonomic groups. Methods We conducted a meta‐analysis of phylogenetic studies, scoring disjunction events within and out of the Andes inferred from biogeographic reconstructions. Results We show that, across time and clades, dispersals among regions in the Andes are approximately as common as dispersals out of the Andes. The greatest number of extra‐Andean disjunctions originated from the northern Andes, even though the northern section of this mountain range is the most recently uplifted. There has been continued bi‐directional movement within the Andes over the last 50 million years. Dispersals northward occur at a slightly, but significantly, greater rate than dispersals southward. Andean plant crown clades tended to be older than animal crown clades, which almost exclusively originate in the last 30 million years. Main Conclusions Our findings reveal that the Andes have equally acted as a reservoir and a corridor of biodiversity across clades with widely divergent dispersal strategies.

Correction: Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)

Triple-oxygen isotopic evidence of prolonged direct bioleaching of pyrite with O2 - Issaku E. Kohl; Bryan Killingsworth; Karen Ziegler; Edward D. Young; Max L. Coleman (Earth and Planetary Science Letters, 2025)

Quest for Orthologs in the era of Data Deluge and AI: Challenges and Innovations in Orthology Prediction and Data Integration - Sina Majidian; Armin Hadziahmetovic; Felix Langschied; Stefano Pascarelli; Silvia Prieto-Baños; Jorge Rojas-Vargas; Lars Arvestad; Jitender Cheema; Salvatore Cosentino; Ingo Ebersberger; Elena Kuzmin; Yannis Nevers; et al. (Journal of Molecular Evolution, 2025)
The rapid advancement of DNA sequencing technologies and computational algorithms has led to an unprecedented surge in genomic data, driven by several large-scale sequencing projects worldwide. Orthology plays a crucial role in understanding evolutionary patterns of genes and their functions. At the last Quest for Orthologs meeting (Montréal, Canada—2024), we discussed recent advances in orthology inference, with a focus on the impact of artificial intelligence (AI), protein structures, RNA splicing isoforms, and protein domain evolution together with other evolutionary considerations. A long-standing challenge in the field is the functional annotation of paralogs, for which we present novel approaches. The meeting also emphasised strategies for integrating diverse genetic features into the concept of orthology, encouraging frameworks that account for elements like alternative splicing, domain organisation, and regulatory sequences. We discuss various applications of orthology and paralogy to environmental research, agriculture, and comparative genomics. Additionally, we report recent progress in orthology inference methodologies and resources. This work represents a collaborative synthesis of insights and innovations presented at the 8th Quest for Orthologs meeting, highlighting current progress while outlining future directions for orthology research.

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

Angiotensin II, miR-34a, and AGTRAP crosstalk in arterial smooth muscle cells - Maria Cristina Florio; Sara Sileno; Liqun Jiang; Marco D’Agostino; Sunayana Begum Syed; Laura Monteonofrio; Mirko Baranzini; Chiara Prampolini; Federica Macrì; Manuel Casaburo; Nadia Fanotti; Stefania Castiglione; et al. (GeroScience, 2025)
Arterial aging is associated with enhanced angiotensin II (Ang II) signaling via Ang II type 1 receptor (AT1R) and with microRNA-34a (miR-34a) increased expression. AT1R-associated protein (ATRAP/Agtrap) binds to AT1R, promotes its internalization, and inhibits Ang II signaling. This study addresses the hypothesis that miR-34a targets ATRAP/Agtrap and enhances Ang II pro-inflammatory signaling via AT1R in arterial vascular smooth muscle cells (VSMC). Our results show that miR-34a exhibits an age-associated increase in Rhesus monkey’s common carotid artery and rat aorta. Further, AGTRAP protein expression is lower in old rat VSMC and in old mice aorta. Ang II enhances miR-34a in old rat VSMC and human aortic smooth muscle cells (HASMC), and inhibits AGTRAP and sirtuin 1 (SIRT1) mRNA/protein expression. In miR-34a-overexpressing HASMC, AGTRAP and SIRT1 mRNA/protein decrease, and these effects are rescued by AGTRAP forced expression. Moreover, miR-34a directly targets AGTRAP and AGTRAP downmodulation further enhances miR-34a expression decreasing SIRT1 in HASMC. Finally, Ang II and miR-34a induce the upregulation of pro-inflammatory genes, interleukin (IL)-6, cyclooxygenase 2 (COX2), monocyte chemoattractant protein-1 (MCP-1), and milk fat globule-epidermal growth factor 8 (MFGE8) in HASMC, and this effect is abolished by AGTRAP forced expression. In conclusion, Ang II upregulates miR-34a, activating a negative feedback loop on AGTRAP that reinforces Ang II signaling. The age-associated AGTRAP downmodulation in central arteries and VSMC underlies a potential miR-34a/AGTRAP role in vascular aging.

Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)
Introduction Species distribution models (SDMs) are increasingly used in fisheries science to understand species’ spatial patterns and improve stock assessments. Method This study developed SDMs for eulachon smelt ( Thaleichthys pacificus ), a threatened, demersal forage fish often caught as bycatch in the United States West Coast ocean shrimp trawl fishery. Using ten years of observer data (2012–2021, n=19,749 with 25.4% being zeros), the study assessed the influence of static (e.g., substrate) and dynamic (e.g., ocean temperature, currents) environmental variables on eulachon abundance. Results The best-performing SDM included near-bottom temperature and current data, outperforming SDMs using only surface variables. Eulachon abundance peaked at ~150 m depth, especially over gravel substrates, and during nighttime. Although none of the SDM-based abundance indices significantly correlated with the Columbia River stock assessment index, bottom-based SDMs showed stronger alignment with the stock assessment (R=0.61, p=0.08 & R=0.62, p=0.07). Discussion Management implications are significant. Rock habitats were associated with higher eulachon bycatch, and vessels can use bottom-typing tools to avoid them. Also, delaying the season opener could reduce bycatch, as eulachon catch was reduced by 0.0109 mt per trawl over the interquartile range of day of the year. These findings can inform Best Management Practices (BMPs), which have historically led to regulatory changes such as the adoption of excluder grates and LED lights. Overall, incorporating near-bottom oceanographic data greatly enhanced predictive performance, especially for demersal species like eulachon. These mechanistic SDMs can be projected forward, aiding future management amid changing ocean conditions. While some discrepancies remain, this approach offers promising insights for adaptive fishery management and conservation of imperiled species like eulachon.

Monitoring Resilience in Coastal Systems: A Comprehensive Assessment - Emma Imen Turki; Elena Ojeda; Ernesto Tonatiuth Mendoza; Gabriela Medellín; Timothy D. Price; Edward Salameh; Xiao Hua Wang; Li Li; Gemma L. Franklin; Alec Torres-Freyermuth (Journal of Marine Science and Engineering, 2025)
This work, conducted within the framework of the international network CRESTE (Coastal Resilience Using Satellites), examines the role of resilience in monitoring coastal evolution across diverse environments in Europe (France, The Netherlands), America (Mexico), Asia (China), and Oceania (Australia). High-resolution morphological datasets, derived from in situ measurements and video monitoring systems, were analyzed for wave- and tide-dominated beaches influenced by both climatic drivers and anthropogenic pressures. Findings indicate that beach resilience is strongly linked to system resistance, which depends on the intensity of climate drivers, including storm frequency, and site-specific conditions related to the type of sediment and its availability, and the presence of anthropogenic activities including coastal structures (e.g., Normandy, Yucatán) and shoreface nourishments (Netherlands). In Batemans Bay (Australia) and Hangzhou Bay (China), assessing the resilience is particularly challenging due to the combined influence of multiple drivers, fluvial inputs, and urban development. Accurate monitoring of coastal resilience across timescales requires accounting for long-term morphological, ecological, and socio-economic processes. This can be enhanced through satellite observations, which, when integrated with in situ measurements, numerical modeling, and artificial intelligence, support a more comprehensive assessment of resilience and refine projections under future climate change and sea-level rise; representing a key focus for further works.

Hydrological variability in the Black Sea region during the last 670,000 years recorded in multi-proxy speleothem records from northern Türkiye - F. Held; H. Cheng; R.L. Edwards; T. Kipfer; O. Tüysüz; K. Koç; S. Affolter; D. Fleitmann (Quaternary Science Reviews, 2025)

Antimony(V) uptake by feroxyhyte (δ′-FeOOH): Insights from X-ray absorption spectroscopy and selective extractions - Mona Hosseinpour Moghaddam; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mohammad Rastegari; Edward D. Burton (Journal of Hazardous Materials, 2025)

Comparing Navcam dust devil detections to transient daytime convective vortex signatures in REMS pressure and ultraviolet data - Emily L. Mason; Scott D. Guzewich; Christopher Edwards; Álvaro Vicente-Retortillo; Daniel Viúdez-Moreiras (Icarus, 2025)

Heat stress analysis using RTMA over heatwave regions in India - Ch. Sridevi; M. V. S. Ramarao; Ashish Routray; B. Tarakesh Lakshman; K. B. R. R. Hari Prasad; Suryakanti Dutta; D. Srinivas; Edward Colón; Annette Gibbs; Manuel Pondeca; V. S. Prasad (Theoretical and Applied Climatology, 2025)

17Oexcess in Devils Hole calcite: an indicator of equilibrium fractionation and paleo moisture sources - Hagit P. Affek; Eugeni Barkan; Yael Tal; Simon D. Steidle; Kathleen A. Wendt; Christoph Spötl; R. Lawrence Edwards; Ekaterina Fishman; Yuri Dublyansky (Earth and Planetary Science Letters, 2025)

Transformation of triclinic birnessite induced by vermicompost-enriched soil organic matter - Oluwadunsin Oyetunji; Oliver A.H. Jones; Suresh Subashchandrabose; Edward D. Burton; Dane Lamb (Chemical Geology, 2025)

Unveiling the Biocidal Effect of Giant Milkweed, Calotropis gigantea (L.) W.T. Aiton On the Cassava Mealybug, Phenacoccus manihoti Matile-Ferrero - K. Mounisha; Y. S. Johnson Thangaraj Edward; M. Kannan; S. Vellaikumar; D. Uma (Journal of Crop Health, 2025)

The archeological implications of handling effort and technological requirements on the exploitation of canarium and African oil palm among tropical Africa populations - Nicolette M. Edwards; Dave N. Schmitt; Karen D. Lupo (Archaeological and Anthropological Sciences, 2025)

Drifting fish aggregation devices as a tool to study oceanic marine protected areas - Arthur Blanluet; Edward T. Game; Kydd Pollock; Nicholas H. Wolff; Jason D. Everett; Sandra Neubert; Daniel C. Dunn; Anthony J. Richardson (Fisheries Research, 2025)

P28-16 Assessment of Motor Activity in Rodents: Positive Control Validation using the VivaMARS Mobile Activity Rack System (MARS) - S. Beck; D. Myers; D. Stannard; S. Edwards; A. Hedge; S. Renaut (Toxicology Letters, 2025)

Persisting neurobehavioral consequences of gestational exposure to cadmium and benzo[a]pyrene in rats - Andrew B. Hawkey; Rongxi Fan; Kala Nwachukwu; Shutong Liu; Anas Gondal; Sarabesh Natarajan; Jade Porter; Melissa Marchese; Giuliana Mesarick; Megan Stout; Corinne Wells; Amir H. Rezvani; et al. (Neurotoxicology and Teratology, 2025)

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

Identification of new genomic loci for seed protein and oil content in the soybean pangenome using genome-wide association and haplotype analyses - Tri D. Vuong; Guangqi He; Haifei Hu; Babu Valliyodan; Dongho Lee; Philipp E. Bayer; William T. Schapaugh; Rene Hessel; David Edwards; Henry T. Nguyen (Theoretical and Applied Genetics, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

A data-driven index for evaluating BMP water quality performance - Elizabeth A. Fassman-Beck; Edward D. Tiernan; Ka Lun Cheng; Kenneth C. Schiff (Water Research, 2025)

Biogeochemical controls on iron speciation and cycling across upland to shoreline gradients in freshwater and estuarine coastal soils (Lake Erie and Chesapeake Bay, United States) - Lucie Stetten; Maxim I. Boyanov; Edward J. O'Loughlin; Shan Pushpajom Thomas; Kathleen R. Beilsmith; Roberta B. Peixoto; Fausto Machado-Silva; Donnie J. Day; Stephanie J. Wilson; Timothy W. Vugteveen; Allison N. Myers-Pigg; Opal Otenburg; et al. (Science of The Total Environment, 2025)

A novel control volume methodology to constrain ecosystem nutrient cycling within a tidal freshwater river - D.R. Mackenzie; D.R. Tait; J. Sippo; A. Ferguson; Rao S; C. Ralph; B. Stewart; M. Call; M. Reading; M. Andskog; D. Laicher-Edwards; D.T. Maher (Estuarine, Coastal and Shelf Science, 2025)

An economical and rapid method of comet assay and micronucleus cytome assay for genotoxicity biomonitoring using clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Edward Inpent Campal; Shubra Singh; Nalini Poojary; Martin Xavier; Kiran D. Rasal; Madhuri S. Pathak; Naresh S. Nagpure (DNA Repair, 2025)

Nitrogen addition alters interactions between ectomycorrhizal host trees and fungal communities in a mixed mycorrhizal tropical rainforest - Georgia S. Seyfried; Joseph D. Edwards; James W. Dalling; Angela D. Kent; Wendy H. Yang (Plant and Soil, 2025)

Genomic evidence reveals a lack of evolutionary differentiation among grasshopper sparrow (Ammodramus savannarum) subspecies - Céline M. Carneiro; W. Alice Boyle; James A. Cox; Juan C. Oteyza; Janet M. Ruth; Edward L. Braun; Jerald D. Noble; James D. Austin (Conservation Genetics, 2025)

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Effects of anaerobic digestion on the dewaterability of sonicated biosludge - Sergio Luna Nino; Torsten Meyer; Elizabeth A. Edwards; D. Grant Allen (Journal of Environmental Management, 2025)

Vertebral elemental composition reveals ontogenetic changes in habitat use in a Northeast Atlantic mesopredator shark - Neil D. Cook; Ana Samperiz; Morten Andersen; Edward Inglis; Marc-Alban Millet; Jo Cable; Sarah E. Perkins (Estuarine, Coastal and Shelf Science, 2025)

Interactive effects of crop types and nitrogen sources on N2O emissions in a cool humid climate - Joannie D’Amours; David E. Pelster; Martin H. Chantigny; Andrew C. VanderZaag; Erin L. Smith; Gilles Bélanger; Émilie Maillard; Marie-Élise Samson; Edward G. Gregorich; Denis A. Angers; Isabelle Royer; Marie-Noëlle Thivierge (Plant and Soil, 2025)
Aims Perennial forages in rotation with annual crops can improve agricultural resilience by increasing soil organic carbon. However, how nitrogen (N) sources interact with rotation diversity to influence soil nitrous oxide (N 2 O) emissions is not well understood. Methods During three snow-free seasons, N 2 O emissions, crop yields, and ancillary variables were measured at three experimental sites with contrasting soil textures (silty clay and sandy loam) in eastern Canada. Using a split-plot design, we compared a corn ( Zea mays L.)-soybean ( Glycine max [L.] Merr.)-corn rotation and a mixed perennial grass sward receiving N via: i) mineral fertilizer (MIN), ii) liquid dairy manure (LDM), and iii) inclusion of alfalfa ( Medicago sativa L.) to the perennial forages with no additional N (LEG). Results When summed across sites over all three years, cumulative N 2 O emissions were greater for LDM than MIN in annual crops (8.75 ± 1.63 and 5.15 ± 0.96 kg N 2 O-N ha –1 , respectively), but not in perennial grasses (2.95 ± 0.55 and 3.76 ± 0.70 kg N 2 O-N ha –1 , respectively). When comparing N sources within each crop type over the three years, MIN generated greater yields than LDM in annual and perennial crops, but lower yield-scaled N 2 O emissions than LDM in annual crops only. During forages post-seeding years, area- and yield-scaled N 2 O emissions induced by LDM and LEG were lower than MIN. Conclusion Our results suggest that for a cool humid climate using LDM or LEG in perennial forages and MIN on annual crops can reduce overall N 2 O emissions, while generating similar or lower yield-scaled emissions.

Recognising and Protecting the National Benefit of Sustainable Fisheries in the UK - Sarah Coulthard; Ainsley Hatt; Phoebe Lewis; Bryce D. Stewart; Michael Roach; Robert Clark; Sam Fanshawe; Carole Sandrine White; Julie Urquhart; Jerry Percy; Tim Gray; Emily Bulled; et al. (Fish and Fisheries, 2025)
Sustainable commercial fishing makes valuable contributions to coastal regions and broader national benefits. This paper offers three arguments in relation to what is required for the societal benefits of sustainable fisheries to be fully realised and considers each in the context of the UK but with global relevance. First, there is a need to raise the profile of the full range of benefits that are delivered through sustainable fisheries to coastal communities and the broader public. In the UK, the delivery of a ‘national benefit’ objective through fisheries is now enshrined in law by the Fisheries Act, 2020; we operationalise this through a new framing that distils eight ‘national benefits’ that all sustainable fisheries should deliver. Second, better acknowledgement of what society gains from sustainable fisheries must be paralleled with recognition of what society is simultaneously at risk of losing through the decline of the fishing fleet. We detail this decline in a new analysis of long‐term UK data, which highlights that the decline is unequally felt, with some regions of the UK, and small‐scale fishing sectors, experiencing loss more acutely. This reality leads us to argue a third point, that if society is to retain and truly harness the benefits that flow from sustainable fisheries, governing bodies must act quickly to ensure that fisheries are environmentally sustainable, diverse and inclusive, pursuing fisheries that ‘leave no one behind’.

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

A novel physiologically-based pharmacokinetic model to estimate reduced CYP3A4 activity in cancer patients utilizing the neutrophil-to-lymphocyte ratio as an inflammatory marker - David E. Coutant; Jessica Rehmel; Donna M. Edwards; Stephen D. Hall (European Journal of Clinical Pharmacology, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Cardiac mitochondria function in embryonic and 1-year old American alligators, Alligator mississippiensis, is not altered by hypoxic incubation or an acute anoxic challenge - Janna Crossley; Jessica D. Rippamonti; Dane A. Crossley; Edward M. Dzialowski (Journal of Comparative Physiology B, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

The microbiome orchestrates contaminant low-dose phytostimulation - Evgenios Agathokleous; Edward J. Calabrese; Stavros D. Veresoglou (Trends in Plant Science, 2025)

Clamping parameters in full-scale tidal turbine blade tests: A case study - Miguel A. Valdivia-Camacho; Sergio Lopez Dubon; Fergus Cuthill; Marek J. Munko; Edward D. McCarthy; Parvez Alam; Conchúr M. Ó Brádaigh (Ocean Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Phylogenetic Structure of Two Euglossine Communities Divided by the Colombian Andes - Edward Hernan Molina-Henao; Oscar Julián Valdez-Benítez; Nolan D. Amon; Stephania Sandoval-Arango; Maria Margarita López-Uribe; Joel Tupac Otero-Ospina (Neotropical Entomology, 2025)

Recycling of lignin-based biocomposites: Improving sustainability and enhancing material strength - Barney H. Miao; Daniel Woo; Darius Javan; Edward J. Garboczi; Robert J. Headrick; Andrew C. Lesh; Zhiye Li; David J. Loftus; Michael D. Lepech (Resources, Conservation and Recycling, 2025)

Photodynamic priming with red light triggers adaptive immune responses in a pancreatic cancer mouse model - Pushpamali De Silva; Mohammad A. Saad; Joseph W.R. Swain; Zhiming Mai; Madeline D. Kidd; Joanna J. Choe; Assiris P. Camargo; Sanjay Anand; Vinay Chandrasekhara; Brian W. Pogue; Kenneth K. Wang; Bryan Q. Spring; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

John Raven, FRS, FRSE: a truly great innovator in plant physiology, photosynthesis and much more - A. W. D. Larkum; P. G. Falkowski; Dianne Edwards; C. B. Osmond; H. Lambers; P. Sanchez-Baracaldo; R. J. Ritchie; J. W. Runcie; P. J. Ralph; M. Westoby; S. Maberly; H. Griffiths; et al. (Photosynthesis Research, 2025)
This is a tribute to a truly inspirational plant biologist, Prof. John A. Raven, FRS, FRSE (25th June 1941– 23rd May 2024), who died at the age of 82. He was a leader in the field of evolution and physiology of algae and land plants. His research touched on many areas including photosynthesis, ion transport, carbon utilisation, mineral use, such as silicon, iron and molybdenum, the evolution of phytoplankton, the evolution of root systems, the impact of global change, especially on the acidification of the oceans, carbon gain and water use in early land plants, and ways of detecting extraterrestrial photosynthesis. Beginning his research career in the Botany School, University of Cambridge, John studied ion uptake in a giant algal cell. This was at the time of great strides brought about by Peter Mitchell (1920–1992) in elucidating the role of energy generation in mitochondria and chloroplasts and the coupling of ion transport systems to energy generation. With Enid MacRobbie and Andrew Smith, John pioneered early work on the involvement of ion transport in the growth and metabolism of plant cells.On leaving Cambridge John took up a lectureship at the University of Dundee in 1971, where he was still attached upon his death. His primary focus over the years, with one of us (Paul Falkowski), was on phytoplankton, the photosynthetic microalgae of the oceans. Still, his publication list of 5 books and over 600 scientific papers spans a very broad range. The many highly cited papers (see Table 1) attest to an outstanding innovator, who influenced a multitude of students and coworkers and a very wide readership worldwide. At the personal level, John Raven was a wonderful human being; he had an extraordinary memory, dredging up facts and little-known scientific papers, like a scientific magician, but at the same time making humorous jokes and involving his colleagues in fun and sympathetic appreciation. Table 1 Ten best cited articles (from google scholar) Citations Date Aquatic Photosynthesis, 3rd EditionP.G. Falkowski & J.A. RavenPrinceton University Press, 2013 3854 2013 The evolution of modern eukaryotic phytoplanktonP.G. Falkowski, M.E. Katz, A.H. Knoll, A. Quigg, J.A. Raven, et alScience 305 , 354–360 1790 2004 C O 2 concentrating mechanisms in algae:mechanisms, environmental modulation, and evolutionM. Giordano, J. Beardall & J.A. RavenAnnu. Rev. Plant Biol. 56 (1), 99–131 1648 2005 Algae as nutritional food sources: revisiting our understandingM.L. Wells, P. Potin, J.S. Craigie, J.A. Raven, S.S. Merchant, et alJournal of applied phycology 29 , 949–982 1527 2017 Plant Nutrient acquisition strategies change with soil ageH. Lambers, J.A. Raven, G.R. Shaver & S.E. SmithTrends in ecology & evolution 23 , 95–103 1488 2008 Ocean acidification due to increasing atmospheric carbon dioxideJ. Raven, K. Caldeira, H. Elderfield, O. Hoegh-Guldberg, P. Liss, et alThe Royal Society, Policy Document, June 2005 1470 2005 Phytoplankton in a changing world: cell size and elemental stoichiometryZ.V. Finkel, J. Beardall, K.J. Flynn, A. Quigg, T.A.V. Rees & J.A. RavenJournal of plankton research 32 , 119–137 1198 2010 Opportunities for improving phosphorus efficiency in crop plantsE.J. Veneklaas, H. Lambers, J. Bragg, P.M. Finnegan, C.E. Lovelock, et alNew phytologist 195 , 306–320 951 2012 Adaptation of unicellular algae to irradiance: an analysis of strategiesK. Richardson, J. Beardall & J.A. RavenNew Phytologist 93 , 157–191 914 1983 N itrogen assimilation and transport in vascular land plants in relation to Intracellular pH regulationJ.A. Raven & F.A. SmithNew Phytologist 76 , 415–431 893 1976 Temperature and algal growth J.A. Raven & R.J. GeiderNew phytologist 110 , 441–461 867 1988 The role of trace metals in photosynthetic electron transport in O 2 -evolving organismsJ.A. Raven, M.C.W. Evans & R.E. KorbPhotosynthesis Research 60 , 111–150 840 1999

Giant milkweed: a comprehensive review of chemical constituents and their insecticidal properties - K. Mounisha; Y. S. Johnson Thangaraj Edward; M. Kannan; S. Vellaikumar; D. Uma; P. Indiragandhi (Phytochemistry Reviews, 2025)

Bonobo (Pan paniscus) Density and Distribution in Central Africa's Largest Rainforest Reserve: Long-term Survey Data Show Pitfalls in Methodological Approaches and Call for Vigilance - Mattia Bessone; Hjalmar S. Kühl; Ilka Herbinger; Gottfried Hohmann; Kouamé Paul N’Goran; Papy Asanzi; Stephen Blake; Michel Basele; Martin Bofeko; Nono Bondjengo; Pitshou Wangongo Bondo; Rigobert Booto; et al. (International Journal of Primatology, 2025)
Conservation measures require accurate estimates of density and abundance and population trend assessments. The bonobo ( Pan paniscus ) is considered Endangered in the IUCN Red List. This classification assumes that available population data are representative. However, with only 30% of the bonobo’s historic geographical range surveyed, reliable information is needed to assess the species' population status. Here, we use information from 13 surveys conducted between 2002 and 2018 in an area of 42,000 km 2 , representing ~27% of bonobo-suitable habitat: Salonga National Park and its corridor, Democratic Republic of the Congo (DRC). Using 8310 km of reconnaissance and transect walks and 27,045 days of camera trapping, we: (1) provide updated estimates of bonobo population density and distribution (42,000 km 2 ; ~5,000 km 2 of which, to the best of our knowledge, have not been surveyed before by scientists), (2) assess population trends (15,758 km 2 ; 2002–2008 vs 2012–2018), (3) compare estimates obtained with different methods, and (4) assess the factors driving bonobo density and distribution. Although we detected a non-significant population decline, our study suggests that Salonga is a bonobo stronghold, with a population ranging between 8244 and 18,308 mature individuals (density: 0.31 individuals/km 2 ). Standing crop nest counts returned non-significantly lower density estimates than camera trap distance sampling. Nest count-estimates were higher in areas with Marantaceae understorey and those farther away from rivers, while camera trap-estimates were higher in areas with lower human presence. Regardless of the method, bonobos were rarer in proximity to villages. They occurred more often in areas of dense forest cover and in proximity to ranger posts. Our results point towards a declining bonobo population in Salonga, but do not provide sufficient evidence to confirm this statistically. Consequently, the continued monitoring of the bonobo population and preservation of the integrity of Salonga, considering its biological and cultural heritage, will be crucial in the preservation of this stronghold of wild bonobos.

Continental‐Scale α ‐ and β ‐Diversity Patterns of Terrestrial Eukaryotic Microbes: Effect of Climate and Microhabitat on Testate Amoeba Assemblages in Eurasian Peatlands - Jiahui Su; Yuri A. Mazei; Andrey N. Tsyganov; Natalia G. Mazei; Victor A. Chernyshov; Alexander A. Komarov; Kirill V. Babeshko; Edward A. D. Mitchell; Satoshi Shimano; Damir A. Saldaev; Basil N. Yakimov (Journal of Biogeography, 2025)
Aim The role of environmental factors that shape the large‐scale distribution of eukaryotic microbes remains understudied. We aimed to disentangle the impacts of latitudinal and longitudinal gradients on the distribution of Sphagnum‐ dwelling testate amoebae in mires and to understand the influence of environmental factors related to both local habitats (hummock—lawn—hollows) and regional climates. Location A range from temperate to subarctic and from the European part to the Far East of Russia (51°–70°N, 32°–158°E). Taxon Testate amoeba (Arcellinida, Euglyphida, and Amphitremida). Methods We analysed the testate amoeba (TA) composition and abundance data from 816 samples collected in 75 peatlands. Linear mixed‐effects models and redundancy analysis were applied to determine the likely environmental drivers of TA α ‐ and β ‐diversity. Results We identified a significant reversed latitudinal gradient in α ‐diversity which negatively correlated with the mean annual temperature. This gradient is microhabitat‐specific, being prominent in lawn and hollow microhabitats, but not in hummocks. Longitude, which corresponds mainly to a gradient of precipitation seasonality, was a significant predictor of TA β ‐diversity, especially in hollows. Main Conclusions Our findings identify climatic factors (e.g., mean annual temperature and precipitation seasonality) as likely shaping the continental‐scale TA α ‐ and β ‐diversity patterns, emphasising the microhabitat‐specific nature of these relationships. The absence of pattern in hummocks is interpreted as evidence for a predominant microhabitat stress (i.e., low moisture and pH) in this habitat.

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Warming Disrupts Plant–Fungal Endophyte Symbiosis More Severely in Leaves Than Roots - Joseph D. Edwards; Melanie R. Kazenel; Yiqi Luo; Joshua S. Lynn; Rebecca L. McCulley; Lara Souza; Carolyn Young; Jennifer A. Rudgers; Stephanie N. Kivlin (Global Change Biology, 2025)
Disruptions to functionally important symbionts with global change will negatively impact plant fitness, with broader consequences for species' abundances, distribution, and community composition. Fungal endophytes that live inside plant leaves and roots could potentially mitigate plant heat stress from global warming. Conversely, disruptions of these symbioses could exacerbate the negative impacts of warming. To better understand the consistency and strength of warming‐induced changes to fungal endophytes, we examined fungal leaf and root endophytes in three grassland warming experiments in the US ranging from 2 to 25 years and spanning 2000 km, 12°C of mean annual temperature, and 600 mm of precipitation. We found that experimental warming disrupted symbiosis between plants and fungal endophytes. Colonization of plant tissues by septate fungi decreased in response to warming by 90% in plant leaves and 35% in roots. Warming also reduced fungal diversity and changed community composition in plant leaves, but not roots. The strength, but not direction, of warming effects on fungal endophytes varied by up to 75% among warming experiments. Finally, warming decoupled fungal endophytes from host metabolism by decreasing the correlation between endophyte community and host metabolome dissimilarity. These effects were strongest in the shorter‐term experiment, suggesting endophyte‐host metabolome function may acclimate to warming over decades. Overall, warming‐driven disruption of fungal endophyte community structure and function suggests that this symbiosis may not be a reliable mechanism to promote plant resilience and ameliorate stress responses under global change.

Magma storage and transport beneath the near-rift Fjallgarðar Volcanic Ridge, Northeast Iceland - Noëmi Löw; Sæmundur A. Halldórsson; Christoph Beier; Enikő Bali; Simon Matthews; Guðmundur H. Guðfinnsson; Edward W. Marshall; Jóhann Helgason; Eemu Ranta; Adam Abersteiner; Jaime D. Barnes; Alberto Caracciolo (Contributions to Mineralogy and Petrology, 2025)

Draft genome of Palmaria palmata and intraspecific genetic variations in the North-East Atlantic - Serena Rosignoli; Masami Inaba; Matthias Schmid; Marcus McHale; Antoine Fort; Maeve D. Edwards; Agnes Mols Mortensen; Roy Bartle; Arild Endal; Aurélien Baud; Christine Maggs; Ronan Sulpice (Algal Research, 2025)

Achieving multifunctionality in green infrastructure projects: a fuzzy evaluation and Gini index of Key drivers in developing countries - S. Seidu; D. J. Edwards; D. Owusu-Manu; D. W. M. Chan; S. F. Abdulai; J. I. T. Buertey (Environment, Development and Sustainability, 2025)
While many developed countries are well advanced in green infrastructure (GI), more efforts are needed to bring less developed regions to speed. Existing evidence shows that GI understanding differs significantly among stakeholders due to the multifunctionality concept. As key technical stakeholders in GI implementation, there is little empirical knowledge of the multifunctional attributes of GI systems among built environment professionals in developing regions. This study provides an in-depth analysis to fill this knowledge gap through a combination of the Gini coefficient and fuzzy synthetic evaluation toward understanding the multifunctionality concept of GI among built environment professionals in developing regions. As a measure of dispersion, the stationary driver points to a constant factor that underpins the implementation of GI across several geographic regions. The need to mitigate urban heat islands and enhance ecosystem services were revealed as the anchors among built environment professionals in supporting GI development; hence, specific attention needs to be accorded to these dimensions in GI policies. Ecosystem services, water resources management, and thermal regulation were identified as the three broad multifunctional drivers of GI in developing nations. For effective water management in GI projects, integrated green-grey infrastructure systems are recommended. To achieve thermal objectives, insulation materials are pivotal. The ecosystem properties are more passive as compared to thermal and water management; hence, specific considerations must be accorded to ensure GI success. The key contribution of the study was the delineation of the key multifunctional factors that support GI adoption and implementation success in developing regions.

Internal tides off the Amazon shelf in the western tropical Atlantic: analysis of SWOT Cal/Val mission data - Michel Tchilibou; Loren Carrere; Florent Lyard; Clément Ubelmann; Gérald Dibarboure; Edward D. Zaron; Brian K. Arbic (Ocean Science, 2025)
This study focuses on the internal tides (ITs) off the Amazon shelf in the tropical Atlantic. It is based on 2 km horizontally gridded observations along the swaths of SWOT (Surface Water and Ocean Topography) track 20 during the calibration/validation phase (Cal/Val, 1 d orbit) from late March to early July 2023. We evaluate the amplitude of M2, N2, and S2 frequencies and use the M2 atlas as an internal tide correction model for SWOT observations. Internal tide amplitudes (models or atlases) are first derived by harmonic analysis of the SWOT sea level anomaly (SLA). The estimation is improved by performing a principal component analysis before the harmonic analysis. The results compare very well with the high-resolution empirical tide (HRET) internal tide model, the reference product for internal tide corrections in altimetry observations. The coherent mode 1 and mode 2 M2 can be distinguished in the internal tide model derived from SWOT, while the higher modes with their strong SLA signature are seen mostly in the incoherent part. In comparison to HRET, the correction of SWOT observations with SWOT-based atlases may be more relevant for this track.

Synthesis of encapsulated nanofertilizer from biogas plant digestate - Edward D. Nasser; Joel Kenneth M. Ngojo; Ramiro Emerson C. Amon; Jayvee Moore S. Dy; Julius J. Rosalia; Chosel P. Lawagon (Bioresource Technology Reports, 2025)

Nitrogen induced soil carbon gains are resistant to loss after the cessation of excess nitrogen inputs - Emel Kangi; Joanna R. Ridgeway; Hannah D. DeHetre; Edward R. Brzostek (Soil Biology and Biochemistry, 2025)

Influence of regulated water discharges on phytoplankton composition and biomass in a subtropical canal - Susan Badylak; Edward J. Phlips; Eric C. Milbrandt; Elise S. Morrison; Benjamin D. Stelling; Shin-Ah Lee; Thomas A. Frankovich; David Kaplan (Journal of Environmental Management, 2025)

Headmen, shamans, and mothers: Natural and sexual selection for computational services - Edward H. Hagen; Zachary H. Garfield; Aaron D. Lightner (Evolution and Human Behavior, 2025)

Numeric ring-reconstructions based on massifs favor a non-oblique south pole-Aitken-forming impact event - Hannes Bernhardt; Jessica M. Walsh; Leon M. Schröder; Jaclyn D. Clark; Megan R. Henriksen; Christopher S. Edwards (Earth and Planetary Science Letters, 2025)

Influence of incorporating beta-cyclodextrin/essential oil-based wood preservative on the bonding strength of wood composite products - Hamed Olayiwola; Edward D. Entsminger; Carson Bedics; Jason T. Street; Santanu Kundu; Yunsang Kim (Carbohydrate Polymers, 2025)

Canopy complexity drives positive effects of tree diversity on productivity in two tree diversity experiments - Catherine Fahey; Dennis Choi; Jianmin Wang; Grant M. Domke; Joseph D. Edwards; Songlin Fei; Stephanie N. Kivlin; Elizabeth A. LaRue; Melissa K. McCormick; William J. McShea; Richard P. Phillips; Jamie Pullen; et al. (Ecology, 2025)
Forest canopy complexity (i.e., the three‐dimensional structure of the canopy) is often associated with increased species diversity as well as high primary productivity across natural forests. However, canopy complexity, tree diversity, and productivity are often confounded in natural forests, and the mechanisms of these relationships remain unclear. Here, we used two large tree diversity experiments in North America to assess three hypotheses: (1) increasing tree diversity leads to increased canopy complexity, (2) canopy complexity is positively related to tree productivity, and (3) the relationship between tree diversity and tree productivity is indirect and driven by the positive effects of canopy complexity. We found that increasing tree diversity from monocultures to mixtures of 12 species increases canopy complexity and productivity by up to 71% and 73%, respectively. Moreover, structural equation modeling indicates that the effects of tree diversity on productivity are indirect and mediated primarily by changes in internal canopy complexity. Ultimately, we suggest that increasing canopy complexity can be a major mechanism by which tree diversity enhances productivity in young forests.

Subsurface basement structures of the Usangu basin, East African rift system, with implications for basin structural configuration and hydrocarbon potential - Edward Pastory; Gabriel D. Mulibo; Isaac M. Marobhe (Tectonophysics, 2024)

Investigating the chemical space coverage of multiple chromatographic and ionization methods using non-targeted analysis on surface and drinking water collected using passive sampling - Angela L. Batt; Laura D. Brunelle; Natalia S. Quinete; Eva K. Stebel; Brian Ng; Piero Gardinali; Alex Chao; Anna K. Huba; Susan T. Glassmeyer; David A. Alvarez; Dana W. Kolpin; Edward T. Furlong; et al. (Science of The Total Environment, 2024)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Neurotoxicology and public health issues of cannabis and cannabinoids - Maxwell C.K. Leung; Edward D. Levin (NeuroToxicology, 2024)

Antimony-bearing schwertmannite transformation to goethite: A driver of antimony mobilization in acid mine drainage - Mohammad Rastegari; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mona Hosseinpour Moghaddam; Edward D. Burton (Journal of Hazardous Materials, 2024)

Is beudantite a stable host phase of arsenic and lead? New insights from molecular-scale kinetic analyses - A.S.M. Fazle Bari; Girish Choppala; Dane Lamb; Jessica L. Hamilton; CI Sathish; Mohammad Mahmudur Rahman; Ravi Naidu; Robert Aughterson; Edward D. Burton (Journal of Hazardous Materials, 2024)

Antimony(V) sorption and coprecipitation with ferrihydrite: An examination of retention mechanisms and the selectivity of commonly-applied extraction procedures - Mona Hosseinpour Moghaddam; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mohammad Rastegari; Edward D. Burton (Journal of Hazardous Materials, 2024)

Investigating the enzymatic response of Plutella xylostella L. (Lepidoptera: Plutellidae) to Metarhizium anisopliae (Metschnikoff) Sorokin (Ascomycota: Hypocreales) Infection: A Comprehensive study - Abarna V.P.; Muthuswami M.; Jeyarajan Nelson S; Johnson Thangaraj Edward Y.S.; Manikanda Boopathi N.; Anita B.; Jeya Sundara Sharmila D. (Journal of Asia-Pacific Entomology, 2024)

A comprehensive analysis of new particle formation across the northwest Atlantic: Analysis of ACTIVATE airborne data - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Simon Kirschler; Hongyu Liu; John B. Nowak; Michael A. Shook; Cassidy Soloff; Kenneth L. Thornhill; et al. (Atmospheric Environment, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Place-based climate commissions: embracing messy governmentality - C. Howarth; L. Edwards; A. Duncan; D. Van der Horst; R. Pringle (Climatic Change, 2024)
The role of the ‘place’ in delivering climate action is vital, however much action on climate change locally is fragmented. Independent place-based climate commissions are a novel structure of climate governance developing at the subnational level across cities, regions and counties in the UK. Little is known about these emerging forms of local climate governance and their experiences of navigating ‘mess’ in governance practices and processes. Building on Castán Broto’s framework of messy governmentalities, this paper seeks to assess the capacity of climate commissions to affect meaningful climate mitigation and adaptation action, to understand how they interact with existing climate governance structures and to consider their longer-term sustainability. This paper examines the nature and impact climate commissions have had on local climate action, drawing on qualitative interviews with chairs, commissioners, members of the secretariat and associated local authorities of the Edinburgh, Belfast, Leeds, Surrey, Yorkshire and Humber, and Lincoln commissions in the UK. Analysing the journeys of the commissions through a lens of messy governmentalities, and a focus on bodies, strategies and knowledges within them, we draw out insights on how climate commissions came about, their function and role, their impact and influence, and how they have evolved.

Traumatic brain injury in companion animals: Pathophysiology and treatment - Molly Wart; Thomas H. Edwards; Julie A. Rizzo; Geoffrey W. Peitz; Armi Pigott; Jonathan M. Levine; Nicholas D. Jeffery (Topics in Companion Animal Medicine, 2024)

High resolution luminescence and radiocarbon dating of Holocene Aeolian silt (loess) in west Greenland - D. Sechi; T. Stevens; P. Hällberg; R.H. Smittenberg; M. Molnár; G.T. Kertész; J.P. Buylaert; R. Schneider; C. Edward; Keld Romer Rasmussen; Niels Aage Tvis Knudsen; S. Andreucci; et al. (Quaternary Geochronology, 2024)

Antimony sorption to schwertmannite in acid sulfate environments - Mohammad Rastegari; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mona Hosseinpour Moghaddam; Edward D. Burton (Journal of Hazardous Materials, 2024)

Optimizing photosynthetic light-harvesting under stars: simple and general antenna models - Samir Chitnavis; Callum Gray; Ifigeneia Rousouli; Edward Gillen; Conrad W. Mullineaux; Thomas J. Haworth; Christopher D. P. Duffy (Photosynthesis Research, 2024)
In the next 10–20 years, several observatories will aim to detect the signatures of oxygenic photosynthesis on exoplanets, though targets must be carefully selected. Most known potentially habitable exo-planets orbit cool M-dwarf stars, which have limited emission in the photosynthetically active region of the spectrum (PAR, $$400< λ < 700$$ 400 < λ < 700 nm) used by Earth’s oxygenic photoautotrophs. Still, recent experiments have shown that model cyanobacteria, algae, and non-vascular plants grow comfortably under simulated M-dwarf light, though vascular plants struggle. Here, we hypothesize that this is partly due to the different ways they harvest light, reflecting some general rule that determines how photosynthetic antenna structures may evolve under different stars. We construct a simple thermodynamic model of an oxygenic antenna-reaction centre supercomplex and determine the optimum structure, size and absorption spectrum under light from several star types. For the hotter G (e.g. the Sun) and K-stars, a small modular antenna is optimal and qualitatively resembles the PSII-LHCII supercomplex of higher plants. For the cooler M-dwarfs, a very large antenna with a steep ’energy funnel’ is required, resembling the cyanobacterial phycobilisome. For the coolest M-dwarfs an upper limit is reached, where increasing antenna size further is subject to steep diminishing returns in photosynthetic output. We conclude that G- and K-stars could support a range of niches for oxygenic photo-autotrophs, including high-light adapted canopy vegetation that may generate detectable bio-signatures. M-dwarfs may only be able to support low light-adapted organisms that have to invest considerable resources in maintaining a large antenna. This may negatively impact global coverage and therefore detectability.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Multimodal nonlinear correlates of behavioural symptoms in frontotemporal dementia - Giovanna Zamboni; Irene Mattioli; Zobair Arya; Manuela Tondelli; Giulia Vinceti; Annalisa Chiari; Mark Jenkinson; Edward D. Huey; Jordan Grafman (Brain Imaging and Behavior, 2024)
Studies exploring the brain correlates of behavioral symptoms in the frontotemporal dementia spectrum (FTD) have mainly searched for linear correlations with single modality neuroimaging data, either structural magnetic resonance imaging (MRI) or fluoro-deoxy-D-glucose positron emission tomography (FDG-PET). We aimed at studying the two imaging modalities in combination to identify nonlinear co-occurring patterns of atrophy and hypometabolism related to behavioral symptoms. We analyzed data from 93 FTD patients who underwent T1-weighted MRI, FDG-PET imaging, and neuropsychological assessment including the Neuropsychiatric Inventory, Frontal Systems Behavior Scale, and Neurobehavioral Rating Scale. We used a data-driven approach to identify the principal components underlying behavioral variability, then related the identified components to brain variability using a newly developed method fusing maps of grey matter volume and FDG metabolism. A component representing apathy, executive dysfunction, and emotional withdrawal was associated with atrophy in bilateral anterior insula and putamen, and with hypometabolism in the right prefrontal cortex. Another component representing the disinhibition versus depression/mutism continuum was associated with atrophy in the right striatum and ventromedial prefrontal cortex for disinhibition, and hypometabolism in the left fronto-opercular region and sensorimotor cortices for depression/mutism. A component representing psychosis was associated with hypometabolism in the prefrontal cortex and hypermetabolism in auditory and visual cortices. Behavioral symptoms in FTD are associated with atrophy and altered metabolism of specific brain regions, especially located in the frontal lobes, in a hierarchical way: apathy and disinhibition are mostly associated with grey matter atrophy, whereas psychotic symptoms are mostly associated with hyper-/hypo-metabolism.

The impact of exercise on food-related inhibitory control— do calories, time of day, and BMI matter? Evidence from an event-related potential (ERP) study - Kaylie A. Carbine; James D. LeCheminant; Tracy A. Kelley; Anita Kapila-Ramirez; Kyle Hill; Travis Masterson; Edward Christensen; Michael J. Larson (Appetite, 2024)

Human recombinant interleukin-6 improves the morphological quality of cryopreserved in vitro produced bovine blastocysts - Mary A. Oliver; Savannah L. Speckhart; J. Lannett Edwards; Michelle L. Rhoads; Alan D. Ealy (Theriogenology, 2024)

Floodplain morphology influences arsenic and antimony spatial distribution in a seasonal acid sulfate soil wetland - Gretchen Wichman; Scott G. Johnston; Edward D. Burton; Damien T. Maher (Journal of Hazardous Materials, 2024)

Tarda and Tagish Lake: Samples from the same outer Solar System asteroid and implications for D- and P-type asteroids - Devin L. Schrader; Edward A. Cloutis; Daniel M. Applin; Jemma Davidson; Zachary A. Torrano; Dionysis Foustoukos; Conel M. O'D. Alexander; Kenneth J. Domanik; Moe Matsuoka; Tomoki Nakamura; Thomas J. Zega; Gregory A. Brennecka; et al. (Geochimica et Cosmochimica Acta, 2024)

The evolution of multiply substituted isotopologues of methane during microbial aerobic oxidation - Jiawen Li; Beverly K. Chiu; Alison M. Piasecki; Xiahong Feng; Joshua D. Landis; Sarah Marcum; Edward D. Young; William D. Leavitt (Geochimica et Cosmochimica Acta, 2024)

Electrotrawling can improve the sustainability of the bottom trawl fishery for sole: a review of the evidence - Adriaan D. Rijnsdorp; Pim G. Boute; Justin C. Tiano; Dick de Haan; Marloes Kraan; Hans Polet; Edward Schram; Maarten Soetaert; Nathalie A. Steins; Martin Lankheet; Karline Soetaert (Reviews in Fish Biology and Fisheries, 2024)
Between 2009 and 2021 almost the complete beam trawl fleet of the Netherlands switched from conventional beam trawls (BT) to pulse trawls (PT) using electrical stimulation to catch sole, Solea solea . Electric fishing, being banned in the EU in 1988, was made possible in 2006 under a derogation. Over the years stakeholders expressed concern about ecosystem effects. Here we review the research conducted. PT improved the selectivity of the fishery and reduced the ecological side effects. PT caught more sole per hour fishing but less discards and benthos than BT. The transition to PT reduced the surface area swept (lower towing speed), sediment depth of disturbance and associated benthic impacts, as well as fuel consumption. Laboratory experiments with 9 fish and 17 benthic invertebrate species showed that exposure to a commercial bipolar pulse stimulus did not result in harmful effects except in cod. Autopsy of cod sampled from PT revealed that 40% had an internal injury. Injury rates in other roundfish species was low (< 2%) and absent in flatfish. Electrical-induced impacts on biogeochemistry were not observed. The transition increased competition with other fishers which fed the resentment against PT. Governance arrangements under which the number of temporary licenses expanded, undermined legitimacy of the gear, resulting in a ban in 2021. Although questions about the ecological impact of electrical stimulation remain, adverse effects are considered negligible in comparison with the benefits.

Praxelis cleggiae (Compositae: Eupatorieae: Praxeliinae), a new species from the granite inselbergs in the east of the Departamento de Santa Cruz, Bolivia - D. J. Nicholas Hind; Sara L. Edwards (Kew Bulletin, 2024)
Summary Praxelis cleggiae (Compositae: Eupatorieae: Praxeliinae) is described and illustrated from the granite inselbergs (upon which it is most common), and on road crown chippings on old roads, in the Departamento de Santa Cruz, Bolivia; it has a disjunct distribution and is also found on the Serranía San Simón, in the San Ignacio Schist belt, Departamento de Beni. Material of this species was mostly determined as P. insignis (Malme) R.M.King & H.Rob., a Brazilian species, described from the metamorphosed sandstone of what is now the Parque Nacional da Chapada dos Guimarães in Mato Grosso State. The two species have some superficial resemblance, but differ significantly in plant size, internode length (relative to leaf length), branching, leaf shape and size, phyllaries, achenes and pappus. The total number of species of Praxelis recognised in Bolivia is now seven, and 20 species in the genus worldwide.

Manure and its biochar affect activities and stoichiometry of soil extracellular enzymes in croplands - Zhengfeng An; Cole D. Gross; Xinli Chen; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Journal of Soils and Sediments, 2024)

Estuarine nekton community shows minimal response following large-scale oyster reef habitat loss in Apalachicola Bay, Florida - Gabrielle D. Love; Zachary A. Siders; David A. Gandy; William E. Pine; Shirley Baker; Edward V. Camp (Hydrobiologia, 2024)

Developing a Genetic Algorithm for Selecting Infrastructure Modifications that Optimize Hydrodynamic Flushing in Old Tampa Bay - Steven D. Meyers; Marcus W. Beck; Edward T. Sherwood; Mark E. Luther (Estuaries and Coasts, 2024)
Impermeable infrastructure such as traffic causeways can reduce the natural hydrodynamic flushing of an estuary, resulting in reduced water quality and increased incidence of harmful algal blooms (HABs). A series of cuts through the three causeways spanning Old Tampa Bay, FL, (OTB) are being considered to help restore the natural circulation of the region, but the number of possible location combinations is computationally challenging to fully assess. A prototype genetic algorithm (GA) was developed to identify the optimal configuration of these cuts through one of the bridge sections that maximizes flushing as represented in a numerical ocean circulation model of OTB. Flushing was measured by integrating the trajectories of over 21,000 passive Lagrangian “particles” using the model velocity fields. The rate of loss of particles initialized near Feather Sound (a region subject to frequent HABs) was used to quantify the “fitness” over which the configurations were optimized. The highest-scoring solution produced a 42% increase in net flushing compared to a no-change baseline. Six independently initialized applications of the GA were conducted. All converged to the same solution within no more than 7 generations. The small population size of the prototype allowed testing of the complete solution space, and verification the found solution was optimal. Elitism (preservation of the highest-ranking solution) was required for convergence. The GA also identified configurations that had similar, but slightly slower, flushing rates. These results will help area managers prioritize or rank combinations of causeway modifications to improve overall water quality conditions in Tampa Bay.

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

University herbaria are uniquely important - Erika J. Edwards; Brent D. Mishler; Charles D. Davis (Trends in Plant Science, 2024)

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Spatial and temporal variability of martian water-ice cloud effective radius in EMIRS thermal infrared observations - Samuel A. Atwood; Michael D. Smith; Michael J. Wolff; Khalid Badri; Christopher S. Edwards; Philip R. Christensen; Alain S.J. Khayat; M.R. El-Maarry (Icarus, 2024)

Subglacial bedform and moat initiation beneath Rutford Ice Stream, West Antarctica - Rebecca Schlegel; Alex M. Brisbourne; Andrew M. Smith; Adam D. Booth; Tavi Murray; Edward C. King; Roger A. Clark (Geomorphology, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

Persisting neurobehavioral consequences of daily or intermittent paternal cannabis administration in F1 and F2 Rats - Andrew B. Hawkey; Sarabesh Natarajan; Olivia Kelly; Anas Gondal; Corinne Wells; Michelle Louise Jones; Amir H. Rezvani; Susan K. Murphy; Edward D. Levin (NeuroToxicology, 2024)

Fostering effective and sustainable scientific collaboration and knowledge exchange: a workshop-based approach to establish a national ecological observatory network (NEON) domain-specific user group - Alison Donnelly; Ankur R. Desai; Katherine A. Heckman; Lucas E. Nave; Michael J. Cramer; Marie Faust; Peter Weishampel; Caleb Slemmons; Christian G. Andresen; Edward Ayres; Stacy R. Cotey; Kathryn M. Docherty; et al. (International Journal of Biometeorology, 2024)
The decision to establish a network of researchers centers on identifying shared research goals. Ecologically specific regions, such as the USA’s National Ecological Observatory Network’s (NEON’s) eco-climatic domains, are ideal locations by which to assemble researchers with a diverse range of expertise but focused on the same set of ecological challenges. The recently established Great Lakes User Group (GLUG) is NEON’s first domain specific ensemble of researchers, whose goal is to address scientific and technical issues specific to the Great Lakes Domain 5 (D05) by using NEON data to enable advancement of ecosystem science. Here, we report on GLUG’s kick off workshop, which comprised lightning talks, keynote presentations, breakout brainstorming sessions and field site visits. Together, these activities created an environment to foster and strengthen GLUG and NEON user engagement. The tangible outcomes of the workshop exceeded initial expectations and include plans for (i) two journal articles (in addition to this one), (ii) two potential funding proposals, (iii) an assignable assets request and (iv) development of classroom activities using NEON datasets. The success of this 2.5-day event was due to a combination of factors, including establishment of clear objectives, adopting engaging activities and providing opportunities for active participation and inclusive collaboration with diverse participants. Given the success of this approach we encourage others, wanting to organize similar groups of researchers, to adopt the workshop framework presented here which will strengthen existing collaborations and foster new ones, together with raising greater awareness and promotion of use of NEON datasets. Establishing domain specific user groups will help bridge the scale gap between site level data collection and addressing regional and larger ecological challenges.

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Steppe-tundra composition and deglacial floristic turnover in interior Alaska revealed by sedimentary ancient DNA (sedaDNA) - Charlotte L. Clarke; Peter D. Heintzman; Youri Lammers; Alistair J. Monteath; Nancy H. Bigelow; Joshua D. Reuther; Ben A. Potter; Paul D.M. Hughes; Inger G. Alsos; Mary E. Edwards (Quaternary Science Reviews, 2024)

Topical Solution for Retinal Delivery: Bevacizumab and Ranibizumab Eye Drops in Anti-Aggregation Formula (AAF) in Rabbits - Steven A. Giannos; Edward R. Kraft; Jonathan D. Luisi; Mary E. Schmitz-Brown; Valentina Reffatto; Kevin H. Merkley; Praveena K. Gupta (Pharmaceutical Research, 2024)
Purpose Wet age-related macular degeneration (AMD) is a blinding retinal disease. Monthly intravitreal anti-VEGF antibody injections of bevacizumab (off-label) and ranibizumab (FDA approved) are the standard of care. Antibody aggregation may interfere with ocular absorption/distribution. This study assessed topical delivery of dilute antibodies to the posterior segment of rabbit eyes using a novel anti-aggregation formula (AAF). Methods Bevacizumab, or biosimilar ranibizumab was diluted to 5 mg/ml in AAF. All rabbits were dosed twice daily. Substudy 1 rabbits (bevacizumab, 100 µl eye drops): Group 1 (bevacizumab/AAF, n = 6); Group 2 (bevacizumab/PBS, n = 7) and Vehicle control (AAF, n = 1). Substudy 2 rabbits (ranibizumab biosimilar/AAF, 50 µl eye drops): (ranibizumab biosimilar/AAF, n = 8). At 14.5 days, serum was drawn from rabbits. Aqueous, vitreous and retina samples were recovered from eyes and placed into AAF aliquots. Tissue analyzed using AAF as diluent. Results Bevacizumab in AAF permeated/accumulated in rabbit aqueous, vitreous and retina 10 times more, than when diluted in PBS. AAF/0.1% hyaluronic acid eye drops, dosed twice daily, provided mean tissue concentrations (ng/g) in retina (29.50), aqueous (12.34), vitreous (3.46), and serum (0.28 ng/ml). Additionally, the highest concentration (ng/g) of ranibizumab biosimilar was present in the retina (18.0), followed by aqueous (7.82) and vitreous (1.47). Serum concentration was negligible (< 0.04 ng/ml). No irritation was observed throughout the studies. Conclusions Bevacizumab and ranibizumab, in an AAF diluent eye drop, can be delivered to the retina, by the twice daily dosing of a low concentration mAb formulation. This may prove to be an adjunct to intravitreal injections.

Quantification of age-related changes in the structure and mechanical function of skin with multiscale imaging - Alan E. Woessner; Nathan J. Witt; Jake D. Jones; Edward A. Sander; Kyle P. Quinn (GeroScience, 2024)
The mechanical properties of skin change during aging but the relationships between structure and mechanical function remain poorly understood. Previous work has shown that young skin exhibits a substantial decrease in tissue volume, a large macro-scale Poisson’s ratio, and an increase in micro-scale collagen fiber alignment during mechanical stretch. In this study, label-free multiphoton microscopy was used to quantify how the microstructure and fiber kinematics of aged mouse skin affect its mechanical function. In an unloaded state, aged skin was found to have less collagen alignment and more non-enzymatic collagen fiber crosslinks. Skin samples were then loaded in uniaxial tension and aged skin exhibited a lower mechanical stiffness compared to young skin. Aged tissue also demonstrated less volume reduction and a lower macro-scale Poisson’s ratio at 10% uniaxial strain, but not at 20% strain. The magnitude of 3D fiber realignment in the direction of loading was not different between age groups, and the amount of realignment in young and aged skin was less than expected based on theoretical fiber kinematics affine to the local deformation. These findings provide key insights on how the collagen fiber microstructure changes with age, and how those changes affect the mechanical function of skin, findings which may help guide wound healing or anti-aging treatments.

Amyloid β accelerates age-related proteome-wide protein insolubility - Edward Anderton; Manish Chamoli; Dipa Bhaumik; Christina D. King; Xueshu Xie; Anna Foulger; Julie K. Andersen; Birgit Schilling; Gordon J. Lithgow (GeroScience, 2024)
Loss of proteostasis is a highly conserved feature of aging across model organisms and results in the accumulation of insoluble protein aggregates. Protein insolubility is also a unifying feature of major age-related neurodegenerative diseases, including Alzheimer's Disease (AD), in which hundreds of insoluble proteins associate with aggregated amyloid beta (Aβ) in senile plaques. Despite the connection between aging and AD risk, therapeutic approaches to date have overlooked aging-driven generalized protein insolubility as a contributing factor. However, proteins that become insoluble during aging in model organisms are capable of accelerating Aβ aggregation in vitro and lifespan in vivo. Here, using an unbiased proteomics approach, we questioned the relationship between Aβ and age-related protein insolubility. Specifically, we uncovered that Aβ expression drives proteome-wide protein insolubility in C. elegans , even in young animals, and this insoluble proteome is highly similar to the insoluble proteome driven by normal aging, this vulnerable sub-proteome we term the core insoluble proteome (CIP). We show that the CIP is enriched with proteins that modify Aβ toxicity in vivo, suggesting the possibility of a vicious feedforward cycle in the context of AD. Importantly, using human genome-wide association studies (GWAS), we show that the CIP is replete with biological processes implicated not only in neurodegenerative diseases but also across a broad array of chronic, age-related diseases (CARDs). This provides suggestive evidence that age-related loss of proteostasis could play a role in general CARD risk. Finally, we show that the geroprotective, gut-derived metabolite, Urolithin A, relieves Aβ toxicity, supporting its use in clinical trials for dementia and age-related diseases.

Adapting the Marine Stewardship Council risk-based framework to estimate impacts on seabirds, marine mammals, marine turtles and sea snakes - Stephanie D. Good; Kate Dewar; Polly Burns; Keith Sainsbury; Richard A. Phillips; Bryan P. Wallace; Caterina Fortuna; Vinay Udyawer; Bruce Robson; Edward F. Melvin; Rohan J.C. Currey (Marine Policy, 2024)

Long- and short-term soil storage methods other than freezing can be useful for DNA-based microbial community analysis - Joseph D. Edwards; Sarah J. Love; Richard P. Phillips; Songlin Fei; Grant Domke; John D. Parker; Melissa McCormick; Elizabeth A. LaRue; Jennifer A. Schweitzer; Joseph K. Bailey; James Fordyce; Stephanie N. Kivlin (Soil Biology and Biochemistry, 2024)

IPD3, a master regulator of arbuscular mycorrhizal symbiosis, affects genes for immunity and metabolism of non-host Arabidopsis when restored long after its evolutionary loss - Eli D. Hornstein; Melodi Charles; Megan Franklin; Brianne Edwards; Simina Vintila; Manuel Kleiner; Heike Sederoff (Plant Molecular Biology, 2024)
Arbuscular mycorrhizal symbiosis (AM) is a beneficial trait originating with the first land plants, which has subsequently been lost by species scattered throughout the radiation of plant diversity to the present day, including the model Arabidopsis thaliana . To explore if elements of this apparently beneficial trait are still present and could be reactivated we generated Arabidopsis plants expressing a constitutively active form of Interacting Protein of DMI3 , a key transcription factor that enables AM within the Common Symbiosis Pathway, which was lost from Arabidopsis along with the AM host trait. We characterize the transcriptomic effect of expressing IPD3 in Arabidopsis with and without exposure to the AM fungus (AMF) Rhizophagus irregularis , and compare these results to the AM model Lotus japonicus and its ipd3 knockout mutant cyclops-4 . Despite its long history as a non-AM species, restoring IPD3 in the form of its constitutively active DNA-binding domain to Arabidopsis altered expression of specific gene networks. Surprisingly, the effect of expressing IPD3 in Arabidopsis and knocking it out in Lotus was strongest in plants not exposed to AMF, which is revealed to be due to changes in IPD3 genotype causing a transcriptional state, which partially mimics AMF exposure in non-inoculated plants. Our results indicate that molecular connections to symbiosis machinery remain in place in this nonAM species, with implications for both basic science and the prospect of engineering this trait for agriculture.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Accuracy of patient race and ethnicity data in a central cancer registry - Rachel R. Codden; Carol Sweeney; Blessing S. Ofori-Atta; Kimberly A. Herget; Kacey Wigren; Sandra Edwards; Marjorie E. Carter; Rachel D. McCarty; Mia Hashibe; Jennifer A. Doherty; Morgan M. Millar (Cancer Causes & Control, 2024)

Soil microbial community response to ectomycorrhizal dominance in diverse neotropical montane forests - Joseph D. Edwards; Alexander H. Krichels; Georgia S. Seyfried; James Dalling; Angela D. Kent; Wendy H. Yang (Mycorrhiza, 2024)
Ectomycorrhizal (EM) associations can promote the dominance of tree species in otherwise diverse tropical forests. These EM associations between trees and their fungal mutualists have important consequences for soil organic matter cycling, yet the influence of these EM-associated effects on surrounding microbial communities is not well known, particularly in neotropical forests. We examined fungal and prokaryotic community composition in surface soil samples from mixed arbuscular mycorrhizal (AM) and ectomycorrhizal (EM) stands as well as stands dominated by EM-associated Oreomunnea mexicana (Juglandaceae) in four watersheds differing in soil fertility in the Fortuna Forest Reserve, Panama. We hypothesized that EM-dominated stands would support distinct microbial community assemblages relative to the mixed AM-EM stands due to differences in carbon and nitrogen cycling associated with the dominance of EM trees. We expected that this microbiome selection in EM-dominated stands would lead to lower overall microbial community diversity and turnover, with tighter correspondence between general fungal and prokaryotic communities. We measured fungal and prokaryotic community composition via high-throughput Illumina sequencing of the ITS2 (fungi) and 16S rRNA (prokaryotic) gene regions. We analyzed differences in alpha and beta diversity between forest stands associated with different mycorrhizal types, as well as the relative abundance of fungal functional groups and various microbial taxa. We found that fungal and prokaryotic community composition differed based on stand mycorrhizal type. There was lower prokaryotic diversity and lower relative abundance of fungal saprotrophs and pathogens in EM-dominated than AM-EM mixed stands. However, contrary to our prediction, there was lower homogeneity for fungal communities in EM-dominated stands compared to mixed AM-EM stands. Overall, we demonstrate that EM-dominated tropical forest stands have distinct soil microbiomes relative to surrounding diverse forests, suggesting that EM fungi may filter microbial functional groups in ways that could potentially influence plant performance or ecosystem function.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Prenatal and perinatal exposure to Per- and polyfluoroalkyl substances (PFAS)-contaminated drinking water impacts offspring neurobehavior and development - Melissa J. Marchese; Tianyi Zhu; Andrew B. Hawkey; Katherine Wang; Emi Yuan; Jinchen Wen; Sara E. Be; Edward D. Levin; Liping Feng (Science of The Total Environment, 2024)

Mineral dust optical properties for remote sensing and global modeling: A review - Patricia Castellanos; Peter Colarco; W. Reed Espinosa; Scott D. Guzewich; Robert C. Levy; Ron L. Miller; Mian Chin; Ralph A. Kahn; Osku Kemppinen; Hans Moosmüller; Edward P. Nowottnick; Adriana Rocha-Lima; et al. (Remote Sensing of Environment, 2024)

Embryonic exposures to cadmium and PAHs cause long-term and interacting neurobehavioral effects in zebrafish - Alexandra Stickler; Andrew B. Hawkey; Anas Gondal; Sarabesh Natarajan; Mikayla Mead; Edward D. Levin (Neurotoxicology and Teratology, 2024)

Overprinting orogenic events, ductile extrusion and strain partitioning during Caledonian transpression, NW Mainland Shetland - Timothy B. Armitage; Robert E. Holdsworth; Robin A. Strachan; Edward D. Dempsey; Richard J. Walker; Diana T. Alvarez-Ruiz; Geoffrey E. Lloyd (Journal of Structural Geology, 2024)

Conflicts and opportunities for commercial tree plantation expansion and biodiversity restoration across Brazil - Gianluca Cerullo; Thomas Worthington; Pedro Brancalion; Joyce Brandão; Francisco d'Albertas; Alison Eyres; Thomas Swinfield; David Edwards; Andrew Balmford (Global Change Biology, 2024)
Substantial global restoration commitments are occurring alongside a rapid expansion in land‐hungry tropical commodities, including to supply increasing demand for wood products. Future commercial tree plantations may deliver high timber yields, shrinking the footprint of production forestry, but there is an as‐yet unquantified risk that plantations may expand into priority restoration areas, with marked environmental costs. Focusing on Brazil—a country of exceptional restoration importance and one of the largest tropical timber producers—we use random forest models and information on the economic, social, and spatial drivers of historic commercial tree plantation expansion to estimate and map the probability of future monoculture tree plantation expansion between 2020 and 2030. We then evaluate potential plantation‐restoration conflicts and opportunities at national and biome‐scales and under different future production and restoration pathways. Our simulations show that of 2.8 Mha of future plantation expansion (equivalent to plantation expansion 2010–2020), ~78,000 ha (3%) is forecast to occur in the top 1% of restoration priority areas for terrestrial vertebrates, with ~547,500 ha (20%) and ~1,300,000 ha (46%) in the top 10% and 30% of priority areas, respectively. Just ~459,000 ha (16%) of expansion is forecast within low‐restoration areas (bottom 30% restoration priorities), and the first 1 Mha of plantation expansion is likely to have disproportionate impacts, with potential restoration‐plantation overlap starkest in the Atlantic Forest but prominent in the Pampas and Cerrado as well. Our findings suggest that robust, coherent land‐use policies must be deployed to ensure that significant trade‐offs between restoration and production objectives are navigated, and that commodity expansion does not undermine the most tractable conservation gains under emerging global restoration agendas. They also highlight the potentially significant role an engaged forestry sector could play in improving biodiversity outcomes in restoration projects in Brazil, and presumably elsewhere.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Assessment of mercury distribution and bioavailability from informal coastal cinnabar mining - Risk to the marine environment - Yusthinus Tobias Male; Amanda Reichelt-Brushett; Edward D. Burton; Alberth Nanlohy (Marine Pollution Bulletin, 2024)

Evaluating ecological benefits of oceanic protected areas - Arthur Blanluet; Edward T. Game; Daniel C. Dunn; Jason D. Everett; Amanda T. Lombard; Anthony J. Richardson (Trends in Ecology & Evolution, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Canopy-mediated microclimate refugia do not match narrow regeneration niches in a managed dry conifer forest - Edward M. Hill; Jeffery B. Cannon; Seth Ex; Troy W. Ocheltree; Miranda D. Redmond (Forest Ecology and Management, 2024)

How well do existing surveys track fish community performance measures in the St. Clair-Detroit River System? - Corbin D. Hilling; Megan L. Belore; James Boase; Justin A. Chiotti; Robin L. DeBruyne; Susan E. Doka; Richard Drouin; Christine M. Mayer; Jeff. T. Tyson; Todd Wills; Edward F. Roseman (Environmental Monitoring and Assessment, 2024)

Ocean climate and hydrodynamics drive decadal shifts in Northeast Atlantic dinoflagellates - Loïck Kléparski; Grégory Beaugrand; Clare Ostle; Martin Edwards; Morten D. Skogen; Nicolas Djeghri; Hjálmar Hátún (Global Change Biology, 2024)
The abundance of large marine dinoflagellates has declined in the North Sea since 1958. Although hypotheses have been proposed to explain this diminution (increasing temperature and wind), the mechanisms behind this pattern have thus far remained elusive. In this article, we study the long‐term changes in dinoflagellate biomass and biodiversity in relation to hydro‐climatic conditions and circulation within the North Atlantic. Our results show that the decline in biomass has paralleled an increase in biodiversity caused by a temperature‐induced northward movement of subtropical taxa along the European shelf‐edge, and facilitated by changes in oceanic circulation (subpolar gyre contraction). However, major changes in North Atlantic hydrodynamics in the 2010s (subpolar gyre expansion and low‐salinity anomaly) stopped this movement, which triggered a biodiversity collapse in the North Sea. Further, North Sea dinoflagellate biomass remained low because of warming. Our results, therefore, reveal that regional climate warming and changes in oceanic circulation strongly influenced shifts in dinoflagellate biomass and biodiversity.

Surface ocean warming near the core of hurricane Sam and its representation in forecast models - Andrew M. Chiodi; Hristina Hristova; Gregory R. Foltz; Jun A. Zhang; Calvin W. Mordy; Catherine R. Edwards; Chidong Zhang; Christian Meinig; Dongxiao Zhang; Edoardo Mazza; Edward D. Cokelet; Eugene F. Burger; et al. (Frontiers in Marine Science, 2024)
On September 30, 2021, a saildrone uncrewed surface vehicle intercepted Hurricane Sam in the northwestern tropical Atlantic and provided continuous observations near the eyewall. Measured surface ocean temperature unexpectedly increased during the first half of the storm. Saildrone current shear and upper-ocean structure from the nearest Argo profiles show an initial trapping of wind momentum by a strong halocline in the upper 30 m, followed by deeper mixing and entrainment of warmer subsurface water into the mixed layer. The ocean initial conditions provided to operational forecast models failed to capture the observed upper-ocean structure. The forecast models failed to simulate the warming and developed a surface cold bias of ~0.5°C by the time peak winds were observed, resulting in a 12-17% underestimation of surface enthalpy flux near the eyewall. Results imply that enhanced upper-ocean observations and, critically, improved assimilation into the hurricane forecast systems, could directly benefit hurricane intensity forecasts.

The underwater soundscape of the North Sea - F. Basan; J.-G. Fischer; R. Putland; J. Brinkkemper; C.A.F. de Jong; B. Binnerts; A. Norro; D. Kühnel; L.-A. Ødegaard; M. Andersson; E. Lalander; J. Tougaard; et al. (Marine Pollution Bulletin, 2024)

Multi-fidelity data-adaptive autonomous seakeeping - Michael D. Levine; Samuel J. Edwards; Dayne Howard; Kenneth Weems; Themistoklis P. Sapsis; Vladas Pipiras (Ocean Engineering, 2024)

Biomass pretreatment with distillable ionic liquids for an effective recycling and recovery approach - Ezinne C. Achinivu; Brian W. Blankenship; Nawa Raj Baral; Hemant Choudhary; Ramu Kakumanu; Mood Mohan; Edward E.K. Baidoo; Corinne D. Scown; Anthe George; Blake A. Simmons; John Gladden (Chemical Engineering Journal, 2024)

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

The relative influence of temperature and ontogeny on groundfish distribution varies across life stages - Lingbo Li; Anne B. Hollowed; Edward D. Cokelet; Aimee A. Keller; Steve J. Barbeaux; Michelle M. McClure; Wayne A. Palsson (Fish and Fisheries, 2024)
Distributional changes for fish populations may be difficult to interpret since temperature responses are often confounded with ontogenetic shifts. However, the relative importance of these two types of fish movement (temperature responses and ontogenetic shifts) to population distribution remains largely unstudied. This study presents the first attempt to compare the two types of movement in depth, latitude and longitude for 10 abundant groundfish species across size class and subregion. We utilized large, quality‐controlled datasets from random depth‐stratified, bottom trawl surveys consistently conducted during the summer along NE Pacific shelf from 1996 to 2015. We show that the size structure of each species varied across years and subregions with dramatically strong or poor recruitments for some species in 2015 during a marine heatwave. Principal component analysis (PCA) demonstrated that ontogenetic shifts in depth represented the primary movement pattern while temperature responses in latitude and longitude constituted a major, but a secondary pattern. Re‐run by size class, PCA results further showed that the influence of temperature and ontogeny on population distribution varied by size classes with greater ontogenetic shifts in smaller fish and elevated temperature responses in larger fish. We further show substantial ontogeny‐induced movements by depth, latitude and longitude with high variability among species and subregions. Our analyses suggest that failing to account for size structure can lead to serious misinterpretation of population distributional changes in all three dimensions: depth, latitude and longitude for populations with or without episodic recruitments.

Fungal community dissimilarity predicts plant–soil feedback strength in a lowland tropical forest - Camille S. Delavaux; Janika K. Angst; Hilario Espinosa; Makenna Brown; Daniel F. Petticord; John W. Schroeder; Kirk Broders; Edward A. Herre; James D. Bever; Thomas W. Crowther (Ecology, 2024)
Soil microbes impact plant community structure and diversity through plant–soil feedbacks. However, linking the relative abundance of plant pathogens and mutualists to differential plant recruitment remains challenging. Here, we tested for microbial mediation of pairwise feedback using a reciprocal transplant experiment in a lowland tropical forest in Panama paired with amplicon sequencing of soil and roots. We found evidence that plant species identity alters the microbial community, and these changes in microbial composition alter subsequent growth and survival of conspecific plants. We also found that greater community dissimilarity between species in their arbuscular mycorrhizal and nonpathogenic fungi predicted increased positive feedback. Finally, we identified specific microbial taxa across our target functional groups that differentially accumulated under conspecific settings. Collectively, these findings clarify how soil pathogens and mutualists mediate net feedback effects on plant recruitment, with implications for management and restoration.

Portion size affects food selection in an immersive virtual reality buffet and is related to measured intake in laboratory meals varying in portion size - John W. Long; Sara J. Pritschet; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Barbara J. Rolls; Travis D. Masterson (Appetite, 2023)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

Significant improvement in freshwater invertebrate biodiversity in all types of English rivers over the past 30 years - Yueming Qu; Virginie Keller; Nuria Bachiller-Jareno; Michael Eastman; Francois Edwards; Monika D. Jürgens; John P. Sumpter; Andrew C. Johnson (Science of The Total Environment, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Episodic population fragmentation and gene flow reveal a trade‐off between heterozygosity and allelic richness - Peta Hill; Chris R. Dickman; Russell Dinnage; Richard P. Duncan; Scott V. Edwards; Aaron Greenville; Stephen D. Sarre; Emily J. Stringer; Glenda M. Wardle; Bernd Gruber (Molecular Ecology, 2023)
In episodic environments like deserts, populations of some animal species exhibit irregular fluctuations such that populations are alternately large and connected or small and isolated. Such dynamics are typically driven by periodic resource pulses due, for example, to large but infrequent rainfall events. The repeated population bottlenecks resulting from fragmentation should lower genetic diversity over time, yet species undergoing these fluctuations appear to maintain high levels of genetic diversity. To resolve this apparent paradox, we simulated a metapopulation of constant size undergoing repeat episodes of fragmentation and change in gene flow to mimic outcomes experienced by mammals in an Australian desert. We show that episodic fragmentation and gene flow have contrasting effects on two measures of genetic diversity: heterozygosity and allelic richness. Specifically, fragmentation into many, small subpopulations, coupled with periods of infrequent gene flow, preserves allelic richness at the expense of heterozygosity. In contrast, fragmentation into a few, large subpopulations maintains heterozygosity at the expense of allelic richness. The strength of the trade‐off between heterozygosity and allelic richness depends on the amount of gene flow and the frequency of gene flow events. Our results imply that the type of genetic diversity maintained among species living in strongly fluctuating environments will depend on the way populations fragment, with our results highlighting different mechanisms for maintaining allelic richness and heterozygosity in small, fragmented populations.

Reply to Discussion of Yule, C. T. G., Daniell, J., Edwards, D. S., Rollet, N., & Roberts, E. M. (2023). Reconciling the onshore/offshore stratigraphy of the Canning Basin and implications for petroleum prospectivity. Australian Journal of Earth Sciences , 70 (5), 691–715 - C. T. G. Yule; J. Daniell; D. S. Edwards; N. Rollet; E. M. Roberts (Australian Journal of Earth Sciences, 2023)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Neonicotinoid mixture alters trophic interactions in a freshwater aquatic invertebrate community - Claire Duchet; Fan Hou; Cailin A. Sinclair; Zhenyu Tian; Alyssa Kraft; Vojtech Kolar; Edward P. Kolodziej; Jenifer K. McIntyre; John D. Stark (Science of The Total Environment, 2023)

Sublethal chemical stimulation of arthropod parasitoids and parasites of agricultural and environmental importance - Evgenios Agathokleous; James D. Blande; Noboru Masui; Edward J. Calabrese; Jing Zhang; Pierre Sicard; Raul Narciso C. Guedes; Giovanni Benelli (Environmental Research, 2023)

Stimulation of insect vectors of pathogens by sublethal environmental contaminants: A hidden threat to human and environmental health? - Evgenios Agathokleous; James D. Blande; Edward J. Calabrese; Raul Narciso C. Guedes; Giovanni Benelli (Environmental Pollution, 2023)

Incorporating Uremic Solute-mediated Inhibition of OAT1/3 Improves PBPK Prediction of Tenofovir Renal and Systemic Disposition in Patients with Severe Kidney Disease - Shih-Yu Chang; Weize Huang; Alenka Chapron; Antonio J. López Quiñones; Joanne Wang; Nina Isoherranen; Danny D. Shen; Edward J. Kelly; Jonathan Himmelfarb; Catherine K. Yeung (Pharmaceutical Research, 2023)

Isopropyl alcohol inhalation versus 5-HT3 antagonists for treatment of nausea: a meta-analysis of randomised controlled trials - James S. Kimber; Joshua G. Kovoor; John M. Glynatsis; Samuel J. West; Thi Thien Nhi Mai; Jonathan Henry W. Jacobsen; Christopher D. Ovenden; Stephen Bacchi; Joseph N. Hewitt; Aashray K. Gupta; Suzanne Edwards; Fiona J. Taverner; et al. (European Journal of Clinical Pharmacology, 2023)
Purpose Nausea is a common and unpleasant sensation for which current therapies such as serotonin (5-HT 3 ) antagonists are often ineffective, while also conferring a risk of potential adverse events. Isopropyl alcohol (IPA) has been proposed as a treatment for nausea. We aimed to compare IPA with 5-HT 3 antagonists for the treatment of nausea across all clinical settings. Methods MEDLINE, EMBASE, PubMed, CENTRAL and CINAHL were searched from inception to 17 July 2023 for randomised controlled trials (RCTs) comparing inhaled IPA and a 5-HT 3 antagonist for treatment of nausea. Severity and duration of nausea, rescue antiemetic use, adverse events and patient satisfaction were the outcomes sought. Risk of bias (RoB) was assessed using Cochrane RoB 2. Random-effects model was used for meta-analysis. Combination of meta-analyses and narrative review was used to synthesise findings. The evidence was appraised using GRADE. Results From 1242 records, 4 RCTs were included with 382 participants. Participants receiving IPA had a significantly lower mean time to 50% reduction in nausea (MD − 20.06; 95% CI − 26.26, − 13.85). Nausea score reduction at 30 min was significantly greater in the IPA group (MD 21.47; 95% CI 15.47, 27.47). IPA led to significantly reduced requirement for rescue antiemetics (OR 0.60; 95% CI 0.37, 0.95; p = 0.03). IPA led to no significant difference in patient satisfaction when compared with a 5-HT 3 antagonist. The overall GRADE assessment of evidence quality ranged from very low to low. Conclusion IPA may provide rapid, effective relief of nausea when compared with 5-HT 3 antagonists.

Icescape‐scale metabolomics reveals cyanobacterial and topographic control of the core metabolism of the cryoconite ecosystem of an Arctic ice cap - Jarishma K. Gokul; Luis A. J. Mur; Andrew J. Hodson; Tristram D. L. Irvine‐Fynn; Aliyah R. Debbonaire; Nozomu Takeuchi; Arwyn Edwards (Environmental Microbiology, 2023)
Glaciers host ecosystems comprised of biodiverse and active microbiota. Among glacial ecosystems, less is known about the ecology of ice caps since most studies focus on valley glaciers or ice sheet margins. Previously we detailed the microbiota of one such high Arctic ice cap, focusing on cryoconite as a microbe‐mineral aggregate formed by cyanobacteria. Here, we employ metabolomics at the scale of an entire ice cap to reveal the major metabolic pathways prevailing in the cryoconite of Foxfonna, central Svalbard. We reveal how geophysical and biotic processes influence the metabolomes of its resident cryoconite microbiota. We observed differences in amino acid, fatty acid, and nucleotide synthesis across the cap reflecting the influence of ice topography and the cyanobacteria within cryoconite. Ice topography influences central carbohydrate metabolism and nitrogen assimilation, whereas bacterial community structure governs lipid, nucleotide, and carotenoid biosynthesis processes. The prominence of polyamine metabolism and nitrogen assimilation highlights the importance of recycling nitrogenous nutrients. To our knowledge, this study represents the first application of metabolomics across an entire ice mass, demonstrating its utility as a tool for revealing the fundamental metabolic processes essential for sustaining life in supraglacial ecosystems experiencing profound change due to Arctic climate change‐driven mass loss.

Light to moderate long-term grazing enhances ecosystem carbon across a broad climatic gradient in northern temperate grasslands - Edward W. Bork; Daniel B. Hewins; Eric G. Lamb; Cameron N. Carlyle; Mark P. Lyseng; Scott X. Chang; Michael J. Alexander; Walter D. Willms; Majid Iravani (Science of The Total Environment, 2023)

Mitochondrial dysfunction and oxidative stress contribute to cross-generational toxicity of benzo(a)pyrene in Danio rerio - Jordan S. Kozal; Nishad Jayasundara; Andrey Massarsky; Casey D. Lindberg; Anthony N. Oliveri; Ellen M. Cooper; Edward D. Levin; Joel N. Meyer; Richard T. Di Giulio (Aquatic Toxicology, 2023)

Impact of growth conditions on the nitrogen, protein, colour and amino acid profiles of the cultured macroalga, Palmaria palmata - Anthony Temitope Idowu; Miryam Amigo-Benavent; Marta Santos-Hernández; Susan Whelan; Maeve D. Edwards; Richard J. FitzGerald (Journal of Applied Phycology, 2023)
The impact of growth conditions on the nitrogen, protein, colour and amino acid profiles of Palmaria palmata (from 2 locations) were investigated. Laboratory cultures of P. palmata were grown over a period of 18 days with and without nutrient addition, i.e., with culture medium (F/2) and urea (0.05 or 0.10 g L −1 ). The total nitrogen (TN) content of cultured P. palmata originating from longlines harvested from Cork increased with the addition of culture medium (F/2) and urea (0.05 g L −1 ) in comparison to the initial sample (4.15 ± 0.05 vs 1.73 ± 0.03%) while biomass from Galway increased with addition of culture medium (F/2) and urea (0.10 g L −1 ) in comparison to the initial sample (3.72 ± 0.05 vs 2.43 ± 0.06%). The protein nitrogen (PN) and non-protein nitrogen (NPN) of cultured P. palmata originating from Galway also increased when grown with the addition of nutrients. Nutrient enrichment during growth influenced the colour characteristics (lightness L*, redness a*, yellowness b* and colour difference ΔE) and the electrophoretic protein profile. Correlations between TN and ΔE (r = 0.945) for Cork originated sample, PN and ΔE (r =-0.944) and NPN and ΔE (r = 0.734) for Galway originated sample were observed. In-gel digestion followed by UPLC-MS/MS demonstrated that RuBiSCo, phycoerythrin and allophycocyanin expression in P. palmata was enhanced with nutrient addition. Amino acid profile and score analysis showed variation as a function of nutrient addition. Overall, nutrient inclusion in the growth medium provides a strategy for the enhanced production of high-quality protein by P. palmata.

Importance of marine-estuarine-riverine connectivity to larvae and early juveniles of estuary-associated fish taxa - Alan K. Whitfield; Edward D. Houde; Francisco J. Neira; Ian C. Potter (Environmental Biology of Fishes, 2023)

An onshore-offshore interpretation of structures in the Devonian rocks of the Pentland Firth, Scotland using high resolution bathymetry and drone-enabled field observations. - Thomas A.G. Utley; Robert E. Holdsworth; Richard J. Walker; Edward D. Dempsey; Ken J.W. McCaffrey; Anna Dichiarante; Thomas L. Jones (Journal of Structural Geology, 2023)

Determining the sustainability of legal wildlife trade - Alice Hughes; Mark Auliya; Sandra Altherr; Brett Scheffers; Jordi Janssen; Vincent Nijman; Chris R. Shepherd; Neil D'Cruze; Emerson Sy; David P. Edwards (Journal of Environmental Management, 2023)

In need-based sharing, sharing is more important than need - Aaron D. Lightner; Anne C. Pisor; Edward H. Hagen (Evolution and Human Behavior, 2023)

Genetically engineered varieties and applied pesticide toxicity in U.S. maize and soybeans: Heterogeneous and evolving impacts - Seungki Lee; GianCarlo Moschini; Edward D. Perry (Ecological Economics, 2023)

Mechanisms and models for industry engagement in collaborative research in commercial fisheries - Matthew R. Baker; Robert Alverson; Ruth Christiansen; Keith Criddle; Danny Eilertsen; Robert J. Foy; John Gauvin; Scott E. Goodman; Leigh Habegger; Bradley P. Harris; Nicole Kimball; Anna Malek Mercer; et al. (Frontiers in Marine Science, 2023)
Data and insights from fishers are essential sources of information to advance understanding of fishery and ecosystem dynamics. Incorporating fisher and industry knowledge holds prospects for improving marine science and fisheries management. We address cooperative research in the context of collaboration between fishers, scientists, industries, universities, and agencies to develop applied research to understand marine ecosystems, inform fishery management, enhance sustainability, govern resource use, and investigate social-economic dynamics. We leverage the insights of more than 100 research scientists, fisheries managers, industry representatives, and fishers to outline actionable recommendations for effective approaches and mechanisms to integrate industry data, perspectives, and insights in fisheries science. We also highlight opportunities and address challenges and limitations to such collaboration.

Deriving spatial wave data from a network of buoys and ships - Raphaël E.G. Mounet; Jiaxin Chen; Ulrik D. Nielsen; Astrid H. Brodtkorb; Ajit C. Pillai; Ian G.C. Ashton; Edward C.C. Steele (Ocean Engineering, 2023)

Food Insecurity and Adequacy of Dietary Intake in Youth and Young Adults With Youth-Onset Type 1 and Type 2 Diabetes - Hope Bercaw; Lauren A. Reid; Jason A. Mendoza; Edward A. Frongillo; Katherine A. Sauder; Beth A. Reboussin; Elizabeth J. Mayer-Davis; Dana Dabelea; Santica M. Marcovina; Carla Mercado; Angela D. Liese (Journal of the Academy of Nutrition and Dietetics, 2023)

Adaptive, multi-paddock, rotational grazing management alters foraging behavior and spatial grazing distribution of free-ranging cattle - David J. Augustine; Sean P. Kearney; Edward J. Raynor; Lauren M. Porensky; Justin D. Derner (Agriculture, Ecosystems & Environment, 2023)

Marine nutrient subsidies promote biogeochemical hotspots in undisturbed, highly humic estuaries - Chris D. Evans; Stacey L. Felgate; Steffi Carter; Mark Stinchcombe; Edward Mawji; Andrew P. Rees; Inma Lebron; Richard Sanders; Paul Brickle; Daniel J. Mayor (Limnology and Oceanography, 2023)
The land‐ocean dissolved organic carbon (DOC) flux represents a significant term within the global carbon budget, with peatland‐dominated regions representing the most intense sources of terrestrial DOC export. As the interface between freshwater and marine systems, estuaries have the potential to act as a filter of the land‐ocean carbon flux, removing terrestrially derived DOC, which is present at low concentrations in the oceans, via a combination of physicochemical and biological processes. However, the fate of peat‐derived DOC within estuaries remains poorly quantified, partly due to the complicating influences of heterogeneous soils, land‐use, point sources, and upstream modification of organic matter. To minimize these modifying factors, we studied DOC and inorganic nutrients in four small, peat‐dominated, minimally disturbed, and oligotrophic Falkland Island estuaries. Contrary to expectations, we found limited evidence of physicochemical estuarine DOC removal, and instead observed apparent “hot zones” of biogeochemical activity, where terrestrially‐derived silicate mixed with inorganic nitrogen and phosphorus entering the estuaries from the nutrient‐rich marine ecosystem. In two estuaries, this coincided with apparent in situ DOC production. We suggest that the observed phenomena of marine nutrient subsidy of estuarine productivity, and flexible utilization of multiple nutrients within the oligotrophic system, may once have been widespread in temperate estuaries. However, this function has been lost in many ecosystems due to catchment eutrophication by agricultural and urban development. We conclude that the estuaries of the Falkland Islands provide a valuable pre‐disturbance analogue for natural biogeochemical functioning in temperate estuaries receiving high organic matter inputs.

Reconstruction of the palaeo‐sea level of Britain and Ireland arising from empirical constraints of ice extent: implications for regional sea level forecasts and North American ice sheet volume - SARAH L. Bradley; JEREMY C. Ely; CHRIS D. Clark; ROBIN J. Edwards; Ian Shennan (Journal of Quaternary Science, 2023)
Reconstructions of palaeo‐sea level are vital for predicting future sea level change and constraining palaeo‐ice sheet reconstructions, as well as being useful for a wide array of applications across Quaternary Science. Previous reconstructions of the palaeo‐sea level of Britain and Ireland relied on a circular tuning of glacio‐isostatic models: input ice sheet thicknesses and extents were iteratively altered to fit relative sea level data. Here we break that circularity by utilizing new data from the BRITICE‐CHRONO project, which constrains the position of the British–Irish ice sheet margin through time, and we compare derived glacio‐isostatic modelling to the rich relative sea level record. We test a combination of plausible ice thickness scenarios which account for the uncertainty of ice margin position over the North Sea, demonstrating the region where regional sea level data could distinguish between different glaciation scenarios. Our optimal reconstruction is then combined with several global‐scale reconstructions. As the signal of the British–Irish Ice Sheet is constrained, we demonstrate how the relative sea level record of Britain and Ireland can be used to test reconstructions of far‐field ice sheets (e.g. Antarctica, Eurasia and the Laurentide). The derived palaeo‐topography data are likely to be useful for multiple disciplines. Finally, our improved method of sea level reconstruction impacts predictions of contemporary vertical land motion.

Reconciling the onshore/offshore stratigraphy of the Canning Basin and implications for petroleum prospectivity - C. T. G. Yule; J. Daniell; D. S. Edwards; N. Rollet; E. M. Roberts (Australian Journal of Earth Sciences, 2023)

Toward a ground-based and long-term meteorological forcing dataset for South Korea - Kyungtae Lee; Do Hyuk Kang; Hahn Chul Jung; Gwangha Park; Changwoo Gye; Sujay Kumar; Edward J. Kim; Christa D. Peters-lidard; EuiHo Hwang (Theoretical and Applied Climatology, 2023)
The Modern-Era Retrospective Analysis for Research and Application version 2 (MERRA-2) is a well-established reanalysis dataset and is widely used for driving global-scale hydrological models. However, owing to its relatively coarse spatial resolution (0.5°), the capability of MERRA-2 is repeatedly challenged in regional-scale studies, especially for smaller areas of interest. In addition, the availability of in situ observation data is a pressing issue for generating meteorological forcing. We developed a grid-based high spatial (0.125°) and temporal (hourly) resolution meteorological forcing dataset, which can evaluate hydrological processes in South Korea using state-of-the-art meteorological observations from 1980 to 2020. The forcing dataset was created by combining Automated Synoptic Observing System (ASOS) in situ measurement data from the Korean Meteorological Administration and MERRA-2 reanalysis datasets. Five meteorological variables were provided in the ASOS-MERRA2 (precipitation, air temperature, surface pressure, specific humidity, and wind speed). The study demonstrates that the region-based and high spatial resolution of ASOS-MERRA2 is superior to the existing MERRA-2 with improvements of all five weather variables, for example, from 5.6 to 2.8 mm root mean square error of precipitation. The ASOS-MERRA2 was more capable of reducing the biases and root mean squared error by improving the coefficient of determination compared with MERRA-2 for all five variables. The newly developed ASOS-MERRA2 provides an opportunity to drive land surface models to evaluate the hydroclimatic conditions in South Korea.

Progesterone-stimulated endometrial cell conditioned media increases in vitro produced bovine embryo blastocyst formation - Mary A. Oliver; Katie D. Peterson; Sadikshya Bhandari; Rebecca R. Payton; J. Lannett Edwards; Daniel J. Mathew (Animal Reproduction Science, 2023)

A complete COI library of Samoan butterflies reveals layers of endemic diversity on oceanic islands - Claudia Bruschini; Eric D. Edwards; Gerard Talavera; Varea D. Vaurasi; Galumalemana F. Latu; Leonardo Dapporto (Zoologica Scripta, 2023)
We investigated the entire butterfly fauna of the Samoan Archipelago (Pacific Ocean) by combining COI barcode sequences for specimens from these islands with those available in repositories at larger biogeographic scale. Haplotype networks and a generalized mixed Yule‐coalescent (GMYC) model were applied to identify evolutionary significant units (ESUs). The ESUs from Samoan islands were compared with ESUs of the same or sister taxa regionally and worldwide to explore the level of endemicity and of congruence between established taxonomy and COI barcodes. The level of ESUs endemicity was similar to that shown by species and subspecies. Australia was the most frequent origin for Samoan lineages, followed by Orient‐Asia. When comparing the agreement and mismatch between established taxonomy and ESUs between the Australia‐Oceania region and Europe and North America, the COI molecular marker revealed a similar performance in taxonomic identification. Despite this overall convergent pattern, the degree of mtDNA divergence and the analysis of functional traits suggested that the mechanisms producing patterns of genetic differentiation in temperate butterflies over ancient continental lands differ to those occurring across a vast ocean into geologically young islands. Mechanisms on Samoan islands include relatively recent and exceptional oceanic dispersal, possibly followed by repeated extinction events. In the Australia‐Oceania region we found a similar fraction of species showing introgression with the maintenance of phenotypic differences as it occurs on the mainland, but the phenomenon was limited to sectors of each species distribution area. Regular gene flow among the Samoan islands seems to prevent allopatric speciation within the archipelago.

Short-term and intermediate-term fine particulate air pollution are synergistically associated with habitual sleep variability in adolescents – A cross-sectional study - Fan He; Jeff D. Yanosky; Edward O. Bixler; Julio Fernandez-Mendoza; Vernon M. Chinchilli; Laila Al-Shaar; Alexandros N. Vgontzas; Duanping Liao (Environmental Research, 2023)

Corrigendum to “A functional size-spectrum model of the global marine ecosystem that resolves zooplankton composition”, Ecological Modelling, 2020, 435: 109265 - Ryan F. Heneghan; Jason D. Everett; Patrick Sykes; Sonia D. Batten; Martin Edwards; Kunio Takahashi; Iain M. Suthers; Julia L. Blanchard; Anthony J. Richardson (Ecological Modelling, 2023)

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Embryonic exposure to PFAS causes long-term, compound-specific behavioral alterations in zebrafish - Andrew B. Hawkey; Mikayla Mead; Sarabesh Natarajan; Anas Gondal; Olivia Jarrett; Edward D. Levin (Neurotoxicology and Teratology, 2023)

Developmental exposure of zebrafish to neonicotinoid pesticides: Long-term effects on neurobehavioral function - Andrew B. Hawkey; Dilanaz Unal; Zade R. Holloway; Edward D. Levin (NeuroToxicology, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Reversibility controls on extreme methane clumped isotope signatures from anaerobic oxidation of methane - Jiarui Liu; Rachel L. Harris; Jeanine L. Ash; James G. Ferry; Sebastian J.E. Krause; Jabrane Labidi; Divya Prakash; Barbara Sherwood Lollar; Tina Treude; Oliver Warr; Edward D. Young (Geochimica et Cosmochimica Acta, 2023)

Phosphomannomutase 2 (PMM2) variants leading to hyperinsulinism-polycystic kidney disease are associated with early-onset inflammatory bowel disease and gastric antral foveolar hyperplasia - Fevronia Kiparissi; Antonia Dastamani; Liina Palm; Aline Azabdaftari; Luis Campos; Edward Gaynor; Stephanie Grünewald; Holm H. Uhlig; Robert Kleta; Detlef Böckenhauer; Kelsey D. J. Jones (Human Genetics, 2023)
Phosphomannomutase 2 (PMM2) deficiency causes Congenital Disorder of Glycosylation (PMM2-CDG), but does not have a recognised association with Inflammatory Bowel Disease (IBD). A distinct clinical syndrome of hyperinsulinism and autosomal recessive polycystic kidney disease (HIPKD) arises in the context of a specific variant in the PMM2 promotor, either in homozygosity, or compound heterozygous with a deleterious PMM2 variant. Here, we describe the development of IBD in three patients with PMM2-HIPKD, with onset of IBD at 0, 6, and 10 years of age. In each case, intestinal inflammation coincided with the unusual finding of gastric antral foveolar hyperplasia. IBD disease was of variable severity at onset but well controlled with conventional and first-line biologic treatment approaches. The organ-level pattern of disease manifestations in PMM2-HIPKD-IBD may reflect a loss of cis -acting regulatory control by hepatocyte nuclear factor 4 alpha (HNF4A). Analysis of published transcriptomic data suggests that IBD most likely arises due to an impact on epithelial cellular function. We identify a specific pattern of variation in PMM2 as a novel association of early-onset IBD with distinctive gastric pathology.

Modes of ingress by larvae and juveniles of marine fishes into estuaries: From microtidal to macrotidal systems - Alan K. Whitfield; Ian C. Potter; Francisco J. Neira; Edward D. Houde (Fish and Fisheries, 2023)
We review published research on the ingress of larvae and early juveniles of marine fishes into estuaries subjected to different tidal regimes and provide perspectives on the abilities and responses of these early‐life stages to the physico‐chemical, hydrodynamic and biological drivers that facilitate such ingress. We focus on documenting ingress and the mechanisms employed by early‐stage fishes from coastal waters to enter different types of microtidal and macrotidal estuaries but also include information on ingress into mesotidal systems. Spawning localities for estuary‐associated marine fishes are assessed with respect to ontogeny of larvae and their ability to ingress estuaries during the preflexion and postflexion stages. The processes and physico‐chemical cues employed by larvae and early juveniles to locate estuaries are reviewed, with olfactory cues being recognised as especially important. Particular emphasis is directed to vertical migratory behaviours and selective tidal stream transport (STST) employed by many larvae ingressing macrotidal estuaries, contrasting with mainly passive flood‐tide entry and active swimming modes typically used by larvae and early juveniles that enter microtidal estuaries and estuarine lakes and lagoon systems.

MOO-GAPS: A multi-objective optimization model for global animal production and sustainability - Adam C. Castonguay; Stephen Polasky; Matthew H. Holden; Mario Herrero; Jinfeng Chang; Daniel Mason-D’Croz; Cecile Godde; Katie Lee; Brett A. Bryan; James Gerber; Edward T. Game; Eve McDonald-Madden (Journal of Cleaner Production, 2023)

Porous titania beads for remediation of arsenic contamination from acid mine drainage - Evelyn Dillon; Bree Morgan; Daniel T. Oldfield; Edward D. Burton; Jessica Veliscek-Carolan (Journal of Environmental Management, 2023)

Climate-driven shifts in pelagic fish distributions in a rapidly changing Pacific Arctic - Robert M. Levine; Alex De Robertis; Daniel Grünbaum; Sharon Wildes; Edward V. Farley; Phyllis J. Stabeno; Christopher D. Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

An experimental analysis of density dependence in meadow voles: Within‐season and delayed effects - Phoebe D. Edwards; Rudy Boonstra; Madan K. Oli (Ecology, 2023)
Wild mammal populations exhibit a variety of dynamics, ranging from fairly stable with little change in population size over time to high‐amplitude cyclic or erratic fluctuations. A persistent question in population ecology is why populations fluctuate as they do. Answering this seemingly simple question has proven to be challenging. Broadly, density‐dependent feedback mechanisms should allow populations to grow at low density and slow or halt growth at high density. However, experimental tests of what demographic processes result in density‐dependent feedback and on what timescale have proven elusive. Here, we used replicated density perturbation experiments and capture‐mark‐recapture analyses to test density‐dependent population growth in populations of meadow voles ( Microtus pennsylvanicus ) during the summer breeding season by manipulating founding population density and observing the pattern of survival, reproduction, and population growth. High population density had no consistent effect on survival rates but generally negatively influenced recruitment and population growth rates. However, these density‐dependent effects varied within the breeding season and across years. Our study provides evidence that density‐dependent feedback mechanisms operate at finer time scales than previously believed and that process, additively with delayed year effects, is key to understanding multiyear population demography.

Martian nonmigrating atmospheric tides in the thermosphere and ionosphere at solar minimum - Scott A. Thaller; Laila Andersson; Edward Thiemann; Marcin D. Pilinski; Xiaohua Fang; Meredith Elrod; Paul Withers; Stephen Bougher; Geoffrey Jenkins (Icarus, 2023)

Porous silicon Fabry-Pérot interferometer designed for sensitive detection of aflatoxin B1 in field crops - D. Nanda Kumar; Ilana Freidman; Edward Sionov; Giorgi Shtenberg (Food Chemistry, 2023)

Is chronic stress a causal mechanism for small mammal population cycles? Reconciling the evidence - Phoebe D. Edwards; Rupert Palme; Rudy Boonstra (Oecologia, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Bioaccessibility of iron in pearl millet flour contaminated with different soil types - Molly Muleya; Scott D. Young; Martin R. Broadley; Edward J.M. Joy; Prosper Chopera; Elizabeth H. Bailey (Food Chemistry, 2023)

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

Profiling human pathogenic repeat expansion regions by synergistic and multi-level impacts on molecular connections - Cong Fan; Ken Chen; Yukai Wang; Edward V. Ball; Peter D. Stenson; Matthew Mort; Albino Bacolla; Hildegard Kehrer-Sawatzki; John A. Tainer; David N. Cooper; Huiying Zhao (Human Genetics, 2023)

Evolving insights into the epidemiology of Moraxella species bloodstream infection from two decades of surveillance in Queensland, Australia - Jessica Schults; Felicity Edwards; Karina Charles; Adam D. Irwin; Claire M. Rickard; Patrick N. A. Harris; David L. Paterson; Kevin Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Abolishment of morphology-based taxa and change to binomial species names: 2022 taxonomy update of the ICTV bacterial viruses subcommittee - Dann Turner; Andrey N. Shkoporov; Cédric Lood; Andrew D. Millard; Bas E. Dutilh; Poliane Alfenas-Zerbini; Leonardo J. van Zyl; Ramy K. Aziz; Hanna M. Oksanen; Minna M. Poranen; Andrew M. Kropinski; Jakub Barylski; et al. (Archives of Virology, 2023)
This article summarises the activities of the Bacterial Viruses Subcommittee of the International Committee on Taxonomy of Viruses for the period of March 2021−March 2022. We provide an overview of the new taxa proposed in 2021, approved by the Executive Committee, and ratified by vote in 2022. Significant changes to the taxonomy of bacterial viruses were introduced: the paraphyletic morphological families Podoviridae , Siphoviridae , and Myoviridae as well as the order Caudovirales were abolished, and a binomial system of nomenclature for species was established. In addition, one order, 22 families, 30 subfamilies, 321 genera, and 862 species were newly created, promoted, or moved.

High summer temperatures are associated with poorer performance of underyearling Atlantic salmon ( Salmo salar ) in upland streams - Fionn R. Bernthal; Ben W. Seaman; Edward Rush; John D. Armstrong; Darryl McLennan; Keith H. Nislow; Neil B. Metcalfe (Journal of Fish Biology, 2023)
Future warming scenarios are predicted to result in an increased frequency of high, and potentially stressful, temperatures in aquatic ecosystems. Here we examined whether the performance of wild underyearling Atlantic salmon ( Salmo salar ) in Scottish streams stocked with identical egg densities was influenced by thermal stress. Biomass and density declined with degree hours exceeding 23°C, indicating apparent mortality or emigration as a possible result of exposure to high temperatures. These results strengthen the need for further action such as riparian tree planting to reduce stream summer temperatures.

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Fortnightly variability of Chl a in the Indonesian seas - Edward D. Zaron; Tonia A. Capuano; Ariane Koch-Larrouy (Ocean Science, 2023)
Twenty years of daily MODIS-Aqua ocean color observations (2002–2022) are used to identify periodic variability of near-surface chlorophyll (Chl a) in the Indonesian seas. The frequency spectrum of Chl a is dominated by the mean and low-frequency monsoonal variability; however, a prominent peak around the fortnightly tidal period, MSf, is present. Harmonic analysis is used to quantify and map the fortnightly Chl a signal, which is discovered to be significant along the continental shelves of NW Australia and at several sites associated with narrow passages between the Lesser Sunda Islands, within the Sulu Archipelago, and at a few other sites in the Philippines Archipelago. Fortnightly variability at the shallow coastal sites is attributed to the spring–neap cycle of barotropic ocean currents, while we hypothesize that the variability in deeper water near the island passages is due to the modulation of vertical nutrient fluxes by baroclinic tidal mixing. The results document the significance of tidal mixing and highlight the heterogeneous character of biophysical processes within the Indonesian seas.

CRISPR-knockout of β-kafirin in sorghum does not recapitulate the grain quality of natural mutants - Karen Massel; Jessica Hintzsche; Jemma Restall; Edward D. Kerr; Benjamin L. Schulz; Ian D. Godwin (Planta, 2023)

Decade long upsurge in mutations associated with pyrethroid resistance in bed bug populations in the USA - Cari D. Lewis; Brenna A. Levine; Coby Schal; Edward L. Vargo; Warren Booth (Journal of Pest Science, 2023)

Using supplemental condensed tannin to mitigate tall fescue toxicosis in non-pregnant, non-lactating ewes consuming tall fescue silage - A.J. Grote; C.C. Nieman; A.R. Morgan; K.P. Coffey; D. Philipp; E.B. Kegley; J.L. Edwards (Animal Feed Science and Technology, 2023)

Guidance on field survey programme design for basement flooding assessment - Albert Z. Jiang; Edward A. McBean; Andrew D. Binns; Bahram Gharabaghi (Hydrological Sciences Journal, 2022)

Sign-oriented Dirichlet Normal Energy: Aligning Dental Topography and Dental Function in the R-package molaR - James D. Pampush; Paul E. Morse; Edward J. Fuselier; Matthew M. Skinner; Richard F. Kay (Journal of Mammalian Evolution, 2022)

Caught red handed: modeling and confirmation of the myeloperoxidase ceruloplasmin alpha-thrombin complex - Yana A. Zabrodskaya; Vladimir V. Egorov; Alexey V. Sokolov; Alexey V. Shvetsov; Yulia E. Gorshkova; Oleksandr I. Ivankov; Valeria A. Kostevich; Nikolay P. Gorbunov; Edward S. Ramsay; Natalya D. Fedorova; Andrey B. Bondarenko; Vadim B. Vasilyev (BioMetals, 2022)

Development of the invasive candidiasis discharge [I Can discharge] model: a mixed methods analysis - Jinhee Jo; Truc T. Tran; Nicholas D. Beyda; Debora Simmons; Joshua A. Hendrickson; Masaad Saeed Almutairi; Faris S. Alnezary; Anne J. Gonzales-Luna; Edward J. Septimus; Kevin W. Garey (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Patients with invasive candidiasis (IC) have complex medical and infectious disease problems that often require continued care after discharge. This study aimed to assess echinocandin use at hospital discharge and develop a transition of care (TOC) model to facilitate discharge for patients with IC. This was a mixed method study design that used epidemiologic assessment to better understand echinocandin use at hospital discharge TOC. Using grounded theory methodology focused on patients given echinocandins during their last day of hospitalization, a TOC model for patients with IC, the invasive candidiasis [I Can] discharge model was developed to better understand discharge barriers. A total of 33% (1405/4211) echinocandin courses were continued until the last day of hospitalization. Of 536 patients chosen for in-depth review, 220 (41%) were discharged home, 109 (20%) were transferred, and 207 (39%) died prior to discharge. Almost half (46%, 151/329) of patients discharged alive received outpatient echinocandin therapy. Independent predictors for outpatient echinocandin use were osteomyelitis (OR, 4.1; 95% CI, 1.1–15.7; p = 0.04), other deep-seated infection (OR, 4.4; 95% CI, 1.7–12.0; p = 0.003), and non-home discharge location (OR, 3.9, 95% CI, 2.0–7.7; p < 0.001). The I Can discharge model was developed encompassing four distinct themes which was used to identify potential barriers to discharge. Significant echinocadin use occurs at hospital discharge TOC. The I Can discharge model may help clinical, policy, and research decision-making processes to facilitate smoother and earlier hospital discharges.

Population genomic structure in Goodman's mouse lemur reveals long‐standing separation of Madagascar's Central Highlands and eastern rainforests - George P. Tiley; Tobias van Elst; Helena Teixeira; Dominik Schüßler; Jordi Salmona; Marina B. Blanco; José M. Ralison; Blanchard Randrianambinina; Rodin M. Rasoloarison; Amanda R. Stahlke; Paul A. Hohenlohe; Lounès Chikhi; et al. (Molecular Ecology, 2022)
Madagascar's Central Highlands are largely composed of grasslands, interspersed with patches of forest. The historical perspective was that Madagascar's grasslands had anthropogenic origins, but emerging evidence suggests that grasslands were a component of the pre‐human Central Highlands vegetation. Consequently, there is now vigorous debate regarding the extent to which these grasslands have expanded due to anthropogenic pressures. Here, we shed light on the temporal dynamics of Madagascar's vegetative composition by conducting a population genomic investigation of Goodman's mouse lemur ( Microcebus lehilahytsara ; Cheirogaleidae). These small‐bodied primates occur both in Madagascar's eastern rainforests and in the Central Highlands, making them a valuable indicator species. Population divergences among forest‐dwelling mammals will reflect changes to their habitat, including fragmentation, whereas patterns of post‐divergence gene flow can reveal formerly wooded migration corridors. To explore these patterns, we used RADseq data to infer population genetic structure, demographic models of post‐divergence gene flow, and population size change through time. The results offer evidence that open habitats are an ancient component of the Central Highlands, and that widespread forest fragmentation occurred naturally during a period of decreased precipitation near the last glacial maximum. Models of gene flow suggest that migration across the Central Highlands has been possible from the Pleistocene through the recent Holocene via riparian corridors. Though our findings support the hypothesis that Central Highland grasslands predate human arrival, we also find evidence for human‐mediated population declines. This highlights the extent to which species imminently threatened by human‐mediated deforestation may already be vulnerable from paleoclimatic conditions.

Agroforestry perennials reduce nitrous oxide emissions and their live and dead trees increase ecosystem carbon storage - Cole D. Gross; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Global Change Biology, 2022)
Agroforestry systems (AFS) contribute to carbon (C) sequestration and reduction in greenhouse gas emissions from agricultural lands. However, previously understudied differences among AFS may underestimate their climate change mitigation potential. In this 3‐year field study, we assessed various C stocks and greenhouse gas emissions across two common AFS (hedgerows and shelterbelts) and their component land uses: perennial vegetated areas with and without trees (woodland and grassland, respectively), newly planted saplings in grassland, and adjacent annual cropland in central Alberta, Canada. Between 2018 and 2020 (~April–October), nitrous oxide emissions were 89% lower under perennial vegetation relative to the cropland (0.02 and 0.18 g N m −2 year −1 , respectively). In 2020, heterotrophic respiration in the woodland was 53% lower in shelterbelts relative to hedgerows (279 and 600 g C m −2 year −1 , respectively). Within the woodland, deadwood C stock was particularly important in hedgerows (35 Mg C ha −1 or 7% of ecosystem C) relative to shelterbelts (2 Mg C ha −1 or −1 found in the cropland, grassland, planted saplings treatment, and woodland, respectively. Shelterbelt and hedgerow woodlands contained 2.09 and 3.03 times more C, respectively, than adjacent cropland. Our findings emphasize the importance of AFS for fostering C sequestration and reducing greenhouse gas emissions and, in particular, retaining hedgerows (legacy woodland) and their associated deadwood across temperate agroecosystems will help mitigate climate change.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Comparative analysis of patient scatter to phantom scatter for computed tomography systems - S. M. Edwards; D. Schick (Physical and Engineering Sciences in Medicine, 2022)

Predicting larval alewife transport in Lake Michigan using hydrodynamic and Lagrangian particle dispersion models - Mark D. Rowe; Sara E. Prendergast; Karen M. Alofs; David B. Bunnell; Edward S. Rutherford; Eric J. Anderson (Limnology and Oceanography, 2022)
Several species of fish in large lakes and marine environments have a pelagic larval stage, and are subject to variable transport that can ultimately regulate survival and recruitment success. Alewife, Alosa pseudoharengus , are subject to transport by complex coastal currents during their pelagic larval stage (~ 30 d). We assessed backward‐trajectory simulations, consisting of a Lagrangian particle dispersion model linked to the Finite Volume Community Ocean Model, to estimate likely hatch locations of aged larval alewife collected from locations on both the eastern and western sides of Lake Michigan during July 2015. We used four deployments of three satellite‐tracked drifter buoys in coastal waters to assess model skill in estimating the origin of a drifter from its final location. We found that the trajectories of drifters varied greatly, depending on wind events and associated coastal transport processes, including upwelling/downwelling and coastal jet currents. In 2 of 12 cases, the backward trajectory simulations failed to predict the drifter origin, associated with transport of 170 km in a narrow coastal jet current. In the remaining 10 cases, the known drifter origin was within 3.5 km of the spatial patch of predicted possible origins for a scenario of horizontal diffusivity (188 m 2 s −1 ) consistent with the offshore model grid resolution. Modeled backward trajectories estimated that alewife originated from the same side of the lake where they were collected, within ~ 100 km of the collection site. Our paper demonstrates the utility of hydrodynamic models to estimate a region of origin for aged larval fish.

Three‐dimensional ontogenetic shifts of groundfish in the Northeast Pacific - Lingbo Li; Anne B. Hollowed; Edward D. Cokelet; Michelle M. McClure; Aimee A. Keller; Steve J. Barbeaux; Wayne A. Palsson (Fish and Fisheries, 2022)
It has been more than 100 years since fish were first described to move to deep waters as size increased, termed ‘Heincke's Law’. However, large‐scale studies on ontogenetic shifts are rare compared with increased reports of distributional changes in response to temperature, often confounded with the ontogenetic shifts. We fill this gap by examining the distribution of ten abundant groundfish species in three dimensions, depth, latitude and longitude, at 10‐cm size intervals within nine subregions of NE Pacific. Here, we utilized large, quality‐controlled datasets from random depth‐stratified, bottom trawl surveys consistently conducted during summer along the NE Pacific shelf from 1996 to 2015. Groundfish demonstrated complex ontogenetic movements in three dimensions across species, size class and subregion. In addition to the expected ontogenetic deepening, shoaling also occurred and some species demonstrated major ontogenetic shifts in longitude and/or latitude with limited changes in depth. Based on standardized ontogenetic shifts in three dimensions, our analyses show that there were significant differences in aggregate fish ontogenetic shifts between small (≤30 cm) and large (>30 cm) size groups. Small fish exhibited substantially larger ontogenetic shifts in depth than the large size group while both groups showed relatively small shifts in latitude and longitude. Our analyses strongly suggest that size structure and ontogenetic shifts should be included in the population distribution.

A Multidisciplinary Computational Framework for Topology Optimisation of Offshore Helidecks - Siamak Farajzadeh Khosroshahi; Marinella Masina; Alessandro Antonini; Edward Ransley; James Mark William Brownjohn; Peter Dobson; Dina D’Ayala (Journal of Marine Science and Engineering, 2022)
Maintaining offshore steel structures is challenging and not environmentally friendly due to the frequent visits for inspection and repairs. Some offshore lighthouses are equipped with carbon steel helidecks fixed onto their lantern galleries in the 1970s to provide easy and safe access to maintenance staff and inspectors. Even though the helidecks supporting structures have maintained their integrity and are still functional in the offshore harsh environmental conditions, their inspection and maintenance remains a challenge due to the need of frequent visits which requires flying to the location of the lighthouse to bring the maintenance staff and equipment. We have developed a multidisciplinary computational framework to design new generation of aluminium helidecks for offshore lighthouses. We calculated the wind speed at the location of the Bishop Rock lighthouse based on the meteorological data, and the load distribution on the helideck due to such a wind condition, using computational fluid dynamic analysis. Then, we used the calculated wind load with other mechanical loads in the events of normal and emergency landings of a helicopter on this structure to find the best design configuration for this helideck. We generated a design space for different configurations of a beam structure and carried out, static, transient and buckling analysis to assess each case using finite element method. The selection criterion was set to find the structure with the minimum volume fraction and compliance while keeping the stress below the allowable stress. We found the structure with eight vertical and circumferential sections featuring two rows of diagonal bracing with one at the base and the other one at the third section from the base of the helideck was the optimum design for the considered loading in this work. This framework can be adopted for the design and optimisation of other offshore structures by other researchers and designers.

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

A Transdisciplinary Approach Towards Studying Direct Mortality Among Demersal Fish and Benthic Invertebrates in the Wake of Pulse Trawling - Edward Schram; Pieke Molenaar; Susan de Koning; Adriaan D. Rijnsdorp (Frontiers in Marine Science, 2022)
Between 2009 and 2020, beam trawlers in the North Sea switched to electrical stimulation to target sole ( Solea solea) . The transition to pulse trawling raised widespread concern about possible adverse effects of electrical stimulation on marine organisms. Environmental NGO’s and small scale fishers claimed that it would electrocute marine life and create a ‘graveyard’ in the wake of pulse trawlers. This paper uses realistic field experiments to investigate the ‘graveyard’ hypothesis. In cooperation with fishers, a field experiment was designed where we simultaneously sampled marine organisms in the wake of pulse trawlers and in untrawled control areas. The impact was quantified by estimating the direct mortality among three dominant fish species and four dominant invertebrate species. In total, nine experimental tows were conducted in two years. Direct mortality among fish and invertebrates was low (0-10%) and did not differ between the pulse trawl track and the untrawled controls. Equally, no impact of the pulse trawl was found on external damages and vitality scores. The limited effects observed are likely due to the mechanical impact of the pulse and the sampling gear. The results of experiment do not support the claim that pulse trawling results in mass mortality among marine organisms in the trawl track. Throughout the research period, the concerns of small-scale fishers on pulse fishing shifted from being focused on biological effects to political and managerial issues. This can partly be attributed to the engagement in and the results of our research and has increased its credibility and salience. By integrating fishers’ knowledge and examining their perceptions through transdisciplinary research, we were able to show the importance of untangling the intricate relation between perceived knowledge gaps and political or management related concerns.

Re-evaluating cancer risks associated with the CHEK2 p.Ser428Phe Ashkenazi Jewish founder pathogenic variant - Yael Laitman; Sarah M. Nielsen; Kathryn E. Hatchell; Rebecca Truty; Rinat Bernstein-Molho; Edward D. Esplin; Eitan Friedman (Familial Cancer, 2022)

Global insights on managing fishery systems for the three pillars of sustainability - Taryn Garlock; James L. Anderson; Frank Asche; Martin D. Smith; Edward Camp; Jingjie Chu; Kai Lorenzen; Stefania Vannuccini (Fish and Fisheries, 2022)
There is growing recognition that fisheries should be managed for all three pillars of sustainability: economic, social and environmental sustainability. Limited quantitative evidence exists on factors supporting social sustainability, much less factors that contribute to multiple dimensions of sustainability. To develop a broader understanding of the factors that influence the performance of fishery management systems in environmental, economic and social pillars, we examine 11 input factors conjectured to contribute to successful fisheries using a global dataset of 145 fisheries case studies. The analysis indicates that management approaches are cross‐cutting and contribute to multiple dimensions of sustainability to varying extents. Importantly, factors exogenous to fisheries management can be as important as fisheries management, suggesting collaboration of fisheries institutions with other public and private institutions is important for sustainable fisheries development.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Attributes of climate resilience in fisheries: From theory to practice - Julia G. Mason; Jacob G. Eurich; Jacqueline D. Lau; Willow Battista; Christopher M. Free; Katherine E. Mills; Kanae Tokunaga; Lily Z. Zhao; Mark Dickey‐Collas; Mireia Valle; Gretta T. Pecl; Joshua E. Cinner; et al. (Fish and Fisheries, 2022)
In a changing climate, there is an imperative to build coupled social‐ecological systems—including fisheries—that can withstand or adapt to climate stressors. Although resilience theory identifies system attributes that supposedly confer resilience, these attributes have rarely been clearly defined, mechanistically explained, nor tested and applied to inform fisheries governance. Here, we develop and apply a comprehensive resilience framework to examine fishery systems across (a) ecological, (b) socio‐economic and (c) governance dimensions using five resilience domains: assets, flexibility, organization, learning and agency. We distil and define 38 attributes that confer climate resilience from a coupled literature‐ and expert‐driven approach, describe how they apply to fisheries and provide illustrative examples of resilience attributes in action. Our synthesis highlights that the directionality and mechanism of these attributes depend on the specific context, capacities, and scale of the focal fishery system and associated stressors, and we find evidence of interdependencies among attributes. Overall, however, we find few studies that test resilience attributes in fisheries across all parts of the system, with most examples focussing on the ecological dimension. As such, meaningful quantification of the attributes’ contributions to resilience remains a challenge. Our synthesis and holistic framework represent a starting point for critical application of resilience concepts to fisheries social‐ecological systems.

Fear at the top: killer whale predation drives white shark absence at South Africa’s largest aggregation site - AV Towner; RGA Watson; AA Kock; Y Papastamatiou; M Sturup; E Gennari; K Baker; T Booth; M Dicken; W Chivell; S Elwen; T Kaschke; et al. (African Journal of Marine Science, 2022)

Genome‐wide sequence data show no evidence of hybridization and introgression among pollinator wasps associated with a community of Panamanian strangler figs - Jordan D. Satler; Edward Allen Herre; Tracy A. Heath; Carlos A. Machado; Adalberto Gómez Zúñiga; John D. Nason (Molecular Ecology, 2022)
The specificity of pollinator host choice influences opportunities for reproductive isolation in their host plants. Similarly, host plants can influence opportunities for reproductive isolation in their pollinators. For example, in the fig and fig wasp mutualism, offspring of fig pollinator wasps mate inside the inflorescence that the mothers pollinate. Although often host specific, multiple fig pollinator species are sometimes associated with the same fig species, potentially enabling hybridization between wasp species. Here, we study the 19 pollinator species ( Pegoscapus spp.) associated with an entire community of 16 Panamanian strangler fig species ( Ficus subgenus Urostigma , section Americanae ) to determine whether the previously documented history of pollinator host switching and current host sharing predicts genetic admixture among the pollinator species, as has been observed in their host figs. Specifically, we use genome‐wide ultraconserved element (UCE) loci to estimate phylogenetic relationships and test for hybridization and introgression among the pollinator species. In all cases, we recover well‐delimited pollinator species that contain high interspecific divergence. Even among pairs of pollinator species that currently reproduce within syconia of shared host fig species, we found no evidence of hybridization or introgression. This is in contrast to their host figs, where hybridization and introgression have been detected within this community, and more generally, within figs worldwide. Consistent with general patterns recovered among other obligate pollination mutualisms (e.g. yucca moths and yuccas), our results suggest that while hybridization and introgression are processes operating within the host plants, these processes are relatively unimportant within their associated insect pollinators.

Soil protist function varies with elevation in the Swiss Alps - Florent Mazel; Lucie Malard; Hélène Niculita‐Hirzel; Erika Yashiro; Heidi K. Mod; Edward A. D. Mitchell; David Singer; Aline Buri; Eric Pinto; Nicolas Guex; Enrique Lara; Antoine Guisan (Environmental Microbiology, 2022)
Summary Protists are abundant and play key trophic functions in soil. Documenting how their trophic contributions vary across large environmental gradients is essential to understand and predict how biogeochemical cycles will be impacted by global changes. Here, using amplicon sequencing of environmental DNA in open habitat soil from 161 locations spanning 2600 m of elevation in the Swiss Alps (from 400 to 3000 m), we found that, over the whole study area, soils are dominated by consumers, followed by parasites and phototrophs. In contrast, the proportion of these groups in local communities shows large variations in relation to elevation. While there is, on average, three times more consumers than parasites at low elevation (400–1000 m), this ratio increases to 12 at high elevation (2000–3000 m). This suggests that the decrease in protist host biomass and diversity toward mountains tops impact protist functional composition. Furthermore, the taxonomic composition of protists that infect animals was related to elevation while that of protists that infect plants or of protist consumers was related to soil pH. This study provides a first step to document and understand how soil protist functions vary along the elevational gradient.

Myocardial work and left ventricular mechanical adaptations following isometric exercise training in hypertensive patients - Jamie M. O’Driscoll; Jamie J. Edwards; Jonathan D. Wiles; Katrina A. Taylor; Paul Leeson; Rajan Sharma (European Journal of Applied Physiology, 2022)

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Observation of Aerosol Generation by Human Subjects During Cardiopulmonary Exercise Testing Using a High-Powered Laser Technique: A Pilot Project - Christopher M. Varga; Keith J. Kwiatkowski; Michael J. Pedro; Herman Groepenhoff; Edward A. Rose; Callum Gray; Kai D. Pinkerton; Michael G. McBride; Stephen M. Paridon (Journal of Medical and Biological Engineering, 2022)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Expanding the horizon of research into the pathogenesis of the white matter diseases: Proceedings of the 2021 Annual Workshop of the Albert Research Institute for White Matter and Cognition - Shawn N. Whitehead; Askiel Bruno; Jeffrey M. Burns; S. Thomas Carmichael; Anna Csiszar; Jodi D. Edwards; Fanny M. Elahi; Giuseppe Faraco; Douglas B. Gould; Deborah R. Gustafson; Vladimir Hachinski; Gary Rosenberg; et al. (GeroScience, 2022)

Left ventricular mechanical, cardiac autonomic and metabolic responses to a single session of high intensity interval training - Jamie J. Edwards; Jonathan D. Wiles; Noemi Vadaszy; Katrina A. Taylor; Jamie M. O’Driscoll (European Journal of Applied Physiology, 2022)

Distinct colony boundaries and larval discrimination in polygyne red imported fire ants ( Solenopsis invicta ) - MacKenzie K. Kjeldgaard; Pierre‐André Eyer; Collin C. McMichael; Alison A. Bockoven; Joanie T. King; Ayumi Hyodo; Thomas W. Boutton; Edward L. Vargo; Micky D. Eubanks (Molecular Ecology, 2022)
Evaluating the factors that promote invasive ant abundance is critical to assess their ecological impact and inform their management. Many invasive ant species show reduced nestmate recognition and an absence of boundaries between unrelated nests, which allow populations to achieve greater densities due to reduced intraspecific competition. We examined nestmate discrimination and colony boundaries in introduced populations of the red imported fire ant ( Solenopsis invicta ; hereafter, fire ant). Fire ants occur in two social forms: monogyne (colonies with a single egg‐laying queen) and polygyne (colonies with multiple egg‐laying queens). In contrast with monogyne nests, polygyne nests are thought to be interconnected due to the reduced antagonism between non‐nestmate polygyne workers, perhaps because polygyne workers habituate the colony to an odour unique to Gp ‐ 9 b ‐carrying adults. However, colony boundaries and nestmate discrimination are poorly documented, particularly for worker‐brood interactions. To delimit boundaries between field colonies, we correlated the exchange of a 15 N‐glycine tracer dissolved in a sucrose solution with social form. We also evaluated nestmate discrimination between polygyne workers and larvae in the laboratory. Counter to our expectations, polygyne colonies behaved identically to monogyne colonies, suggesting both social forms maintain strict colony boundaries. Polygyne workers also preferentially fed larval nestmates and may have selectively cannibalized non‐nestmates. The levels of relatedness among workers in polygyne colonies was higher than those previously reported in North America (mean ± standard error: 0.269 ± 0.037). Our study highlights the importance of combining genetic analyses with direct quantification of resource exchange to better understand the factors influencing ant invasions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Passive-Sampler-Based Bioavailability Assessment of PCB Congeners Associated with Aroclor-Containing Paint Chips in the Presence of Sediment - Guilherme R. Lotufo; Philip T. Gidley; Andrew D. McQueen; David W. Moore; Deborah A. Edwards; Jeffery Hardenstine; Allen D. Uhler (Archives of Environmental Contamination and Toxicology, 2022)
This is the first investigation of the bioavailability of PCBs associated with paint chips (PC) dispersed in sediment. Bioavailability of PCB-containing PC in sediment was measured using ex situ polyethylene passive samplers (PS) and compared to that of PCBs from field-collected sediments. PC were mixed in freshwater sediment from a relatively uncontaminated site with no known PCB contamination sources and from a contaminated site with non-paint PCB sources. PC

Predicting phenotypes from genetic, environment, management, and historical data using CNNs - Jacob D. Washburn; Emre Cimen; Guillaume Ramstein; Timothy Reeves; Patrick O’Briant; Greg McLean; Mark Cooper; Graeme Hammer; Edward S. Buckler (Theoretical and Applied Genetics, 2021)

The Use of Hypnotics for Insomnia Disorder in Saudi Arabia: A Survey of Patients’ Experiences and Perceptions - Ali M. Dobia; Kath M. Ryan; Ahmed S. BaHammam; Mohammed H. Abutaleb; Rawaah Y. Alwadani; Alexander D. Edwards (Sleep and Vigilance, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Mean sea level and tidal change in Ireland since 1842: a case study of Cork - David T. Pugh; Edmund Bridge; Robin Edwards; Peter Hogarth; Guy Westbrook; Philip L. Woodworth; Gerard D. McCarthy (Ocean Science, 2021)
Knowledge of regional changes in mean sea level and local changes in tides are crucial to inform effective climate adaptation. An essential element is the availability of accurate observations of sea level. Sea level data in the Republic of Ireland, prior to the establishment of the National Tide Gauge Network in the mid-2000s, are limited but belie a wealth of historical data available in archival form. In this study, we digitize records located in Cork Harbour, Ireland, from 1842 and show how short-duration (6–8 weeks), high-quality data with a large interval to the present can accurately inform tidal and mean sea level changes. We consider error sources in detail. We estimate for the main M2 tidal constituent that the accuracy of these historical measurements is 1 % and 2 min for amplitude and phase, respectively, once adjustments for seasonal and nodal effects are made. Our mean sea level estimates are accurate to the 2 cm level, once adjustments for atmospheric and seasonal effects are made. Our results show tidal stability with a 2 % change in the amplitude of the M2 component, 4 min change in the phase over a period of 177 years, and mean sea level rise of 40 cm in the Cork Harbour area from 1842 to 2019, approximately in line with global mean sea level trends plus local glacial isostatic adjustment. More broadly, we show that with careful seasonal, nodal, and atmospheric corrections, together with knowledge of benchmark provenance, these historic, survey-oriented data can accurately inform of sea level changes.

Editorial: Before-After Control-Impact (BACI) Studies in the Ocean - Kerri D. Seger; Renata Sousa-Lima; Juan J. Schmitter-Soto; Edward R. Urban (Frontiers in Marine Science, 2021)

Seasonal variations in the synoptic climatology of air pollution in Birmingham, UK - Edward C. Hodgson; Ian D. Phillips (Theoretical and Applied Climatology, 2021)
A synoptic typing approach was undertaken to examine the seasonal relationship (winter versus summer) between air mass types and pollutant concentrations of O 3 , PM10, NO x , NO 2 and CO in Birmingham, UK, from 2000 to 2015. Daily means of seven surface meteorological variables were entered into a P-mode principal component analysis. Three principal components explained 72.2% (72.9%) of the variance in winter (summer). Cluster analysis was used to group together days with similar PC scores and thus similar meteorological conditions. Six clusters provided the best air mass classification in both seasons. High pollutant concentrations were associated with anticyclonic types. In particular, tropical (polar) continental air mass type was most likely to produce extremely high concentrations in summer (winter). In winter, a sequence of Polar Continental (cool and humid) and Binary Mid-latitude Anticyclonic Maritime—Sub-Polar Cyclonic Maritime (cold and dry) induced severe pollution episodes in all pollutants. Whilst the mean duration of severe pollution episodes varied little between winter and summer (O 3 was an exception, with severe episodes lasting 20% longer in summer), high pollutant extremes were more common in winter. This was due to more favourable meteorological conditions (e.g. temperature inversions) and increased anthropogenic emissions during the cold season.

Effects of sustained GABA releasing implants on pancreatic islets in mice - Kevin C. Ling; D. Walker Hagan; Jorge Santini-González; Edward A. Phelps (Drug Delivery and Translational Research, 2021)

Matching a snail’s pace: successful use of environmental DNA techniques to detect early stages of invasion by the destructive New Zealand mud snail - James D. Woodell; Maurine Neiman; Edward P. Levri (Biological Invasions, 2021)

The ghost of a giant – Six hypotheses for how an extinct megaherbivore structured kelp forests across the North Pacific Rim - Cameron D. Bullen; Alberto A. Campos; Edward J. Gregr; Iain McKechnie; Kai M. A. Chan (Global Ecology and Biogeography, 2021)
Aim The global decline of megafauna is believed to have had significant and widespread ecological impacts. One such extinction of likely important consequence is the 18th century extinction of the Steller’s sea cow ( Hydrodamalis gigas ); however, little has been written about how the loss of this megaherbivore may have impacted coastal ecosystem dynamics. Drawing on historical evidence, sea cow biology, kelp forest ecology, and the ecology of extant sirenians, we propose several discrete hypotheses about the effects Steller’s sea cows may have had on kelp forest dynamics of the North Pacific. Location North Pacific Ocean. Time period Pre‐1760s. Major taxa studied Steller’s sea cow ( Hydrodamalis gigas ). Results & conclusions The evidence we review suggests that Steller’s sea cows exerted substantial direct and indirect influences on kelp forests, likely affecting the physical ecosystem structure, productivity, nutrient cycling, species interactions, and export of nutrients to surrounding ecosystems. This suggests that kelp forest dynamics and resilience were already significantly altered prior to the influence of more recent and well‐known stressors, such as industrial fishing and climate change, and illustrates the important ecological roles that are lost with megafaunal extinction.

The dangers of misrepresenting wildlife trade: response to Natusch et al. 2021 - David P. Edwards; Neil D'Cruze; Sandra Altherr; Alice Hughes; Jordi Janssen; Vincent Nijman; Stesha A. Pasachnik; Brett R. Scheffers; Chris R. Shepherd; Emerson Sy; Mark Auliya (Conservation Biology, 2021)

Cyclical Patterns and a Regime Shift in the Character of Phytoplankton Blooms in a Restricted Sub-Tropical Lagoon, Indian River Lagoon, Florida, United States - Edward J. Phlips; Susan Badylak; Natalie G. Nelson; Lauren M. Hall; Charles A. Jacoby; Margaret A. Lasi; Jean C. Lockwood; Janice D. Miller (Frontiers in Marine Science, 2021)
This paper examines the character of phytoplankton blooms in a restricted sub-tropical lagoon along the Atlantic coast of central Florida. The results of the 23-year study (1997–2020) provide evidence for multiple types of variability in bloom activity, including cyclical patterns, stochastic events, and most prominently a regime shift in composition and intensity. Cyclical patterns (e.g., El Niño/La Niña periods) and stochastic events (e.g., tropical storms) influenced rainfall levels, which in turn impacted nutrient concentrations in the water column and the timing and intensity of blooms. In 2011, a major change occurred in the character of blooms, with a dramatic increase in peak biomass levels of blooms and the appearance of new dominant taxa, including the brown tide species Aureoumbra lagunensis and other nanoplanktonic species. Results of quantitative analyses reveal system behavior indicative of a regime shift. The shift coincided with widespread losses of seagrass community and reduced drift algae biomass. A combination of exceptionally low water temperatures in the winters of 2009/2010 and 2010/2011, hypersaline conditions associated with drought conditions, and high light attenuation caused by blooms appear to have contributed to the widespread and protracted decline in seagrass and drift macroalgal communities in the lagoon, leading to shifts in distribution of internal and external nutrient sources toward phytoplankton.

Cystic fibrosis improves COVID-19 survival and provides clues for treatment of SARS-CoV-2 - Edward H. Abraham; Guido Guidotti; Eliezer Rapaport; David Bower; Jack Brown; Robert J. Griffin; Andrew Donnelly; Ellen D. Waitzkin; Kenon Qamar; Mark A. Thompson; Sukumar Ethirajan; Kent Robinson (Purinergic Signalling, 2021)
Systemic pools of ATP are elevated in individuals homozygous for cystic fibrosis (CF) as evidenced by elevated blood and plasma ATP levels. This elevated ATP level seems to provide benefit in the presence of advanced solid tumors (Abraham et al., Nature Medicine 2(5):593–596, 1996). We published in this journal a paper showing that IV ATP can elevate the depleted ATP pools of advanced cancer patients up to levels found in CF patients with subsequent clinical, biochemical, and quality of life (QOL) improvements (Rapaport et al., Purinergic Signalling 11(2): 251–262, 2015). We hypothesize that the elevated ATP levels seen in CF patients may be benefiting CF patients in another way: by improving their survival after contracting COVID-19. We discuss here the reasoning behind this hypothesis and suggest how these findings might be applied clinically in the general population.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

A Study of the Potential Impact of Dredging the Corpus Christi Ship Channel on Passive Particle Transport - Eirik Valseth; Mark D. Loveland; Clint Dawson; Edward J. Buskey (Journal of Marine Science and Engineering, 2021)
We present a study of the potential impact of deepening the Corpus Christi Ship Channel through Aransas Pass; in particular, we study the effect on the transport of red drum fish larvae due to the change in channel depth. The study was conducted by high resolution simulation of the circulation of the seawater entering and exiting the pass for the current and proposed Ship Channel depths. The computer model incorporates tides and meteorological forcing and includes the entire Gulf of Mexico and the North American Atlantic coast. The corresponding transport of larvae modeled as passive particles due to the sea water circulation is established by releasing particles in the nearshore region outside Aransas Pass and subsequently tracking their trajectories. We compare the difference in the number of larvae that successfully reach appropriate nursery grounds inside Aransas Pass for four distinctive initial larvae positions in the nearshore region. Our results indicate that the change in channel depth does not significantly alter the number of red drum larvae that reach suitable nursery grounds, overall, across all considered scenarios, we see a net increase of 0.5%.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Leaching Rate of Polychlorinated Biphenyls (PCBs) from Marine Paint Chips - Allen D. Uhler; Jeffery H. Hardenstine; Deborah A. Edwards; Guilherme R. Lotufo (Archives of Environmental Contamination and Toxicology, 2021)
Polychlorinated biphenyls (PCBs) were added to certain marine vessel bottom paints as a plasticizer to improve the adhesion and durability of the paint. The most common PCB formulation used to amend such paints was Aroclor 1254. Fugitive Aroclor-containing paint chips generated from vessel maintenance and repair operations represent a potential source of PCB contamination to sediments. Limited published studies indicate that Aroclor-containing paint is largely inert and exhibits low PCB leaching into water; however, the rate and degree of leaching of PCBs from paint chips have not been directly studied. This laboratory-based study evaluated the rate and extent of leaching of PCBs from paint chips into freshwater. The results of this investigation demonstrate that the rate of PCB dissolution from paint chips decreased rapidly and exponentially over time. Based on this study, it is estimated that the rate of leaching of PCBs from paint chips would cease after approximately 3 years of exposure to water. When all leachable PCBs were exhausted, it is estimated that less than 1% of the mass of PCBs in the paint chips was amenable to dissolution. The results of this experiment suggest that Aroclor-containing paint chips found in sediments are likely short-term sources of dissolved-phase PCB to pore or surface waters and that the majority of the PCBs in paint chips remain in the paint matrix and unavailable for partitioning into water. Graphic Abstract

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Recent progress on combining geomorphological and geochronological data with ice sheet modelling, demonstrated using the last British–Irish Ice Sheet - Jeremy C. Ely; Chris D. Clark; Richard C. A. Hindmarsh; Anna L. C. Hughes; Sarah L. Greenwood; Sarah L. Bradley; Edward Gasson; Lauren Gregoire; Niall Gandy; Chris R. Stokes; David Small (Journal of Quaternary Science, 2021)
Palaeo‐ice sheets are important analogues for understanding contemporary ice sheets, offering a record of ice sheet behaviour that spans millennia. There are two main approaches to reconstructing palaeo‐ice sheets. Empirical reconstructions use the available glacial geological and chronological evidence to estimate ice sheet extent and dynamics but lack direct consideration of ice physics. In contrast, numerically modelled simulations implement ice physics, but often lack direct quantitative comparison with empirical evidence. Despite being long identified as a fruitful scientific endeavour, few ice sheet reconstructions attempt to reconcile the empirical and model‐based approaches. To achieve this goal, model‐data comparison procedures are required. Here, we compare three numerically modelled simulations of the former British–Irish Ice Sheet with the following lines of evidence: (a) position and shape of former margin positions, recorded by moraines; (b) former ice‐flow direction and flow‐switching, recorded by flowsets of subglacial bedforms; and (c) the timing of ice‐free conditions, recorded by geochronological data. These model–data comparisons provide a useful framework for quantifying the degree of fit between numerical model simulations and empirical constraints. Such tools are vital for reconciling numerical modelling and empirical evidence, the combination of which will lead to more robust palaeo‐ice sheet reconstructions with greater explicative and ultimately predictive power.

Antarctic desert soil bacteria exhibit high novel natural product potential, evaluated through long‐read genome sequencing and comparative genomics - Nicole Benaud; Richard J. Edwards; Timothy G. Amos; Paul M. D'Agostino; Carolina Gutiérrez‐Chávez; Kate Montgomery; Iskra Nicetic; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Actinobacteria and Proteobacteria are important producers of bioactive natural products (NP), and these phyla dominate in the arid soils of Antarctica, where metabolic adaptations influence survival under harsh conditions. Biosynthetic gene clusters (BGCs) which encode NPs, are typically long and repetitious high G + C regions difficult to sequence with short‐read technologies. We sequenced 17 Antarctic soil bacteria from multi‐genome libraries, employing the long‐read PacBio platform, to optimize capture of BGCs and to facilitate a comprehensive analysis of their NP capacity. We report 13 complete bacterial genomes of high quality and contiguity, representing 10 different cold‐adapted genera including novel species. Antarctic BGCs exhibited low similarity to known compound BGCs (av. 31%), with an abundance of terpene, non‐ribosomal peptide and polyketide‐encoding clusters. Comparative genome analysis was used to map BGC variation between closely related strains from geographically distant environments. Results showed the greatest biosynthetic differences to be in a psychrotolerant Streptomyces strain, as well as a rare Actinobacteria genus, Kribbella , while two other Streptomyces spp. were surprisingly similar to known genomes. Streptomyces and Kribbella BGCs were predicted to encode antitumour, antifungal, antibacterial and biosurfactant‐like compounds, and the synthesis of NPs with antibacterial, antifungal and surfactant properties was confirmed through bioactivity assays.

Environmental Drivers of Forage Fishes and Benthic Invertebrates at Multiple Spatial Scales in a Large Temperate Estuary - Ryan J. Woodland; Andre Buchheister; Robert J. Latour; Carlos Lozano; Edward Houde; Christopher J. Sweetman; Mary C. Fabrizio; Troy D. Tuckey (Estuaries and Coasts, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

The Path to an Ecosystem Approach for Forage Fish Management: A Case Study of Atlantic Menhaden - Kristen A. Anstead; Katie Drew; David Chagaris; Amy M. Schueller; Jason E. McNamee; Andre Buchheister; Geneviève Nesslage; Jim H. Uphoff Jr.; Michael J. Wilberg; Alexei Sharov; Micah J. Dean; Jeffrey Brust; et al. (Frontiers in Marine Science, 2021)
Atlantic menhaden ( Brevoortia tyrannus ) support the largest fishery by volume on the United States East Coast, while also playing an important role as a forage species. Managers’ and stakeholders’ increasing concerns about the impact of Atlantic menhaden harvest on ecosystem processes led to an evolution in the assessment and management of this species from a purely single-species approach to an ecosystem approach. The first coastwide stock assessment of Atlantic menhaden for management used a single-species virtual population analysis (VPA). Subsequent assessments used a forward projecting statistical catch-at-age framework that incorporated estimates of predation mortality from a multispecies VPA while analytical efforts continued toward the development of ecosystem models and explicit ecological reference points (ERPs) for Atlantic menhaden. As an interim step while ecosystem models were being developed, a series of ad hoc measures to preserve Atlantic menhaden biomass for predators were used by managers. In August 2020, the Atlantic States Marine Fisheries Commission formally adopted an ecological modeling framework as a tool to set reference points and harvest limits for the Atlantic menhaden that considers their role as a forage fish. This is the first example of a quantitative ecosystem approach to setting reference points on the United States Atlantic Coast and it represents a significant advance for forage fish management. This case study reviews the history of Atlantic menhaden stock assessments and management, outlines the progress on the current implementation of ERPs for this species, and highlights future research and management needs to improve and expand ecosystem-based fisheries management.

Exploring the Pacific Arctic Seasonal Ice Zone With Saildrone USVs - Andrew M. Chiodi; Chidong Zhang; Edward D. Cokelet; Qiong Yang; Calvin W. Mordy; Chelle L. Gentemann; Jessica N. Cross; Noah Lawrence-Slavas; Christian Meinig; Michael Steele; Don E. Harrison; Phyllis J. Stabeno; et al. (Frontiers in Marine Science, 2021)
More high-quality, in situ observations of essential marine variables are needed over the seasonal ice zone to better understand Arctic (or Antarctic) weather, climate, and ecosystems. To better assess the potential for arrays of uncrewed surface vehicles (USVs) to provide such observations, five wind-driven and solar-powered saildrones were sailed into the Chukchi and Beaufort Seas following the 2019 seasonal retreat of sea ice. They were equipped to observe the surface oceanic and atmospheric variables required to estimate air-sea fluxes of heat, momentum and carbon dioxide. Some of these variables were made available to weather forecast centers in real time. Our objective here is to analyze the effectiveness of existing remote ice navigation products and highlight the challenges and opportunities for improving remote ice navigation strategies with USVs. We examine the sources of navigational sea-ice distribution information based on post-mission tabulation of the sea-ice conditions encountered by the vehicles. The satellite-based ice-concentration analyses consulted during the mission exhibited large disagreements when the sea ice was retreating fastest (e.g., the 10% concentration contours differed between analyses by up to ∼175 km). Attempts to use saildrone observations to detect the ice edge revealed that in situ temperature and salinity measurements varied sufficiently in ice bands and open water that it is difficult to use these variables alone as a reliable ice-edge indicator. Devising robust strategies for remote ice zone navigation may depend on developing the capability to recognize sea ice and initiate navigational maneuvers with cameras and processing capability onboard the vehicles.

Catchment-scale groundwater-flow and recharge paradox revealed from base flow analysis during the Australian Millennium Drought (Mt Lofty Ranges, South Australia) - Thomas T. Anderson; Erick A. Bestland; Ilka Wallis; Peter J. C. Kretschmer; Lesja Soloninka; Edward W. Banks; Adrian D. Werner; Dioni I. Cendón; Markus M. Pichler; Huade Guan (Hydrogeology Journal, 2021)

Comparison of blood cultures versus T2 Candida Panel in management of candidemia at a large community hospital - Taylor D. Steuber; Lauren Butler; Adam Sawyer; Rachel Chappell; Jonathan Edwards (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Revisiting the Colletotrichum species causing anthracnose of almond in Australia - D. D. de Silva; R. C. Mann; J. Kaur; P. N Ekanayake; T. I Sawbridge; S. McKay; P. W. J. Taylor; J. Edwards (Australasian Plant Pathology, 2021)

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Macroecological patterns of forest structure and allometric scaling in mangrove forests - Andre S. Rovai; Robert R. Twilley; Edward Castañeda‐Moya; Stephen R. Midway; Daniel A. Friess; Carl C. Trettin; Jacob J. Bukoski; Atticus E.L. Stovall; Paulo R. Pagliosa; Alessandra L. Fonseca; Richard A. Mackenzie; Aslan Aslan; et al. (Global Ecology and Biogeography, 2021)
Aim Mangrove wetlands span broad geographical gradients, resulting in functionally diverse tree communities. We asked whether latitudinal variation, allometric scaling relationships and species composition influence mangrove forest structure and biomass allocation across biogeographical regions and distinct coastal morphologies. Location Global. Time period Present. Major taxa studied Mangrove ecosystems. Methods We built the largest field‐based dataset on mangrove forest structure and biomass to date ( c . 2,800 plots from 67 countries) to address macroecological questions pertaining to structural and functional diversity of mangroves spanning biogeographical and coastal morphology gradients. We used frequentist inference statistics and machine learning models to determine environmental drivers that control biomass allocation within and across mangrove communities globally. Results Allometric scaling relationships and forest structural complexity were consistent across biogeographical and coastal morphology gradients, suggesting that mangrove biomass is controlled by regional forcings rather than by latitude or species composition. For instance, nearly 40% of the global variation in biomass was explained by regional climate and hydroperiod, revealing nonlinear thresholds that control biomass accumulation across broad geographical gradients. Furthermore, we found that ecosystem‐level carbon stocks (average 401 ± 48 MgC/ha, covering biomass and the top 1 m of soil) varied little across diverse coastal morphologies, reflecting regional bottom‐up geomorphic controls that shape global patterns in mangrove biomass apportioning. Main conclusions Our findings reconcile views of wetland and terrestrial forest macroecology. Similarities in stand structural complexity and cross‐site size–density relationships across multiscale environmental gradients show that resource allocation in mangrove ecosystems is independent of tree size and invariant to species composition or latitude. Mangroves follow a universal fractal‐based scaling relationship that describes biomass allocation for several other terrestrial tree‐dominated communities. Understanding how mangroves adhere to these universal allometric rules can improve our ability to account for biomass apportioning and carbon stocks in response to broad geographical gradients.

Correction to: Amitifadine, a triple reuptake inhibitor, reduces self-administration of the opiate remifentanil in rats - Edward D. Levin; Corinne Wells; Andrew Hawkey; Zade Holloway; Graham Blair; Alexander Vierling; Ashley Ko; Caroline Pace; John Modarres; Anthony McKinney; Amir H. Rezvani; Jed E. Rose (Psychopharmacology, 2021)

Longitudinal uncoupling of the heart and arteries with aging in a community-dwelling population - Majd AlGhatrif; Chris H. Morrell; Lewis C. Becker; Paul D. Chantler; Samer S. Najjar; Luigi Ferrucci; Gary Gerstenblith; Edward G. Lakatta (GeroScience, 2021)

Animal‐borne video from a sea turtle reveals novel anti‐predator behaviors - Jenna L. Hounslow; Oliver J. D. Jewell; Sabrina Fossette; Scott Whiting; Anton D. Tucker; Anthony Richardson; David Edwards; Adrian C. Gleiss (Ecology, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Breath Hold Facilitates Targeted Deposition of Aerosolized Droplets in a 3D Printed Bifurcating Airway Tree - Adam H. Sonnenberg; Edward Taylor; Jarred R. Mondoñedo; Samer Bou Jawde; Samir D. Amin; Jiaxi Song; Mark W. Grinstaff; Béla Suki (Annals of Biomedical Engineering, 2021)

Accuracy assessment of global internal-tide models using satellite altimetry - Loren Carrere; Brian K. Arbic; Brian Dushaw; Gary Egbert; Svetlana Erofeeva; Florent Lyard; Richard D. Ray; Clément Ubelmann; Edward Zaron; Zhongxiang Zhao; Jay F. Shriver; Maarten Cornelis Buijsman; et al. (Ocean Science, 2021)
Altimeter measurements are corrected for several geophysical parameters in order to access ocean signals of interest, like mesoscale or sub-mesoscale variability. The ocean tide is one of the most critical corrections due to the amplitude of the tidal elevations and to the aliasing phenomena of high-frequency signals into the lower-frequency band, but the internal-tide signatures at the ocean surface are not yet corrected globally. Internal tides can have a signature of several centimeters at the surface with wavelengths of about 50–250 km for the first mode and even smaller scales for higher-order modes. The goals of the upcoming Surface Water Ocean Topography (SWOT) mission and other high-resolution ocean measurements make the correction of these small-scale signals a challenge, as the correction of all tidal variability becomes mandatory to access accurate measurements of other oceanic signals. In this context, several scientific teams are working on the development of new internal-tide models, taking advantage of the very long altimeter time series now available, which represent an unprecedented and valuable global ocean database. The internal-tide models presented here focus on the coherent internal-tide signal and they are of three types: empirical models based upon analysis of existing altimeter missions, an assimilative model and a three-dimensional hydrodynamic model. A detailed comparison and validation of these internal-tide models is proposed using existing satellite altimeter databases. The analysis focuses on the four main tidal constituents: M2, K1, O1 and S2. The validation process is based on a statistical analysis of multi-mission altimetry including Jason-2 and Cryosphere Satellite-2 data. The results show a significant altimeter variance reduction when using internal-tide corrections in all ocean regions where internal tides are generating or propagating. A complementary spectral analysis also gives some estimation of the performance of each model as a function of wavelength and some insight into the residual non-stationary part of internal tides in the different regions of interest. This work led to the implementation of a new internal-tide correction (ZARON'one) in the next geophysical data records version-F (GDR-F) standards.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Differences in joint power distribution in high and low lactate threshold cyclists - Brian K. Leary; Heath M. Burton; Emre Vardarli; Anthony S. Wolfe; Charles K. Crawford; John D. Akins; Edward F. Coyle (European Journal of Applied Physiology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

The Human Gene Mutation Database (HGMD®): optimizing its use in a clinical diagnostic or research setting - Peter D. Stenson; Matthew Mort; Edward V. Ball; Molly Chapman; Katy Evans; Luisa Azevedo; Matthew Hayden; Sally Heywood; David S. Millar; Andrew D. Phillips; David N. Cooper (Human Genetics, 2020)
The Human Gene Mutation Database (HGMD ® ) constitutes a comprehensive collection of published germline mutations in nuclear genes that are thought to underlie, or are closely associated with human inherited disease. At the time of writing (June 2020), the database contains in excess of 289,000 different gene lesions identified in over 11,100 genes manually curated from 72,987 articles published in over 3100 peer-reviewed journals. There are primarily two main groups of users who utilise HGMD on a regular basis; research scientists and clinical diagnosticians. This review aims to highlight how to make the most out of HGMD data in each setting.

The Process and Benefits of Developing Prototype Climate Services—Examples in China - Chris D. Hewitt; Nicola Golding; Peiqun Zhang; Tyrone Dunbar; Philip E. Bett; Joanne Camp; Timothy D. Mitchell; Edward Pope (Journal of Meteorological Research, 2020)

Modeling the interactive effects of nutrient loads, meteorology, and invasive mussels on suitable habitat for Bighead and Silver Carp in Lake Michigan - Peter J. Alsip; Hongyan Zhang; Mark D. Rowe; Edward Rutherford; Doran M. Mason; Catherine Riseng; Zhenming Su (Biological Invasions, 2020)
Anthropogenic stressors that affect ecological processes in the Laurentian Great Lakes can impact their susceptibility to bioinvasions. Bighead Hypophthalmichthys nobilis and Silver Carp H. molitrix , collectively ‘bigheaded carps’ (BHC), are planktivorous fishes threatening to invade Lake Michigan. While previous studies indicate the lake contains habitat suitable for BHC growth, there is a need to understand how anthropogenic-driven changes to the abiotic and biotic environment could alter its vulnerability to BHC. We applied a spatially explicit model of BHC growth rate potential (GRP; g g −1 d −1 ) to nine biophysical model scenarios to evaluate changes in habitat suitability in Lake Michigan. Scenarios differed in meteorology (cool, reference, warm), annual tributary phosphorus loads (0, 3300, and 5600 MTA), and the presence/absence of invasive dreissenid mussels. Mussel effects on BHC GRP relied on their contact with the surface mixed layer (SML), the depth of which was affected by meteorology. The warm year advanced the expansion of Bighead Carp habitat by increasing temperature-dependent foraging rates and lessening the time of competitive interaction with mussels due to earlier stratification separating mussels from the SML. Phosphorus loads were the most influential driver of the lake’s suitability. Compared to present conditions, we estimate BHC could have grown an additional 8–40% annually in the 1980s when mussels were not in the lake and phosphorus loads were higher. Our study demonstrates how climate change and nutrient enrichment can increase Lake Michigan’s vulnerability to BHC by affecting thermal regime and productivity, thereby limiting negative effects of dreissenid mussels on BHC growth.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

The role of herbivory in the macroevolution of vertebrate hormone dynamics - Phoebe D. Edwards; Nicholas Sookhan; Rudy Boonstra (Ecology Letters, 2020)
Vertebrates have high species‐level variation in circulating hormone concentrations, and the functional significance of this variation is largely unknown. We tested the hypothesis that interspecific differences in hormone concentrations are partially driven by plant consumption, based on the prediction that herbivores should have higher basal hormone levels to ‘outcompete’ plant endocrine disruptors. We compared levels of glucocorticoids (GCs), the hormones with the most available data, across 166 species. Using phylogenetically informed comparisons, we found that herbivores had higher GC levels than carnivores. Furthermore, we found that the previously described negative relationship between GC levels and body mass only held in herbivores, not carnivores, and that the effect of diet was greatest at extreme body sizes. These findings demonstrate the far‐reaching effects of diet on animal physiology, and provide evidence that herbivory influences circulating hormone concentrations. We urge future direct testing of the relationship between phytochemical load and GC levels.

Effects of sub-chronic methylphenidate on risk-taking and sociability in zebrafish (Danio rerio) - Rebecca G. Brenner; Anthony N. Oliveri; Walter Sinnott-Armstrong; Edward D. Levin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Poly (ether) sulfone electrospun nanofibrous membranes embedded with graphene oxide quantum dots with antimicrobial activity - Charmaine S. Tshangana; Adolph A. Muleja; Edward N. Nxumalo; Sabelo D. Mhlanga (Environmental Science and Pollution Research, 2020)

Amitifadine, a triple reuptake inhibitor, reduces self-administration of the opiate remifentanil in rats - Edward D. Levin; Corinne Wells; Andrew Hawkey; Zade Holloway; Graham Blair; Alexander Vierling; Ashley Ko; Caroline Pace; John Modarres; Anthony McKinney; Amir H. Rezvani; Jed E. Rose (Psychopharmacology, 2020)

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Virulence/avirulence patterns among Leptosphaeria maculans isolates determines expression of resistance, senescence and yellowing in cotyledons of Brassica napus - A. Dolatabadian; J. Batley; D. Edwards; M. J. Barbetti (European Journal of Plant Pathology, 2020)

Soil protist diversity in the Swiss western Alps is better predicted by topo‐climatic than by edaphic variables - Christophe V. W. Seppey; Olivier Broennimann; Aline Buri; Erika Yashiro; Eric Pinto‐Figueroa; David Singer; Quentin Blandenier; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; Antoine Guisan; Enrique Lara (Journal of Biogeography, 2020)
Aim Trends in spatial patterns of diversity in macroscopic organisms can be well predicted from correlative models, using topo‐climatic variables for plants and animals allowing inference over large scales. By contrast, diversity in soil microorganisms is generally considered as mostly driven by edaphic variables and, therefore, difficult to extrapolate on a large spatial scale based on predictive models. Here, we compared the power of topo‐climatic versus edaphic variables for predicting the diversity of various soil protist groups at the regional scale. Location Swiss western Alps. Taxa Full protist community and nine clades belonging respectively to three functional groups: parasites (Apicomplexa, Peronosporomycetes and Phytomyxea), phagotrophs (Sarcomonadea, Tubulinea and Spirotrichea) and phototrophs (Chlorophyta, Trebouxiophyceae and Diatomeae). Methods We extracted soil DNA from 178 sites along a wide range of elevations with a random‐stratified sampling design. We defined protist Operational Taxonomic Units assemblages by metabarcoding of the V4 region of the rRNA small subunit gene. We assessed and modelled the diversity (Shannon index) patterns of all above‐mentioned taxonomic groups based on topo‐climatic (topography, slope southness, slope steepness and average summer temperature) and edaphic (soil temperature, relative humidity, pH, electroconductivity, phosphorus percentage, carbon/nitrogen, loss on ignition and shale percentage) variables in Generalized Additive Models (GAM). Results The respective significance of topo‐climatic and edaphic variables varied among taxonomic and—to a certain extent—functional groups: while many variables explained significantly the diversity of the three phototrophs this was less the case for the three parasites. Topo‐climatic variables had a better predictive power than edaphic variables, yet predictive power varied among taxonomic groups. Main conclusions Topo‐climatic variables (particularly slope steepness and summer temperature if we consider their significance in the GAMs) were, on average, better predictors of protist diversity at the landscape scale than edaphic variables. However, the predictive power of these variables on diversity differed considerably among taxonomic groups; such relationships may be due to direct and/or indirect (e.g. biotic) influences (like with parasitic taxa, where low predictive power is most likely explained by the absence of information on the hosts’ distribution). Future prospects include using such spatial models to predict hotspots of diversity and disease outbreaks.

Dissolved Gas and Metal Composition of Hydrothermal Plumes From a 2008 Submarine Eruption on the Northeast Lau Spreading Center - Tamara Baumberger; Marvin D. Lilley; John E. Lupton; Edward T. Baker; Joseph A. Resing; Nathaniel J. Buck; Sharon L. Walker; Gretchen L. Früh-Green (Frontiers in Marine Science, 2020)

A case of aberrant CD8 T cell–restricted IL-7 signaling with a Janus kinase 3 defect–associated atypical severe combined immunodeficiency - Aaruni Khanolkar; Jeffrey D. Wilks; Guorong Liu; Bridget M. Simpson; Edward A. Caparelli; Dawn A. Kirschmann; Jenna Bergerson; Ramsay L. Fuleihan (Immunologic Research, 2020)

Relationships among white-tailed deer density, harvest, and landscape metrics in TN, USA - Heidi L. Adams; Robert E. Kissell; Daryl Ratajczak; Edward L. Warr; Roger D. Applegate; Lynn Barrett; Tabitha Lavacot; David Graves (European Journal of Wildlife Research, 2020)
Landscape and harvest indices are frequently used to represent white-tailed deer ( Odocoileus virginianus ) density. However, the relationship between deer density and specific landscape indices is unclear. Harvest is another metric often used to estimate deer density. Our objective was to model the relationship among deer density, landscape metrics, and harvest density of deer in TN, USA. We estimated deer density across 11 regions in 2011 using distance sampling techniques. We developed 18 a priori models to assess relationships among deer density, harvest density, and landscape metrics. Estimates of deer density ranged from 1.85 to 19.99 deer/km 2 . Deer density was best predicted by harvest density and harvest density + percent woody area. However, harvest density was the only important variable in predicting deer density (Σω i = 0.700). Results of this study emphasize the significance of harvest density in deer management. While the importance of harvest as a management tool for deer is likely to increase as landscapes are fragmented and urbanized, specific management guidelines should be based upon deer densities and landscape metrics when they are important.

Conservation genetics of Madagascar’s critically endangered ploughshare tortoise (Astrochelys yniphora) - Angelo R. Mandimbihasina; Cynthia L. Frasier; Ryan A. Hagenson; Brittani A. D. Robertson; Shannon E. Engberg; Richard E. Lewis; Lance G. Woolaver; Emilienne Razafimahatratra; Lydia L. Rabetafika; Edward E. Louis (Conservation Genetics, 2020)

Biogeographic barriers, Pleistocene refugia, and climatic gradients in the southeastern Nearctic drive diversification in cornsnakes ( Pantherophis guttatus complex) - Edward A. Myers; Alexander D. McKelvy; Frank T. Burbrink (Molecular Ecology, 2020)
The southeastern Nearctic is a biodiversity hotspot that is also rich in cryptic species. Numerous hypotheses (e.g., vicariance, local adaptation, and Pleistocene speciation in glacial refugia) have been tested in an attempt to explain diversification and the observed pattern of extant biodiversity. However, previous phylogeographic studies have both supported and refuted these hypotheses. Therefore, while data support one or more of these diversification hypotheses, it is likely that taxa are forming within this region in species‐specific ways. Here, we generate a genomic data set for the cornsnakes ( Pantherophis guttatus complex), which are widespread across this region, spanning both biogeographic barriers and climatic gradients. We use phylogeographic model selection combined with hindcast ecological niche models to determine regions of habitat stability through time. This combined approach suggests that numerous drivers of population differentiation explain the current diversity of this group of snakes. The Mississippi River caused initial speciation in this species complex, with more recent divergence events linked to adaptations to ecological heterogeneity and allopatric Pleistocene refugia. Lastly, we discuss the taxonomy of this group and suggest there may be additional cryptic species in need of formal recognition.

Nitric oxide mediates oxylipin production and grazing defense in diatoms - Matthew D. Johnson; Bethanie R. Edwards; David J. Beaudoin; Benjamin A. S. Van Mooy; Assaf Vardi (Environmental Microbiology, 2020)
Summary Diatom blooms are important features of productive marine ecosystems and are known to support higher trophic levels. However, when stressed or wounded, diatoms can produce oxylipin molecules known to inhibit the reproduction and development of copepods and decrease microzooplankton growth rates. Using oxylipin chemical treatments, lipidomic analysis and functional genomic approaches, we provide evidence that nitric oxide (NO) and oxylipin signalling pathways in diatoms respond to protist grazers, resulting in increased defence fitness and survival. Exposure of the diatom Phaeodactylum tricornutum to the dinoflagellate Oxyrrhis marina resulted in NO production by P . tricornutum and pronounced change in its dissolved oxylipin profile. Experimentally elevating levels of NO also resulted in increased oxylipin production, and lower overall grazing rates. Furthermore, O . marina preferentially grazed on P . tricornutum prey with lower levels of NO, suggesting that this molecule and its effect on oxylipin pathways play a key role in prey selection. Exposure of O . marina grazing on P . tricornutum to exogenous oxylipins also decreased grazing rates, which is consistent with a grazing deterrence role for these molecules. These results suggest that NO and oxylipin production help to structure diatom communities, in part by modulating interactions with microzooplankton predators.

Diffusion magnetic resonance imaging-derived free water detects neurodegenerative pattern induced by interferon-γ - Marcelo Febo; Pablo D. Perez; Carolina Ceballos-Diaz; Luis M. Colon-Perez; Huadong Zeng; Edward Ofori; Todd E. Golde; David E. Vaillancourt; Paramita Chakrabarty (Brain Structure and Function, 2020)

Changes in benthic community composition associated with the outbreak of the corallimorph, Rhodactis howesii, at Palmyra Atoll - Amanda L. Carter; Clinton B. Edwards; Michael D. Fox; Corinne G. Amir; Yoan Eynaud; Maggie D. Johnson; Levi S. Lewis; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Atmospheric drivers of winter above‐freezing temperatures and associated rainfall in western Canada - Brandi W. Newton; Barrie R. Bonsal; Thomas W. D. Edwards; Terry D. Prowse; Glenn R. McGregor (International Journal of Climatology, 2019)
Winter thaw episodes, especially when accompanied by rain, can significantly deplete the winter snowpack, which is a critical water storage component in the mountainous headwater regions of the major river basins of western Canada. Here we identify the characteristic synoptic‐scale mid‐tropospheric atmospheric circulation regimes that tend to foster such extreme hydrologic events using self‐organizing map analysis of meteorological reanalysis data from 1949 to 2012. Daily winter 500 hPa geopotential height fields over the Pacific Ocean and western Canada are classified into 12 dominant synoptic types, for which conditional probabilities of above‐freezing temperatures and rainfall are then calculated and mapped using daily high‐resolution gridded data. Results show that above‐freezing surface air temperatures and rain events in winter are commonly associated with the occurrence of a ridge of high pressure over western Canada, which induces southwesterly advection of relatively warm, moist maritime air masses into the continental interior, and that the intensity and spatial footprint of the surface climate response is related to the strength and position of the ridge. Conversely, the development of a ridge of high pressure over the Pacific Ocean and adjacent trough of low pressure over western Canada, which favours northwesterly to westerly mid‐tropospheric flow over the continental interior in winter, tends to suppress the occurrence of above‐freezing temperatures and rain. The synoptic type most strongly associated with winter thaw and rain events underwent a statistically significant step‐change increase in mean frequency in 1977, accompanied by a corresponding step‐change decrease in the frequency of the dominant synoptic type depicting westerly (zonal) circulation, coinciding with a well‐documented shift to a positive phase of the Pacific Decadal Oscillation.

Bridging From Monitoring to Solutions-Based Thinking: Lessons From CalCOFI for Understanding and Adapting to Marine Climate Change Impacts - Natalya D. Gallo; Elizabeth Drenkard; Andrew R. Thompson; Edward D. Weber; Deb Wilson-Vandenberg; Sam McClatchie; J. Anthony Koslow; Brice X. Semmens (Frontiers in Marine Science, 2019)

Complete genome sequence of bovine herpesvirus type 1.1 (BoHV-1.1) Los Angeles (LA) strain and its genotypic relationship to BoHV-1.1 Cooper and more recently isolated wild-type field strains - Jean M. d’Offay; Robert W. Fulton; R. Eberle; Edward J. Dubovi; Christopher C. L. Chase (Archives of Virology, 2019)

Predictability of non-phase-locked baroclinic tides in the Caribbean Sea - Edward D. Zaron (Ocean Science, 2019)
The predictability of the sea surface height expression of baroclinic tides is examined with 96 h forecasts produced by the AMSEAS operational forecast model during 2013–2014. The phase-locked tide, both barotropic and baroclinic, is identified by harmonic analysis of the 2-year record and found to agree well with observations from tide gauges and satellite altimetry within the Caribbean Sea. The non-phase-locked baroclinic tide, which is created by time-variable mesoscale stratification and currents, may be identified from residual sea level anomalies (SLAs) near the tidal frequencies. The predictability of the non-phase-locked tide is assessed by measuring the difference between a forecast – centered at T+36, T+60, or T+84 h – and the model's later verifying analysis for the same time. Within the Caribbean Sea, where a baroclinic tidal sea level range of ±5 cm is typical, the forecast error for the non-phase-locked tidal SLA is correlated with the forecast error for the subtidal (mesoscale) SLA. Root mean square values of the former range from 0.5 to 2 cm, while the latter ranges from 1 to 6 cm, for a typical 84 h forecast. The spatial and temporal variability of the forecast error is related to the dynamical origins of the non-phase-locked tide and is briefly surveyed within the model.

An approach to forecast grain crop yield using multi-layered, multi-farm data sets and machine learning - Patrick Filippi; Edward J. Jones; Niranjan S. Wimalathunge; Pallegedara D. S. N. Somarathna; Liana E. Pozza; Sabastine U. Ugbaje; Thomas G. Jephcott; Stacey E. Paterson; Brett M. Whelan; Thomas F. A. Bishop (Precision Agriculture, 2019)

Evidence of a high-density brown hyena population within an enclosed reserve: the role of fenced systems in conservation - S. Edwards; J. Noack; L. Heyns; D. Rodenwoldt (Mammal Research, 2019)

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Plan S and publishing: reply to Lehtomäki et al. 2019 - Michael A. McCarthy; Mark A. Burgman; Fuwen Wei; Frith C. Jarrad; Carlo Rondinini; Carolina Murcia; Helene D. Marsh; H. Resit Akçakaya; Karen J. Esler; Edward T. Game; Mark W. Schwartz (Conservation Biology, 2019)

DNA of diverse adenoviruses detected in Cameroonian rodent and shrew species - Joseph Diffo; Valantine Ngum Ndze; Nkom Felix Ntumvi; Jean-Michel Takuo; Moctar M. M. Mouiche; Ubald Tamoufe; Julius Nwobegahay; Matthew LeBreton; Amethyst Gillis; Bradley S. Schneider; Joseph M. Fair; Corina Monagin; et al. (Archives of Virology, 2019)

Public–Private Partnerships to Advance Regional Ocean-Observing Capabilities: A Saildrone and NOAA-PMEL Case Study and Future Considerations to Expand to Global Scale Observing - Christian Meinig; Eugene F. Burger; Nora Cohen; Edward D. Cokelet; Meghan F. Cronin; Jessica N. Cross; Sebastien de Halleux; Richard Jenkins; Andrew T. Jessup; Calvin W. Mordy; Noah Lawrence-Slavas; Adrienne J. Sutton; et al. (Frontiers in Marine Science, 2019)

Dopaminergic drug treatment remediates exaggerated cingulate prediction error responses in obsessive-compulsive disorder - Graham K. Murray; Franziska Knolle; Karen D. Ersche; Kevin J. Craig; Sanja Abbott; Shaila S. Shabbir; Naomi A. Fineberg; John Suckling; Barbara J. Sahakian; Edward T. Bullmore; Trevor W. Robbins (Psychopharmacology, 2019)

Limited coral mortality following acute thermal stress and widespread bleaching on Palmyra Atoll, central Pacific - Michael D. Fox; Amanda L. Carter; Clinton B. Edwards; Yuichiro Takeshita; Maggie D. Johnson; Vid Petrovic; Corinne G. Amir; Enric Sala; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Interacting cogs in the machinery of the renin angiotensin system - Lizelle Lubbe; Edward D Sturrock (Biophysical Reviews, 2019)

Subregional differences in groundfish distributional responses to anomalous ocean bottom temperatures in the northeast Pacific - Lingbo Li; Anne B. Hollowed; Edward D. Cokelet; Steven J. Barbeaux; Nicholas A. Bond; Aimee A. Keller; Jacquelynne R. King; Michelle M. McClure; Wayne A. Palsson; Phyllis J. Stabeno; Qiong Yang (Global Change Biology, 2019)
Although climate‐induced shifts in fish distribution have been widely reported at the population level, studies that account for ontogenetic shifts and subregional differences when assessing responses are rare.In this study, groundfish distributional changes in depth, latitude, and longitude were assessed at different size classes by species within nine subregions. We examined large, quality‐controlled datasets of depth‐stratified‐random bottom trawl surveys conducted during summer in three large regions—the Gulf of Alaska and the west coasts of Canada and the United States—over the period 1996–2015, a time period punctuated by a marine “heat wave.” Temporal biases in bottom temperature were minimized by subdividing each region into three subregions, each with short‐duration surveys. Near‐bottom temperatures, weighted by stratum area, were unsynchronized across subregions and exhibited varying subregional interannual variability. The weighted mean bottom depths in the subregions also vary largely among subregions. The centroids (centers of gravity) of groundfish distribution were weighted with catch per unit effort and stratum area for 10 commercially important groundfish species by size class and subregion. Our multivariate analyses showed that there were significant differences in aggregate fish movement responses to warm temperatures across subregions but not among species or sizes. Groundfish demonstrated poleward responses to warming temperatures only in a few subregions and moved shallower or deeper to seek colder waters. The temperature responses of groundfish depended on where they were. Under global warming, groundfish may form geographically distinct thermal ecoregions along the northeast Pacific shelf. Shallow‐depth species exhibited greatly different distributional responses to temperature changes across subregions while deep‐depth species of different subregions tend to have relatively similar temperature responses. Future climate studies would benefit by considering fish distributions on small subregional scales.

Late Holocene environmental changes and anthropogenic impact in Dee Why Lagoon, New South Wales - C. Chagué; D. Edwards; J. Ruszczyk; P. Gadd; A. Zawadzki; G. Jacobsen; D. Fierro; J. Goralewski; L. Clement; A. Albani (Australian Journal of Earth Sciences, 2019)

Strong genetic isolation despite wide distribution in a commercially exploited coastal shark - Kelvin L. Hull; Tamaryn A. Asbury; Charlene da Silva; Matthew Dicken; Ana Veríssimo; Edward D. Farrell; Stefano Mariani; Carlotta Mazzoldi; Ilaria A. M. Marino; Lorenzo Zane; Simo N. Maduna; Aletta E. Bester-van der Merwe (Hydrobiologia, 2019)

Combining supervised run interval training or moderate-intensity continuous training with the diabetes prevention program on clinical outcomes - Nicole M. Gilbertson; Joan A. Mandelson; Kathryn Hilovsky; Jeremy D. Akers; Trent A. Hargens; David L. Wenos; Elizabeth S. Edwards (European Journal of Applied Physiology, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Debris flow impact on flexible barrier: effects of debris-barrier stiffness and flow aspect ratio - Dong-ri Song; Gordon G. D. Zhou; Clarence Edward Choi; Yun Zheng (Journal of Mountain Science, 2019)

How “The Blob” affected groundfish distributions in the Gulf of Alaska - Qiong Yang; Edward D. Cokelet; Phyllis J. Stabeno; Lingbo Li; Anne B. Hollowed; Wayne A. Palsson; Nicholas A. Bond; Steven J. Barbeaux (Fisheries Oceanography, 2019)
We investigated the distributional shifts of groundfish in response to anomalous ocean conditions, particularly the recent anomalously warm period (2014–2016; “The Blob”), based on data from ten Gulf of Alaska bottom trawl surveys conducted by the Alaska Fisheries Science Center during 1996–2015. Six groundfish species were considered: Pacific cod ( Gadus macrocephalus ), arrowtooth flounder ( Atheresthes stomias ), walleye pollock ( Gadus chalcogrammus ), Pacific ocean perch ( Sebastes alutus ), northern rock sole ( Lepidopsetta polyxystra ), and southern rock sole ( Lepidopsetta bilineata ). Ontogenetic differences were examined by dividing data for each fish species into size classes. Our study demonstrated that after accounting for size‐specific depth preferences, the spatial responses of groundfish to anomalous ocean conditions differed by species and foraging guild in the central Gulf of Alaska. Pacific cod and arrowtooth flounder showed similar responses to ocean warming, but different responses to cooling. In general, Pacific cod moved to deeper depths in warmer years and moved to shallower depths in colder years. Arrowtooth flounder also moved deeper in warmer years. However, in colder years, large arrowtooth flounder (>40 cm) shifted toward shallower depths while smaller‐sized fish shifted toward deeper depths. In warmer years, large pollock (>30 cm) moved to deeper waters while smaller pollock (10–20 cm) moved to shallower waters. Pacific ocean perch exhibited an opposite response to thermal changes in habitat compared with Pacific cod and arrowtooth flounder. They moved deeper in colder years, but there was no clear change in depth as a function of size in response to warmer habitat.

Phosphate‐limited ocean regions select for bacterial populations enriched in the carbon–phosphorus lyase pathway for phosphonate degradation - Oscar A. Sosa; Daniel J. Repeta; Edward F. DeLong; Mohammad D. Ashkezari; David M. Karl (Environmental Microbiology, 2019)
Summary In tropical and subtropical oceanic surface waters phosphate scarcity can limit microbial productivity. However, these environments also have bioavailable forms of phosphorus incorporated into dissolved organic matter (DOM) that microbes with the necessary transport and hydrolysis metabolic pathways can access to supplement their phosphorus requirements. In this study we evaluated how the environment shapes the abundance and taxonomic distribution of the bacterial carbon–phosphorus (C–P) lyase pathway, an enzyme complex evolved to extract phosphate from phosphonates. Phosphonates are organophosphorus compounds characterized by a highly stable C–P bond and are enriched in marine DOM. Similar to other known bacterial adaptions to low phosphate environments, C–P lyase was found to become more prevalent as phosphate concentrations decreased. C–P lyase was particularly enriched in the Mediterranean Sea and North Atlantic Ocean, two regions that feature sustained periods of phosphate depletion. In these regions, C–P lyase was prevalent in several lineages of Alphaproteobacteria ( Pelagibacter , SAR116, Roseobacter and Rhodospirillales ), Gammaproteobacteria, and Actinobacteria . The global scope of this analysis supports previous studies that infer phosphonate catabolism via C–P lyase is an important adaptive strategy implemented by bacteria to alleviate phosphate limitation and expands the known geographic extent and taxonomic affiliation of this metabolic pathway in the ocean.

A Global Plankton Diversity Monitoring Program - Sonia D. Batten; Rana Abu-Alhaija; Sanae Chiba; Martin Edwards; George Graham; R. Jyothibabu; John A. Kitchener; Philippe Koubbi; Abigail McQuatters-Gollop; Erik Muxagata; Clare Ostle; Anthony J. Richardson; et al. (Frontiers in Marine Science, 2019)

Comparison of metabolomic responses of earthworms to sub-lethal imidacloprid exposure in contact and soil tests - Vivek D. Dani; Brian P. Lankadurai; Edward G. Nagato; André J. Simpson; Myrna J. Simpson (Environmental Science and Pollution Research, 2019)

Modeling Temperature Regime and Physical Habitat Impacts from Restored Streamflow - Russell T. Bair; Benjamin W. Tobin; Brian D. Healy; Claire E. Spangenberg; Hampton K. Childres; Edward R. Schenk (Environmental Management, 2019)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Dynamics in the global protected‐area estate since 2004 - Edward Lewis; Brian MacSharry; Diego Juffe‐Bignoli; Nyeema Harris; Georgina Burrows; Naomi Kingston; Neil D. Burgess (Conservation Biology, 2019)
Nations of the world have committed to a number of goals and targets to address global environmental challenges. Protected areas have for centuries been a key strategy in conservation and play a major role in addressing current challenges. The most important tool used to track progress on protected‐area commitments is the World Database on Protected Areas (WDPA). Periodic assessments of the world's protected‐area estate show steady growth over the last 2 decades. However, the current method, which uses the latest version of the WDPA, does not show the true dynamic nature of protected areas over time and does not provide information on sites removed from the WDPA. In reality, this method can only show growth or remain stable. We used GIS tools in an approach to assess protected‐area change over time based on 12 temporally distinct versions of the WDPA that quantify area added and removed from the WDPA annually from 2004 to 2016. Both the narrative of continual growth of protected area and the counter‐narrative of protected area removal were overly simplistic. The former because growth was almost entirely in the marine realm and the latter because some areas removed were reprotected in later years. On average 2.5 million km 2 was added to the WDPA annually and 1.1 million km 2 was removed. Reasons for the inclusion and removal of protected areas in the WDPA database were in part due to data‐quality issues but also to on‐the‐ground changes. To meet the 17% protected‐area component of Aichi Biodiversity Target 11 by 2020, which stood at 14.7% in 2016, either the rate of protected‐area removal must decrease or the rate of protected‐area designation and addition to the WDPA must increase.

Global Observations of Fine-Scale Ocean Surface Topography With the Surface Water and Ocean Topography (SWOT) Mission - Rosemary Morrow; Lee-Lueng Fu; Fabrice Ardhuin; Mounir Benkiran; Bertrand Chapron; Emmanuel Cosme; Francesco d’Ovidio; J. Thomas Farrar; Sarah T. Gille; Guillaume Lapeyre; Pierre-Yves Le Traon; Ananda Pascual; et al. (Frontiers in Marine Science, 2019)

Mechanisms of CYP3A Induction During Pregnancy: Studies in HepaRG Cells - Madhav Sachar; Edward J. Kelly; Jashvant D. Unadkat (The AAPS Journal, 2019)

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

The U.S. Climate Resilience Toolkit: evidence of progress - Edward P. Gardiner; David D. Herring; James F. Fox (Climatic Change, 2019)

Interactive Effects of Hypoxia and Temperature on Coastal Pelagic Zooplankton and Fish - Michael R. Roman; Stephen B. Brandt; Edward D. Houde; James J. Pierson (Frontiers in Marine Science, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

Development of community of practice to support quantitative risk assessment for synthetic biology products: contaminant bioremediation and invasive carp control as cases - Benjamin D. Trump; Christy Foran; Taylor Rycroft; Matthew D. Wood; Nirzwan Bandolin; Mariana Cains; Timothy Cary; Fiona Crocker; Nicholas A. Friedenberg; Patrick Gurian; Kerry Hamilton; Jan Jeffrey Hoover; et al. (Environment Systems and Decisions, 2018)

Genome variations between rhizosphere and bulk soil ecotypes of a Pseudomonas koreensis population - Lucas Dantas Lopes; Michele de C. Pereira e Silva; Alexandra J. Weisberg; Edward W. Davis; Qing Yan; Camila de S. Varize; Chih‐Feng Wu; Jeff H. Chang; Joyce E. Loper; Fernando D. Andreote (Environmental Microbiology, 2018)
Summary Bulk soil and rhizosphere are soil compartments selecting different microbial communities. However, it is unknown whether this selection also can change the genome content of specific bacterial taxa, splitting a population in distinct ecotypes. To answer this question we compared the genome sequences of 53 isolates obtained from sugarcane rhizosphere (28) and bulk soil (25). These isolates were previously classified in the Pseudomonas koreensis subgroup of the P. fluorescens complex. Phylogenomics showed a trend of separation between bulk soil and rhizosphere isolates. Discriminant analysis of principal components (DAPC) identified differences in the accessory genome of rhizosphere and bulk soil sub‐populations. We found significant changes in gene frequencies distinguishing rhizosphere from bulk soil ecotypes, for example, enrichment of phosphatases and xylose utilization ( xut ) genes, respectively. Phenotypic assays and deletion of xutA gene indicated that accumulation of xut genes in the bulk soil sub‐population provided a higher growth capacity in a d ‐xylose medium, supporting the corresponding genomic differences. Despite the clear differences distinguishing the two ecotypes, all 53 isolates were classified in a single 16S rRNA gene OTU. Collectively, our results revealed that the gene pool and ecological behavior of a bacterial population can be different for ecotypes living in neighbouring soil habitats.

Correction to: Utilizing crowdsourcing to enhance the mitigation and management of landslides - Clarence Edward Choi; Yifei Cui; Gordon G. D. Zhou (Landslides, 2018)

Abundance and Distribution of Reef-Associated Fishes Around Small Oil and Gas Platforms in the Northern Gulf of Mexico’s Hypoxic Zone - David B. Reeves; Edward J. Chesney; Ryan T. Munnelly; Donald M. Baltz; Brian D. Marx (Estuaries and Coasts, 2018)

Ras-Related C3 Botulinum Toxin Substrate 1 Promotes Axonal Regeneration after Stroke in Mice - Lin Liu; Hui Yuan; Yanhua Yi; Edward C. Koellhoffer; Yashasvee Munshi; Fan Bu; Yi Zhang; Zhenggang Zhang; Louise D. McCullough; Jun Li (Translational Stroke Research, 2018)

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

Contemporary and emerging fisheries in The Bahamas—Conservation and management challenges, achievements and future directions - Krista D. Sherman; Aaron D. Shultz; Craig P. Dahlgren; Claire Thomas; Edward Brooks; Annabelle Brooks; Daniel R. Brumbaugh; Lester Gittens; Karen J. Murchie (Fisheries Management and Ecology, 2018)
The harvest of marine resources has long‐standing cultural and economic importance to The Bahamas and other small island developing states. Tourists and residents place a demand on local marine resources, particularly Caribbean spiny lobster , Panulirus argus (Latreille), queen conch, Lobatus gigas (Linnaeus) and Nassau grouper, Epinephelus striatus (Bloch), and many fishery products are also sold on the global market. Illegal, unreported and unregulated fishing coupled with inadequate regulations and enforcement are the main factors contributing to the decline of Bahamian fisheries along with other anthropogenic impacts. This article reviews the status of fisheries management in The Bahamas using economically and ecologically important species as case studies to highlight conservation successes, knowledge gaps and deficiencies in existing management approaches. The review concludes with an examination of how emerging fisheries and improved conservation management strategies have the potential to improve economic and food security throughout the archipelago.

Utilizing crowdsourcing to enhance the mitigation and management of landslides - Clarence Edward Choi; Yifei Cui; Gordon G. D. Zhou (Landslides, 2018)

A lateral-to-mesial organization of human ventral visual cortex at birth - P. Barttfeld; S. Abboud; H. Lagercrantz; U. Adén; N. Padilla; A. D. Edwards; L. Cohen; M. Sigman; S. Dehaene; G. Dehaene-Lambertz (Brain Structure and Function, 2018)

Critical comparison of molecular methods for detection and enumeration of the harmful algal species, Heterosigma akashiwo, in environmental water samples - Christopher R. Main; Dianne I. Greenfield; Cameron Doll; Yanfei Wang; Edward B. Whereat; Rebecca Mortensen; D. Tye Pettay; Kathryn J. Coyne (Journal of Applied Phycology, 2018)

Spatiotemporal heterogeneity and patterning of developing renal blood vessels - Edward Daniel; D. Berfin Azizoglu; Anne R. Ryan; Tezin A. Walji; Christopher P. Chaney; Gabrielle I. Sutton; Thomas J. Carroll; Denise K. Marciano; Ondine Cleaver (Angiogenesis, 2018)

The DRD2 Taq1A A1 Allele May Magnify the Risk of Alzheimer’s in Aging African-Americans - Kenneth Blum; Rajendra D. Badgaiyan; Georgia M. Dunston; David Baron; Edward J. Modestino; Thomas McLaughlin; Bruce Steinberg; Mark S. Gold; Marjorie C. Gondré-Lewis (Molecular Neurobiology, 2018)

Contaminants of Emerging Concern in Wastewaters in Barbados, West Indies - Quincy A. Edwards; Tamanna Sultana; Sergei M. Kulikov; Leah D. Garner-O’Neale; Viviane Yargeau; Chris D. Metcalfe (Bulletin of Environmental Contamination and Toxicology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Molecular Cloning and Comparative Analysis of a PR-1-RK Hybrid Gene from Triticum urartu, the A-Genome Progenitor of Hexaploid Wheat - Shunwen Lu; Justin D. Faris; Michael C. Edwards (Plant Molecular Biology Reporter, 2018)

Long-term grazing impacts on vegetation diversity, composition, and exotic species presence across an aridity gradient in northern temperate grasslands - Mark P. Lyseng; Edward W. Bork; Daniel B. Hewins; Mike J. Alexander; Cameron N. Carlyle; Scott X. Chang; Walter D. Willms (Plant Ecology, 2018)

Comparative, collaborative, and integrative risk governance for emerging technologies - Igor Linkov; Benjamin D. Trump; Elke Anklam; David Berube; Patrick Boisseasu; Christopher Cummings; Scott Ferson; Marie-Valentine Florin; Bernard Goldstein; Danail Hristozov; Keld Alstrup Jensen; Georgios Katalagarianakis; et al. (Environment Systems and Decisions, 2018)

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

In situ swimming behaviors and oxygen consumption rates of juvenile lemon sharks (Negaprion brevirostris) - Ian A. Bouyoucos; Cory D. Suski; John W. Mandelman; Edward J. Brooks (Environmental Biology of Fishes, 2018)

Exploring the genetic and adaptive diversity of a pan-Mediterranean crop wild relative: narrow-leafed lupin - Mahsa Mousavi-Derazmahalleh; Philipp E. Bayer; Bruno Nevado; Bhavna Hurgobin; Dmitry Filatov; Andrzej Kilian; Lars G. Kamphuis; Karam B. Singh; Jens D. Berger; James K. Hane; David Edwards; William Erskine; et al. (Theoretical and Applied Genetics, 2018)

A three-dimensional numerical study of river plume mixing processes in Otsuchi Bay, Japan - Kaushik Sasmal; Eiji Masunaga; Adrean Webb; Oliver B. Fringer; Edward S. Gross; Matthew D. Rayson; Hidekatsu Yamazaki (Journal of Oceanography, 2018)

Selectivity underlies the dissociation between seasonal prey availability and prey consumption in a generalist predator - Thomas D. Whitney; Michael I. Sitvarin; Edward A. Roualdes; Simon J. Bonner; James D. Harwood (Molecular Ecology, 2018)
Generalist predators are capable of selective foraging, but are predicted to feed in close proportion to prey availability to maximize energetic intake especially when overall prey availability is low. By extension, they are also expected to feed in a more frequency‐dependent manner during winter compared to the more favourable foraging conditions during spring, summer and fall seasons. For 18 months, we observed the foraging patterns of forest‐dwelling wolf spiders from the genus Schizocosa (Araneae: Lycosidae) using PCR ‐based gut‐content analysis and simultaneously monitored the activity densities of two common prey: springtails (Collembola) and flies (Diptera). Rates of prey detection within spider guts relative to rates of prey collected in traps were estimated using Roualdes’ c st model and compared using various linear contrasts to make inferences pertaining to seasonal prey selectivity. Results indicated spiders foraged selectively over the course of the study, contrary to predictions derived from optimal foraging theory. Even during winter, with overall low prey densities, the relative rates of predation compared to available prey differed significantly over time and by prey group. Moreover, these spiders appeared to diversify their diets; the least abundant prey group was consistently overrepresented in the diet within a given season. We suggest that foraging in generalist predators is not necessarily restricted to frequency dependency during winter. In fact, foraging motives other than energy maximization, such as a more nutrient‐focused strategy, may also be optimal for generalist predators during prey‐scarce winters.

Environmental filtering and phylogenetic clustering correlate with the distribution patterns of cryptic protist species - David Singer; Anush Kosakyan; Christophe V. W. Seppey; Amandine Pillonel; Leonardo D. Fernández; Diego Fontaneto; Edward A. D. Mitchell; Enrique Lara (Ecology, 2018)
The community composition of any group of organisms should theoretically be determined by a combination of assembly processes including resource partitioning, competition, environmental filtering, and phylogenetic legacy. Environmental DNA studies have revealed a huge diversity of protists in all environments, raising questions about the ecological significance of such diversity and the degree to which they obey to the same rules as macroscopic organisms. The fast‐growing cultivable protist species on which hypotheses are usually experimentally tested represent only a minority of the protist diversity. Addressing these questions for the lesser known majority can only be inferred through observational studies. We conducted an environmental DNA survey of the genus Nebela , a group of closely related testate (shelled) amoeba species, in different habitats within Sphagnum ‐dominated peatlands. Identification based on the mitochondrial cytochrome c oxidase 1 gene, allowed species‐level resolution as well as phylogenetic reconstruction. Community composition varied strongly across habitats and associated environmental gradients. Species showed little overlap in their realized niche, suggesting resource partitioning, and a strong influence of environmental filtering driving community composition. Furthermore, phylogenetic clustering was observed in the most nitrogen‐poor samples, supporting phylogenetic inheritance of adaptations in the group of N. guttata . This study showed that the studied free‐living unicellular eukaryotes follow to community assembly rules similar to those known to determine plant and animal communities; the same may be true for much of the huge functional and taxonomic diversity of protists.

Evaluation of the convergent validity of an estimated cardiorespiratory fitness algorithm - Paul D. Loprinzi; Meghan K. Edwards; Ovuokerie Addoh; John P. Bentley (European Journal of Applied Physiology, 2018)

Glucosamine use and risk of colorectal cancer: results from the Cancer Prevention Study II Nutrition Cohort - Elizabeth D. Kantor; Christina C. Newton; Edward L. Giovannucci; Marjorie L. McCullough; Peter T. Campbell; Eric J. Jacobs (Cancer Causes & Control, 2018)

Tipping point in plant–fungal interactions under severe drought causes abrupt rise in peatland ecosystem respiration - Vincent E. J. Jassey; Monika K. Reczuga; Małgorzata Zielińska; Sandra Słowińska; Bjorn J. M. Robroek; Pierre Mariotte; Christophe V. W. Seppey; Enrique Lara; Jan Barabach; Michał Słowiński; Luca Bragazza; Bogdan H. Chojnicki; et al. (Global Change Biology, 2018)
Ecosystems are increasingly prone to climate extremes, such as drought, with long‐lasting effects on both plant and soil communities and, subsequently, on carbon (C) cycling. However, recent studies underlined the strong variability in ecosystem's response to droughts, raising the issue of nonlinear responses in plant and soil communities. The conundrum is what causes ecosystems to shift in response to drought. Here, we investigated the response of plant and soil fungi to drought of different intensities using a water table gradient in peatlands—a major C sink ecosystem. Using moving window structural equation models, we show that substantial changes in ecosystem respiration, plant and soil fungal communities occurred when the water level fell below a tipping point of −24 cm. As a corollary, ecosystem respiration was the greatest when graminoids and saprotrophic fungi became prevalent as a response to the extreme drought. Graminoids indirectly influenced fungal functional composition and soil enzyme activities through their direct effect on dissolved organic matter quality, while saprotrophic fungi directly influenced soil enzyme activities. In turn, increasing enzyme activities promoted ecosystem respiration. We show that functional transitions in ecosystem respiration critically depend on the degree of response of graminoids and saprotrophic fungi to drought. Our results represent a major advance in understanding the nonlinear nature of ecosystem properties to drought and pave the way towards a truly mechanistic understanding of the effects of drought on ecosystem processes.

Exposure to Sublethal Ammonia Concentrations Alters the Duration and Intensity of Agonistic Interactions in the Crayfish, Orconectes rusticus - David D. Edwards; Katie L. Klotz; Paul A. Moore (Bulletin of Environmental Contamination and Toxicology, 2018)

Resource partitioning among syntopic Characidae corroborated by gut content and stable isotope analyses - Karine O. Bonato; Edward D. Burress; Clarice B. Fialho; Jonathan W. Armbruster (Hydrobiologia, 2018)

SDF-1 induces TNF-mediated apoptosis in cardiac myocytes - Andrew A. Jarrah; Martina Schwarskopf; Edward R. Wang; Thomas LaRocca; Ashwini Dhume; Shihong Zhang; Lahouria Hadri; Roger J. Hajjar; Alison D. Schecter; Sima T. Tarzami (Apoptosis, 2018)

Microbial functional diversity covaries with permafrost thaw‐induced environmental heterogeneity in tundra soil - Mengting M. Yuan; Jin Zhang; Kai Xue; Liyou Wu; Ye Deng; Jie Deng; Lauren Hale; Xishu Zhou; Zhili He; Yunfeng Yang; Joy D. Van Nostrand; Edward A. G. Schuur; et al. (Global Change Biology, 2018)
Permafrost soil in high latitude tundra is one of the largest terrestrial carbon (C) stocks and is highly sensitive to climate warming. Understanding microbial responses to warming‐induced environmental changes is critical to evaluating their influences on soil biogeochemical cycles. In this study, a functional gene array (i.e., geochip 4.2) was used to analyze the functional capacities of soil microbial communities collected from a naturally degrading permafrost region in Central Alaska. Varied thaw history was reported to be the main driver of soil and plant differences across a gradient of minimally, moderately, and extensively thawed sites. Compared with the minimally thawed site, the number of detected functional gene probes across the 15–65 cm depth profile at the moderately and extensively thawed sites decreased by 25% and 5%, while the community functional gene β‐diversity increased by 34% and 45%, respectively, revealing decreased functional gene richness but increased community heterogeneity along the thaw progression. Particularly, the moderately thawed site contained microbial communities with the highest abundances of many genes involved in prokaryotic C degradation, ammonification, and nitrification processes, but lower abundances of fungal C decomposition and anaerobic‐related genes. Significant correlations were observed between functional gene abundance and vascular plant primary productivity, suggesting that plant growth and species composition could be co‐evolving traits together with microbial community composition. Altogether, this study reveals the complex responses of microbial functional potentials to thaw‐related soil and plant changes and provides information on potential microbially mediated biogeochemical cycles in tundra ecosystems.

Tropical soils are a reservoir for fluorescent Pseudomonas spp. biodiversity - Lucas Dantas Lopes; Edward W. Davis; Michele de C. Pereira e Silva; Alexandra J. Weisberg; Luana Bresciani; Jeff H. Chang; Joyce E. Loper; Fernando D. Andreote (Environmental Microbiology, 2018)
Summary Fluorescent Pseudomonas spp. are widely studied for their beneficial activities to plants. To explore the genetic diversity of Pseudomonas spp. in tropical regions, we collected 76 isolates from a Brazilian soil. Genomes were sequenced and compared to known strains, mostly collected from temperate regions. Phylogenetic analyses classified the isolates in the P. fluorescens (57) and P. putida (19) groups. Among the isolates in the P. fluorescens group, most (37) were classified in the P. koreensis subgroup and two in the P. jessenii subgroup. The remaining 18 isolates fell into two phylogenetic subclades distinct from currently recognized P. fluorescens subgroups, and probably represent new subgroups. Consistent with their phylogenetic distance from described subgroups, the genome sequences of strains in these subclades are asyntenous to the genome sequences of members of their neighbour subgroups. The tropical isolates have several functional genes also present in known fluorescent Pseudomonas spp. strains. However, members of the new subclades share exclusive genes not detected in other subgroups, pointing to the potential for novel functions. Additionally, we identified 12 potential new species among the 76 isolates from the tropical soil. The unexplored diversity found in the tropical soil is possibly related to biogeographical patterns.

Navigational efficiency in a biased and correlated random walk model of individual animal movement - Joseph D. Bailey; Jamie Wallis; Edward A. Codling (Ecology, 2018)
Understanding how an individual animal is able to navigate through its environment is a key question in movement ecology that can give insight into observed movement patterns and the mechanisms behind them. Efficiency of navigation is important for behavioral processes at a range of different spatio‐temporal scales, including foraging and migration. Random walk models provide a standard framework for modeling individual animal movement and navigation. Here we consider a vector‐weighted biased and correlated random walk ( BCRW ) model for directed movement (taxis), where external navigation cues are balanced with forward persistence. We derive a mathematical approximation of the expected navigational efficiency for any BCRW of this form and confirm the model predictions using simulations. We demonstrate how the navigational efficiency is related to the weighting given to forward persistence and external navigation cues, and highlight the counter‐intuitive result that for low (but realistic) levels of error on forward persistence, a higher navigational efficiency is achieved by giving more weighting to this indirect navigation cue rather than direct navigational cues. We discuss and interpret the relevance of these results for understanding animal movement and navigation strategies.

Oligopeptide Transport in Rat Lung Alveolar Epithelial Cells is Mediated by Pept2 - Hovhannes J. Gukasyan; Tomomi Uchiyama; Kwang-Jin Kim; Carsten Ehrhardt; Sharon K. Wu; Zea Borok; Edward D. Crandall; Vincent H.L. Lee (Pharmaceutical Research, 2017)

The Differential Absorption of a Series of P-Glycoprotein Substrates in Isolated Perfused Lungs from Mdr1a/1b Genetic Knockout Mice can be Attributed to Distinct Physico-Chemical Properties: an Insight into Predicting Transporter-Mediated, Pulmonary Specific Disposition - Daniel F. Price; Chris N. Luscombe; Peter J. Eddershaw; Chris D. Edwards; Mark Gumbleton (Pharmaceutical Research, 2017)

Contaminants of emerging concern in surface waters in Barbados, West Indies - Quincy A. Edwards; Sergei M. Kulikov; Leah D. Garner-O’Neale; Chris D. Metcalfe; Tamanna Sultana (Environmental Monitoring and Assessment, 2017)

Toxicity of Cadmium, Copper, and Zinc to the Threatened Chiricahua Leopard Frog (Lithobates [Rana] chiricahuensis) - Robin D. Calfee; Edward E. Little (Bulletin of Environmental Contamination and Toxicology, 2017)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Untangling the proximate causes and underlying drivers of deforestation and forest degradation in Myanmar - Cheng Ling Lim; Graham W. Prescott; Jose Don T. De Alban; Alan D. Ziegler; Edward L. Webb (Conservation Biology, 2017)
Political transitions often trigger substantial environmental changes. In particular, deforestation can result from the complex interplay among the components of a system—actors, institutions, and existing policies—adapting to new opportunities. A dynamic conceptual map of system components is particularly useful for systems in which multiple actors, each with different worldviews and motivations, may be simultaneously trying to alter different facets of the system, unaware of the impacts on other components. In Myanmar, a global biodiversity hotspot with the largest forest area in mainland Southeast Asia, ongoing political and economic reforms are likely to change the dynamics of deforestation drivers. A fundamental conceptual map of these dynamics is therefore a prerequisite for interventions to reduce deforestation. We used a system‐dynamics approach and causal‐network analysis to determine the proximate causes and underlying drivers of forest loss and degradation in Myanmar from 1995 to 2016 and to articulate the linkages among them. Proximate causes included infrastructure development, timber extraction, and agricultural expansion. These were stimulated primarily by formal agricultural, logging, mining, and hydropower concessions and economic investment and social issues relating to civil war and land tenure. Reform of land laws, the link between natural resource extraction and civil war, and the allocation of agricultural concessions will influence the extent of future forest loss and degradation in Myanmar. The causal‐network analysis identified priority areas for policy interventions, for example, creating a public registry of land‐concession holders to deter corruption in concession allocation. We recommend application of this analytical approach to other countries, particularly those undergoing political transition, to inform policy interventions to reduce forest loss and degradation.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Comparing the use of live trees and deadwood for larval foraging by aye-ayes (Daubentonia madagascariensis) at Kianjavato and Torotorofotsy, Madagascar - Timothy M. Sefczek; Domenico Randimbiharinirina; Brigitte M. Raharivololona; Joseph D. Rabekianja; Edward E. Louis (Primates, 2017)

Effects of sampling interval on the frequency - magnitude relationship of rockfalls detected from terrestrial laser scanning using semi-automated methods - Megan van Veen; D. Jean Hutchinson; Ryan Kromer; Matthew Lato; Tom Edwards (Landslides, 2017)

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

The tooth, the whole tooth and nothing but the tooth: tooth shape and ontogenetic shift dynamics in the white shark Carcharodon carcharias - G. C. A. French; M. Stürup; S. Rizzuto; J. H. van Wyk; D. Edwards; R. W. Dolan; S. P. Wintner; A. V. Towner; W. O. H. Hughes (Journal of Fish Biology, 2017)
Results from this study of the white shark Carcharodon carcharias include measurements obtained using a novel photographic method that reveal significant differences between the sexes in the relationship between tooth cuspidity and shark total length, and a novel ontogenetic change in male tooth shape. Males exhibit broader upper first teeth and increased distal inclination of upper third teeth with increasing length, while females do not present a consistent morphological change. Substantial individual variation, with implications for pace of life syndrome, was present in males and tooth polymorphism was suggested in females. Sexual differences and individual variation may play major roles in ontogenetic changes in tooth morphology in C. carcharias , with potential implications for their foraging biology. Such individual and sexual differences should be included in studies of ontogenetic shift dynamics in other species and systems.

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Body shape variation within the Southern Cavefish, Typhlichthys subterraneus (Percopsiformes: Amblyopsidae) - Pamela B. H. Burress; Edward D. Burress; Jonathan W. Armbruster (Zoomorphology, 2017)

Long-Term Spatio-Temporal Variation in Runoff Curve Number under Consistent Cover Conditions: a Southeastern US Case Study - D. R. Edwards (Water Resources Management, 2017)

Differential efficacies of the nicotinic α4β2 desensitizing agents in reducing nicotine self-administration in female rats - Amir H. Rezvani; Susan Slade; Corinne Wells; Venkata M. Yenugonda; Yong Liu; Milton L. Brown; Yingxian Xiao; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2017)

Optimisation of kelp (Laminaria digitata) gametophyte growth and gametogenesis: effects of photoperiod and culture media - J. J. Ratcliff; A. Soler-Vila; D. Hanniffy; M. P. Johnson; M. D. Edwards (Journal of Applied Phycology, 2017)

Establishing the link between market orientation and agricultural commercialization: Empirical evidence from Northern Ghana - Edward Martey; Prince M. Etwire; Alexander Nimo Wiredu; Benjamin D. K. Ahiabor (Food Security, 2017)

Elemental composition of Malawian rice - Edward J. M. Joy; E. Louise Ander; Martin R. Broadley; Scott D. Young; Allan D. C. Chilimba; Elliott M. Hamilton; Michael J. Watts (Environmental Geochemistry and Health, 2017)

Greater temperature sensitivity of plant phenology at colder sites: implications for convergence across northern latitudes - Janet Prevéy; Mark Vellend; Nadja Rüger; Robert D. Hollister; Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Karin Clark; Elisabeth J. Cooper; Bo Elberling; Anna M. Fosaa; Gregory H. R. Henry; et al. (Global Change Biology, 2017)
Warmer temperatures are accelerating the phenology of organisms around the world. Temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions, in part because small changes in temperature constitute greater relative changes in thermal balance at colder sites. To test this hypothesis, we examined up to 20 years of phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. A similar pattern was seen over time for the flowering phenology of a widespread species, Cassiope tetragona . These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms.

The Human Gene Mutation Database: towards a comprehensive repository of inherited mutation data for medical research, genetic diagnosis and next-generation sequencing studies - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Evans; Matthew Hayden; Sally Heywood; Michelle Hussain; Andrew D. Phillips; David N. Cooper (Human Genetics, 2017)

The evolutionary ecology (evo-eco) of plant asexual reproduction - Karl J. Niklas; Edward D. Cobb (Evolutionary Ecology, 2017)

Plants, microorganisms, and soil temperatures contribute to a decrease in methane fluxes on a drained Arctic floodplain - Min Jung Kwon; Felix Beulig; Iulia Ilie; Marcus Wildner; Kirsten Küsel; Lutz Merbold; Miguel D. Mahecha; Nikita Zimov; Sergey A. Zimov; Martin Heimann; Edward A. G. Schuur; Joel E. Kostka; et al. (Global Change Biology, 2017)
As surface temperatures are expected to rise in the future, ice‐rich permafrost may thaw, altering soil topography and hydrology and creating a mosaic of wet and dry soil surfaces in the Arctic. Arctic wetlands are large sources of CH 4 , and investigating effects of soil hydrology on CH 4 fluxes is of great importance for predicting ecosystem feedback in response to climate change. In this study, we investigate how a decade‐long drying manipulation on an Arctic floodplain influences CH 4 ‐associated microorganisms, soil thermal regimes, and plant communities. Moreover, we examine how these drainage‐induced changes may then modify CH 4 fluxes in the growing and nongrowing seasons. This study shows that drainage substantially lowered the abundance of methanogens along with methanotrophic bacteria, which may have reduced CH 4 cycling. Soil temperatures of the drained areas were lower in deep, anoxic soil layers (below 30 cm), but higher in oxic topsoil layers (0–15 cm) compared to the control wet areas. This pattern of soil temperatures may have reduced the rates of methanogenesis while elevating those of CH 4 oxidation, thereby decreasing net CH 4 fluxes. The abundance of Eriophorum angustifolium , an aerenchymatous plant species, diminished significantly in the drained areas. Due to this decrease, a higher fraction of CH 4 was alternatively emitted to the atmosphere by diffusion, possibly increasing the potential for CH 4 oxidation and leading to a decrease in net CH 4 fluxes compared to a control site. Drainage lowered CH 4 fluxes by a factor of 20 during the growing season, with postdrainage changes in microbial communities, soil temperatures, and plant communities also contributing to this reduction. In contrast, we observed CH 4 emissions increased by 10% in the drained areas during the nongrowing season, although this difference was insignificant given the small magnitudes of fluxes. This study showed that long‐term drainage considerably reduced CH 4 fluxes through modified ecosystem properties.

Does Aquaculture Support the Needs of Nutritionally Vulnerable Nations? - Christopher D. Golden; Katherine L. Seto; Madan M. Dey; Oai L. Chen; Jessica A. Gephart; Samuel S. Myers; Matthew Smith; Bapu Vaitla; Edward H. Allison (Frontiers in Marine Science, 2017)

Lifetime number of ovulatory cycles and epithelial ovarian cancer risk in African American women - Lauren C. Peres; Patricia G. Moorman; Anthony J. Alberg; Elisa V. Bandera; Jill Barnholtz-Sloan; Melissa Bondy; Michele L. Cote; Ellen Funkhouser; Edward S. Peters; Ann G. Schwartz; Paul D. Terry; Sarah E. Abbott; et al. (Cancer Causes & Control, 2017)

Molecular cloning and characterization of two novel genes from hexaploid wheat that encode double PR-1 domains coupled with a receptor-like protein kinase - Shunwen Lu; Justin D. Faris; Michael C. Edwards (Molecular Genetics and Genomics, 2017)

Laboratory bioassays and field-cage trials of Metarhizium spp. isolates with field-collected Mormon crickets (Anabrus simplex) - Chad A. Keyser; Éverton K. K. Fernandes; Drauzio E. N. Rangel; R. Nelson Foster; Larry E. Jech; K. Chris Reuter; Lonnie R. Black; Stefan Jaronski; Darl D. Flake; Edward W. Evans; Donald W. Roberts (BioControl, 2017)

Rotor Tracking Using Phase of Electrograms Recorded During Atrial Fibrillation - Caroline H. Roney; Chris D. Cantwell; Norman A. Qureshi; Rasheda A. Chowdhury; Emmanuel Dupont; Phang Boon Lim; Edward J. Vigmond; Jennifer H. Tweedy; Fu Siong Ng; Nicholas S. Peters (Annals of Biomedical Engineering, 2017)

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

Litter decay controlled by temperature, not soil properties, affecting future soil carbon - Edward G. Gregorich; Henry Janzen; Benjamin H. Ellert; Bobbi L. Helgason; Budong Qian; Bernie J. Zebarth; Denis A. Angers; Ronald P. Beyaert; Craig F. Drury; Scott D. Duguid; William E. May; Brian G. McConkey; et al. (Global Change Biology, 2017)
Widespread global changes, including rising atmospheric CO 2 concentrations, climate warming and loss of biodiversity, are predicted for this century; all of these will affect terrestrial ecosystem processes like plant litter decomposition. Conversely, increased plant litter decomposition can have potential carbon‐cycle feedbacks on atmospheric CO 2 levels, climate warming and biodiversity. But predicting litter decomposition is difficult because of many interacting factors related to the chemical, physical and biological properties of soil, as well as to climate and agricultural management practices. We applied 13 C‐labelled plant litter to soil at ten sites spanning a 3500‐km transect across the agricultural regions of Canada and measured its decomposition over five years. Despite large differences in soil type and climatic conditions, we found that the kinetics of litter decomposition were similar once the effect of temperature had been removed, indicating no measurable effect of soil properties. A two‐pool exponential decay model expressing undecomposed carbon simply as a function of thermal time accurately described kinetics of decomposition. ( R 2 = 0.94; RMSE = 0.0508). Soil properties such as texture, cation exchange capacity, pH and moisture, although very different among sites, had minimal discernible influence on decomposition kinetics. Using this kinetic model under different climate change scenarios, we projected that the time required to decompose 50% of the litter (i.e. the labile fractions) would be reduced by 1–4 months, whereas time required to decompose 90% of the litter (including recalcitrant fractions) would be reduced by 1 year in cooler sites to as much as 2 years in warmer sites. These findings confirm quantitatively the sensitivity of litter decomposition to temperature increases and demonstrate how climate change may constrain future soil carbon storage, an effect apparently not influenced by soil properties.

By their own devices: invasive Argentine ants have shifted diet without clear aid from symbiotic microbes - Yi Hu; David A. Holway; Piotr Łukasik; Linh Chau; Adam D. Kay; Edward G. LeBrun; Katie A. Miller; Jon G. Sanders; Andrew V. Suarez; Jacob A. Russell (Molecular Ecology, 2017)
The functions and compositions of symbiotic bacterial communities often correlate with host ecology. Yet cause–effect relationships and the order of symbiont vs. host change remain unclear in the face of ancient symbioses and conserved host ecology. Several groups of ants exemplify this challenge, as their low‐nitrogen diets and specialized symbioses appear conserved and ancient. To address whether nitrogen‐provisioning symbionts might be important in the early stages of ant trophic shifts, we studied bacteria from the Argentine ant, Linepithema humile – an invasive species that has transitioned towards greater consumption of sugar‐rich, nitrogen‐poor foods in parts of its introduced range. Bacteria were present at low densities in most L. humile workers, and among those yielding quality 16S rRNA amplicon sequencing data, we found just three symbionts to be common and dominant. Two, a Lactobacillus and an Acetobacteraceae species, were shared between native and introduced populations. The other, a Rickettsia , was found only in two introduced supercolonies. Across an eight‐year period of trophic reduction in one introduced population, we found no change in symbionts, arguing against a relationship between natural dietary change and microbiome composition. Overall, our findings thus argue against major changes in symbiotic bacteria in association with the invasion and trophic shift of L. humile . In addition, genome content from close relatives of the identified symbionts suggests that just one can synthesize most essential amino acids; this bacterium was only modestly abundant in introduced populations, providing little support for a major role of nitrogen‐provisioning symbioses in Argentine ant's dietary shift.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Fishing degrades size structure of coral reef fish communities - James P. W. Robinson; Ivor D. Williams; Andrew M. Edwards; Jana McPherson; Lauren Yeager; Laurent Vigliola; Russell E. Brainard; Julia K. Baum (Global Change Biology, 2017)
Fishing pressure on coral reef ecosystems has been frequently linked to reductions of large fishes and reef fish biomass. Associated impacts on overall community structure are, however, less clear. In size‐structured aquatic ecosystems, fishing impacts are commonly quantified using size spectra, which describe the distribution of individual body sizes within a community. We examined the size spectra and biomass of coral reef fish communities at 38 US ‐affiliated Pacific islands that ranged in human presence from near pristine to human population centers. Size spectra ‘steepened’ steadily with increasing human population and proximity to market due to a reduction in the relative biomass of large fishes and an increase in the dominance of small fishes. Reef fish biomass was substantially lower on inhabited islands than uninhabited ones, even at inhabited islands with the lowest levels of human presence. We found that on populated islands size spectra exponents decreased (analogous to size spectra steepening) linearly with declining biomass, whereas on uninhabited islands there was no relationship. Size spectra were steeper in regions of low sea surface temperature but were insensitive to variation in other environmental and geomorphic covariates. In contrast, reef fish biomass was highly sensitive to oceanographic conditions, being influenced by both oceanic productivity and sea surface temperature. Our results suggest that community size structure may be a more robust indicator than fish biomass to increasing human presence and that size spectra are reliable indicators of exploitation impacts across regions of different fish community compositions, environmental drivers, and fisheries types. Size‐based approaches that link directly to functional properties of fish communities, and are relatively insensitive to abiotic variation across biogeographic regions, offer great potential for developing our understanding of fishing impacts in coral reef ecosystems.

Valuing increased zinc (Zn) fertiliser-use in Pakistan - Edward J. M. Joy; Waqar Ahmad; Munir H. Zia; Diriba B. Kumssa; Scott D. Young; E. Louise Ander; Michael J. Watts; Alexander J. Stein; Martin R. Broadley (Plant and Soil, 2017)

Evolution of a small hydrothermal eruption episode through a mud pool of varying depth and rheology, White Island, NZ - M. J. Edwards; B. M. Kennedy; A. D. Jolly; B. Scheu; P. Jousset (Bulletin of Volcanology, 2017)

The functionality of α-kafirin promoter and α-kafirin signal peptide - Guoquan Liu; Kyle C. Lamont; Norazlina Ahmad; Alison Tomkins; Stephen R. Mudge; Edward K. Gilding; Ian D. Godwin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Alcohol dependence-induced regulation of the proliferation and survival of adult brain progenitors is associated with altered BDNF-TrkB signaling - Sucharita S. Somkuwar; McKenzie J. Fannon; Miranda C. Staples; Eva R. Zamora-Martinez; Alvaro I. Navarro; Airee Kim; Jacqueline A. Quigley; Scott Edwards; Chitra D. Mandyam (Brain Structure and Function, 2016)

Variability and anatomical specificity of the orbitofrontothalamic fibers of passage in the ventral capsule/ventral striatum (VC/VS): precision care for patient-specific tractography-guided targeting of deep brain stimulation (DBS) in obsessive compulsive disorder (OCD) - Nikolaos Makris; Yogesh Rathi; Palig Mouradian; Giorgio Bonmassar; George Papadimitriou; Wingkwai I. Ing; Edward H. Yeterian; Marek Kubicki; Emad N. Eskandar; Lawrence L. Wald; Qiuyun Fan; Aapo Nummenmaa; et al. (Brain Imaging and Behavior, 2016)

Metabolome‐mediated biocryomorphic evolution promotes carbon fixation in G reenlandic cryoconite holes - Joseph M. Cook; Arwyn Edwards; Mark Bulling; Luis A. J. Mur; Sophie Cook; Jarishma K. Gokul; Karen A. Cameron; Michael Sweet; Tristram D. L. Irvine‐Fynn (Environmental Microbiology, 2016)
Summary Microbial photoautotrophs on glaciers engineer the formation of granular microbial‐mineral aggregates termed cryoconite which accelerate ice melt, creating quasi‐cylindrical pits called ‘cryoconite holes’. These act as biogeochemical reactors on the ice surface and provide habitats for remarkably active and diverse microbiota. Evolution of cryoconite holes towards an equilibrium depth is well known, yet interactions between microbial activity and hole morphology are currently weakly addressed. Here, we experimentally perturbed the depths and diameters of cryoconite holes on the Greenland Ice Sheet. Cryoconite holes responded by sensitively adjusting their shapes in three dimensions (‘biocryomorphic evolution’) thus maintaining favourable conditions for net autotrophy at the hole floors. Non‐targeted metabolomics reveals concomitant shifts in cyclic AMP and fucose metabolism consistent with phototaxis and extracellular polymer synthesis indicating metabolomic‐level granular changes in response to perturbation. We present a conceptual model explaining this process and suggest that it results in remarkably robust net autotrophy on the Greenland Ice Sheet. We also describe observations of cryoconite migrating away from shade, implying a degree of self‐regulation of carbon budgets over mesoscales. Since cryoconite is a microbe‐mineral aggregate, it appears that microbial processes themselves form and maintain stable autotrophic habitats on the surface of the Greenland ice sheet.

Development of a Novel Quantitative Structure-Activity Relationship Model to Accurately Predict Pulmonary Absorption and Replace Routine Use of the Isolated Perfused Respiring Rat Lung Model - Chris D. Edwards; Chris Luscombe; Peter Eddershaw; Edith M. Hessel (Pharmaceutical Research, 2016)

Fission-fusion dynamics in black-and-white ruffed lemurs may facilitate both feeding strategies and communal care of infants in a spatially and temporally variable environment - Sheila M. Holmes; Adam D. Gordon; Edward E. Louis; Steig E. Johnson (Behavioral Ecology and Sociobiology, 2016)

Water–energy balance, past ecological perturbations and evolutionary constraints shape the latitudinal diversity gradient of soil testate amoebae in south‐western South America - Leonardo D. Fernández; Bertrand Fournier; Reinaldo Rivera; Enrique Lara; Edward A. D. Mitchell; Cristián E. Hernández (Global Ecology and Biogeography, 2016)
Aim To assess the largely neglected patterns and causes of latitudinal diversity gradients in soil protists, using South American testate amoebae as model organisms. Location South‐western South America (SSA). Methods We assessed the relationship among richness, latitude and predictions of eight ecological hypotheses in SSA, a region characterized by harsh abiotic conditions northward and southward from mid‐latitudes. We also examined the patterns of latitudinal variation in species range sizes, species composition and phylogenetic relatedness among species to assess whether the responses of species to current climate rely on evolutionary constraints. Results Richness followed a unimodal trend with abrupt declines northward and southward from mid‐latitudes. This trend was mostly explained by water–energy balance. To our knowledge, this mechanism has never been reported for soil microorganisms before. Species range sizes were larger northward and southward from mid‐latitudes, a pattern which we have called the ‘two‐way Rapoport effect’. Species composition was due to turnover at mid‐latitudes and to nestedness towards low and high latitudes. Species at mid‐latitudes tended to be less related to each other than those at low and high latitudes, supporting the existence of evolutionary constraints to water–energy availability. Main conclusions The unimodal response of species diversity to water and energy availability stems from a combination of the ancestral adaptation of testate amoebae to warm, humid climates and past climate changes that set up permanent harsh abiotic conditions northward and southward from mid‐latitudes. Given that other soil microorganisms also depend on water and energy to survive and reproduce, we predict that the unimodal response to water–energy balance observed will also be valid for a large number of microbial groups in SSA. While this diversity trend may not hold true for testate amoebae from other regions, we predict that their evolutionary constraints to water–energy availability will always produce strong relationships among richness, water and energy at large spatial‐scales.

Cytotoxic oplopane sesquiterpenoids from Arnoglossum atriplicifolium - Jason A. Clement; Rachel M. Bleich; Hailey E. Campbell; Kristin Naylor; Matthew J. Flood; Ryan M. Kelly; Shi-Biao Wu; Edward J. Kennelly; Jeffrey D. Schmitt (Natural Product Research, 2016)

Use of a coupled soil-root-leaf model to optimise phosphate fertiliser use efficiency in barley - J. Heppell; S. Payvandi; P. Talboys; K. C. Zygalakis; D. Langton; R. Sylvester-Bradley; A. C. Edwards; R. Walker; P. Withers; D. L. Jones; T. Roose (Plant and Soil, 2016)

Measuring Nutrition Literacy in Breast Cancer Patients: Development of a Novel Instrument - Heather D. Gibbs; Edward F. Ellerbeck; Christie Befort; Byron Gajewski; Amy R. Kennett; Qing Yu; Danielle Christifano; Debra K. Sullivan (Journal of Cancer Education, 2016)

Intramuscular MAPK signaling following high volume and high intensity resistance exercise protocols in trained men - Adam M. Gonzalez; Jay R. Hoffman; Jeremy R. Townsend; Adam R. Jajtner; Carleigh H. Boone; Kyle S. Beyer; Kayla M. Baker; Adam J. Wells; Gerald T. Mangine; Edward H. Robinson; David D. Church; Leonardo P. Oliveira; et al. (European Journal of Applied Physiology, 2016)

Fine-scale spatial variation in ice cover and surface temperature trends across the surface of the Laurentian Great Lakes - Lacey A. Mason; Catherine M. Riseng; Andrew D. Gronewold; Edward S. Rutherford; Jia Wang; Anne Clites; Sigrid D. P. Smith; Peter B. McIntyre (Climatic Change, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Reduction of nicotine self-administration by chronic nicotine infusion with H1 histamine blockade in female rats - Edward D. Levin; Brandon J. Hall; Autri Chattopadhyay; Susan Slade; Corinne Wells; Amir H. Rezvani; Jed E. Rose (Psychopharmacology, 2016)

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Taxon interactions control the distributions of cryoconite bacteria colonizing a High Arctic ice cap - Jarishma K. Gokul; Andrew J. Hodson; Eli R. Saetnan; Tristram D. L. Irvine‐Fynn; Philippa J. Westall; Andrew P. Detheridge; Nozomu Takeuchi; Jennifer Bussell; Luis A. J. Mur; Arwyn Edwards (Molecular Ecology, 2016)
Microbial colonization of glacial ice surfaces incurs feedbacks which affect the melting rate of the ice surface. Ecosystems formed as microbe–mineral aggregates termed cryoconite locally reduce ice surface albedo and represent foci of biodiversity and biogeochemical cycling. Consequently, greater understanding the ecological processes in the formation of functional cryoconite ecosystems upon glacier surfaces is sought. Here, we present the first bacterial biogeography of an ice cap, evaluating the respective roles of dispersal, environmental and biotic filtration occurring at local scales in the assembly of cryoconite microbiota. 16S rRNA gene amplicon semiconductor sequencing of cryoconite colonizing a Svalbard ice cap coupled with digital elevation modelling of physical parameters reveals the bacterial community is dominated by a ubiquitous core of generalist taxa, with evidence for a moderate pairwise distance–decay relationship. While geographic position and melt season duration are prominent among environmental predictors of community structure, the core population of taxa appears highly influential in structuring the bacterial community. Taxon co‐occurrence network analysis reveals a highly modular community structured by positive interactions with bottleneck taxa, predominantly Actinobacteria affiliated to isolates from soil humus. In contrast, the filamentous cyanobacterial taxon (assigned to Leptolyngbya/Phormidesmis pristleyi ) which dominates the community and binds together granular cryoconite are poorly connected to other taxa. While our study targeted one ice cap, the prominent role of generalist core taxa with close environmental relatives across the global cryosphere indicate discrete roles for cosmopolitan Actinobacteria and Cyanobacteria as respective keystone taxa and ecosystem engineers of cryoconite ecosystems colonizing ice caps.

Hyperspectral logging of middle Cambrian marine sediments with hydrocarbon prospectivity: a case study from the southern Georgina Basin, northern Australia - B. Ayling; J. Huntington; B. Smith; D. Edwards (Australian Journal of Earth Sciences, 2016)

Manganese-Enhanced Magnetic Resonance Imaging Reflects Brain Pathology During Progressive HIV-1 Infection of Humanized Mice - Aditya N. Bade; Santhi Gorantla; Prasanta K. Dash; Edward Makarov; Balasrinivasa R. Sajja; Larisa Y. Poluektova; Jiangtao Luo; Howard E. Gendelman; Michael D. Boska; Yutong Liu (Molecular Neurobiology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

A conceptual framework for analyzing deltas as coupled social–ecological systems: an example from the Amazon River Delta - Eduardo S. Brondizio; Nathan D. Vogt; Andressa V. Mansur; Edward J. Anthony; Sandra Costa; Scott Hetrick (Sustainability Science, 2016)

Selection and intake of algal species in butterfish (Odax pullus; Labridae) - Edward J. C. Baker; Marcus Clauss; Kendall D. Clements (Marine Biology, 2016)

Formal modelling of predator preferences using molecular gut-content analysis - Edward A. Roualdes; Simon J. Bonner; Thomas D. Whitney; James D. Harwood (Environmental and Ecological Statistics, 2016)

Projections of climate change effects on discharge and inundation in the Amazon basin - Mino Viana Sorribas; Rodrigo C. D. Paiva; John M. Melack; Juan Martin Bravo; Charles Jones; Leila Carvalho; Edward Beighley; Bruce Forsberg; Marcos Heil Costa (Climatic Change, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Biophysical controls on dissolved organic carbon concentrations of Alaskan coastal temperate rainforest streams - David V. D’Amore; Rick T. Edwards; Frances E. Biles (Aquatic Sciences, 2016)

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Accelerating Adverse Outcome Pathway Development Using Publicly Available Data Sources - Noffisat O. Oki; Mark D. Nelms; Shannon M. Bell; Holly M. Mortensen; Stephen W. Edwards (Current Environmental Health Reports, 2016)

A legacy of human‐induced ecosystem changes: spatial processes drive the taxonomic and functional diversities of testate amoebae in Sphagnum peatlands of the Galápagos - Bertrand Fournier; Emily E. D. Coffey; W. O. van der Knaap; Leonardo D. Fernández; Anatoly Bobrov; Edward A. D. Mitchell (Journal of Biogeography, 2016)
Aim Our aims were to compare the composition of testate amoeba ( TA ) communities from Santa Cruz Island, Galápagos Archipelago, which are likely in existence only as a result of anthropogenic habitat transformation, with similar naturally occurring communities from northern and southern continental peatlands. Additionally, we aimed at assessing the importance of niche‐based and dispersal‐based processes in determining community composition and taxonomic and functional diversity. Location The humid highlands of the central island of Santa Cruz, Galápagos Archipelago. Methods We survey the alpha, beta and gamma taxonomic and functional diversities of TA , and the changes in functional traits along a gradient of wet to dry habitats. We compare the TA community composition, abundance and frequency recorded in the insular peatlands with that recorded in continental peatlands of Northern and Southern Hemispheres. We use generalized linear models to determine how environmental conditions influence taxonomic and functional diversity as well as the mean values of functional traits within communities. We finally apply variance partitioning to assess the relative importance of niche‐ and dispersal‐based processes in determining community composition. Results TA communities in Santa Cruz Island were different from their Northern Hemisphere and South American counterparts with most genera considered as characteristic for Northern Hemisphere and South American Sphagnum peatlands missing or very rare in the Galápagos. Functional traits were most correlated with elevation and site topography and alpha functional diversity to the type of material sampled and site topography. Community composition was more strongly correlated with spatial variables than with environmental ones. Main conclusions TA communities of the Sphagnum peatlands of Santa Cruz Island and the mechanisms shaping these communities contrast with Northern Hemisphere and South American peatlands. Soil moisture was not a strong predictor of community composition most likely because rainfall and clouds provide sufficient moisture. Dispersal limitation was more important than environmental filtering because of the isolation of the insular peatlands from continental ones and the young ecological history of these ecosystems.

Soil microorganisms behave like macroscopic organisms: patterns in the global distribution of soil euglyphid testate amoebae - Enrique Lara; Ludovic Roussel‐Delif; Bertrand Fournier; David M. Wilkinson; Edward A. D. Mitchell (Journal of Biogeography, 2016)
Aim Patterns of α‐ and β‐diversity of soil protist communities and the factors that shape them remain largely unknown. We undertook a world‐wide survey of forest litter to investigate the patterns of diversity in a group of testate amoebae. We aimed to assess: (1) whether there is a latitudinal gradient in α‐diversity, and (2) whether β‐diversity was correlated solely with environmental factors commonly used in soil biology research or if it was also independently explained by geographical barriers. Location World‐wide. Methods We studied the diversity of Euglyphida, a common group of testate amoebae, in 35 samples of forest litter and moss samples from a global survey, using small subunit rRNA gene sequences. We assessed the relationship between sample α‐diversity and latitude using generalized additive models ( GAM ). Furthermore, we determined the relationships between community composition and geographical models (distance‐based Moran's Eigenvector Maps – db‐ MEM ) using Generalized UniFrac distances ( GU niFrac). We also investigated the relationship between individual measured soil parameters, WorldClim data and diversity (alpha plus beta) using both raw data and synthetic variables obtained through principal components analysis. Results We recorded 245 phylotypes belonging to 6 out of 7 known Euglyphida families, plus four novel deep clades. Euglyphid α‐diversity was positively correlated with temperature and negatively with latitude and litter C/N ratio. Euglyphida community structure was correlated with the spatial eigenvector Db‐ MEM 31, independently of all measured environmental variables. Db‐ MEM 31 corresponds to a natural barrier constituted by the Northern Hemisphere desert belt. Beta diversity was correlated with other environmental variables, such as pH , isothermality and temperature in the coldest month of the year. Main conclusions Soil euglyphid α‐diversity displays a latitudinal gradient, and β‐diversity is not only correlated with climatic and physicochemical parameters but also with geographical barriers. Such patterns of diversity were until recently believed to be characteristic only for macroscopic organisms.

Environmental Correlates of Body Mass in True Lemurs (Eulemur spp.) - Adam D. Gordon; Steig E. Johnson; Edward E. Louis (International Journal of Primatology, 2016)

Fixed prey cue preferences among Dusky Pigmy Rattlesnakes (Sistrurus miliarius barbouri) raised on different long-term diets - Matthew L. Holding; Edward H. Kern; Robert D. Denton; H. Lisle Gibbs (Evolutionary Ecology, 2016)

The impact of the introduction of fidaxomicin on the management of Clostridium difficile infection in seven NHS secondary care hospitals in England: a series of local service evaluations - S. D. Goldenberg; S. Brown; L. Edwards; D. Gnanarajah; P. Howard; D. Jenkins; D. Nayar; M. Pasztor; S. Oliver; T. Planche; J. A. T. Sandoe; P. Wade; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Evaluation of cystatin C as an early biomarker of cadmium nephrotoxicity in the rat - Walter C. Prozialeck; Aaron VanDreel; Christopher D. Ackerman; Ian Stock; Alexander Papaeliou; Christian Yasmine; Kristen Wilson; Peter C. Lamar; Victoria L. Sears; Joshua Z. Gasiorowski; Karyn M. DiNovo; Vishal S. Vaidya; et al. (BioMetals, 2016)

Utilizing an Ingestible Biosensor to Assess Real-Time Medication Adherence - Peter R. Chai; Jose Castillo-Mancilla; Eric Buffkin; Chad Darling; Rochelle K. Rosen; Keith J. Horvath; Edwin D. Boudreaux; Gregory K. Robbins; Patricia L. Hibberd; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

Retrospective stable isotope analysis reveals ecosystem responses to river regulation over the last century - Thomas F. Turner; Trevor J. Krabbenhoft; Michael L. Collyer; Corey A. Krabbenhoft; Melanie S. Edwards; Zachary D. Sharp (Ecology, 2015)
Disruption of natural flow regimes, nutrient pollution, and other consequences of human population growth and development have impacted most major rivers of the world. Alarming losses of aquatic biodiversity coincide with human‐caused river alteration, but effects of biotic homogenization on aquatic ecosystem processes are not as well documented. This is because unaltered systems for comparison are scarce, and some ecosystem‐wide effects may take decades to manifest. We evaluated aquatic ecosystem responses to extensive river‐floodplain engineering and nutrient addition in the Rio Grande of southwestern North America as revealed by changes in trophic structure of, and resource availability to, the fish community. Stable Isotope Analysis (SIA) was conducted on museum‐preserved fishes collected over a 70‐year period of intensive river management and exponential human population growth. Trophic complexity and resource heterogeneity for fish consumers (measured as “isotopic niche breadth”) decreased following sediment deprivation and channelization, and these effects persist into the present. Increased nutrient inputs led to δ 15 N enrichment in the entire fish community at all affected sites, and a shift to autochthonous sources of carbon at the most proximal site downstream of wastewater release, probably via bottom‐up transfer. Overall, retrospective SIA of apex consumers suggests radical change and functional impairment of a floodplain river ecosystem already marked by significant biodiversity loss.

The checkered history of checkerboard distributions: reply - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2015)

Aquatic vegetation mediates the relationship between hydrologic connectivity and water quality in a managed floodplain - Michael D. Kaller; Richard F. Keim; Brandon L. Edwards; A. Raynie Harlan; Tiffany E. Pasco; William E. Kelso; D. Allen Rutherford (Hydrobiologia, 2015)

Defining adult bonefish (Albula vulpes) movement corridors around Grand Bahama in the Bahamian Archipelago - Karen J. Murchie; Aaron D. Shultz; Jeffrey A. Stein; Steven J. Cooke; Justin Lewis; Jason Franklin; Greg Vincent; Edward J. Brooks; Julie E. Claussen; David P. Philipp (Environmental Biology of Fishes, 2015)

Evaluation of microbial transport during aerobic bioaugmentation of an RDX-contaminated aquifer - Fiona H. Crocker; Karl J. Indest; Carina M. Jung; Dawn E. Hancock; Mark E. Fuller; Paul B. Hatzinger; Simon Vainberg; Jonathan D. Istok; Edward Wilson; Mandy M. Michalsen (Biodegradation, 2015)

Digital innovation through partnership between nature conservation organisations and academia: A qualitative impact assessment - Carlos Galán-Díaz; Peter Edwards; John D. Nelson; René van der Wal (Ambio, 2015)

Cosmogenic dating of Late Pleistocene glaciation, southern tropical Andes, Peru - Jeremy D. Shakun; Peter U. Clark; Shaun A. Marcott; Edward J. Brook; Nathaniel A. Lifton; Marc Caffee; William R. Shakun (Journal of Quaternary Science, 2015)
We present 30 10 Be dates on three moraines formed by small glaciers in the southern tropical Andes of Peru to determine the timing of the local Last Glacial Maximum (LGM) and subsequent deglaciation. Two terminal moraines indicate that the local LGM ended at 23.5 ± 0.5 and 21.2 ± 0.8 ka, or well before the end of the global LGM (20–19 ka). A recessional moraine perched at the base of a steep valley wall has a 10 Be age of 19.8 ± 0.3 ka, suggesting that glaciers had largely retreated from the area during the earliest stages of the last termination and before the onset of the deglacial CO 2 rise and increase in tropical sea surface temperatures. These ages generally agree with other tropical glacial chronologies and reflect a broad synchroneity between low‐ and high‐latitude deglaciation at the LGM, but the trigger for early deglaciation of the tropics remains unclear.

Pack hunting by minute soil testate amoebae: nematode hell is a naturalist's paradise - Edward A. D. Mitchell (Environmental Microbiology, 2015)

Hypoxia-induced expression of phosducin-like 3 regulates expression of VEGFR-2 and promotes angiogenesis - Srimathi Srinivasan; Vipul Chitalia; Rosana D. Meyer; Edward Hartsough; Manisha Mehta; Itrat Harrold; Nicole Anderson; Hui Feng; Lois E. H. Smith; Yan Jiang; Catherine E. Costello; Nader Rahimi (Angiogenesis, 2015)

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Role of nicotinic receptors in the lateral habenula in the attenuation of amphetamine-induced prepulse inhibition deficits of the acoustic startle response in rats - José A. Larrauri; Dennis A. Burke; Brandon J. Hall; Edward D. Levin (Psychopharmacology, 2015)

Acid sphingomyelinase inhibition protects mice from lung edema and lethal Staphylococcus aureus sepsis - Huiming Peng; Cao Li; Stephanie Kadow; Brian D. Henry; Jörg Steinmann; Katrin Anne Becker; Andrea Riehle; Natalie Beckmann; Barbara Wilker; Pin-Lan Li; Timothy Pritts; Michael J. Edwards; et al. (Journal of Molecular Medicine, 2015)

Multi-tensor investigation of orbitofrontal cortex tracts affected in subcaudate tractotomy - Jimmy C. Yang; George Papadimitriou; Ryan Eckbo; Edward H. Yeterian; Lichen Liang; Darin D. Dougherty; Sylvain Bouix; Yogesh Rathi; Martha Shenton; Marek Kubicki; Emad N. Eskandar; Nikos Makris (Brain Imaging and Behavior, 2015)

From Red Tides to Green and Brown Tides: Bloom Dynamics in a Restricted Subtropical Lagoon Under Shifting Climatic Conditions - Edward J. Phlips; Susan Badylak; Margaret A. Lasi; Robert Chamberlain; Whitney C. Green; Lauren M. Hall; Jane A. Hart; Jean C. Lockwood; Janice D. Miller; Lori J. Morris; Joel S. Steward (Estuaries and Coasts, 2015)

Structural reorganization of pyramidal neurons in the medial prefrontal cortex of alcohol dependent rats is associated with altered glial plasticity - Airee Kim; Eva R. Zamora-Martinez; Scott Edwards; Chitra D. Mandyam (Brain Structure and Function, 2015)

Zinc-enriched fertilisers as a potential public health intervention in Africa - Edward J. M. Joy; Alexander J. Stein; Scott D. Young; E. Louise Ander; Michael J. Watts; Martin R. Broadley (Plant and Soil, 2015)

Cichlid fishes as models of ecological diversification: patterns, mechanisms, and consequences - Edward D. Burress (Hydrobiologia, 2015)

Real-Time Mobile Detection of Drug Use with Wearable Biosensors: A Pilot Study - Stephanie Carreiro; David Smelson; Megan Ranney; Keith J. Horvath; R. W. Picard; Edwin D. Boudreaux; Rashelle Hayes; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Worldwide phylogeography of the invasive ctenophore Mnemiopsis leidyi (Ctenophora) based on nuclear and mitochondrial DNA data - K. M. Bayha; M. H. Chang; C. L. Mariani; J. L. Richardson; D. L. Edwards; T. S. DeBoer; C. Moseley; E. Aksoy; M. B. Decker; P. M. Gaffney; G. R. Harbison; J. H. McDonald; et al. (Biological Invasions, 2015)

Diversity within the genus Elymus (Poaceae: Triticeae) as investigated by the analysis of the nr5S rDNA variation in species with St and H haplomes - B. R. Baum; T. Edwards; D. A. Johnson (Molecular Genetics and Genomics, 2015)

Tolerance of wheat to vegetative stage soil waterlogging is conditioned by both constitutive and adaptive QTL - Diana C. Ballesteros; R. Esten Mason; Christopher K. Addison; M. Andrea Acuña; M. Nelly Arguello; Nithya Subramanian; Randall Galen Miller; Haley Sater; Edward E. Gbur; David Miller; Carl A. Griffey; Marla D. Barnett; et al. (Euphytica, 2015)

Field study demonstrates that exotic parasitoids (Hymenoptera: Encyrtidae) of mealybugs (Hemiptera: Pseudococcidae) are absent from a native forest habitat in New Zealand - John G. Charles; Shaun A. Forgie; Asha Chhagan; Robert D. Edwards (BioControl, 2015)

Use of structured expert judgment to forecast invasions by bighead and silver carp in Lake Erie - Marion E. Wittmann; Roger M. Cooke; John D. Rothlisberger; Edward S. Rutherford; Hongyan Zhang; Doran M. Mason; David M. Lodge (Conservation Biology, 2015)
Identifying which nonindigenous species will become invasive and forecasting the damage they will cause is difficult and presents a significant problem for natural resource management. Often, the data or resources necessary for ecological risk assessment are incomplete or absent, leaving environmental decision makers ill equipped to effectively manage valuable natural resources. Structured expert judgment (SEJ) is a mathematical and performance‐based method of eliciting, weighting, and aggregating expert judgments. In contrast to other methods of eliciting and aggregating expert judgments (where, for example, equal weights may be assigned to experts), SEJ weights each expert on the basis of his or her statistical accuracy and informativeness through performance measurement on a set of calibration variables. We used SEJ to forecast impacts of nonindigenous Asian carp ( Hypophthalmichthys spp.) in Lake Erie, where it is believed not to be established. Experts quantified Asian carp biomass, production, and consumption and their impact on 4 fish species if Asian carp were to become established. According to experts, in Lake Erie Asian carp have the potential to achieve biomass levels that are similar to the sum of biomasses for several fishes that are harvested commercially or recreationally. However, the impact of Asian carp on the biomass of these fishes was estimated by experts to be small, relative to long term average biomasses, with little uncertainty. Impacts of Asian carp in tributaries and on recreational activities, water quality, or other species were not addressed. SEJ can be used to quantify key uncertainties of invasion biology and also provide a decision‐support tool when the necessary information for natural resource management and policy is not available. El Uso de Juicio Experto Estructurado para Predecir Invasiones de Carpas Asiáticas en el Lago Erie

Fluorescent protein‐mediated colour polymorphism in reef corals: multicopy genes extend the adaptation/acclimatization potential to variable light environments - John R. Gittins; Cecilia D'Angelo; Franz Oswald; Richard J. Edwards; Jörg Wiedenmann (Molecular Ecology, 2015)
The genomic framework that enables corals to adjust to unfavourable conditions is crucial for coral reef survival in a rapidly changing climate. We have explored the striking intraspecific variability in the expression of coral pigments from the green fluorescent protein ( GFP ) family to elucidate the genomic basis for the plasticity of stress responses among reef corals. We show that multicopy genes can greatly increase the dynamic range over which corals can modulate transcript levels in response to the light environment. Using the red fluorescent protein amil FP 597 in the coral Acropora millepora as a model, we demonstrate that its expression increases with light intensity, but both the minimal and maximal gene transcript levels vary markedly among colour morphs. The pigment concentration in the tissue of different morphs is strongly correlated with the number of gene copies with a particular promoter type. These findings indicate that colour polymorphism in reef corals can be caused by the environmentally regulated expression of multicopy genes. High‐level expression of amil FP 597 is correlated with reduced photodamage of zooxanthellae under acute light stress, supporting a photoprotective function of this pigment. The cluster of light‐regulated pigment genes can enable corals to invest either in expensive high‐level pigmentation, offering benefits under light stress, or to rely on low tissue pigment concentrations and use the conserved resources for other purposes, which is preferable in less light‐exposed environments. The genomic framework described here allows corals to pursue different strategies to succeed in habitats with highly variable light stress levels. In summary, our results suggest that the intraspecific plasticity of reef corals’ stress responses is larger than previously thought.

Cryptic structure and niche divergence within threatened Galápagos giant tortoises from southern Isabela Island - D. L. Edwards; R. C. Garrick; W. Tapia; A. Caccone (Conservation Genetics, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Evaluation of Acoustic Membrane Microparticle (AMMP) Technology for a Sensitive Ligand Binding Assay to Support Pharmacokinetic Determinations of a Biotherapeutic - Shannon D. Chilewski; W. Matthew Dickerson; Johanna R. Mora; Ashley Saab; Edward M. Alderman (The AAPS Journal, 2014)

Mapping the shadow of experience of extreme weather events - Peter D. Howe; Hilary Boudet; Anthony Leiserowitz; Edward W. Maibach (Climatic Change, 2014)

A regime shift in Lake Superior ice cover, evaporation, and water temperature following the warm El Niñ winter of 1997–1998 - Katherine Van Cleave; John D. Lenters; Jia Wang; Edward M. Verhamme (Limnology and Oceanography, 2014)
Significant trends in Lake Superior water temperature and ice cover have been observed in recent decades, and these trends have typically been analyzed using standard linear regression techniques. Although the linear trends are statistically significant and contribute to an understanding of environmental change, a careful examination of the trends shows important nonlinearities. We identify a pronounced step change that occurred in Lake Superior following the warm El Niño winter of 1997–1998, resulting in a “regime shift” in summer evaporation rate, water temperature, and numerous metrics of winter ice cover. This statistically significant step change accounts for most of the long‐term trends in ice cover, water temperature, and evaporation during the period 1973–2010, and it was preceded (and followed) by insignificant linear trends in nearly all of the metrics examined. The 1998 step change is associated with a decrease in winter ice duration of 39 d (a 34% decline), an increase of ∼ 2–3°C in mean surface water temperature (July–September averages), and a 91% increase in July–August evaporation rates, reflecting an earlier start to the summer evaporation season. Maximum wintertime ice extent decreased by nearly a factor of two, from an average of 69% of the lake surface area (before 1997–1998) to 36% after the step change. This reassessment of long‐term trends highlights the importance of nonlinear regime shifts such as the 1997–1998 break point—an event that may be related to a similar shift in the Pacific Decadal Oscillation that occurred around the same time. These pronounced changes in Lake Superior physical characteristics are likely to have important implications for the broader lake ecosystem.

Real Exposure: Field Measurement of Chemical Plumes in Headwater Streams - David D. Edwards; Paul A. Moore (Archives of Environmental Contamination and Toxicology, 2014)

The Pink Eye Syndrome Does Not Impair Tuber Fresh Cut Wound-Related Responses - Edward C. Lulai; Jonathan D. Neubauer; Linda L. Huckle; Jeffrey C. Suttle (American Journal of Potato Research, 2014)

Range‐wide multilocus phylogeography of the red fox reveals ancient continental divergence, minimal genomic exchange and distinct demographic histories - Mark J. Statham; James Murdoch; Jan Janecka; Keith B. Aubry; Ceiridwen J. Edwards; Carl D. Soulsbury; Oliver Berry; Zhenghuan Wang; David Harrison; Malcolm Pearch; Louise Tomsett; Judith Chupasko; et al. (Molecular Ecology, 2014)
Widely distributed taxa provide an opportunity to compare biogeographic responses to climatic fluctuations on multiple continents and to investigate speciation. We conducted the most geographically and genomically comprehensive study to date of the red fox ( Vulpes vulpes ), the world's most widely distributed wild terrestrial carnivore. Analyses of 697 bp of mitochondrial sequence in ~1000 individuals suggested an ancient Middle Eastern origin for all extant red foxes and a 400 kya ( SD = 139 kya) origin of the primary North American (Nearctic) clade. Demographic analyses indicated a major expansion in Eurasia during the last glaciation (~50 kya), coinciding with a previously described secondary transfer of a single matriline (Holarctic) to North America. In contrast, North American matrilines (including the transferred portion of Holarctic clade) exhibited no signatures of expansion until the end of the Pleistocene (~12 kya). Analyses of 11 autosomal loci from a subset of foxes supported the colonization time frame suggested by mt DNA (and the fossil record) but, in contrast, reflected no detectable secondary transfer, resulting in the most fundamental genomic division of red foxes at the Bering Strait. Endemic continental Y‐chromosome clades further supported this pattern. Thus, intercontinental genomic exchange was overall very limited, consistent with long‐term reproductive isolation since the initial colonization of North America. Based on continental divergence times in other carnivoran species pairs, our findings support a model of peripatric speciation and are consistent with the previous classification of the North American red fox as a distinct species, V. fulva .

Salt accumulation and depletion in the root-zone of the halophyte Atriplex nummularia Lindl.: influence of salinity, leaf area and plant water use - Hesham F. Alharby; Timothy D. Colmer; Edward G. Barrett-Lennard (Plant and Soil, 2014)

How to communicate the scientific consensus on climate change: plain facts, pie charts or metaphors? - Sander L. van der Linden; Anthony A. Leiserowitz; Geoffrey D. Feinberg; Edward W. Maibach (Climatic Change, 2014)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Global‐scale patterns of assemblage structure of soil nematodes in relation to climate and ecosystem properties - Uffe N. Nielsen; Edward Ayres; Diana H. Wall; Grace Li; Richard D. Bardgett; Tiehang Wu; James R. Garey (Global Ecology and Biogeography, 2014)
Aim To conduct the first global‐scale investigation of soil nematode assemblages using a standardized approach to quantify how environmental and climatic variables influence family assemblage structure in nematodes and determine whether nematode families have restricted distributions. Location Global. Methods We collected soil nematodes within four 10 m × 10 m plots distributed evenly along a 900‐m transect at each of 12 sites representing multiple ecosystem types across a latitudinal gradient (68° N to 77° S ) on six continents. We assigned > 28,000 individuals to family level and trophic group morphologically. Results We recorded a total of 43 nematode families, but sites varied considerably in family richness (1–30). Families differed in their ranges with 12 families occurring at 10 or more sites, while 14 families occurred at three or fewer sites. Total nematode and trophic group abundances were generally related to soil characteristics, including bulk density and soil moisture, but we found no good predictor of family richness, diversity or evenness at the plot level. Family richness, diversity and evenness were considerably lower in the high‐latitude polar desert than elsewhere, but only family diversity showed a significant, albeit weak, latitudinal gradient. Nematode assemblage composition was quite strongly related to climate: 65% and 58% of the variation in assemblage composition across sites could be accounted for by mean annual rainfall and temperature, respectively. Main conclusions Nematode families display macroecological patterns similar to other organisms, such as a positive abundance–range size relationship and restricted distribution of some families. Local nematode abundances were related to soil characteristics, but we found no relationships between family richness and environmental or climatic variables. Family composition was related to mean annual rainfall and temperature, suggesting that climate is a good predictor of local assemblage structure. As a result, climate change may have a significant impact on nematode assemblages, with potential implications for ecosystem functioning.

Involvement of nucleus accumbens AMPA receptor trafficking in augmentation of D- amphetamine reward in food-restricted rats - Xing-Xiang Peng; Soledad Cabeza de Vaca; Edward B. Ziff; Kenneth D. Carr (Psychopharmacology, 2014)

Predicting Nonlinear Pharmacokinetics of Omeprazole Enantiomers and Racemic Drug Using Physiologically Based Pharmacokinetic Modeling and Simulation: Application to Predict Drug/Genetic Interactions - Fang Wu; Lu Gaohua; Ping Zhao; Masoud Jamei; Shiew-Mei Huang; Edward D. Bashaw; Sue-Chih Lee (Pharmaceutical Research, 2014)

What does the nr5S DNA multigene family tell us about the genomic relationship between Dasypyrum breviaristatum and D. villosum (Triticeae: Poaceae)? - B. R. Baum; T. Edwards; D. A. Johnson (Molecular Genetics and Genomics, 2014)

Non‐native acylated homoserine lactones reveal that LuxIR quorum sensing promotes symbiont stability - Sarah V. Studer; Julia A. Schwartzman; Jessica S. Ho; Grant D. Geske; Helen E. Blackwell; Edward G. Ruby (Environmental Microbiology, 2014)
Summary Quorum sensing, a group behaviour coordinated by a diffusible pheromone signal and a cognate receptor, is typical of bacteria that form symbioses with plants and animals. LuxIR ‐type N ‐acyl L‐homoserine ( AHL ) quorum sensing is common in Gram‐negative Proteobacteria , and many members of this group have additional quorum‐sensing networks. The bioluminescent symbiont V ibrio fischeri encodes two AHL signal synthases: AinS and LuxI . AinS ‐dependent quorum sensing converges with LuxI ‐dependent quorum sensing at the LuxR regulatory element. Both AinS ‐ and LuxI ‐mediated signalling are required for efficient and persistent colonization of the squid host, E uprymna scolopes . The basis of the mutualism is symbiont bioluminescence, which is regulated by both LuxI ‐ and AinS ‐dependent quorum sensing, and is essential for maintaining a colonization of the host. Here, we used chemical and genetic approaches to probe the dynamics of LuxI ‐ and AinS ‐mediated regulation of bioluminescence during symbiosis. We demonstrate that both native AHLs and non‐native AHL analogues can be used to non‐invasively and specifically modulate induction of symbiotic bioluminescence via LuxI ‐dependent quorum sensing. Our data suggest that the first day of colonization, during which symbiont bioluminescence is induced by LuxIR , is a critical period that determines the stability of the V . fischeri population once symbiosis is established.

Tree Response to Experimental Watershed Acidification - N. K. Jensen; E. J. Holzmueller; P. J. Edwards; M. Thomas-Van Gundy; D. R. DeWalle; K. W. J. Williard (Water, Air, & Soil Pollution, 2014)

Non-linear Increases in Danazol Exposure with Dose in Older vs. Younger Beagle Dogs: The Potential Role of Differences in Bile Salt Concentration, Thermodynamic Activity, and Formulation Digestion - Mette U. Anby; Hywel D. Williams; Orlagh Feeney; Glenn A. Edwards; Hassan Benameur; Colin W. Pouton; Christopher J. H. Porter (Pharmaceutical Research, 2014)

Comparison of anchovy biomass estimates measured by trawls, egg production methods and hydro-acoustics in the Chesapeake Bay and the Korea Strait - Sukgeun Jung; Edward D. Houde (Ocean Science Journal, 2014)

Tundra and boreal forest of interior Alaska during terminal MIS 6 and MIS 5e - Nancy H. Bigelow; Mary E. Edwards; Scott A. Elias; Thomas D. Hamilton; Charles E. Schweger (Vegetation History and Archaeobotany, 2014)

Bioanalytical Method Validation: Concepts, Expectations and Challenges in Small Molecule and Macromolecule—A Report of PITTCON 2013 Symposium - Edward D. Bashaw; Binodh DeSilva; Mark J. Rose; Yow-Ming C. Wang; Chinmay Shukla (The AAPS Journal, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Spatio-temporal Variability in Larval-Stage Feeding and Nutritional Sources as Factors Influencing Striped Bass (Morone saxatilis) Recruitment Success - Allison C. Shideler; Edward D. Houde (Estuaries and Coasts, 2014)

Controls on water balance of shallow thermokarst lakes and their relations with catchment characteristics: a multi‐year, landscape‐scale assessment based on water isotope tracers and remote sensing in Old Crow Flats, Yukon (Canada) - Kevin W. Turner; Brent B. Wolfe; Thomas W. D. Edwards; Trevor C. Lantz; Roland I. Hall; Guillaume Larocque (Global Change Biology, 2014)
Many northern lake‐rich regions are undergoing pronounced hydrological change, yet inadequate knowledge of the drivers of these landscape‐scale responses hampers our ability to predict future conditions. We address this challenge in the thermokarst landscape of Old Crow Flats ( OCF ) using a combination of remote sensing imagery and monitoring of stable isotope compositions of lake waters over three thaw seasons (2007–2009). Quantitative analysis confirmed that the hydrological behavior of lakes is strongly influenced by catchment vegetation and physiography. Catchments of snowmelt‐dominated lakes, typically located in southern peripheral areas of OCF , encompass high proportions of woodland/forest and tall shrub vegetation (mean percent land cover = ca. 60%). These land cover types effectively capture snow and generate abundant snowmelt runoff that offsets lake water evaporation. Rainfall‐dominated lakes that are not strongly influenced by evaporation are typically located in eastern and northern OCF where their catchments have higher proportions of dwarf shrub/herbaceous and sparse vegetation (ca. 45%), as well as surface water (ca. 20%). Evaporation‐dominated lakes, are located in the OCF interior where their catchments are distinguished by substantially higher lake area to catchment area ratios ( LA / CA = ca. 29%) compared to low evaporation‐influenced rainfall‐dominated (ca. 10%) and snowmelt‐dominated (ca. 4%) lakes. Lakes whose catchments contain >75% combined dwarf shrub/herbaceous vegetation and surface water are most susceptible to evaporative lake‐level drawdown, especially following periods of low precipitation. Findings indicate that multiple hydrological trajectories are probable in response to climate‐driven changes in precipitation amount and seasonality, vegetation composition, and thermokarst processes. These will likely include a shift to greater snowmelt influence in catchments experiencing expansion of tall shrubs, greater influence from evaporation in catchments having higher proportions of surface water, and an increase in the rate of thermokarst lake expansion and probability of drainage. Local observations suggest that some of these changes are already underway.

Current Challenges in Bioequivalence, Quality, and Novel Assessment Technologies for Topical Products - Avraham Yacobi; Vinod P. Shah; Edward D. Bashaw; Eva Benfeldt; Barbara Davit; Derek Ganes; Tapash Ghosh; Isadore Kanfer; Gerald B. Kasting; Lindsey Katz; Robert Lionberger; Guang Wei Lu; et al. (Pharmaceutical Research, 2014)

Cost-effective IMTA: a comparison of the production efficiencies of mussels and seaweed - Susan L. Holdt; Maeve D. Edwards (Journal of Applied Phycology, 2014)

Cold habituation does not improve manual dexterity during rest and exercise in 5 °C - Matthew D. Muller; Yongsuk Seo; Chul-Ho Kim; Edward J. Ryan; Brandon S. Pollock; Keith J. Burns; Ellen L. Glickman (International Journal of Biometeorology, 2014)

Persistence of 2,4-D and its Effects on Benthic Macroinvertebrates Following Spring Treatment of Eurasian Watermilfoil, Myriophyllum spicatum L. in Two Lakes in Southeastern Wisconsin, USA - E. A. Harrahy; D. S. Edwards; C. J. Hedman (Bulletin of Environmental Contamination and Toxicology, 2014)

Role of Neurotrophic Factor Alterations in the Neurodegenerative Process in HIV Associated Neurocognitive Disorders - Jerel Fields; Wilmar Dumaop; T. D. Langford; Edward Rockenstein; E. Masliah (Journal of Neuroimmune Pharmacology, 2014)

Decisional Support throughout the Cancer Journey for Older Women Diagnosed with Early Stage Breast Cancer: A Single Institutional Study - Roseanna Presutti; Laura D’Alimonte; Merrylee McGuffin; Hanbert Chen; Edward Chow; Jean-Philippe Pignol; Lisa Di Prospero; Mary Doherty; Alex Kiss; Jennifer Wong; Justin Lee; Stanley Liu; et al. (Journal of Cancer Education, 2014)

Closing the circle: is it feasible to rehabilitate reefs with sexually propagated corals? - J. R. Guest; M. V. Baria; E. D. Gomez; A. J. Heyward; A. J. Edwards (Coral Reefs, 2014)

The corallivorous flatworm Amakusaplana acroporae: an invasive species threat to coral reefs? - Benjamin C. C. Hume; Cecilia D’Angelo; Anna Cunnington; Edward G. Smith; Jörg Wiedenmann (Coral Reefs, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Spring-summer temperatures since AD 1780 reconstructed from stable oxygen isotope ratios in white spruce tree-rings from the Mackenzie Delta, northwestern Canada - Trevor J. Porter; Michael F. J. Pisaric; Robert D. Field; Steven V. Kokelj; Thomas W. D. Edwards; Peter deMontigny; Richard Healy; Allegra N. LeGrande (Climate Dynamics, 2014)

Rapeseed rotation, compost and biocontrol amendments reduce soilborne diseases and increase tuber yield in organic and conventional potato production systems - Edward Bernard; Robert P. Larkin; Stellos Tavantzis; M. Susan Erich; Andrei Alyokhin; Serena D. Gross (Plant and Soil, 2014)

The Human Gene Mutation Database: building a comprehensive mutation repository for clinical and molecular genetics, diagnostic testing and personalized genomic medicine - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Shaw; Andrew D. Phillips; David N. Cooper (Human Genetics, 2014)
The Human Gene Mutation Database (HGMD ® ) is a comprehensive collection of germline mutations in nuclear genes that underlie, or are associated with, human inherited disease. By June 2013, the database contained over 141,000 different lesions detected in over 5,700 different genes, with new mutation entries currently accumulating at a rate exceeding 10,000 per annum. HGMD was originally established in 1996 for the scientific study of mutational mechanisms in human genes. However, it has since acquired a much broader utility as a central unified disease-oriented mutation repository utilized by human molecular geneticists, genome scientists, molecular biologists, clinicians and genetic counsellors as well as by those specializing in biopharmaceuticals, bioinformatics and personalized genomics. The public version of HGMD ( https://www.hgmd.cf.ac.uk ) is freely available to registered users from academic institutions/non-profit organizations whilst the subscription version (HGMD Professional) is available to academic, clinical and commercial users under license via BIOBASE GmbH.

Syncoilin is an intermediate filament protein in activated hepatic stellate cells - E. Rossen; Z. Liu; D. Blijweert; N. Eysackers; I. Mannaerts; B. Schroyen; A. El Taghdouini; B. Edwards; K. E. Davies; E. Sokal; M. Najimi; H. Reynaert; et al. (Histochemistry and Cell Biology, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Parkinson disease loci in the mid-western Amish - M. F. Davis; A. C. Cummings; L. N. D’Aoust; L. Jiang; D. R. Velez Edwards; R. Laux; L. Reinhart-Mercer; D. Fuzzell; W. K. Scott; M. A. Pericak-Vance; S. L. Lee; J. L. Haines (Human Genetics, 2013)

The importance of health co-benefits in macroeconomic assessments of UK Greenhouse Gas emission reduction strategies - Henning Tarp Jensen; Marcus R. Keogh-Brown; Richard D. Smith; Zaid Chalabi; Alan D. Dangour; Mike Davies; Phil Edwards; Tara Garnett; Moshe Givoni; Ulla Griffiths; Ian Hamilton; James Jarrett; et al. (Climatic Change, 2013)
We employ a single-country dynamically-recursive Computable General Equilibrium model to make health-focussed macroeconomic assessments of three contingent UK Greenhouse Gas (GHG) mitigation strategies, designed to achieve 2030 emission targets as suggested by the UK Committee on Climate Change. In contrast to previous assessment studies, our main focus is on health co-benefits additional to those from reduced local air pollution. We employ a conservative cost-effectiveness methodology with a zero net cost threshold. Our urban transport strategy (with cleaner vehicles and increased active travel) brings important health co-benefits and is likely to be strongly cost-effective; our food and agriculture strategy (based on abatement technologies and reduction in livestock production) brings worthwhile health co-benefits, but is unlikely to eliminate net costs unless new technological measures are included; our household energy efficiency strategy is likely to breakeven only over the long term after the investment programme has ceased (beyond our 20 year time horizon). We conclude that UK policy makers will, most likely, have to adopt elements which involve initial net societal costs in order to achieve future emission targets and longer-term benefits from GHG reduction. Cost-effectiveness of GHG strategies is likely to require technological mitigation interventions and/or demand-constraining interventions with important health co-benefits and other efficiency-enhancing policies that promote internalization of externalities. Health co-benefits can play a crucial role in bringing down net costs, but our results also suggest the need for adopting holistic assessment methodologies which give proper consideration to welfare-improving health co-benefits with potentially negative economic repercussions (such as increased longevity).

The checkered history of checkerboard distributions - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2013)
To address the idea that the process of interspecific competition can be inferred from data on geographical distribution alone and that evidence from geographical distribution implies an important role for interspecific competition in shaping ecological communities, we reexamine the occurrence of “true checkerboard” distributions among the land and freshwater birds in three Melanesian archipelagoes: Vanuatu, the Bismarck Archipelago, and the Solomon Islands. We use the most recently published distributional records and explicitly include the geography of the distributions of species within each archipelago. We use the overlap of convex hulls to estimate the overlap in the geographic range for each pair of species in each of these archipelagoes. We define a “true checkerboard” to consist of a pair of species with exclusive island‐by‐island distributions, but that have overlapping geographical ranges. To avoid the “dilution effect,” we follow Diamond and Gilpin in focusing only on congeneric and within‐guild species pairs as potential competitors. Few, if any, “true checkerboards” exist in these archipelagoes that could possibly have been influenced by competitive interactions, and even “true checkerboards” can arise for reasons other than interspecific competition. The similarity between related species pairs (congeneric and within‐guild pairs) and unrelated species pairs in their deviation from expectation of the number of islands shared and the overlap of their geographic ranges indicates that these are not distinct statistical populations, but rather a single population of species pairs. Our result, which is based on an examination of the distributional data alone, is consistent with the interpretation that, in these avifaunas, the distributions of congeneric, within‐guild, and unrelated species pairs are shaped by a common set of biological and physical environmental processes.

Acetochlor Persistence in Surface and Subsurface Soil Samples - Rubem S. Oliveira; William C. Koskinen; Carrie D. Graff; James L. Anderson; David J. Mulla; Edward A. Nater; Diego G. Alonso (Water, Air, & Soil Pollution, 2013)

Ecology of testate amoebae in peatlands of central China and development of a transfer function for paleohydrological reconstruction - Yangmin Qin; Edward A. D. Mitchell; Mariusz Lamentowicz; Richard J. Payne; Enrique Lara; Yansheng Gu; Xianyu Huang; Hongmei Wang (Journal of Paleolimnology, 2013)

Current status on production and utilization of spider plant (Cleome gynandra L.) an underutilized leafy vegetable in Kenya - Cecilia M. Onyango; Catherine N. Kunyanga; Edward G. Ontita; Rama D. Narla; John W. Kimenju (Genetic Resources and Crop Evolution, 2013)

Seasonal reproduction of male Gambusia holbrooki (eastern mosquitofish) from two Florida lakes - Thea M. Edwards; Hilary D. Miller; Gunnar Toft; Louis J. Guillette (Fish Physiology and Biochemistry, 2013)

Holarctic phylogeography of the testate amoeba H yalosphenia papilio (Amoebozoa: Arcellinida) reveals extensive genetic diversity explained more by environment than dispersal limitation - Thierry J. Heger; Edward A. D. Mitchell; Brian S. Leander (Molecular Ecology, 2013)
Although free‐living protists play essential roles in aquatic and soil ecology, little is known about their diversity and phylogeography, especially in terrestrial ecosystems. We used mitochondrial cytochrome c oxidase subunit 1 (COI) gene sequences to investigate the genetic diversity and phylogeography of the testate amoeba morphospecies Hyalosphenia papilio in 42 Sphagnum (moss) ‐ dominated peatlands in North America, Europe and Asia. Based on ≥1% sequence divergence threshold, our results from single‐cell PCRs of 301 individuals revealed 12 different genetic lineages and both the general mixed Yule‐coalescent (GMYC) model and the automatic barcode gap discovery (ABGD) methods largely support the hypothesis that these 12 H. papilio lineages correspond to evolutionary independent units (i.e. cryptic species). Our data also showed a high degree of genetic heterogeneity within different geographical regions. Furthermore, we used variation partitioning based on partial redundancy analyses ( pRDA ) to evaluate the contributions of climate and dispersal limitations on the distribution patterns of the different genetic lineages. The largest fraction of the variation in genetic lineage distribution was attributed to purely climatic factors (21%), followed by the joint effect of spatial and bioclimatic factors (13%), and a purely spatial effect (3%). Therefore, these data suggest that the distribution patterns of H. papilio genetic lineages in the Northern Hemisphere are more influenced by climatic conditions than by dispersal limitations.

Studying small purse‐seine vessel fishing behavior with tuna catch data: Implications for eastern Pacific Ocean dolphin conservation - Cleridy E. Lennert‐Cody; Jeremy D. Rusin; Mark N. Maunder; Edward H. Everett; Erick D. Largacha Delgado; Patrick K. Tomlinson (Marine Mammal Science, 2013)
Despite achievements in dolphin conservation for the tuna purse‐seine fishery of the eastern Pacific Ocean, debate continues about the magnitude and importance of dolphin mortality caused by small (unobserved) vessels. In‐port sampling of tuna catch size composition is a potentially cost‐effective means of identifying unobserved vessels that may be catching tunas associated with dolphins because yellowfin tuna caught in association with dolphins are larger, on average, than those caught in other types of purse‐seine sets. A classification algorithm to predict purse‐seine set type (“dolphin” vs . “nondolphin”) was built from port‐sampling data on yellowfin tuna length‐frequencies and the date and location of fishing of large (observed) vessels. This classification algorithm was used to screen the port‐sampling data of small vessels collected during 2006‐2009, assuming the fishing practices of the two groups resulted in similar catch characteristics. From these results, hypothetical time series of dolphin mortality for small vessels were constructed and incorporated into a population dynamics model, along with mortalities of large vessels. Results suggest that any dolphin mortality of small vessels is unlikely to be substantially affecting trends in dolphin abundance. These results underscore the importance of in‐port sampling, in combination with at‐sea observation and fishery‐independent surveys, to effective management.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

The Effects of Estrogen in Ischemic Stroke - Edward C. Koellhoffer; Louise D. McCullough (Translational Stroke Research, 2013)

Demographic patterns in the peacock grouper (Cephalopholis argus), an introduced Hawaiian reef fish - Mary K. Donovan; Alan M. Friedlander; Edward E. DeMartini; Megan J. Donahue; Ivor D. Williams (Environmental Biology of Fishes, 2013)

Risk of dietary magnesium deficiency is low in most African countries based on food supply data - Edward J. M. Joy; Scott D. Young; Colin R. Black; E. Louise Ander; Michael J. Watts; Martin R. Broadley (Plant and Soil, 2013)

Estimation of impulse response between electromyogram signals for use in conduction delay distribution estimation - Tahsin Hassan; Kyle C. D. McIntosh; David A. Gabriel; Edward A. Clancy (Medical & Biological Engineering & Computing, 2013)

Initial epidemic area is strongly associated with the yearly extent of soybean rust spread in North America - Christopher C. Mundt; LaRae D. Wallace; Tom W. Allen; Clayton A. Hollier; Robert C. Kemerait; Edward J. Sikora (Biological Invasions, 2013)

Relationships between testate amoeba communities and water quality in Lake Donghu, a large alkaline lake in Wuhan, China - Yangmin Qin; Bertrand Fournier; Enrique Lara; Yansheng Gu; Hongmei Wang; Yongde Cui; Xiaoke Zhang; Edward A. D. Mitchell (Frontiers of Earth Science, 2013)

An fMRI Compatible Wrist Robotic Interface to Study Brain Development in Neonates - A. G. Allievi; A. Melendez-Calderon; T. Arichi; A. D. Edwards; E. Burdet (Annals of Biomedical Engineering, 2013)

Microevolution in time and space: SNP analysis of historical DNA reveals dynamic signatures of selection in A tlantic cod - Nina O. Therkildsen; Jakob Hemmer‐Hansen; Thomas D. Als; Douglas P. Swain; M. Joanne Morgan; Edward A. Trippel; Stephen R. Palumbi; Dorte Meldrup; Einar E. Nielsen (Molecular Ecology, 2013)
Little is known about how quickly natural populations adapt to changes in their environment and how temporal and spatial variation in selection pressures interact to shape patterns of genetic diversity. We here address these issues with a series of genome scans in four overfished populations of Atlantic cod ( G adus morhua ) studied over an 80‐year period. Screening of >1000 gene‐associated single‐nucleotide polymorphisms ( SNP s) identified 77 loci that showed highly elevated levels of differentiation, likely as an effect of directional selection, in either time, space or both. Exploratory analysis suggested that temporal allele frequency shifts at certain loci may correlate with local temperature variation and with life history changes suggested to be fisheries induced. Interestingly, however, largely nonoverlapping sets of loci were temporal outliers in the different populations and outliers from the 1928 to 1960 period showed almost complete stability during later decades. The contrasting microevolutionary trajectories among populations resulted in sequential shifts in spatial outliers, with no locus maintaining elevated spatial differentiation throughout the study period. Simulations of migration coupled with observations of temporally stable spatial structure at neutral loci suggest that population replacement or gene flow alone could not explain all the observed allele frequency variation. Thus, the genetic changes are likely to at least partly be driven by highly dynamic temporally and spatially varying selection. These findings have important implications for our understanding of local adaptation and evolutionary potential in high gene flow organisms and underscore the need to carefully consider all dimensions of biocomplexity for evolutionarily sustainable management.

Additive effects of three auxins and copper on sorghum in vitro root induction - Guoquan Liu; Edward K. Gilding; Ian D. Godwin (In Vitro Cellular & Developmental Biology - Plant, 2013)

The biogeography of marine plankton traits - Andrew D. Barton; Andrew J. Pershing; Elena Litchman; Nicholas R. Record; Kyle F. Edwards; Zoe V. Finkel; Thomas Kiørboe; Ben A. Ward (Ecology Letters, 2013)
Changes in marine plankton communities driven by environmental variability impact the marine food web and global biogeochemical cycles of carbon and other elements. To predict and assess these community shifts and their consequences, ecologists are increasingly investigating how the functional traits of plankton determine their relative fitness along environmental and biological gradients. Laboratory, field and modelling studies are adopting this trait‐based approach to map the biogeography of plankton traits that underlies variations in plankton communities. Here, we review progress towards understanding the regulatory roles of several key plankton functional traits, including cell size, N 2 ‐fixation and mixotrophy among phytoplankton, and body size, ontogeny and feeding behaviour for zooplankton. The trait biogeographical approach sheds light on what structures plankton communities in the current ocean, as well as under climate change scenarios, and also allows for finer resolution of community function because community trait composition determines the rates of significant processes, including carbon export. Although understanding of trait biogeography is growing, uncertainties remain that stem, in part, from the paucity of observations describing plankton functional traits. Thus, in addition to recommending widespread adoption of the trait‐based approach, we advocate for enhanced collection, standardisation and dissemination of plankton functional trait data.

Effects of chronic sazetidine-A, a selective α4β2 neuronal nicotinic acetylcholine receptors desensitizing agent on pharmacologically-induced impaired attention in rats - Amir H. Rezvani; Marty Cauley; Yingxian Xiao; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2013)

Links between Indo-Pacific climate variability and drought in the Monsoon Asia Drought Atlas - Caroline C. Ummenhofer; Rosanne D. D’Arrigo; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climate Dynamics, 2013)

Serum 25-hydroxyvitamin D and breast cancer in the military: a case–control study utilizing pre-diagnostic serum - Sharif B. Mohr; Edward D. Gorham; John E. Alcaraz; Christopher I. Kane; Caroline A. Macera; J. Kellogg Parsons; Deborah L. Wingard; Ronald Horst; Cedric F. Garland (Cancer Causes & Control, 2013)

Clinal variation in colony breeding structure and level of inbreeding in the subterranean termites R eticulitermes flavipes and R . grassei - Edward L. Vargo; Laurianne Leniaud; Lois E. Swoboda; Sarah E. Diamond; Michael D. Weiser; Dini M. Miller; Anne‐Geneviève Bagnères (Molecular Ecology, 2013)
Social insects exhibit remarkable variation in their colony breeding structures, both within and among species. Ecological factors are believed to be important in shaping reproductive traits of social insect colonies, yet there is little information linking specific environmental variables with differences in breeding structure. Subterranean termites (Rhinotermitidae) show exceptional variation in colony breeding structure, differing in the number of reproductives and degree of inbreeding; colonies can be simple families headed by a single pair of monogamous reproductives (king and queen) or they can be extended families headed by multiple inbreeding neotenic reproductives (wingless individuals). Using microsatellite markers, we characterized colony breeding structure and levels of inbreeding in populations over large parts of the range of the subterranean termites Reticulitermes flavipes in the USA and R. grassei in Europe. Combining these new data with previous results on populations of both species, we found that latitude had a strong effect on the proportion of extended‐family colonies in R. flavipes and on levels of inbreeding in both species. We examined the effect of several environmental variables that vary latitudinally; while the degree of inbreeding was greatest in cool, moist habitats in both species, seasonality affected the species differently. Inbreeding in R. flavipes was most strongly associated with climatic variables (mean annual temperature and seasonality), whereas nonclimatic variables, including the availability of wood substrate and soil composition, were important predictors of inbreeding in R. grassei . These results are the first showing that termite breeding structure is shaped by local environmental factors and that species can vary in their responses to these factors.

Niche differentiation and spatial partitioning in the evolution of two Australian monsoon tropical tree species - Robert D. Edwards; Michael D. Crisp; Lyn G. Cook (Journal of Biogeography, 2013)
Aim Geographical and climatic barriers to organismal dispersal and distribution play a major role in speciation. We use a sister‐pair of widespread savanna trees ( M elaleuca argentea and M . fluviatilis ) to test the influence of putative barriers on divergence within and between species across an otherwise continuous landscape. Location The A ustralian monsoon tropics ( AMT ). Methods Chloroplast and nuclear DNA sequences were used to estimate variation between and within species. Hypotheses invoking vicariance and ecological speciation as the mechanisms of divergence between species were explicitly tested using ecological niche modelling. Results We found little evidence for divergence across the C arpentaria B asin, although some chloroplast DNA haplotypes were restricted to regions to the east or west. Pilbara populations were distinct from those to the east across the Great Sandy Desert, including those from the Kimberley. There was a complex pattern of genetic divergence and niche differentiation among M . argentea and M . fluviatilis within a region of secondary range overlap coincident with currently recognized species boundaries across the Great Dividing Range. Main conclusions The two morphospecies are ecologically and genetically distinct, and maintain those differences in sympatry. Speciation might have occurred in allopatry in separate drainage basins that later came into contact. The P ilbara population appears to be distinct but requires further investigation.

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

Factors modulating cottongrass seedling growth stimulation to enhanced nitrogen and carbon dioxide: compensatory tradeoffs in leaf dynamics and allocation to meet potassium-limited growth - Andy Siegenthaler; Alexandre Buttler; Philippe Grosvernier; Jean-Michel Gobat; Mats B. Nilsson; Edward A. D. Mitchell (Oecologia, 2013)

Trophic analysis of two subtropical South American freshwater crabs using stable isotope ratios - Edward D. Burress; Michael M. Gangloff; Lynn Siefferman (Hydrobiologia, 2013)

Life cycle comparison of hydrothermal liquefaction and lipid extraction pathways to renewable diesel from algae - Edward D. Frank; Amgad Elgowainy; Jeongwoo Han; Zhichao Wang (Mitigation and Adaptation Strategies for Global Change, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Testosterone induces off-line perceptual learning - Nicholas D. Wright; Thomas Edwards; Stephen M. Fleming; Raymond J. Dolan (Psychopharmacology, 2012)

Temperature-Dependent Clustering Behavior of Aethina Tumida Murray in Apis Mellifera L. Colonies - Edward B. Atkinson; James D. Ellis (Journal of Insect Behavior, 2012)

Regular dental visits are associated with earlier stage at diagnosis for oral and pharyngeal cancer - Scott M. Langevin; Dominique S. Michaud; Melissa Eliot; Edward S. Peters; Michael D. McClean; Karl T. Kelsey (Cancer Causes & Control, 2012)

Microbial cell budgets of an A rctic glacier surface quantified using flow cytometry - T. D. L. Irvine‐Fynn; A. Edwards; S. Newton; H. Langford; S. M. Rassner; J. Telling; A. M. Anesio; A. J. Hodson (Environmental Microbiology, 2012)
Summary Uncertainty surrounds estimates of microbial cell and organic detritus fluxes from glacier surfaces. Here, we present the first enumeration of biological particles draining from a supraglacial catchment, on M idtre L ovénbreen ( S valbard) over 36 days. A stream cell flux of 1.08 × 10 7 cells m −2 h −1 was found, with strong inverse, non‐linear associations between water discharge and biological particle concentrations. Over the study period, a significant decrease in cell‐like particles exhibiting 530 nm autofluorescence was noted. The observed total fluvial export of ∼ 7.5 × 10 14 cells equates to 15.1–72.7 g C , and a large proportion of these cells were small ( 7 cells m −2 h −1 . Analysis of surface ice cores revealed cell concentrations comparable to previous studies (6 × 10 4 cells ml −1 ) but, critically, showed no variation with depth in the uppermost 1 m. The physical retention and growth of particulates at glacier surfaces has two implications: to contribute to ice mass thinning through feedbacks altering surface albedo, and to potentially seed recently deglaciated terrain with cells, genes and labile organic matter. This highlights the merit of further study into glacier surface hydraulics and biological processes.

Effects of AZD3480, a neuronal nicotinic acetylcholine receptor agonist, and donepezil on dizocilpine-induced attentional impairment in rats - Amir H. Rezvani; Marty C. Cauley; Edwin C. Johnson; Gregory J. Gatto; Edward D. Levin (Psychopharmacology, 2012)

Gene expression changes of interconnected spared cortical neurons 7 days after ischemic infarct of the primary motor cortex in the rat - Edward T. R. Urban; Scott D. Bury; H. Scott Barbay; David J. Guggenmos; Yafeng Dong; Randolph J. Nudo (Molecular and Cellular Biochemistry, 2012)

Carbon outcomes of major land‐cover transitions in SE Asia: great uncertainties and REDD + policy implications - Alan D. Ziegler; Jacob Phelps; Jia QI Yuen; Edward L. Webb; Deborah Lawrence; Jeff M. Fox; Thilde B. Bruun; Stephen J. Leisz; Casey M. Ryan; Wolfram Dressler; Ole Mertz; Unai Pascual; et al. (Global Change Biology, 2012)
Policy makers across the tropics propose that carbon finance could provide incentives for forest frontier communities to transition away from swidden agriculture (slash‐and‐burn or shifting cultivation) to other systems that potentially reduce emissions and/or increase carbon sequestration. However, there is little certainty regarding the carbon outcomes of many key land‐use transitions at the center of current policy debates. Our meta‐analysis of over 250 studies reporting above‐ and below‐ground carbon estimates for different land‐use types indicates great uncertainty in the net total ecosystem carbon changes that can be expected from many transitions, including the replacement of various types of swidden agriculture with oil palm, rubber, or some other types of agroforestry systems. These transitions are underway throughout Southeast Asia, and are at the heart of REDD + debates. Exceptions of unambiguous carbon outcomes are the abandonment of any type of agriculture to allow forest regeneration (a certain positive carbon outcome) and expansion of agriculture into mature forest (a certain negative carbon outcome). With respect to swiddening, our meta‐analysis supports a reassessment of policies that encourage land‐cover conversion away from these [especially long‐fallow] systems to other more cash‐crop‐oriented systems producing ambiguous carbon stock changes – including oil palm and rubber. In some instances, lengthening fallow periods of an existing swidden system may produce substantial carbon benefits, as would conversion from intensely cultivated lands to high‐biomass plantations and some other types of agroforestry. More field studies are needed to provide better data of above‐ and below‐ground carbon stocks before informed recommendations or policy decisions can be made regarding which land‐use regimes optimize or increase carbon sequestration. As some transitions may negatively impact other ecosystem services, food security, and local livelihoods, the entire carbon and noncarbon benefit stream should also be taken into account before prescribing transitions with ambiguous carbon benefits.

Assimilating GlobColour ocean colour data into a pre-operational physical-biogeochemical model - D. A. Ford; K. P. Edwards; D. Lea; R. M. Barciela; M. J. Martin; J. Demaria (Ocean Science, 2012)
As part of the GlobColour project, daily chlorophyll a observations, derived using remotely sensed ocean colour data from the MERIS, MODIS and SeaWiFS sensors, are produced. The ability of these products to be assimilated into a pre-operational global coupled physical-biogeochemical model has been tested, on both a hindcast and near-real-time basis, and the impact on the system assessed. The assimilation was found to immediately and considerably improve the bias, root mean square error and correlation of modelled surface chlorophyll concentration compared to the GlobColour observations, an improvement which was sustained throughout the year and in every ocean basin. Errors against independent in situ chlorophyll observations were also reduced, both at and beneath the ocean surface. However, the model fit to in situ observations was not consistently better than that of climatology, due to errors in the underlying model. The assimilation scheme used is multivariate, updating all biogeochemical model state variables at all depths. The other variables were not degraded by the assimilation, with annual mean surface fields of nutrients, alkalinity and carbon variables remaining of similar quality compared to climatology. There was evidence of improved representation of zooplankton concentration, and reduced errors were seen against in situ observations of nitrate and pCO2, but too few observations were available to conclude about global model skill. The near-real-time GlobColour products were found to be sufficiently reliable for operational purposes, and of benefit to both operational-style systems and reanalyses.

Egg Placement by Anopheles gambiae (Diptera:Culicidae) as Influenced by Resting Surface Slope and Enclosure - Megan L. Fritz; Edward D. Walker; James R. Miller (Journal of Insect Behavior, 2012)

Extensive gaps and biases in our knowledge of a well‐known fauna: implications for integrating biological traits into macroecology - Elizabeth H. M. Tyler; Paul J. Somerfield; Edward Vanden Berghe; Julie Bremner; Emma Jackson; Olivia Langmead; Maria Lourdes D. Palomares; Thomas J. Webb (Global Ecology and Biogeography, 2012)
Aim Ecologists seeking to describe patterns at ever larger scales require compilations of data on the global abundance and distribution of species. Comparable compilations of biological data are needed to elucidate the mechanisms behind these patterns, but have received far less attention. We assess the availability of biological data across an entire assemblage: the well‐documented demersal marine fauna of the United Kingdom. We also test whether data availability for a species depends on its taxonomic group, maximum body size, the number of times it has been recorded in a global biogeographic database, or its commercial and conservation importance. Location Seas of the United Kingdom. Methods We defined a demersal marine fauna of 973 species from 15 phyla and 40 classes using five extensive surveys around the British Isles. We then quantified the availability of data on eight key biological traits (termed biological knowledge) for each species from online databases. Relationships between biological knowledge and our predictors were tested with generalized linear models. Results Full data on eight fundamental biological traits exist for only 9% ( n = 88) of the UK demersal marine fauna, and 20% of species completely lack data. Clear trends in our knowledge exist: fish (median biological knowledge score = six traits) are much better known than invertebrates (one trait). Biological knowledge increases with biogeographic knowledge and (to a lesser extent) with body size, and is greater in species that are commercially exploited or of conservation concern. Main conclusions Our analysis reveals deep ignorance of the basic biology of a well‐studied fauna, highlighting the need for far greater efforts to compile biological trait data. Clear biases in our knowledge, relating to how well sampled or ‘important’ species are suggests that caution is required in extrapolating small subsets of biologically well‐known species to ecosystem‐level studies.

Effects of vicariant barriers, habitat stability, population isolation and environmental features on species divergence in the south‐western Australian coastal reptile community - D. L. EDWARDS; J. S. KEOGH; L. L. KNOWLES (Molecular Ecology, 2012)
Identifying explicit hypotheses regarding the factors determining genetic structuring within species can be difficult, especially in species distributed in historically dynamic regions. To contend with these challenges, we use a framework that combines species distribution models, environmental data and multi‐locus genetic data to generate and explore phylogeographic hypotheses for reptile species occupying the coastal sand‐dune and sand‐plain habitats of the south‐western Australian biodiversity hotspot, a community which has both a high diversity of endemics and has varied dramatically in spatial extent over time. We use hierarchical amova , summary statistic and distance‐based analyses to explicitly test specific phylogeographic hypotheses. Namely, we test if biogeographic vicariance across barriers, habitat stability, population isolation along a linear habitat or fragmentation across different environments can explain genetic divergence within five co‐distributed squamate reptile species. Our results show that patterns of genetic variation reflect complex and species‐specific interactions related to the spatial distribution of habitats present currently and during repeated glacial minima, as opposed to being associated with historical factors such as habitat stability between glacial and inter‐glacial periods or vicariant barriers. We suggest that the large impact of habitat characteristics over time (i.e. relative levels of habitat connectivity, climatic gradients and spatial heterogeneity of soil types) reflects the ecological restrictions of the sand‐dune and sand‐plain reptile communities and may explain the lack of concordance across taxa. The study demonstrates the general utility of the approach for assemblage‐level, as well as single species, phylogeographic study, including its usefulness for exploring biologically informed hypotheses about what factors have influenced patterns of genetic variation.

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Assessing the effects of chronic sazetidine-A delivery on nicotine self-administration in both male and female rats - Joshua E. Johnson; Susan Slade; Corinne Wells; Ann Petro; Hannah Sexton; Amir H. Rezvani; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Yingxian Xiao; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2012)

Incorporating invasive weeds into a plant indicator method (LakeSPI) to assess lake ecological condition - M. D. de Winton; J. S. Clayton; T. Edwards (Hydrobiologia, 2012)

Nasopharyngeal Necrosis After Chronic Opioid (Oxycodone/Acetaminophen) Insufflation - Christopher D. Rosenbaum; Katherine L. Boyle; Edward W. Boyer (Journal of Medical Toxicology, 2012)

Algal eating habits of phycologists attending the ISAP Halifax Conference and members of the general public - Maeve D. Edwards; Susan Løvstad Holdt; Stephen Hynes (Journal of Applied Phycology, 2012)

Examining the effects of former cannabis use on cerebellum-dependent eyeblink conditioning in humans - Adam B. Steinmetz; Chad R. Edwards; Jennifer M. Vollmer; Molly A. Erickson; Brian F. O’Donnell; William P. Hetrick; Patrick D. Skosnik (Psychopharmacology, 2012)

Plant growth and physiology under heterogeneous salinity - Nadia Bazihizina; Edward G. Barrett-Lennard; Timothy D. Colmer (Plant and Soil, 2012)

Linear and angular control of circular walking in healthy older adults and subjects with cerebellar ataxia - Adam D. Goodworth; Caroline Paquette; Geoffrey Melvill Jones; Edward W. Block; William A. Fletcher; Bin Hu; Fay B. Horak (Experimental Brain Research, 2012)

Monitoring the effects of Rodolia cardinalis on Icerya purchasi populations on the Galapagos Islands - Carolina Calderón Alvarez; Charlotte E. Causton; Mark S. Hoddle; Christina D. Hoddle; Roy van Driesche; Edward J. Stanek (BioControl, 2012)

Synthetic scaffold coating with adeno-associated virus encoding BMP2 to promote endogenous bone repair - Kenneth M. Dupont; Joel D. Boerckel; Hazel Y. Stevens; Tamim Diab; Yash M. Kolambkar; Masahiko Takahata; Edward M. Schwarz; Robert E. Guldberg (Cell and Tissue Research, 2012)

Rights‐based fisheries governance: from fishing rights to human rights - Edward H Allison; Blake D Ratner; Björn Åsgård; Rolf Willmann; Robert Pomeroy; John Kurien (Fish and Fisheries, 2012)
In the last twenty years, policy prescriptions for addressing the global crisis in fisheries have centred on strengthening fisheries governance through clarifying exclusive individual or community rights of access to fishery resources. With a focus on small‐scale developing‐country fisheries in particular, we argue that basing the case for fishery governance reform on assumed economic incentives for resource stewardship is insufficient when there are other sources of insecurity in people’s lives that are unrelated to the state of fishery resources. We argue that more secure, less vulnerable fishers make more effective and motivated fishery managers in the context of participatory or rights‐based fisheries governance, and we further suggest that insecurity among fishers living in poverty can be most effectively addressed by social and political development that invokes the existing legal framework supporting the Universal Declaration of Human Rights. This perspective goes well beyond the widely advocated notion of ‘rights‐based fishing’ and aligns what fishery sector analysts call the ‘rights‐based approach’ with the same terminology used in the context of international development. Embedding the fisheries governance challenge within a broader perspective of human rights enhances the chances of achieving both human development and resource sustainability outcomes in small‐scale fisheries of developing countries.

The safety of studies with intravenous Δ9-tetrahydrocannabinol in humans, with case histories - Michelle Carbuto; R. Andrew Sewell; Ashley Williams; Kim Forselius-Bielen; Gabriel Braley; Jacqueline Elander; Brian Pittman; Ashley Schnakenberg; Savita Bhakta; Edward Perry; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Effect of cold acclimatization on exercise economy in the cold - Matthew D. Muller; Chul-Ho Kim; David M. Bellar; Edward J. Ryan; Yongsuk Seo; Sarah M. Muller; Ellen L. Glickman (European Journal of Applied Physiology, 2012)

The α2-adrenergic antagonist idazoxan counteracts prepulse inhibition deficits caused by amphetamine or dizocilpine in rats - José A. Larrauri; Edward D. Levin (Psychopharmacology, 2012)

Machine vision-based localization of nucleic and cytoplasmic injection sites on low-contrast adherent cells - Hadi Esmaeilsabzali; Kelly Sakaki; Nikolai Dechev; Robert D. Burke; Edward J. Park (Medical & Biological Engineering & Computing, 2012)

Evaluation of Fluorescent Phosphatidylserine Substrates for the Aminophospholipid Flippase in Mammalian Cells - Bryan A. Smith; Edward J. O’Neil; Andrew J. Lampkins; James R. Johnson; Jung-Jae Lee; Erin L. Cole; Bradley D. Smith (Journal of Fluorescence, 2012)

Modelling the effect of size on the aerial dispersal of microorganisms - David M. Wilkinson; Symeon Koumoutsaris; Edward A. D. Mitchell; Isabelle Bey (Journal of Biogeography, 2012)
Aim We investigate the long‐standing question of whether the small size of microbes allows most microbial species to colonize all suitable sites around the globe or whether their ranges are limited by opportunities for dispersal. In this study we use a modelling approach to investigate the effect of size on the probability of between‐continent dispersal using virtual microorganisms in a global model of the Earth’s atmosphere. Location Global. Methods We use a computer model of global atmospheric circulation to investigate the effect of microbe size (effective diameters of 9, 20, 40 and 60 μm) on the probability of aerial dispersal. Results We found that for smaller microbes, once airborne, dispersal is remarkably successful over a 1‐year period. The most striking results are the extensive within‐hemisphere distribution of virtual microbes of 9 and 20 μm diameter and the lack of dispersal between the Northern and Southern Hemispheres during the year‐long time‐scale of our simulations. Main conclusions Above a diameter of 20 μm wind dispersal of virtual microbes between continents becomes increasingly unlikely, and it does not occur at all (within our simulated 1‐year period) for those of 60 μm diameter. Within our simulation, the success of small microbes in long‐distance dispersal is due both to their greater abundance and to their longer time in the atmosphere – once airborne – compared with larger microbes.

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Migratory flyway and geographical distance are barriers to the gene flow of influenza virus among North American birds - Tommy Tsan‐Yuk Lam; Hon S. Ip; Elodie Ghedin; David E. Wentworth; Rebecca A. Halpin; Timothy B. Stockwell; David J. Spiro; Robert J. Dusek; James B. Bortner; Jenny Hoskins; Bradley D. Bales; Dan R. Yparraguirre; et al. (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 24–33 Abstract Despite the importance of migratory birds in the ecology and evolution of avian influenza virus (AIV), there is a lack of information on the patterns of AIV spread at the intra‐continental scale. We applied a variety of statistical phylogeographic techniques to a plethora of viral genome sequence data to determine the strength, pattern and determinants of gene flow in AIV sampled from wild birds in North America. These analyses revealed a clear isolation‐by‐distance of AIV among sampling localities. In addition, we show that phylogeographic models incorporating information on the avian flyway of sampling proved a better fit to the observed sequence data than those specifying homogeneous or random rates of gene flow among localities. In sum, these data strongly suggest that the intra‐continental spread of AIV by migratory birds is subject to major ecological barriers, including spatial distance and avian flyway.

Dabigatran: Review of Pharmacology and Management of Bleeding Complications of This Novel Oral Anticoagulant - Michael Ganetsky; Kavita M. Babu; Steven D. Salhanick; Robert S. Brown; Edward W. Boyer (Journal of Medical Toxicology, 2011)

MHC region and risk of systemic lupus erythematosus in African American women - Edward A. Ruiz-Narvaez; Patricia A. Fraser; Julie R. Palmer; L. Adrienne Cupples; David Reich; Ying A. Wang; John D. Rioux; Lynn Rosenberg (Human Genetics, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

The effect of landscape heterogeneity and host movement on a tick-borne pathogen - Edward O. Jones; Steven D. Webb; Francisco J. Ruiz-Fons; Steven Albon; Lucy Gilbert (Theoretical Ecology, 2011)

Alcohol impairs brain reactivity to explicit loss feedback - Lindsay D. Nelson; Christopher J. Patrick; Paul Collins; Alan R. Lang; Edward M. Bernat (Psychopharmacology, 2011)

Patterns of Root Dynamics in Mangrove Forests Along Environmental Gradients in the Florida Coastal Everglades, USA - Edward Castañeda-Moya; Robert R. Twilley; Victor H. Rivera-Monroy; Brian D. Marx; Carlos Coronado-Molina; Sharon M. L. Ewe (Ecosystems, 2011)

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

Altered pain responses in abstinent (±)3,4-methylenedioxymethamphetamine (MDMA, “ecstasy”) users - Una D. McCann; Robert R. Edwards; Michael T. Smith; Kristen Kelley; Michael Wilson; Francis Sgambati; George Ricaurte (Psychopharmacology, 2011)

Assessment of coastal storm impacts on contaminant body burdens of oysters collected from the gulf of Mexico - Dennis A. Apeti; Gunnar G. Lauenstein; John D. Christensen; Edward W. Johnson; Andrew Mason (Environmental Monitoring and Assessment, 2011)

Searching for a Sustainable Environmental Ethic - Edward L. Barnard; Justin D. Barnard (Journal of Forestry, 2011)

RETRACTED ARTICLE: Neurotoxic effects of the HCV core protein are mediated by sustained activation of ERK via TLR2 signaling - Amy D. Paulino; Kiren Ubhi; Edward Rockenstein; Anthony Adame; Leslie Crews; Scott Letendre; Ronald Ellis; Ian P. Everall; Igor Grant; Eliezer Masliah (Journal of NeuroVirology, 2011)

Recognizing Contemporary Roles of Swidden Agriculture in Transforming Landscapes of Southeast Asia - ALAN D. ZIEGLER; JEFF M. FOX; EDWARD L. WEBB; CHRISTINE PADOCH; STEVE J. LEISZ; ROB A. CRAMB; OLE MERTZ; THILDE B. BRUUN; TRAN DUC VIEN (Conservation Biology, 2011)

Distribution of Fusarium mycotoxins in UK wheat mill fractions - S.G. Edwards; E.T. Dickin; S. MacDonald; D. Buttler; C.M. Hazel; S. Patel; K.A. Scudamore (Food Additives & Contaminants: Part A, 2011)

High frequency variability of the Atlantic meridional overturning circulation - B. Balan Sarojini; J. M. Gregory; R. Tailleux; G. R. Bigg; A. T. Blaker; D. R. Cameron; N. R. Edwards; A. P. Megann; L. C. Shaffrey; B. Sinha (Ocean Science, 2011)
We compare the variability of the Atlantic meridional overturning circulation (AMOC) as simulated by the coupled climate models of the RAPID project, which cover a wide range of resolution and complexity, and observed by the RAPID/MOCHA array at about 26° N. We analyse variability on a range of timescales, from five-daily to interannual. In models of all resolutions there is substantial variability on timescales of a few days; in most AOGCMs the amplitude of the variability is of somewhat larger magnitude than that observed by the RAPID array, while the time-mean is within about 10 % of the observational estimate. The amplitude of the simulated annual cycle is similar to observations, but the shape of the annual cycle shows a spread among the models. A dynamical decomposition shows that in the models, as in observations, the AMOC is predominantly geostrophic (driven by pressure and sea-level gradients), with both geostrophic and Ekman contributions to variability, the latter being exaggerated and the former underrepresented in models. Other ageostrophic terms, neglected in the observational estimate, are small but not negligible. The time-mean of the western boundary current near the latitude of the RAPID/MOCHA array has a much wider model spread than the AMOC does, indicating large differences among models in the simulation of the wind-driven gyre circulation, and its variability is unrealistically small in the models. In many RAPID models and in models of the Coupled Model Intercomparison Project Phase 3 (CMIP3), interannual variability of the maximum of the AMOC wherever it lies, which is a commonly used model index, is similar to interannual variability in the AMOC at 26° N. Annual volume and heat transport timeseries at the same latitude are well-correlated within 15–45° N, indicating the climatic importance of the AMOC. In the RAPID and CMIP3 models, we show that the AMOC is correlated over considerable distances in latitude, but not the whole extent of the North Atlantic; consequently interannual variability of the AMOC at 50° N, where it is particularly relevant to European climate, is not well-correlated with that of the AMOC at 26° N, where it is monitored by the RAPID/MOCHA array.

Validity of the Actical for estimating free-living physical activity - Scott E. Crouter; Diane M. DellaValle; Magdalene Horton; Jere D. Haas; Edward A. Frongillo; David R. Bassett (European Journal of Applied Physiology, 2011)

Mood and selective attention in the cold: the effect of interval versus continuous exercise - Matthew D. Muller; Sarah M. Muller; Chul-Ho Kim; Edward J. Ryan; John Gunstad; Ellen L. Glickman (European Journal of Applied Physiology, 2011)

Fluorine-free mixed amphiphilic polymers based on PDMS and PEG side chains for fouling release applications - Harihara S. Sundaram; Youngjin Cho; Michael D. Dimitriou; Craig J. Weinman; John A. Finlay; Gemma Cone; Maureen E. Callow; James A. Callow; Edward J. Kramer; Christopher K. Ober (Biofouling, 2011)

Role of individual and developmental differences in voluntary cocaine intake in rats - Nicole L. Schramm-Sapyta; Marty C. Cauley; Dalene K. Stangl; Susan Glowacz; K. Amy Stepp; Edward D. Levin; Cynthia M. Kuhn (Psychopharmacology, 2011)

Sazetidine-A, a selective α4β2 nicotinic acetylcholine receptor ligand: effects on dizocilpine and scopolamine-induced attentional impairments in female Sprague–Dawley rats - Amir H. Rezvani; Marty Cauley; Hannah Sexton; Yingxian Xiao; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2011)

Designing Interventions to Overcome Poor Numeracy and Improve Medication Adherence in Chronic Illness, Including HIV/Aids - John O. Moore; Edward W. Boyer; Steven Safren; Gregory K. Robbins; Edwin D. Boudreaux; Rochelle Rosen; Bruce Barton; Frank Moss (Journal of Medical Toxicology, 2011)

Mitochondrial genome sequence of Unionicola parkeri (Acari: Trombidiformes: Unionicolidae): molecular synapomorphies between closely-related Unionicola gill mites - Dale D. Edwards; Lesley E. Jackson; Amy J. Johnson; Brian R. Ernsting (Experimental and Applied Acarology, 2011)

Pain and thermal sensation in the cold: the effect of interval versus continuous exercise - Matthew D. Muller; Sarah M. Muller; Edward J. Ryan; David M. Bellar; Chul-Ho Kim; Ellen L. Glickman (European Journal of Applied Physiology, 2011)

T cell recognition of weak ligands: roles of signaling, receptor number, and affinity - Lindsay J. Edwards; Brian D. Evavold (Immunologic Research, 2011)

“Dead Zone” dynamics in Lake Erie: the importance of weather and sampling intensity for calculated hypolimnetic oxygen depletion rates - Joseph D. Conroy; Leon Boegman; Hongyan Zhang; William J. Edwards; David A. Culver (Aquatic Sciences, 2011)

Peripheral biomarkers of cognitive response to dopamine receptor agonist treatment - Karen D. Ersche; Jonathan P. Roiser; Mark Lucas; Enrico Domenici; Trevor W. Robbins; Edward T. Bullmore (Psychopharmacology, 2011)

JNJ-39220675, a novel selective histamine H3 receptor antagonist, reduces the abuse-related effects of alcohol in rats - Ruggero Galici; Amir H. Rezvani; Leah Aluisio; Brian Lord; Edward D. Levin; Ian Fraser; Jamin Boggs; Natalie Welty; James R. Shoblock; S. Timothy Motley; Michael A. Letavic; Nicholas I. Carruthers; et al. (Psychopharmacology, 2011)

Macroscale factors affecting diatom abundance: a synergistic use of Continuous Plankton Recorder and satellite remote sensing data - Dionysios E. Raitsos; Samantha J. Lavender; Christos D. Maravelias; John Haralabous; Abigail McQuatters-Gollop; Martin Edwards; Philip C. Reid (International Journal of Remote Sensing, 2011)

Village environs as source of nitrate contamination in groundwater: a case study in basaltic geo-environment in central India - D. V. Reddy; P. Nagabhushanam; Edward Peters (Environmental Monitoring and Assessment, 2011)

Neuronavigation Increases the Physiologic and Behavioral Effects of Low-Frequency rTMS of Primary Motor Cortex in Healthy Subjects - S. Bashir; D. Edwards; A. Pascual-Leone (Brain Topography, 2011)

Nanomaterial interactions with and trafficking across the lung alveolar epithelial barrier: implications for health effects of air-pollution particles - Nazanin R. Yacobi; Farnoosh Fazllolahi; Yong Ho Kim; Arnold Sipos; Zea Borok; Kwang-Jin Kim; Edward D. Crandall (Air Quality, Atmosphere & Health, 2011)

Interdecadal declines in flood frequency increase primary production in lakes of a northern river delta - SUZANNE McGOWAN; PETER R. LEAVITT; ROLAND I. HALL; BRENT B. WOLFE; THOMAS W. D. EDWARDS; TAMMY KARST‐RIDDOCH; SHEILA R. VARDY (Global Change Biology, 2011)
Human activities and climate change have greatly altered flooding regimes in many of the world's river deltas, but the impact of such changes remains poorly quantified on decadal to multidecadal timescales. This study identified the response of delta lake primary production (measured as the concentration of sedimentary pigments) to variations in flood frequency using spatial surveys and paleolimnological analyses of lakes in the Peace‐Athabasca Delta (PAD), Canada. Surveys of 61 lakes spanning a range of hydrological conditions showed that those lakes that received flood waters less frequently were associated with elevated algal production (surface sedimentary pigments) and, in some lakes, increased growth of emergent macrophytes and epiphytic diatoms. Paleolimnological analyses of five lakes corroborated the contemporary spatial survey results by showing that production of pigments from most algal groups increased during recent periods of lower flood frequency in the 20th century as determined from increases in cellulose‐inferred lake‐water oxygen isotope composition and plant macrofossils, but remained stable in a ‘reference’ basin. In general, past periods of elevated algal production coincided with the increased abundance of submerged macrophytes or emergent vegetation that provide habitat for attached algae. These results suggest that interdecadal declines in river discharge arising from increased aridity, hydrologic regulation or consumptive water use will cause long‐term increases in primary production and alter ecosystem processes (carbon sequestration, biological diversity) in aquatic delta ecosystems similar to the PAD where lakes become nutrient‐rich in the absence of flooding.

Time‐series analyses of Monterey Bay coastal microbial picoplankton using a ‘genome proxy’ microarray - Virginia I. Rich; Vinh D. Pham; John Eppley; Yanmei Shi; Edward F. DeLong (Environmental Microbiology, 2011)
Summary To investigate the temporal, spatial and phylogenetic resolution of marine microbial community structure and variability, we designed and expanded a genome proxy array (an oligonucleotide microarray targeting marine microbial genome fragments and genomes), evaluated it against metagenomic sequencing, and applied it to time‐series samples from the Monterey Bay. The expanded array targeted 268 microbial genotypes across much of the known diversity of cultured and uncultured marine microbes. The target abundances measured by the array were highly correlated to pyrosequence‐based abundances (linear regression R 2 = 0.85–0.91, P

Host migration impacts on the phylogeography of Lyme Borreliosis spirochaete species in Europe - Stephanie A. Vollmer; Antra Bormane; Ruth E. Dinnis; Frederik Seelig; Andrew D. M. Dobson; David M. Aanensen; Marianne C. James; Michael Donaghy; Sarah E. Randolph; Edward J. Feil; Klaus Kurtenbach; Gabriele Margos (Environmental Microbiology, 2011)
Summary The geographic patterns of transmission opportunities of vector‐borne zoonoses are determined by a complex interplay between the migration patterns of the host and the vector. Here we examine the impact of host migration on the spread of a tick‐borne zoonotic disease, using Lyme Borreliosis (LB) spirochaetal species in Europe. We demonstrate that the migration of the LB species is dependent on and limited by the migration of their respective hosts. We note that populations of Borrelia spp. associated with birds ( Borrelia garinii and B. valaisiana ) show limited geographic structuring between countries compared with those associated with small mammals ( Borrelia afzelii ), and we argue that this can be explained by higher rates of migration in avian hosts. We also show the presence of B. afzelii strains in England and, through the use of the multi‐locus sequence analysis scheme, reveal that the strains are highly structured. This pattern in English sites is very different from that observed at the continental sites, and we propose that these may be recent introductions.

The biology and ecology of the ocean sunfish Mola mola: a review of current knowledge and future research perspectives - Edward C. Pope; Graeme C. Hays; Tierney M. Thys; Thomas K. Doyle; David W. Sims; Nuno Queiroz; Victoria J. Hobson; Lukas Kubicek; Jonathan D. R. Houghton (Reviews in Fish Biology and Fisheries, 2010)

PPI deficit induced by amphetamine is attenuated by the histamine H1 antagonist pyrilamine, but is exacerbated by the serotonin 5-HT2 antagonist ketanserin - José A. Larrauri; Edward D. Levin (Psychopharmacology, 2010)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Spatial drought reconstructions for central High Asia based on tree rings - Keyan Fang; Nicole Davi; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Rosanne D’Arrigo (Climate Dynamics, 2010)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Impaired visuospatial associative memory and attention in obsessive compulsive disorder but no evidence for differential dopaminergic modulation - Sharon Morein-Zamir; Kevin J. Craig; Karen D. Ersche; Sanja Abbott; Ulrich Muller; Naomi A. Fineberg; Edward T. Bullmore; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2010)

Late Holocene paleohydrology of Kluane Lake, Yukon Territory, Canada - Janice Brahney; John J. Clague; Thomas W. D. Edwards; Brian Menounos (Journal of Paleolimnology, 2010)

A probabilistic calibration of climate sensitivity and terrestrial carbon change in GENIE-1 - Philip B. Holden; N. R. Edwards; K. I. C. Oliver; T. M. Lenton; R. D. Wilkinson (Climate Dynamics, 2010)

Age independent and position-dependent alterations in motor unit activity of the biceps brachii - B. Harwood; D. L. Edwards; J. M. Jakobi (European Journal of Applied Physiology, 2010)

Reconstructed droughts for the southeastern Tibetan Plateau over the past 568 years and its linkages to the Pacific and Atlantic Ocean climate variability - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Nicole Davi (Climate Dynamics, 2010)

Response of testate amoeba assemblages to environmental and climatic changes during the Lateglacial–Holocene transition at Lake Lautrey (Jura Mountains, eastern France) - Adeline A. J. Wall; Michel Magny; Edward A. D. Mitchell; Boris Vannière; Daniel Gilbert (Journal of Quaternary Science, 2010)
We tested the response of lacustrine testate amoebae (thecamoebians) to climate and environmental changes for the Lateglacial–Holocene transition. The palaeoenvironmental history of the study site (Lake Lautrey, Jura Mountains, eastern France) was previously established based on high‐resolution multi‐proxy studies of the same core. The present study is characterised by a high taxonomic resolution (54 taxa), inclusion of small species (down to 25 µm) and high total counts (>500 individuals per sample on average). Changes in the composition of testate amoeba assemblages (dominant species and assemblage structure), as well as in the accumulation rate (tests cm −2 a −1 ), corresponded to major climatic phases (i.e. Oldest Dryas, Bølling–Allerød Interstadial, Younger Dryas, Preboreal) as well as changes in organic matter inputs. Furthermore, decreases in the accumulation rate characterised minor short‐lived cooling events, such as Older Dryas event or Gerzensee oscillation. However, the Preboreal oscillation, which was well registered by other proxies at Lake Lautrey, could not be recognised in the testate amoeba record. This work demonstrates that lacustrine testate amoebae can be used for palaeoclimatic and palaeoecological reconstructions. Nevertheless, a better understanding of the relation between climate, organic matter and lacustrine testate amoebae requires further high‐resolution studies based on multi‐proxy approaches and the development of appropriate modern analogues. Copyright © 2010 John Wiley & Sons, Ltd.

Specificity between Neotropical tree seedlings and their fungal mutualists leads to plant–soil feedback - Scott A. Mangan; Edward A. Herre; James D. Bever (Ecology, 2010)
A growing body of evidence obtained largely from temperate grassland studies suggests that feedbacks occurring between plants and their associated soil biota are important to plant community assemblage. However, few studies have examined the importance of soil organisms in driving plant–soil feedbacks in forested systems. In a tropical forest in central Panama, we examined whether interactions between tree seedlings and their associated arbuscular mycorrhizal fungi (AMF) lead to plant–soil feedback. Specifically, do tropical seedlings modify their own AMF communities in a manner that either favors or inhibits the next cohort of conspecific seedlings (i.e., positive or negative feedback, respectively)? Seedlings of two shade‐tolerant tree species ( Eugenia nesiotica , Virola surinamensis ) and two pioneer tree species ( Luehea seemannii , Apeiba aspera ) were grown in pots containing identical AMF communities composed of equal amounts of inoculum of six co‐occurring AMF species. The different AMF–host combinations were all exposed to two light levels. Under low light (2% PAR), only two of the six AMF species sporulated, and we found that host identity did not influence composition of AMF spore communities. However, relative abundances of three of the four AMF species that produced spores were influenced by host identity when grown under high light (20% PAR). Furthermore, spores of one of the AMF species, Glomus geosporum , were common in soils of Luehea and Eugenia but absent in soils of Apeiba and Virola . We then conducted a reciprocal experiment to test whether AMF communities previously modified by Luehea and Apeiba differentially affected the growth of conspecific and heterospecific seedlings. Luehea seedling growth did not differ between soils containing AMF communities modified by Luehea and Apeiba . However, Apeiba seedlings were significantly larger when grown with Apeiba ‐modified AMF communities, as compared to Apeiba seedlings grown with Luehea ‐modifed AMF communities. Our experiments suggest that interactions between tropical trees and their associated AMF are species‐specific and that these interactions may shape both tree and AMF communities through plant–soil feedback.

Effects of sazetidine-A, a selective α4β2 nicotinic acetylcholine receptor desensitizing agent on alcohol and nicotine self-administration in selectively bred alcohol-preferring (P) rats - Amir H. Rezvani; Susan Slade; Cori Wells; Ann Petro; Lawrence Lumeng; Ting-Kai Li; Yingxian Xiao; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Jed E. Rose; Kenneth J. Kellar; et al. (Psychopharmacology, 2010)

First Results of the Regional Earthquake Likelihood Models Experiment - Danijel Schorlemmer; J. Douglas Zechar; Maximilian J. Werner; Edward H. Field; David D. Jackson; Thomas H. Jordan (Pure and Applied Geophysics, 2010)

Species-specific effects of polyploidisation and plant traits of Centaurea maculosa and Senecio inaequidens on rhizosphere microorganisms - Aurélie Thébault; Beat Frey; Edward A. D. Mitchell; Alexandre Buttler (Oecologia, 2010)

Separation of grassland litter and ecosite influences on seasonal soil moisture and plant growth dynamics - Eliza S. Deutsch; Edward W. Bork; Walter D. Willms (Plant Ecology, 2010)

The influence of interval versus continuous exercise on thermoregulation, torso hemodynamics, and finger dexterity in the cold - Matthew D. Muller; Edward J. Ryan; David M. Bellar; Chul-Ho Kim; Robert P. Blankfield; Sarah M. Muller; Ellen L. Glickman (European Journal of Applied Physiology, 2010)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Manganese and Sulfate Removal from a Synthetic Mine Drainage Through Pilot Scale Bioreactor Batch Experiments - A. D. Karathanasis; J. D. Edwards; C. D. Barton (Mine Water and the Environment, 2010)

A Simple Method for Enzymatic Synthesis of Unlabeled and Radiolabeled Hydroxycinnamate-CoA - Carsten Rautengarten; Edward Baidoo; Jay D. Keasling; Henrik Vibe Scheller (BioEnergy Research, 2010)

Formulation Development and In Vivo Evaluation of a New Dry Powder Formulation of Albuterol Sulphate in Beagle Dogs - Philip J. Kuehl; Edward G. Barrett; Jacob D. McDonald; Karin Rudolph; David Vodak; Dan Dobry; David Lyon (Pharmaceutical Research, 2010)

Fructose and moderately high dietary salt-induced hypertension: prevention by a combination of N-acetylcysteine and l-arginine - Sudesh Vasdev; Vicki D. Gill; Edward Randell; Yingchun Han; Veeresh Gadag (Molecular and Cellular Biochemistry, 2010)

Historical and paleolimnological evidence for expansion of Lake Athabasca (Canada) during the Little Ice Age - R. Niloshini Sinnatamby; Yi Yi; Michael A. Sokal; Kenneth P. Clogg-Wright; Taro Asada; Sheila R. Vardy; Tammy L. Karst-Riddoch; William M. Last; John W. Johnston; Roland I. Hall; Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 2010)

Oxidation of Free L-histidine by tert-Butylhydroperoxide - Bruce D. Mason; Melissa McCracken; Edward J. Bures; Bruce A. Kerwin (Pharmaceutical Research, 2010)

Conserved synteny at the protein family level reveals genes underlying Shewanella species’ cold tolerance and predicts their novel phenotypes - Tatiana V. Karpinets; Anna Y. Obraztsova; Yanbing Wang; Denise D. Schmoyer; Guruprasad H. Kora; Byung H. Park; Margrethe H. Serres; Margaret F. Romine; Miriam L. Land; Terence B. Kothe; Jim K. Fredrickson; Kenneth H. Nealson; et al. (Functional & Integrative Genomics, 2010)

Estimating Uncertainty in Ecosystem Budget Calculations - Ruth D. Yanai; John J. Battles; Andrew D. Richardson; Corrie A. Blodgett; Dustin M. Wood; Edward B. Rastetter (Ecosystems, 2010)

Butterflyfishes feed on externally brooded larvae of the blue coral, Heliopora coerulea - R. D. Villanueva; A. J. Edwards (Coral Reefs, 2010)

Comparative genomics based on massive parallel transcriptome sequencing reveals patterns of substitution and selection across 10 bird species - AXEL KÜNSTNER; JOCHEN B. W. WOLF; NICLAS BACKSTRÖM; OSCEOLA WHITNEY; CHRISTOPHER N. BALAKRISHNAN; LAINY DAY; SCOTT V. EDWARDS; DANIEL E. JANES; BARNEY A. SCHLINGER; RICHARD K. WILSON; ERICH D. JARVIS; WESLEY C. WARREN; et al. (Molecular Ecology, 2010)
Next‐generation sequencing technology provides an attractive means to obtain large‐scale sequence data necessary for comparative genomic analysis. To analyse the patterns of mutation rate variation and selection intensity across the avian genome, we performed brain transcriptome sequencing using Roche 454 technology of 10 different non‐model avian species. Contigs from de novo assemblies were aligned to the two available avian reference genomes, chicken and zebra finch. In total, we identified 6499 different genes across all 10 species, with ∼1000 genes found in each full run per species. We found evidence for a higher mutation rate of the Z chromosome than of autosomes (male‐biased mutation) and a negative correlation between the neutral substitution rate ( d S ) and chromosome size. Analyses of the mean d N / d S ratio (ω) of genes across chromosomes supported the Hill–Robertson effect (the effect of selection at linked loci) and point at stochastic problems with ω as an independent measure of selection. Overall, this study demonstrates the usefulness of next‐generation sequencing for obtaining genomic resources for comparative genomic analysis of non‐model organisms.

A near‐annual palaeohydrological study based on testate amoebae from a sub‐alpine mire: surface wetness and the role of climate during the instrumental period - Mariusz Lamentowicz; Willem Van Der Knaap; Łukasz Lamentowicz; Jacqueline F. N. Van Leeuwen; Edward A. D. Mitchell; Tomasz Goslar; Christian Kamenik (Journal of Quaternary Science, 2010)
We present the first testate amoeba‐based palaeohydrological reconstruction from the Swiss Alps, and the first depth to the water table (DWT) calibration dataset for this region. Compared to existing models, our new calibration dataset performs well (RMSEP = 4.88), despite the length of the water table gradient covered (53 cm). The present‐day topography and vegetation of the study mire Mauntschas suggest that it is partly ombrotrophic (large Sphagnum fuscum hummocks, one of which was the coring site) but mostly under the minerotrophic influence of springs in the mire and runoff from the surrounding area. Ombrotrophic Sphagnum fuscum hummocks developed at the sampling site only during the last 50 years, when testate amoebae indicate a shift towards dry and/or acid conditions. Prior to AD 1950 the water table was much higher, suggesting that the influence of the mineral‐rich water prevented the development of ombrotrophic hummocks. The reconstructed DWT correlated with Pinus cembra pollen accumulation rates, suggesting that testate amoebae living on the mire and P. cembra growing outside of it partly respond to the same factor(s). Finally, temperature trends from the nearby meteorological station paralleled trends in reconstructed DWT. However, contrary to other studies made on raised bogs of northwestern Europe, the highest correlation was observed for winter temperature, despite the fact that testate amoebae would more logically respond to moisture conditions during the growing season. The observed correlation with winter temperature might reflect a control of winter severity on surface moisture during at least the first part of the growing season, through snow melt and soil frost phenomena influencing run‐off. More ecohydrological work on sub‐alpine mires is needed to understand the relationships between climate, testate amoebae and peatland development. Copyright © 2009 John Wiley & Sons, Ltd.

Ecosystem Services as a Common Language for Coastal Ecosystem‐Based Management - ELISE F. GRANEK; STEPHEN POLASKY; CARRIE V. KAPPEL; DENISE J. REED; DAVID M. STOMS; EVAMARIA W. KOCH; CHRIS J. KENNEDY; LORI A. CRAMER; SALLY D. HACKER; EDWARD B. BARBIER; SHANKAR ASWANI; MARY RUCKELSHAUS; et al. (Conservation Biology, 2010)
Ecosystem‐based management is logistically and politically challenging because ecosystems are inherently complex and management decisions affect a multitude of groups. Coastal ecosystems, which lie at the interface between marine and terrestrial ecosystems and provide an array of ecosystem services to different groups, aptly illustrate these challenges. Successful ecosystem‐based management of coastal ecosystems requires incorporating scientific information and the knowledge and views of interested parties into the decision‐making process. Estimating the provision of ecosystem services under alternative management schemes offers a systematic way to incorporate biogeophysical and socioeconomic information and the views of individuals and groups in the policy and management process. Employing ecosystem services as a common language to improve the process of ecosystem‐based management presents both benefits and difficulties. Benefits include a transparent method for assessing trade‐offs associated with management alternatives, a common set of facts and common currency on which to base negotiations, and improved communication among groups with competing interests or differing worldviews. Yet challenges to this approach remain, including predicting how human interventions will affect ecosystems, how such changes will affect the provision of ecosystem services, and how changes in service provision will affect the welfare of different groups in society. In a case study from Puget Sound, Washington, we illustrate the potential of applying ecosystem services as a common language for ecosystem‐based management.

Utilisation of rodent species by larvae and nymphs of hard ticks (Ixodidae) in two habitats in NE Poland - Anna Paziewska; Lucyna Zwolińska; Philip D. Harris; Anna Bajer; Edward Siński (Experimental and Applied Acarology, 2010)

Comparing plasma and faecal measures of steroid hormones in Adelie penguins Pygoscelis adeliae - Calum Edward Ninnes; J. R. Waas; N. Ling; S. Nakagawa; J. C. Banks; D. G. Bell; A. Bright; P. W. Carey; J. Chandler; Q. J. Hudson; J. R. Ingram; K. Lyall; et al. (Journal of Comparative Physiology B, 2010)

Reconstructing ENSO: the influence of method, proxy data, climate forcing and teleconnections - Rob Wilson; Edward Cook; Rosanne D'Arrigo; Nadja Riedwyl; Michael N. Evans; Alexander Tudhope; Rob Allan (Journal of Quaternary Science, 2010)
In this study we compare three newly developed independent NINO3.4 sea surface temperature (SST) reconstructions using data from (1) the central Pacific (corals), (2) the TexMex region of the USA (tree rings) and (3) other regions in the Tropics (corals and an ice core) which are teleconnected with central Pacific SSTs in the 20th century. Although these three reconstructions are strongly calibrated and well verified, inter‐proxy comparison shows a significant weakening in inter‐proxy coherence in the 19th century. This breakdown in common signal could be related to insufficient data, dating errors in some of the proxy records or a breakdown in El Niño–Southern Oscillation's (ENSO's) influence on other regions. However, spectral analysis indicates that each reconstruction portrays ENSO‐like spectral properties. Superposed epoch analysis also shows that each reconstruction shows a generally consistent ‘El Niño‐like’ response to major volcanic events in the following year, while during years T + 4 to T + 7 ‘La Niña‐like’ conditions prevail. These results suggest that each of the series expresses ENSO‐like ‘behaviour’, but this ‘behaviour’ does not appear to be spatially or temporally consistent. This result may reflect published observations that there appear to be distinct ‘types’ of ENSO variability depending on location within the tropical Pacific. Future work must address potential dating issues within some proxies (i.e. sampling of multiple coral heads for one location) as well as assessing the time stability of local climate relationships with central Pacific SSTs. More emphasis is needed on sampling new and extending old coral proxy records from the crucial central and eastern tropical Pacific region. Copyright © 2009 John Wiley & Sons, Ltd. and © Crown Copyright 2009.

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

How many is enough? Determining optimal count totals for ecological and palaeoecological studies of testate amoebae - Richard J. Payne; Edward A. D. Mitchell (Journal of Paleolimnology, 2009)

Fractured bedrock and saprolite hydrogeologic controls on groundwater/surface-water interaction: a conceptual model (Australia) - Edward W. Banks; Craig T. Simmons; Andrew J. Love; Roger Cranswick; Adrian D. Werner; Erick A. Bestland; Martin Wood; Tania Wilson (Hydrogeology Journal, 2009)

Mitochondrial genome sequence of Unionicola foili (Acari: Unionicolidae): a unique gene order with implications for phylogenetic inference - Brian R. Ernsting; Dale D. Edwards; Katie J. Aldred; Jeffrey S. Fites; Caroline R. Neff (Experimental and Applied Acarology, 2009)

Characterization of 20 microsatellite marker loci in the Malagasy tree boa (Sanzinia madagascariensis madagascariensis) - Manjaka A. Ramanana; Carolyn A. Bailey; Gary D. Shore; Olga Ramilijaona; Rick A. Brenneman; Edward E. Louis (Conservation Genetics, 2009)

Urothelial carcinoma: Stem cells on the edge - William D. Brandt; William Matsui; Jonathan E. Rosenberg; Xiaobing He; Shizhang Ling; Edward M. Schaeffer; David M. Berman (Cancer and Metastasis Reviews, 2009)

Hybridization and polymorphic microsatellite markers for two lagomorph species (Genus Sylvilagus): implications for conservation - Leah K. Berkman; Melody J. Saltzgiver; Edward J. Heist; Clayton K. Nielsen; Charlotte L. Roy; Paul D. Scharine (Conservation Genetics Resources, 2009)

A peroxynitrite complex of copper: formation from a copper–nitrosyl complex, transformation to nitrite and exogenous phenol oxidative coupling or nitration - Ga Young Park; Subramanian Deepalatha; Simona C. Puiu; Dong-Heon Lee; Biplab Mondal; Amy A. Narducci Sarjeant; Diego del Rio; Monita Y. M. Pau; Edward I. Solomon; Kenneth D. Karlin (JBIC Journal of Biological Inorganic Chemistry, 2009)

A Small-Scale Sulfate-Reducing Bioreactor for Manganese Removal from a Synthetic Mine Drainage - J. D. Edwards; C. D Barton; A. D. Karathanasis (Water, Air, & Soil Pollution, 2009)

Toxic Elements in Aquatic Sediments: Distinguishing Natural Variability from Anthropogenic Effects - Aixin Hou; Ronald D. DeLaune; MeiHuey Tan; Margaret Reams; Edward Laws (Water, Air, & Soil Pollution, 2009)

Characterization of 26 microsatellite marker loci in the fossa (Cryptoprocta ferox) - Barbara R. Vogler; Carolyn A. Bailey; Gary D. Shore; Susie M. McGuire; Shannon E. Engberg; Joerns Fickel; Edward E. Louis; Rick A. Brenneman (Conservation Genetics, 2009)

Characterization of 18 microsatellite marker loci in the white-collared lemur (Eulemur cinereiceps) - Hobinjatovo Tokiniaina; Carolyn A. Bailey; Gary D. Shore; Kira E. Delmore; Steig E. Johnson; Edward E. Louis; Rick A. Brenneman (Conservation Genetics, 2009)

Are adolescents more vulnerable to drug addiction than adults? Evidence from animal models - Nicole L. Schramm-Sapyta; Q. David Walker; Joseph M. Caster; Edward D. Levin; Cynthia M. Kuhn (Psychopharmacology, 2009)

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

A record of Lateglacial and early Holocene environmental and ecological change from southwestern Connecticut, USA - W. Wyatt Oswald; David R. Foster; Elaine D. Doughty; Edward K. Faison (Journal of Quaternary Science, 2009)
Analyses of a sediment core from Highstead Swamp in southwestern Connecticut, USA, reveal Lateglacial and early Holocene ecological and hydrological changes. Lateglacial pollen assemblages are dominated by Picea and Pinus subg. Pinus , and the onset of the Younger Dryas (YD) cold interval is evidenced by higher abundance of Abies and Alnus viridis subsp. crispa . As climate warmed at the end of the YD, Picea and Abies declined and Pinus strobus became the dominant upland tree species. A shift from lacustrine sediment to organic peat at the YD–Holocene boundary suggests that the lake that existed in the basin during the Lateglacial interval developed into a swamp in response to reduced effective moisture. A change in wetland vegetation from Myrica gale to Alnus incana subsp. rugosa and Sphagnum is consistent with this interpretation of environmental changes at the beginning of the Holocene. Copyright © 2009 John Wiley & Sons, Ltd.

Characterization of 20 microsatellite markers in the plowshare tortoise, Astrochelys yniphora - Angelo R. Mandimbihasina; Shannon E. Engberg; Gary D. Shore; Emilienne Razafimahatratra; Hafany Tiandray; Richard E. Lewis; Rick A. Brenneman; Edward E. Louis (Conservation Genetics, 2009)

Characterization of 22 microsatellite marker loci in the Madagascar rousette (Rousettus madagascariensis) - Andoniaina R. Andrianaivoarivelo; Gary D. Shore; Susie M. McGuire; Richard K. B. Jenkins; Olga Ramilijaona; Edward E. Louis; Rick A. Brenneman (Conservation Genetics, 2009)

Characterization of 21 microsatellite marker loci in the silky sifaka (Propithecus candidus) - Susie M. McGuire; George P. Emodi; Gary D. Shore; Rick A. Brenneman; Edward E. Louis (Conservation Genetics, 2009)

Manual and oculomotor performance develop contemporaneously but independently during continuous tracking - Eric D. Vidoni; Jason S. McCarley; Jodi D. Edwards; Lara A. Boyd (Experimental Brain Research, 2009)

The influence of evolutionary distance between cross-species microsatellites and primer base-pair composition on allelic dropout rates - Carl D. Soulsbury; Graziella Iossa; Keith J. Edwards (Conservation Genetics, 2009)

Moisture variability across China and Mongolia: 1951–2005 - Jinbao Li; Edward R. Cook; Rosanne D’arrigo; Fahu Chen; Xiaohua Gou (Climate Dynamics, 2009)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

The effects of cannabinoids on serum cortisol and prolactin in humans - Mohini Ranganathan; Gabriel Braley; Brian Pittman; Thomas Cooper; Edward Perry; John Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2009)

Estuarine Ecosystem Response Captured Using a Synoptic Climatology - David G. Kimmel; W. David Miller; Lawrence W. Harding; Edward D. Houde; Michael R. Roman (Estuaries and Coasts, 2009)

Near real‐time, autonomous detection of marine bacterioplankton on a coastal mooring in Monterey Bay, California, using rRNA‐targeted DNA probes - Christina M. Preston; Roman Marin; Scott D. Jensen; Jason Feldman; James M. Birch; Eugene I. Massion; Edward F. DeLong; Marcelino Suzuki; Kevin Wheeler; Christopher A. Scholin (Environmental Microbiology, 2009)
Summary A sandwich hybridization assay (SHA) was developed to detect 16S rRNAs indicative of phylogenetically distinct groups of marine bacterioplankton in a 96‐well plate format as well as low‐density arrays printed on a membrane support. The arrays were used in a field‐deployable instrument, the Environmental Sample Processor (ESP). The SHA employs a chaotropic buffer for both cell homogenization and hybridization, thus target sequences are captured directly from crude homogenates. Capture probes for seven of nine different bacterioplankton clades examined reacted specifically when challenged with target and non‐target 16S rRNAs derived from in vitro transcribed 16S rRNA genes cloned from natural samples. Detection limits were between 0.10–1.98 and 4.43– 12.54 fmole ml −1 homogenate for the 96‐well plate and array SHA respectively. Arrays printed with five of the bacterioplankton‐specific capture probes were deployed on the ESP in Monterey Bay, CA, twice in 2006 for a total of 25 days and also utilized in a laboratory time series study. Groups detected included marine alphaproteobacteria, SAR11, marine cyanobacteria, marine group I crenarchaea, and marine group II euryarchaea. To our knowledge this represents the first report of remote in situ DNA probe‐based detection of marine bacterioplankton.

Targeted transgene integration in plant cells using designed zinc finger nucleases - Charles Q. Cai; Yannick Doyon; W. Michael Ainley; Jeffrey C. Miller; Russell C. DeKelver; Erica A. Moehle; Jeremy M. Rock; Ya-Li Lee; Robbi Garrison; Lisa Schulenberg; Ryan Blue; Andrew Worden; et al. (Plant Molecular Biology, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Preliminary evidence of cannabinoid effects on brain-derived neurotrophic factor (BDNF) levels in humans - Deepak Cyril D’Souza; Brian Pittman; Edward Perry; Arthur Simen (Psychopharmacology, 2009)

Avian host community structure and prevalence of West Nile virus in Chicago, Illinois - Scott R. Loss; Gabriel L. Hamer; Edward D. Walker; Marilyn O. Ruiz; Tony L. Goldberg; Uriel D. Kitron; Jeffrey D. Brawn (Oecologia, 2009)

Application of the probability-based Maryland Biological Stream Survey to the state’s assessment of water quality standards - Mark T. Southerland; Jon H. Vølstad; Edward D. Weber; Ronald J. Klauda; Charles A. Poukish; Matthew C. Rowe (Environmental Monitoring and Assessment, 2009)

Duplication of AP1 within the Spinacia oleracea L. AP1/FUL clade is followed by rapid amino acid and regulatory evolution - D. Noah Sather; Edward M. Golenberg (Planta, 2009)

Border Treatment to Reduce Insecticide Use in Seed Potato Production: Biological, Economic, and Managerial Analysis - Matthew W. Carroll; Edward B. Radcliffe; Ian V. MacRae; David W. Ragsdale; Kent D. Olson; Thaddee Badibanga (American Journal of Potato Research, 2009)

Nicotine effects on learning in zebrafish: the role of dopaminergic systems - Donnie Eddins; Ann Petro; Paul Williams; Daniel T. Cerutti; Edward D. Levin (Psychopharmacology, 2009)

Characterizing microbial diversity in production water from an Alaskan mesothermic petroleum reservoir with two independent molecular methods - Vinh D. Pham; Linda L. Hnatow; Shiping Zhang; Robert D. Fallon; Scott C. Jackson; Jean‐Francois Tomb; Edward F. DeLong; Sharon J. Keeler (Environmental Microbiology, 2009)
Summary The phylogenetic diversity of Bacteria and Archaea within a biodegraded, mesothermic petroleum reservoir in the Schrader Bluff Formation of Alaska was examined by two culture‐independent methods based on fosmid and small‐subunit rRNA gene PCR clone libraries. Despite the exclusion of certain groups by each method, there was overall no significant qualitative difference in the diversity of phylotypes recovered by the two methods. The resident Bacteria belonged to at least 14 phylum‐level lineages, including the polyphyletic Firmicutes , which accounted for 36.2% of all small‐subunit rRNA gene‐containing (SSU + ) fosmid clones identified. Members of uncultured divisions were also numerous and made up 35.2% of the SSU + fosmid clones. Clones from domain Archaea accounted for about half of all SSU + fosmids, suggesting that their cell numbers were comparable to those of the Bacteria in this microbial community. In contrast to the Bacteria , however, nearly all archaeal clones recovered by both methods were related to methanogens, especially acetoclastic methanogens, while the plurality of bacterial fosmid clones was affiliated with Synergistes ‐like acetogenic Firmicutes that possibly degrade longer‐chain carboxylic acid components in the crude oil to acetate. These data suggest that acetate may be a key intermediary metabolite in this subsurface anaerobic food chain, which leads to methane production as the primary terminal electron sink.

Head CT in patient with metabolic acidosis - Kavita M. Babu; C. D. Rosenbaum; Edward W. Boyer (Journal of Medical Toxicology, 2008)

Using patterns of genetic structure based on microsatellite loci to test hypotheses of current hybridization, ancient hybridization and incomplete lineage sorting in Conradina (Lamiaceae) - C. E. EDWARDS; D. E. SOLTIS; P. S. SOLTIS (Molecular Ecology, 2008)
Hybridization and/or incomplete sorting of ancestral polymorphism are commonly implicated to explain discordant phylogenetic analyses of closely related species complexes. One genus in which these phenomena have been suggested to have played major roles based on phylogenetic data is Conradina , a genus of mints (Lamiaceae) endemic to the southeastern USA containing several endangered species. The goals of this study were to use microsatellite data to better understand patterns of genetic structure in Conradina, to test hypotheses of recent or ancient hybridization and incomplete lineage sorting, and to clarify species boundaries. Individuals from 55 populations representing all Conradina species were genotyped using 10 microsatellite loci. Analyses of the patterns of genetic structure in Conradina revealed a clear differentiation of populations following recognized species boundaries, indicating that species have diverged from one another genetically and interspecific hybridization has not occurred recently. Neither ancient hybridization nor incomplete lineage sorting is supported as the sole cause of species nonmonophyly, suggesting that both may have contributed to patterns found in phylogenetic trees; however, analyses of other types of data may be more appropriate to distinguish between these two hypotheses. Because all described species appear to be valid entities, the current listing status of most endangered species of Conradina is appropriate; however, populations of Conradina canescens are genetically differentiated into three groups, each of which may merit species status, and several recently discovered populations of Conradina in Dunn's Creek State Park in Florida are highly differentiated genetically and also appear to represent a new species.

A region of barley chromosome 6H harbors multiple major genes associated with net type net blotch resistance - M. Abu Qamar; Z. H. Liu; J. D. Faris; S. Chao; M. C. Edwards; Z. Lai; J. D. Franckowiak; T. L. Friesen (Theoretical and Applied Genetics, 2008)

Characterization of twenty-one microsatellites developed from Propithecus diadema - Roger Ramarokoto; Runhua Lei; Justin Vincent; Sabine Day; Gary D. Shore; Rick A. Brenneman; Edward E. Louis (Conservation Genetics, 2008)

Reproduction in the sea pen Pennatula phosphorea (Anthozoa: Pennatulacea) from the west coast of Scotland - D. C. B. Edwards; C. G. Moore (Marine Biology, 2008)

Prevalence and predictors of cancer screening among American Indian and Alaska native people: the EARTH study - Mary Catherine Schumacher; Martha L. Slattery; Anne P. Lanier; Khe-Ni Ma; Sandra Edwards; Elizabeth D. Ferucci; Lillian Tom-Orme (Cancer Causes & Control, 2008)

Cell-type-specific level of DNA nucleotide excision repair in primary human mammary and ovarian epithelial cell cultures - Jean J. Latimer; Jennifer M. Johnson; Tiffany D. Miles; Jason M. Dimsdale; Robert P. Edwards; Joseph L. Kelley; Stephen G. Grant (Cell and Tissue Research, 2008)

Common tree growth anomalies over the northeastern Tibetan Plateau during the last six centuries: implications for regional moisture change - JINBAO LI; EDWARD R. COOK; ROSANNE D'ARRIGO; FAHU CHEN; XIAOHUA GOU; JIANFENG PENG; JIANGUO HUANG (Global Change Biology, 2008)
The world's hydrological cycle is believed to intensify with global warming, yet current climate models have only a limited ability to assess moisture responses at regional scales. Tree‐ring records are a valuable source of information for understanding long‐term, regional‐scale moisture changes, particularly for large regions such as the Tibetan Plateau (TP), where the observational data are short and sparse. Here, we present a new ring‐width chronology developed from Qilian Juniper ( Sabina przewalskii ) wood at two sites on the northeastern TP. This chronology, combined with others from the same region, demonstrates that tree growth anomalies are linked to regional late spring to early summer moisture availability. Although late monsoon season precipitation in the study area decreased during recent decades, tree growth continued to increase due to persistent moisture availability in the early monsoon season. Comparison with global sea surface temperatures (SSTs) indicates that early (late) monsoon season precipitation is closely related to tropical Pacific (Indian Ocean) SSTs, suggesting a possible seasonal shift in the dominant moisture source area for monsoonal precipitation over the northeastern TP. It is further shown that there is a very high degree of coherency regarding low‐frequency tree growth anomalies over the northeastern TP during the last six centuries. The most prominent drought epoch occurred during ca. 1450–1500, which may have been caused by a significant decrease in the thermal gradient between the Eurasian continent and the tropical oceans. A persistent tree growth increase since the 1880s is coincident with global warming, suggesting an intensified early monsoon season moisture regime in the study area.

Phylogenetic analyses of ribosomal DNA‐containing bacterioplankton genome fragments from a 4000 m vertical profile in the North Pacific Subtropical Gyre - Vinh D. Pham; Konstantinos T. Konstantinidis; Tsultrim Palden; Edward F. DeLong (Environmental Microbiology, 2008)
Summary High‐throughput identification of rRNA gene‐containing clones in large insert metagenomic libraries is difficult, because of the high background of host ribosomal RNA (rRNA) and rRNA genes. To address this challenge, a membrane hybridization method was developed to identify all bacterial small subunit rRNA‐containing fosmid clones of microbial community DNA from seven different depths in the North Pacific Subtropical Gyre. Out of 101,376 clones screened, 751 rDNA‐containing clones were identified that grouped in ∼60 different clades. Several rare sequences only remotely related to known groups were detected, including a Wolbachia ‐related sequence containing a putative intron or intervening sequence, as well as seven sequences from Order Myxococcales not previously detected in pelagic habitats. Stratified, depth‐specific population structure was evident within both cultured and uncultured lineages. Conversely, some eurybathyal members of the genera Alcanivorax and Rhizobium shared identical small subunit ribosomal DNA sequences that were distributed from surface waters to the 4000 m depth. Comparison with similar analyses in Monterey Bay microbial communities revealed previously recognized, as well as some distinctive, depth‐stratified partitioning that distinguished coastal from open ocean bacterioplankton populations. While some bias was evident in fosmid clone recovery in a few particular lineages, the overall phylogenetic group recovery and distributions were consistent with previous studies, as well as with direct shotgun sequence data from the same source DNA.

Potential implications of differential preservation of testate amoeba shells for paleoenvironmental reconstruction in peatlands - Edward A. D. Mitchell; Richard J. Payne; Mariusz Lamentowicz (Journal of Paleolimnology, 2008)

Age- and sex-related differences in muscle activation for a discrete functional task - B. Harwood; D. L. Edwards; J. M. Jakobi (European Journal of Applied Physiology, 2008)

Characterization of 20 microsatellites marker loci in the golden-crowned sifaka (Propithecus tattersalli) - Andriamahery Razafindrakoto; Erwan Quéméré; Gary D. Shore; Susie M. McGuire; Edward E. Louis; Rick A. Brenneman (Conservation Genetics, 2008)

Characterization of 20 microsatellites developed from Propithecus deckeni coronatus with cross-amplification in Propithecus deckeni deckeni - Runhua Lei; Susie M. McGuire; Gary D. Shore; Edward E. Louis; Rick A. Brenneman (Conservation Genetics, 2008)

Testate amoebae analysis in ecological and paleoecological studies of wetlands: past, present and future - Edward A. D. Mitchell; Daniel J. Charman; Barry G. Warner (Biodiversity and Conservation, 2008)

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)

Geochemical reconstruction of late Holocene drainage and mixing in Kluane Lake, Yukon Territory - Janice Brahney; John J. Clague; Brian Menounos; Thomas W. D. Edwards (Journal of Paleolimnology, 2008)

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Relationship of predation potential to mortality of Calanus finmarchicus on Georges Bank, northwest Atlantic - Mark D. Ohman; Edward G. Durbin; Jeffrey A. Runge; Barbara K. Sullivan; David B. Field (Limnology and Oceanography, 2008)
Based on 29 cruises on Georges Bank between January and June, conducted as part of the U.S. Global Ocean Ecosystem Dynamics program, we describe seasonal and spatial variability of early life history mortality for the planktonic copepod Calanus finmarchicus and relate mortality to an index of predation potential from a suite of suspension‐feeding predators. Emphasis is placed on the earliest life history phase wherein peak mortality occurs. Instantaneous mortality rates for a combined egg‐through‐nauplius‐3 stage show a recurrent seasonal pattern of a modest elevation in January followed by a seasonal peak in May of all 5 study yr. Spatial differences exist in mortality rates, with a higher probability of mortality on the southern flank in winter and a pronounced seasonal maximum on the bank crest in May. Three hypotheses associated, respectively, with egg hatching success, advection, and invertebrate predation were evaluated to account for the seasonal and spatial mortality patterns. Variations in egg‐hatching success are inconsistent with the observed seasonal patterns of loss. Off‐bank advection, particularly on the southern flank, appears to be the dominant loss term in January. Apart from this winter period, egg mortality is associated with predation potential. Comparison of an index of daily rates of egg loss with an index of consumption rates of eggs by suspended hydroids, hydromedusae, and five species of planktonic copepods show general agreement between mortality and predation in both seasonal variation and spatial patterns. Of the predator taxa, late copepodid and adult C. finmarchicus , supplemented by planktonic hydroids, appear to have the largest quantitative predation effect.

Return of Salmon-Derived Nutrients from the Riparian Zone to the Stream during a Storm in Southeastern Alaska - Jason B. Fellman; Eran Hood; Rick T. Edwards; David V. D’Amore (Ecosystems, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Autumn migration and wintering of northern fulmars (Fulmarus glacialis) from the Canadian high Arctic - Mark L. Mallory; Jason A. Akearok; Darryl B. Edwards; Kieran O’Donovan; Cynthia D. Gilbert (Polar Biology, 2008)

Liver lesions in demersal fishes near a large ocean outfall on the San Pedro Shelf, California - Edward Basmadjian; Edwin M. Perkins; Charles R. Phillips; Daniel J. Heilprin; Susan D. Watts; Douglas R. Diener; Mark S. Myers; Kelly A. Koerner; Michael J. Mengel; George Robertson; Jeffrey L. Armstrong; Andrew L. Lissner; et al. (Environmental Monitoring and Assessment, 2008)

Multi-species spawning of corals in north-western Philippines - K. C. Vicentuan; J. R. Guest; M. V. Baria; P. C. Cabaitan; R. M. Dizon; R. D. Villanueva; P. M. Aliño; A. J. Edwards; E. D. Gomez; A. J. Heyward (Coral Reefs, 2008)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Pyrethroid tolerance is associated with elevated expression of antioxidants and agricultural practice in Anopheles arabiensis sampled from an area of cotton fields in Northern Cameroon - PIE MÜLLER; MOUHAMADOU CHOUAÏBOU; PATRICIA PIGNATELLI; JOSIANE ETANG; EDWARD D. WALKER; MARTIN J. DONNELLY; FRÉDÉRIC SIMARD; HILARY RANSON (Molecular Ecology, 2008)
Spraying of agricultural crops with insecticides can select for resistance in nontarget insects and this may compromise the use of insecticides for the control of vector‐borne diseases. The tolerance of the malaria vector, Anopheles arabiensis to deltamethrin was determined in a field population from a cotton‐growing region of Northern Cameroon both prior to and midway through the 4‐month period of insecticide application to the cotton crop. A 1.6‐fold increase in the median knockdown time was observed. To determine whether this increased tolerance was associated with constitutively elevated levels of genes commonly associated with insecticide resistance, RNA was extracted from F 1 progeny from family lines of field‐caught mosquitoes and hybridized to the Anopheles gambiae detox chip. The experimental design avoided the confounding effects of colonization, and this study is the first to measure gene expression in the progeny of gravid, wild‐caught mosquitoes. Several genes with antioxidant roles, including superoxide dismutases, a glutathione S‐transferase and a thioredoxin‐dependent peroxidase, and a cytochrome P450 showed elevated expression in mosquito families collected during the insecticide‐spraying programme. These genes may constitute an important general defence mechanism against insecticides. Intriguingly, the levels of expression of these genes were strongly correlated suggesting a common regulatory mechanism.

Contrasting success in the restoration of plant and phytophagous beetle assemblages of species-rich mesotrophic grasslands - B. A. Woodcock; A. R. Edwards; C. S. Lawson; D. B. Westbury; A. J. Brook; S. J. Harris; V. K. Brown; S. R. Mortimer (Oecologia, 2008)

Textural, mineralogical and stable isotope studies of hydrothermal alteration in the main sulfide zone of the Great Dyke, Zimbabwe and the precious metals zone of the Sonju Lake Intrusion, Minnesota, USA - Chusi Li; Edward M. Ripley; Thomas Oberthür; James D. Miller; Gregory D. Joslin (Mineralium Deposita, 2008)

Atlantic reef fish biogeography and evolution - S. R. Floeter; L. A. Rocha; D. R. Robertson; J. C. Joyeux; W. F. Smith‐Vaniz; P. Wirtz; A. J. Edwards; J. P. Barreiros; C. E. L. Ferreira; J. L. Gasparini; A. Brito; J. M. Falcón; et al. (Journal of Biogeography, 2008)
Aim To understand why and when areas of endemism (provinces) of the tropical Atlantic Ocean were formed, how they relate to each other, and what processes have contributed to faunal enrichment. Location Atlantic Ocean. Methods The distributions of 2605 species of reef fishes were compiled for 25 areas of the Atlantic and southern Africa. Maximum‐parsimony and distance analyses were employed to investigate biogeographical relationships among those areas. A collection of 26 phylogenies of various Atlantic reef fish taxa was used to assess patterns of origin and diversification relative to evolutionary scenarios based on spatio‐temporal sequences of species splitting produced by geological and palaeoceanographic events. We present data on faunal (species and genera) richness, endemism patterns, diversity buildup (i.e. speciation processes), and evaluate the operation of the main biogeographical barriers and/or filters. Results Phylogenetic (proportion of sister species) and distributional (number of shared species) patterns are generally concordant with recognized biogeographical provinces in the Atlantic. The highly uneven distribution of species in certain genera appears to be related to their origin, with highest species richness in areas with the greatest phylogenetic depth. Diversity buildup in Atlantic reef fishes involved (1) diversification within each province, (2) isolation as a result of biogeographical barriers, and (3) stochastic accretion by means of dispersal between provinces. The timing of divergence events is not concordant among taxonomic groups. The three soft (non‐terrestrial) inter‐regional barriers (mid‐Atlantic, Amazon, and Benguela) clearly act as ‘filters’ by restricting dispersal but at the same time allowing occasional crossings that apparently lead to the establishment of new populations and species. Fluctuations in the effectiveness of the filters, combined with ecological differences among provinces, apparently provide a mechanism for much of the recent diversification of reef fishes in the Atlantic. Main conclusions Our data set indicates that both historical events (e.g. Tethys closure) and relatively recent dispersal (with or without further speciation) have had a strong influence on Atlantic tropical marine biodiversity and have contributed to the biogeographical patterns we observe today; however, examples of the latter process outnumber those of the former.

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Zonation of forest vegetation and soils of Mount Cameroon, West Africa - John Proctor; Ian D. Edwards; Robert W. Payton; Laszlo Nagy (Plant Ecology, 2007)

Effects of atmospheric dynamics and ocean resolution on bi-stability of the thermohaline circulation examined using the Grid ENabled Integrated Earth system modelling (GENIE) framework - T. M. Lenton; R. Marsh; A. R. Price; D. J. Lunt; Y. Aksenov; J. D. Annan; T. Cooper-Chadwick; S. J. Cox; N. R. Edwards; S. Goswami; J. C. Hargreaves; P. P. Harris; et al. (Climate Dynamics, 2007)

Diagnosis and management of small‐scale fisheries in developing countries - Neil L Andrew; Christophe Béné; Stephen J Hall; Edward H Allison; Simon Heck; Blake D Ratner (Fish and Fisheries, 2007)
Small‐scale fisheries (SSF) make important but undervalued contributions to the economies of some of the world’s poorest countries. They also provide much of the animal protein needed by societies in which food security remains a pressing issue. Assessment and management of these fisheries is usually inadequate or absent and they continue to fall short of their potential as engines for development and social change. In this study, we bring together existing theory and methods to suggest a general scheme for diagnosing and managing SSF. This approach can be adapted to accommodate the diversity of these fisheries in the developing world. Many threats and solutions to the problems that beset SSF come from outside the domain of the fishery. Significant improvements in prospects for fisheries will require major changes in societal priorities and values, with consequent improvements in policy and governance. Changes in development policy and science reflect these imperatives but there remains a need for intra‐sectoral management that builds resilience and reduces vulnerability to those forces beyond the influence of small‐scale fishers.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Enhancement of Insulin Transport Across Primary Rat Alveolar Epithelial Cell Monolayers by Endogenous Cellular Factor(s) - Rana Bahhady; Kwang-Jin Kim; Zea Borok; Edward D. Crandall; Wei-Chiang Shen (Pharmaceutical Research, 2007)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

Plasma protein advanced glycation end products, carboxymethyl cysteine, and carboxyethyl cysteine, are elevated and related to nephropathy in patients with diabetes - Ahmed A. Mostafa; Edward W. Randell; Sudesh C. Vasdev; Vicki D. Gill; Yingchun Han; Vereesh Gadag; Ahmed A. Raouf; Hala El Said (Molecular and Cellular Biochemistry, 2007)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Measuring global gene expression in polyploidy; a cautionary note from allohexaploid wheat - Rebecca Poole; Gary Barker; Ian D. Wilson; Jane A. Coghill; Keith J. Edwards (Functional & Integrative Genomics, 2007)

Toxicity of cobalt-complexed cyanide to Oncorhynchus mykiss, Daphnia magna, and Ceriodaphnia dubia - Edward E. Little; Robin D. Calfee; Peter Theodorakos; Zoe Ann Brown; Craig A. Johnson (Environmental Science and Pollution Research, 2007)

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

Allelic dropout from a high-quality DNA source - Carl D. Soulsbury; Graziella Iossa; Keith J. Edwards; Philip J. Baker; Stephen Harris (Conservation Genetics, 2007)

AAPS-FDA Workshop White Paper: Microdialysis Principles, Application and Regulatory Perspectives - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (Pharmaceutical Research, 2007)

Post‐glacial changes in spatial patterns of vegetation across southern New England - W. Wyatt Oswald; Edward K. Faison; David R. Foster; Elaine D. Doughty; Brian R. Hall; Barbara C. S. Hansen (Journal of Biogeography, 2007)
Aim We analysed lake‐sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post‐glacial climatic changes, (2) landscape‐scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north‐central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus , Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north‐central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non‐metric multi‐dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr bp ). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr bp ; by Pinus strobus from 11,500 to 10,500 cal yr bp ; and by P. strobus and Tsuga between 10,500 and 9500 cal yr bp . At 9500–8000 cal yr bp , however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr bp , when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid‐Holocene Tsuga decline (5500–3500 cal yr bp ), but the pattern weakened during the late‐Holocene (3500–300 cal yr bp ) and European‐settlement intervals. Within‐group similarity declined in response to the uneven late‐Holocene expansion of Castanea , while between‐group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr bp . The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.

AAPS-FDA workshop white paper: Microdialysis principles, application, and regulatory perspectives report from the Joint AAPS-FDA Workshop, November 4–5, 2005, Nashville, TN - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (The AAPS Journal, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

A long‐term chlorophyll dataset reveals regime shift in North Sea phytoplankton biomass unconnected to nutrient levels - Abigail McQuatters-Gollop; Dionysios E. Raitsos; Martin Edwards; Yaswant Pradhan; Laurence D. Mee; Samantha J. Lavender; Martin J. Attrill (Limnology and Oceanography, 2007)
During the 1980s, a rapid increase in the Phytoplankton Colour Index (PCI), a semiquantitative visual estimate of algal biomass, was observed in the North Sea as part of a regionwide regime shift. Two new data sets created from the relationship between the PCI and SeaWiFS chlorophyll a (Chl a ) quantify differences in the previous and current regimes for both the anthropogenically affected coastal North Sea and the comparatively unaffected open North Sea. The new regime maintains a 13% higher Chl a concentration in the open North Sea and a 21% higher concentration in coastal North Sea waters. However, the current regime has lower total nitrogen and total phosphorus concentrations than the previous regime, although the molar N: P ratio in coastal waters is now well above the Redfield ratio and continually increasing. Besides becoming warmer, North Sea waters are also becoming clearer (i.e., less turbid), thereby allowing the normally light‐limited coastal phytoplankton to more effectively utilize lower concentrations of nutrients. Linear regression analyses indicate that winter Secchi depth and sea surface temperature are the most important predictors of coastal Chl a , while Atlantic inflow is the best predictor of open Chl a ; nutrient concentrations are not a significant predictor in either model. Thus, despite decreasing nutrient concentrations, Chl a continues to increase, suggesting that climatic variability and water transparency may be more important than nutrient concentrations to phytoplankton production at the scale of this study.

Life on the edge: African malaria mosquito (Anopheles gambiae s. l.) larvae are amphibious - James R. Miller; Juan Huang; John Vulule; Edward D. Walker (The Science of Nature, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Phylogeny of Bonatea (Orchidaceae: Habenariinae) based on molecular and morphological data - M. E. Ponsie; A. Mitchell; T. J. Edwards; S. D. Johnson (Plant Systematics and Evolution, 2007)

Progress in isotope paleohydrology using lake sediment cellulose - Brent B. Wolfe; Matthew D. Falcone; Ken P. Clogg-Wright; Cherie L. Mongeon; Yi Yi; Bronwyn E. Brock; Natalie A. St. Amour; William A. Mark; Thomas W. D. Edwards (Journal of Paleolimnology, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Breeding system of a plesiomorphic floral type: an investigation of small flowered Streptocarpus (Gesneriaceae) species - M. Hughes; G. MacMaster; M. Möller; D. U. Bellstedt; T. J. Edwards (Plant Systematics and Evolution, 2006)

Transdermal nicotine attenuates depression symptoms in nonsmokers: a double-blind, placebo-controlled trial - F. Joseph McClernon; F. Berry Hiott; Eric C. Westman; Jed E. Rose; Edward D. Levin (Psychopharmacology, 2006)

Ventral hippocampal α7 and α4β2 nicotinic receptor blockade and clozapine effects on memory in female rats - Ana Pocivavsek; Laura Icenogle; Edward D. Levin (Psychopharmacology, 2006)

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Neuronal Network Models of Phase Separation Between Limb CPGs of Digging Sand Crabs - A. Hodge; R. Edwards; D. H. Paul; P. van den Driessche (Biological Cybernetics, 2006)

Assembling a mutualism: ant symbionts locate their host plants by detecting volatile chemicals - D. P. Edwards; M. Hassall; W. J. Sutherland; D. W. Yu (Insectes Sociaux, 2006)

Reinvestigation of the method used to map the electronic structure of blue copper proteins by NMR relaxation - D. Flemming Hansen; Serge I. Gorelsky; Ritimukta Sarangi; Keith O. Hodgson; Britt Hedman; Hans E. M. Christensen; Edward I. Solomon; Jens J. Led (JBIC Journal of Biological Inorganic Chemistry, 2006)

Trans-Endplate Nucleotomy Increases Deformation and Creep Response in Axial Loading - Wade Johannessen; Jordan M. Cloyd; Grace D. O'Connell; Edward J. Vresilovic; Dawn M. Elliott (Annals of Biomedical Engineering, 2006)

Nickel hyperaccumulation by Streptanthus polygaloides protects against the folivore Plutella xylostella (Lepidoptera: Plutellidae) - Edward M. Jhee; Robert S. Boyd; Micky D. Eubanks; Micheal A. Davis (Plant Ecology, 2006)

Nicotinic effects on cognitive function: behavioral characterization, pharmacological specification, and anatomic localization - Edward D. Levin; F. Joseph McClernon; Amir H. Rezvani (Psychopharmacology, 2006)

Timing of nicotine effects on learning in zebrafish - Edward D. Levin; Joy Limpuangthip; Tara Rachakonda; Miram Peterson (Psychopharmacology, 2006)

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Oracle-based optimization applied to climate model calibration - Cesar Beltran; N. R. Edwards; A. B. Haurie; J.-P. Vial; D. S. Zachary (Environmental Modeling & Assessment, 2006)

Effectiveness of Metal–Metal and Metal–Organic Compound Combinations Against Plutella xylostella: Implications for Plant Elemental Defense - Edward M. Jhee; Robert S. Boyd; Micky D. Eubanks (Journal of Chemical Ecology, 2006)

Phosphodiesterase inhibition by sildenafil citrate attenuates a maze learning impairment in rats induced by nitric oxide synthase inhibition - Bryan D. Devan; Jonna L. Bowker; Kara B. Duffy; Ila S. Bharati; Mariana Jimenez; Demetrio Sierra-Mercado; Christopher M. Nelson; Edward L. Spangler; Donald K. Ingram (Psychopharmacology, 2006)

Trace Metal Distribution and Enrichment in Benthic, Estuarine Sediments: Southport Broadwater, Australia - Edward D. Burton; Ian R. Phillips; Darryl W. Hawker (Environmental Geochemistry and Health, 2005)

Refugia, dispersal and divergence in a forest archipelago: a study of Streptocarpus in eastern South Africa - M. HUGHES; M. MÖLLER; D. U. BELLSTEDT; T. J. EDWARDS; M. DE VILLIERS (Molecular Ecology, 2005)
We describe a scenario of plant speciation across a relict forest archipelago in South Africa involving Pleistocene habitat expansion‐contraction cycles, dispersal and adaptation to lower temperatures. This is the first population level study using molecular data in South African forests and has significant implications for conservation efforts in this area. Populations of the mesophytic forest floor herbs Streptocarpus primulifolius sensu lato and Streptocarpus rexii were sampled throughout their range in the naturally fragmented forests of eastern South Africa in order to investigate population genetic and phylogenetic patterns within the species complex, using nuclear microsatellites, nuclear ribosomal ITS (internal transcribed spacer) sequences and chloroplast genome sequences. S . primulifolius harbours high levels of genetic diversity at both the nuclear (mean H E = 0.50) and the chloroplast level (each population fixed for a unique haplotype). This is consistent with populations of these coastal species being Pleistocene relicts. In contrast, populations of S . rexii in cooler habitats at higher altitudes and lower latitudes harbour little or no nuclear genetic diversity (mean H E = 0.09) and most share a common chloroplast haplotype. The split of S . rexii from populations intermediate between the two species ( S . cf. primulifolius ) occurred between 0 and 0.44 million years ago according to the calibrated ITS phylogeny of the taxa. The low genetic diversity and homogeneity of S . rexii is congruent with this species having reached its current range during the Holocene. We found no evidence of monophyly of any of the taxa in this study, which we consider a consequence of recent evolution in a fragmented habitat.

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Hydroxyl and Peroxy Radical Chemistry in a Rural Area of Central Pennsylvania: Observations and Model Comparisons - Xinrong Ren; William H. Brune; Christopher A. Cantrell; Gavin D. Edwards; Terry Shirley; Andrew R. Metcalf; Robert L. Lesher (Journal of Atmospheric Chemistry, 2005)

Sequence evolution and sex-specific expression patterns of the C class floral identity gene, SpAGAMOUS, in dioecious Spinacia oleracea L - D. Noah. Sather; Amber York; Kevin J. Pobursky; Edward M. Golenberg (Planta, 2005)

Evaluating Wolf Translocation as a Nonlethal Method to Reduce Livestock Conflicts in the Northwestern United States - ELIZABETH H. BRADLEY; DANIEL H. PLETSCHER; EDWARD E. BANGS; KYRAN E. KUNKEL; DOUGLAS W. SMITH; CURT M. MACK; THOMAS J. MEIER; JOSEPH A. FONTAINE; CARTER C. NIEMEYER; MICHAEL D. JIMENEZ (Conservation Biology, 2005)
Successful nonlethal management of livestock predation is important for conserving rare or endangered carnivores. In the northwestern United States, wolves ( Canis lupus ) have been translocated away from livestock to mitigate conflicts while promoting wolf restoration. We assessed predation on livestock, pack establishment, survival, and homing behavior of 88 translocated wolves with radiotelemetry to determine the effectiveness of translocation in our region and consider how it may be improved. More than one‐quarter of translocated wolves preyed on livestock after release. Most translocated wolves (67%) never established or joined a pack, although eight new packs resulted from translocations. Translocated wolves had lower annual survival (0.60) than other radio‐collared wolves (0.73), with government removal the primary source of mortality. In northwestern Montana, where most wolves have settled in human‐populated areas with livestock, survival of translocated wolves was lowest (0.41) and more wolves proportionally failed to establish packs (83%) after release. Annual survival of translocated wolves was highest in central Idaho (0.71) and more wolves proportionally established packs (44%) there than in the other two recovery areas. Translocated wolves showed a strong homing tendency; most of those that failed to home still showed directional movement toward capture sites. Wolves that successfully returned to capture sites were more likely to be adults, hard (immediately) rather than soft (temporarily held in enclosure) released, and translocated shorter distances than other wolves that did not return home. Success of translocations varied and was most affected by the area in which wolves were released. We suggest managers translocating wolves or other large carnivores consider soft releasing individuals (in family groups, if social) when feasible because this may decrease homing behavior and increase release‐site fidelity.

Impairment of specific episodic memory processes by sub-psychotic doses of ketamine: the effects of levels of processing at encoding and of the subsequent retrieval task - Garry D. Honey; Rebekah A. E. Honey; Sam R. Sharar; Danielle C. Turner; Edith Pomarol-Clotet; Dharshan Kumaran; Jon S. Simons; Xiangen Hu; Michael D. Rugg; Edward T. Bullmore; Paul C. Fletcher (Psychopharmacology, 2005)

Intercellular adhesion molecule-1 and childhood asthma - Yu-Fen Li; Yo-Hsuang Tsao; W. James Gauderman; David V. Conti; Edward Avol; Louis Dubeau; Frank D. Gilliland (Human Genetics, 2005)

Development of baroreflex and endocrine responses to hypotensive stress in newborn foals and lambs - S. J. O’Connor; D. S. Gardner; J. C. Ousey; N. Holdstock; P. Rossdale; C. M. B. Edwards; A. L. Fowden; D. A. Giussani (Pflügers Archiv - European Journal of Physiology, 2005)

Origin of phlogopite-orthopyroxene inclusions in chromites from the Merensky Reef of the Bushveld Complex, South Africa - Chusi Li; Edward M. Ripley; Arindam Sarkar; Dongbok Shin; Wolfgang D. Maier (Contributions to Mineralogy and Petrology, 2005)

Alteration of the embryo transcriptome of hexaploid winter wheat (Triticum aestivum cv. Mercia) during maturation and germination - Ian D. Wilson; Gary L. A. Barker; Chungui Lu; Jane A. Coghill; Richard W. Beswick; John R. Lenton; Keith J. Edwards (Functional & Integrative Genomics, 2005)

Osteoblast Elastic Modulus Measured by Atomic Force Microscopy Is Substrate Dependent - Erica Takai; Kevin D. Costa; Aisha Shaheen; Clark T. Hung; X. Edward Guo (Annals of Biomedical Engineering, 2005)

Development of anonymous cDNA microarrays to study changes to the Senecio floral transcriptome during hybrid speciation - MATTHEW J. HEGARTY; JOANNA M. JONES; IAN D. WILSON; GARY L. BARKER; JANE A. COGHILL; PATRICIA SANCHEZ‐BARACALDO; GUOQING LIU; RICHARD J. A. BUGGS; RICHARD J. ABBOTT; KEITH J. EDWARDS; SIMON J. HISCOCK (Molecular Ecology, 2005)
Interspecific hybridization is an important process through which abrupt speciation can occur. In recent years, genetic changes associated with hybrid speciation have been identified through a variety of techniques, including AFLP/SSR mapping, GISH/FISH and cDNA‐AFLP differential display. However, progress in using microarray technology to analyse whole genome/transcriptome changes associated with hybrid speciation has been limited due to the lack of extensive sequence data for many hybrid species and the difficulties in extrapolating results from commercially available microarrays for model species onto nonmodel hybrid taxa. Increasingly therefore researchers studying nonmodel systems are turning to the development of ‘anonymous’ cDNA microarrays, where the time and cost of producing microarrays is reduced by printing unsequenced cDNA clones, and sequencing only those clones that display interesting expression patterns. Here we describe the creation, testing and preliminary use of anonymous cDNA microarrays to study changes in floral transcriptome associated with allopolyploid speciation in the genus Senecio. We report a comparison of gene expression between the allohexaploid hybrid, Senecio cambrensis , its parental taxa Senecio squalidus (diploid) and Senecio vulgaris (tetraploid), and the intermediate triploid (sterile) hybrid Senecio × baxteri . Anonymous microarray analysis revealed dramatic differences in floral gene expression between these four taxa and demonstrates the power of this technique for studies of the genetic impact of hybridization in nonmodel flowering plants.

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Nitrogen/phosphorus leaf stoichiometry and the scaling of plant growth - Karl J. Niklas; Thomas Owens; Peter B. Reich; Edward D. Cobb (Ecology Letters, 2005)
We adopted previous N : P stoichiometric models for zooplankton relative growth to predict the relative growth rates of the leaves μ L of vascular plants assuming that annual leaf growth in dry mass is dictated by how leaf nitrogen N L is allocated to leaf proteins and how leaf phosphorus P L is allocated to rRNA. This model is simplified provided that N L scales as some power function of P L across the leaves of different species. This approach successfully predicted the μ L of 131 species of vascular plants based on the observation that, across these species, N L scaled, on average, as the 3/4 power of P L , i.e. N L ∝ P . When juxtaposed with prior allometric theory and observations, our findings suggest that a transformation in N : P stoichiometry occurs when the plant body undergoes a transition from primary to secondary growth.

Nicotinic–serotonergic drug interactions and attentional performance in rats - Amir H. Rezvani; D. Patrick Caldwell; Edward D. Levin (Psychopharmacology, 2005)

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine - Hyun-Sang Cho; Deepak C. D’Souza; Ralitza Gueorguieva; Edward B. Perry; Steven Madonick; Laurence P. Karper; Anissa Abi-Dargham; Aysenil Belger; Walid Abi-Saab; Deborah Lipschitz; Alexandre Bennet; John P. Seibyl; et al. (Psychopharmacology, 2005)

Preliminary evidence of attenuation of the disruptive effects of the NMDA glutamate receptor antagonist, ketamine, on working memory by pretreatment with the group II metabotropic glutamate receptor agonist, LY354740, in healthy human subjects - John H. Krystal; Walid Abi-Saab; Edward Perry; D. Cyril D’Souza; Nianjin Liu; Ralitza Gueorguieva; Lisa McDougall; Tracy Hunsberger; Aysenil Belger; Louise Levine; Alan Breier (Psychopharmacology, 2005)

Nicotine physical dependence and tolerance in the mouse following chronic oral administration - Sheri D. Grabus; Billy R. Martin; Angela M. Batman; Rachel F. Tyndale; Edward Sellers; M. Imad Damaj (Psychopharmacology, 2005)

Climate variability and campylobacter infection: an international study - R. Sari Kovats; Sally J. Edwards; Dominique Charron; John Cowden; Rennie M. D’Souza; Kristie L. Ebi; Charmaine Gauci; Peter Gerner-Smidt; Shakoor Hajat; Simon Hales; Gloria Hernández Pezzi; Bohumir Kriz; et al. (International Journal of Biometeorology, 2005)

Gene regulation in planta by plant-derived engineered zinc finger protein transcription factors - Rachel Holmes-Davis; Guofu Li; Andrew C. Jamieson; Edward J. Rebar; Qiang Liu; Yanhong Kong; Casey C. Case; Philip D. Gregory (Plant Molecular Biology, 2005)

6-Alkylsalicylic Acids and 6-Alkylresorcylic Acids from Ants in the Genus Crematogaster from Brunei - T. H. JONES; S. R. BRUNNER; A. A. EDWARDS; D. W. DAVIDSON; R. R. SNELLING (Journal of Chemical Ecology, 2005)

Molecular Analysis of the Relatedness of Five Domesticated Turkey Strains - Edward J. Smith; Tuoyu Geng; Elizabeth Long; F. William Pierson; D. Phillip Sponenberg; Cal Larson; Robert Gogal (Biochemical Genetics, 2005)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

An efficient climate forecasting method using an intermediate complexity Earth System Model and the ensemble Kalman filter - J. C. Hargreaves; J. D. Annan; N. R. Edwards; R. Marsh (Climate Dynamics, 2004)

The role of nitric oxide in plant growth regulation and responses to abiotic stresses - Małgorzata Kopyra; Edward A. Gwó d (Acta Physiologiae Plantarum, 2004)

Mapping Ds insertions in barley using a sequence-based approach - L. D. Cooper; L. Marquez-Cedillo; J. Singh; A. K. Sturbaum; S. Zhang; V. Edwards; K. Johnson; A. Kleinhofs; S. Rangel; V. Carollo; P. Bregitzer; P. G. Lemaux; et al. (Molecular Genetics and Genomics, 2004)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)

Toxicological Evaluation and QSAR Modelling of Aromatic Amines to Chlorella vulgaris - T. I. Netzeva; J. C. Dearden; R. Edwards; A. D. P. Worgan; M. T. D. Cronin (Bulletin of Environmental Contamination and Toxicology, 2004)

The Chemistry of Exploding Ants, Camponotus SPP. (Cylindricus COMPLEX) - T. H. Jones; D. A. Clark; A. A. Edwards; D. W. Davidson; T. F. Spande; R. R. Snelling (Journal of Chemical Ecology, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

Tree physiological responses to above‐ground herbivory directly modify below‐ground processes of soil carbon and nitrogen cycling - Edward Ayres; James Heath; Malcolm Possell; Helaina I. J. Black; Gerhard Kerstiens; Richard D. Bardgett (Ecology Letters, 2004)
Above‐ground herbivory is ubiquitous in terrestrial ecosystems, yet its impacts on below‐ground processes and consequences for plants remain ambiguous. To examine whether physiological responses of individual trees may potentially modify soil nutrient availability, we subjected Fagus sylvatica L. (European beech) and Abies alba Mill. (silver fir) to simulated foliar herbivory over two growing seasons. Above‐ground herbivory enhanced N mineralization and inorganic N availability in the soil. The total input of C from the plant roots to the soil is not known; however, carbon sequestration in the soil, measured using stable isotopic techniques, was unaffected by herbivory. Fagus responded to herbivory by producing larger leaves, with increased photosynthetic capacity and N content, which largely compensated for the loss of biomass; Abies exhibited no such response. We conclude that despite large interspecific differences in the growth response, tree physiological responses to foliar herbivory are capable of directly modifying soil biological processes.

Sources and predictors of resolvable indel polymorphism assessed using rice as a model - J. D. Edwards; V. M. Lee; S. R. McCouch (Molecular Genetics and Genomics, 2004)

Characterisation of early transcriptional changes involving multiple signalling pathways in the Mla13 barley interaction with powdery mildew ( Blumeria graminis f. sp. hordei ) - Ingo Hein; Edward I. Campbell; Mary Woodhead; Peter E. Hedley; Vanessa Young; Wayne L. Morris; Luke Ramsay; Joerg Stockhaus; Paul R. J. Birch; Gary D. Lyon; Adrian C. Newton (Planta, 2004)

Compositional variations of olivine from the Jinchuan Ni–Cu sulfide deposit, western China: implications for ore genesis - Chusi Li; Zhanghua Xu; Sybrand A. de Waal; Edward M. Ripley; Wolfgang D. Maier (Mineralium Deposita, 2004)

Indentation Determined Mechanoelectrochemical Properties and Fixed Charge Density of Articular Cartilage - X. Lux Lu; Daniel D. N. Sun; X. Edward Guo; Faye H. Chen; W. Michael Lai; Van C. Mow (Annals of Biomedical Engineering, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Chronic transdermal nicotine patch treatment effects on cognitive performance in age-associated memory impairment - Heidi K. White; Edward D. Levin (Psychopharmacology, 2004)

EXPLANT-CELL CULTURE OF PRIMARY MAMMARY TUMORS FROM MMTV-c-Myc TRANSGENIC MICE - XU FANG PEI; MARCIA S. NOBLE; MARIA ANTONIETTA DAVOLI; EDWARD ROSFJORD; MADDALENA T. TILLI; PRISCILLA A. FURTH; ROBERT RUSSELL; MICHAEL D. JOHNSON; ROBERT B. DICKSON (In Vitro Cellular & Developmental Biology - Animal, 2004)

Characterization of 20 microsatellite marker loci in the west Indian rock iguana (Cyclura nubila) - Junghwa An; Julie A. Sommer; Gary D. Shore; Janet E. Williamson; Rick A. Brenneman; Edward E. Louis (Conservation Genetics, 2004)

Mercury in the marine food chain in the Southern Ocean at Macquarie Island: an analysis of a top predator, Patagonian toothfish ( Dissostichus eleginoides ) and a mid-trophic species, the warty squid ( Moroteuthis ingens ) - Tertia McArthur; Edward C. V. Butler; George D. Jackson (Polar Biology, 2003)

Genetic variation and founder effects in the parasitoid wasp, Diaeretiella rapae (M’intosh) (Hymenoptera: Braconidae: Aphidiidae), affecting its potential as a biological control agent - D. A. Baker; H. D. Loxdale; O. R. Edwards (Molecular Ecology, 2003)
The effects of recent colonization on the aphid parasitoid, Diaeretiella rapae (M’Intosh) (Hymenoptera: Braconidae: Aphidiidae), in Western Australia were investigated. When compared with populations from the Old World, the results of a microsatellite analysis show that the insects have low allelic length and low allele frequency variation, revealing that these individuals experienced a significant founder effect. Marked genetic differentiation between populations was also revealed, which has potentially important implications for host utilization in this species when introduced to a new geographical area(s). Low genetic variation and gene flow in a founder population could limit evolutionary potential in Australia, including the ability of a population to mount a response to newly introduced hosts, such as the Russian wheat aphid, Diuraphis noxia (Mordvilko). Although the actual importance of genetic diversity in the success of biological control agents is unclear, current theory concerning the potential impact of genetic bottlenecks on additive genetic variance is discussed.

Family history and colorectal cancer: predictors of risk - M.L. Slattery; T.R. Levin; K. Ma; D. Goldgar; R. Holubkov; S. Edwards (Cancer Causes & Control, 2003)

NMDA receptor antagonist effects, cortical glutamatergic function, and schizophrenia: toward a paradigm shift in medication development - John H. Krystal; D. Cyril D'Souza; Daniel Mathalon; Edward Perry; Aysenil Belger; Ralph Hoffman (Psychopharmacology, 2003)

Adolescent-onset nicotine self-administration modeled in female rats - Edward D. Levin; Amir H. Rezvani; Daniel Montoya; Jed E. Rose; H. Scott Swartzwelder (Psychopharmacology, 2003)

Involvement of Nrf2 and JNK1 in the Activation of Antioxidant Responsive Element (ARE) by Chemopreventive Agent Phenethyl Isothiocyanate (PEITC) - Young-Sam Keum; Edward D. Owuor; Bok-Ryang Kim; Rong Hu; A.-N. Tony Kong (Pharmaceutical Research, 2003)

Effects of a fire-retardant chemical to fathead minnows in experimental streams - Robin D. Calfee; Edward E. Little (Environmental Science and Pollution Research, 2003)

PCB Congener Distribution in Estuarine Water, Sediment and Fish Samples: Implications for Monitoring Programs - Thomas J. Fikslin; Edward D. Santoro (Environmental Monitoring and Assessment, 2003)

Transcytosis of GCSF-Transferrin Across Rat Alveolar Epithelial Cell Monolayers - Adam Widera; Kwang-Jin J. Kim; Edward D. Crandall; Wei-Chiang Shen (Pharmaceutical Research, 2003)

Differences in native soil ecology associated with invasion of the exotic annual chenopod, Halogeton glomeratus - Jeffrey J. Duda; D. Carl Freeman; John M. Emlen; Jayne Belnap; Stanley G. Kitchen; John C. Zak; Edward Sobek; Mary Tracy; James Montante (Biology and Fertility of Soils, 2003)

Dendroclimatic signals in long tree‐ring chronologies from the Himalayas of Nepal - Edward R. Cook; Paul J. Krusic; Philip D. Jones (International Journal of Climatology, 2003)
We describe the development of a tree‐ring chronology network in Nepal that is suitable for reconstructing temperature‐related climate forcing over the past few hundred years. The network is composed of 32 tree‐ring chronologies and is represented by five indigenous tree species. An empirical orthogonal function analysis of the chronologies over the common interval 1796–92 indicates the existence of coherent large‐scale signals among the tree‐ring chronologies that are hypothesized to reflect, in part, broad‐scale climate forcing related to temperatures. A long monthly temperature record for Kathmandu is developed and used to test this hypothesis. In so doing, significant monthly and seasonal temperature responses are identified that provide guidance for the formal reconstruction of two temperature seasons: February–June (1546–91) and October–February (1605–91). Each reconstruction indicates the occurrence of unusually cold temperatures in 1815–22, which coincides with the eruption of Tambora in Indonesia. A novel method is also used to add probable missing multi‐centennial temperature variance to each reconstruction. The resulting ‘adjusted’ reconstructions strongly reflect patterns of temperature variability associated with Little Ice Age cooling and warming into the 20th century, with the October–February season exhibiting the strongest increase in temperature over the past ∼400 years. Only the October–February season shows any evidence for late‐ 20th century warming, whereas February–June temperatures have actually cooled since 1960 (as with the observational series). Copyright © 2003 Royal Meteorological Society

Effects of ultraviolet radiation on toad early life stages - Edward E. Little; Robin D. Calfee; David L. Fabacher; Cynthia Carey; Vicki S. Blazer; Elizabeth M. Middleton (Environmental Science and Pollution Research, 2003)

Minisatellite DNA profiling detects lineages and parentage in the endangered kakapo (Strigops habroptilus) despite low microsatellite DNA variation - Hilary C. Miller; David M. Lambert; Craig D. Millar; Bruce C. Robertson; Edward O. Minot (Conservation Genetics, 2003)

Sometimes you see them, sometimes you don't: IPSCs in the rat superficial superior colliculus - Michelle D. Edwards; Bettina Platt (Experimental Brain Research, 2003)

Parallel changes in agonistic and non-agonistic behaviors during dominance hierarchy formation in crayfish - J. Herberholz; M. M. Sen; D. H. Edwards (Journal of Comparative Physiology A, 2003)

Parallels and contrasts between iron and copper metabolism - Michael D. Garrick; Marco T. Núñez; Manuel Olivares; Edward D. Harris (BioMetals, 2003)

Pretranslational control of Menkes disease gene expression - Edward D. Harris; Manchi C.M. Reddy; Sudeep Majumdar; Mariela Cantera (BioMetals, 2003)

Class I molecules with similar peptide-binding specificities are the result of both common ancestry and convergent evolution - Alessandro Sette; John Sidney; Brian D. Livingston; John L. Dzuris; Claire Crimi; Christopher M. Walker; Scott Southwood; Edward J. Collins; Austin L. Hughes (Immunogenetics, 2003)

Optimized Region Finding and Edge Detection of Knee Cartilage Surfaces from Magnetic Resonance Images - Elsa D. Angelini; Edward J. Ciaccio (Annals of Biomedical Engineering, 2003)

Body mass index and colon cancer: an evaluation of the modifying effects of estrogen (United States) - M.L. Slattery; Rachel Ballard-Barbash; Sandra Edwards; Bette J. Caan; John D. Potter (Cancer Causes & Control, 2003)

Chlorophyll reduction in the seed of Brassica napus with a glutamate 1-semialdehyde aminotransferase antisense gene* - Edward W.T. Tsang; Jingyi Yang; Qing Chang; Goska Nowak; Allan Kolenovsky; D. Ian McGregor; Wilfred A. Keller (Plant Molecular Biology, 2003)

Incidence of Stress in Benthic Communities along the U.S. Atlantic and Gulf of Mexico Coasts within Different Ranges of Sediment Contamination from Chemical Mixtures - Jeffrey L. Hyland; W. Leonard Balthis; Virginia D. Engle; Edward R. Long; John F. Paul; J. Kevin Summers; Robert F. Van Dolah (Environmental Monitoring and Assessment, 2003)

N ylon B arium S ulphate G illnet R educes P orpoise and S eabird M ortality - Edward A. Trippel; Norman L. Holy; Debra L. Palka; Travis D. Shepherd; Gary D. Melvin; John M. Terhune (Marine Mammal Science, 2003)

Does the cerebellum play a role in podokinetic adaptation? - Gammon M. Earhart; William A. Fletcher; Fay B. Horak; Edward W. Block; Kimberly D. Weber; Oksana Suchowersky; Geoffrey Melvill Jones (Experimental Brain Research, 2002)

Random amplified polymorphic DNA analysis of kinship within host-associated populations of the symbiotic water mite Unionicola foili (Acari: Unionicolidae) - Dale D. Edwards; Daniel E. Deatherage; Brian R. Ernsting (Experimental and Applied Acarology, 2002)

Characterization of the flanking regions of Zea mays microsatellites reveals a large number of useful sequence polymorphisms - R. Mogg; J. Batley; S. Hanley; D. Edwards; H. O'Sullivan; K. Edwards (Theoretical and Applied Genetics, 2002)

Book Review: Hubbert's Peak: The Impending World Oil Shortage. Kenneth S. Deffeyes, Princeton University Press, 2002, 203 p., ISBN 0-691-09086-6, U.S. $24.95 - John D. Edwards (Natural Resources Research, 2002)

Auditory Temporal Computation: Interval Selectivity Based on Post-Inhibitory Rebound - Edward W. Large; John D. Crawford (Journal of Computational Neuroscience, 2002)

Introduction Special Issue on Locally Conservative Numerical Methods for Flow in Porous Media - Michael G. Edwards; Raytcho D. Lazarov; Ivan Yotov (Computational Geosciences, 2002)

On birth and death in the sea - Mark D. Ohman; Jeffrey A. Runge; Edward G. Durbin; David B. Field; Barbara Niehoff (Hydrobiologia, 2002)

Region Specific Modeling of Cardiac Muscle: Comparison of Simulated and Experimental Potentials - Adam L. Muzikant; Edward W. Hsu; Patrick D. Wolf; Craig S. Henriquez (Annals of Biomedical Engineering, 2002)

DIETS OF FIN, SEI, AND SPERM WHALES IN BRITISH COLUMBIA: AN ANALYSIS OF COMMERCIAL WHALING RECORDS, 1963–1967 - Rowenna D. Flinn; Andrew W. Trites; Edward J. Gregr; R. Ian Perry (Marine Mammal Science, 2002)
A bstract Diets of fin ( Balaenoptera physalus ), sei ( Balaenoptera borealis ), and sperm whales ( Physeter macrocephalus ) were estimated from the stomach contents of individuals killed along the British Columbia coast from 1963 to 1967. The dominant prey types of fin whales were euphausiids, with minor contributions from copepods and fish. Sei whale stomachs contained primarily copepods in three years, whereas euphausiids or a variety of fish dominated the diet in the other two years. Sperm whales consumed primarily North Pacific giant squid ( Moroteuthis robusta ), but secondary prey differed between males and females. Female sperm whales frequently consumed ragfish ( Icosteus spp.) and other fish, whereas the male diet also contained rockfish ( Sebastes spp.). The high abundance of euphausiids along the British Columbia coast likely contributed to the presence of a summer resident population of fin whales. The high abundance of large copepods farther north probably influenced the migration of sei whales through the offshore waters of British Columbia. Sperm whale stomach contents differed by sex reflecting location and possibly breeding behaviors.

Dry matter production and boron concentrations of vegetative and reproductive tissues of canola and sunflower plants grown in nutrient solution - A. Asad; F. P. C. Blamey; D. G. Edwards (Plant and Soil, 2002)

A high degree of genetic diversity is revealed in Isatis spp. (dyer's woad) by amplified fragment length polymorphism (AFLP) - K. Gilbert; S. Garton; M. Karam; G. Arnold; A. Karp; K. Edwards; D. Cooke; J. Barker (Theoretical and Applied Genetics, 2002)

Development and mapping of SSR markers for maize - Natalya Sharopova; Michael D. McMullen; Linda Schultz; Steve Schroeder; Hector Sanchez-Villeda; Jack Gardiner; Dean Bergstrom; Katherine Houchins; Susan Melia-Hancock; Theresa Musket; Ngozi Duru; Mary Polacco; et al. (Plant Molecular Biology, 2002)

Trends in application of gas-phase bioreactors - Edward D. Schroeder (Reviews in Environmental Science and Bio/Technology, 2002)

A modeling study of the interaction and electron transfer between cytochrome b 5 and some oxidized haemoglobins - Richard D. Kidd; Edward N. Baker; Thomas Brittain (JBIC Journal of Biological Inorganic Chemistry, 2002)

Parallel Cascade Recognition of Exon and Intron DNA Sequences - Michael J. Korenberg; Edward D. Lipson; James R. Green; Jerry E. Solomon (Annals of Biomedical Engineering, 2002)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

The C1 locus in maize (Zea mays L.): effect on gene expression - J. Edwards; D. Stoltzfus; P. A. Peterson (Theoretical and Applied Genetics, 2001)

A Weichselian deglaciation model applied to the Early Permian glaciation in the northeast Karoo Basin, South Africa - Sylvi Haldorsen; Victor Von Brunn; Rodney Maud; Edward D. Truter (Journal of Quaternary Science, 2001)
It generally is assumed that the Early Permian Gondwana deglaciation in South Africa started with a collapse of the marine ice‐sheet. The northeast part of the Karoo Basin became ice‐free as a result of this collapse. The deglaciation here probably took place under temperate glacial conditions. Three glacial phases have been identified. Phase 1: the marine ice retreat of 400 km over the northeast Karoo Basin, which may have been completed over a few thousand years. The glaciers grounded in the shallower areas around the shore of the basin. Phase 2: the smaller, now mainly continental ice‐sheet here re‐stabilised and remained more or less stationary for several tens of thousand years. During this phase, between 50 and 200 m of massive glaciomarine mud with dropstones accumulated in the open, marine basin that became ice‐free during Phase 1. Isostatic uplift, as a response to the first rapid deglaciation phase, can be traced in the inland part of the region. Phase 3: the final deglaciation may have taken 10 to 20 kyr. After this time no new ice sheet was built up over southern Africa. The entire Early Permian deglaciation of the northeast Karoo Basin was completed within thousands rather than millions of years. Phases 1 and 3 had lengths similar to typical Quaternary deglaciations, whereas Phase 2 was a long, stable phase, more similar to a full Quaternary glaciation. Copyright © 2001 John Wiley & Sons, Ltd.

A maize bacterial artificial chromosome (BAC) library from the European flint inbred line F2 - D. M. O’Sullivan; P. J. Ripoll; M. Rodgers; K. J. Edwards (Theoretical and Applied Genetics, 2001)

The test-retest reliability of gas exchange kinetics in humans using a pseudo random binary sequence exercise test - A. M. Edwards; N. V. Challis; J. H. Chapman; D. B. Claxton; M. L. Fysh (European Journal of Applied Physiology, 2001)

Potassium nutrition effects on seed alkaloid concentrations, yield and mineral content of lupins (Lupinus angustifolius) - P. Gremigni; M. T. F. Wong; N. K. Edwards; D. Harris; J. Hamblin (Plant and Soil, 2001)

STATUS AND ECOLOGY OF SOTALIA FLUVIATILIS IN THE CAYOS MISKITO RESERVE, NICARAGUA - Holly H. Edwards; Gary D. Schnell (Marine Mammal Science, 2001)
A bstract In March through May of 1996–1998, we conducted research in the Cayos Miskito Reserve, Nicaragua, to assess the status, ecology, and distribution of Sotalia fluviatilis , a dolphin known from southern Brazil to Honduras. Aerial and boat surveys of lagoons, inlets, and coastal areas were conducted and observational information collected on Sotalia activity, behavior, and other factors relating to its ecology. During boat surveys 183 groups (536 individuals) were sighted (for areas with Sotalia , mean overall density = 0.604 individuals/km 2 , coastal areas = 0.647/km 2 , inlets = 0.578/km 2 , and lagoons = 0.486/km 2 ). Overall, based on all sightings, mean group size was 3.01 (SD = 1.79, range 1–15) and varied among years ( x̄ = 4.20 in 1996, 2.58 in 1997, and 3.39 in 1998), but not for different months. We estimate that 49 Sotalia inhabited the portions of the Reserve we studied. Sightings of Sotalia groups were non‐random (nearest‐neighbor analysis); clumping of sightings indicates that some areas were preferred. In both Pahara inlet and Wauhta lagoon, sightings were more frequent after 1200 than in the morning. In coastal areas Sotalia were sighted most often within 100 m of shore (54.0%), less often from 101 to 200 m (39.1%), and infrequently from 201 to 300 m (6.8%). Seldom were animals observed in more than 5 m of water, and usually it was considerably shallower ( i. e. , i. e. , traveling, feeding, socializing, resting, and other), based on time of group sighting (70.3%) and during instantaneous sampling (56.3%). Resource distribution appears to be an important factor influencing Sotalia distribution in the Reserve.

The Downstream Activation Sequence of the Strict Late Herpes Simplex Virus Type 1 UL38 Promoter Interacts With hTAFII70, a Component of TFIID - Matthew D. Petroski; Gayathri B. Devi-Rao; Marcia K. Rice; Edward K. Wagner (Virus Genes, 2001)

The ctenophore Mnemiopsis in native and exotic habitats: U.S. estuaries versus the Black Sea basin - Jennifer E. Purcell; Tamara A. Shiganova; Mary Beth Decker; Edward D. Houde (Hydrobiologia, 2001)

Identification of amino acids in the leader peptide of Methanococcus voltae preflagellin that are important in posttranslational processing - Nikhil A. Thomas; Edward D. Chao; Ken F. Jarrell (Archives of Microbiology, 2001)

Breeding biology, resource partitioning and reproductive effort of a dioecious shrub, Clutia pulchella L. (Euphorbiaceae) - D. I. Thompson; T. J. Edwards (Plant Systematics and Evolution, 2001)

A Useful In Vitro Model for Transport Studies of Alveolar Epithelial Barrier - Kwang-Jin Kim; Zea Borok; Edward D. Crandall (Pharmaceutical Research, 2001)

The CD45 locus in cattle: allelic polymorphism and evidence for exceptional positive natural selection - Keith T. Ballingall; Lillian Waibochi; Declan J. McKeever; Edward C. Holmes; Christopher H. Woelk; Niall D. MacHugh; Vittoria Lutje (Immunogenetics, 2001)

Tissue distribution and functional expression of the human voltage-gated sodium channel β3 subunit - Edward B. Stevens; Peter J. Cox; Bhaval S. Shah; Alistair K. Dixon; Peter J. Richardson; Robert D. Pinnock; Kevin Lee (Pflügers Archiv - European Journal of Physiology, 2001)

AN IN VITRO MODEL FOR MURINE URETERIC EPITHELIAL CELLS - P. LaMont Bryant; Lola M. Reid; Edward S. Diala; Barbara D. Abbott; Angela R. Buckalew (In Vitro Cellular & Developmental Biology - Animal, 2001)

Progressive crustal contamination of the Bushveld Complex: evidence from Nd isotopic analyses of the cumulate rocks - Wolfgang D. Maier; Nicholas T. Arndt; Edward A. Curl (Contributions to Mineralogy and Petrology, 2000)

Ontogeny of Alarm Pheromone Secretion in Pea Aphid, Acyrthosiphon pisum - Edward B. Mondor; D. Scott Baird; K. N. Slessor; B. D. Roitberg (Journal of Chemical Ecology, 2000)

Physical Characterization of Large Porous Particles for Inhalation - Rajiv Gupta; R Vanbever; J Mintzes; J Nice; D Chen; R Batycky; R Langer; DA Edwards (Pharmaceutical Research, 2000)

Genome scan identifies a locus affecting gamma-globin level in human beta-cluster YAC transgenic mice - Sluan D. Lin; Phil Cooper; Jingly Fung; Heinz-Ulrich G. Weier; Edward M. Rubin (Mammalian Genome, 2000)

The Potato Association of America - Steven R. James; Lori Wing; Ronald Knight; Barbara Harrity; Devid H. Lambert; Bud Platt; Al Reeves; Bill Bohl; Lind Sanford; Alexander D. Pavlista; Ed Plissey; Richard Sawyer; et al. (American Journal of Potato Research, 2000)

Nociceptin/orphanin FQ (N/OFQ) induces a quasi-morphine abstinence syndrome in the rat - David H. Malin; J. Ronald Lake; William D. Moon; Debora Moy; Ana L. Montellano; Edward Moy; Tracy D. Campbell; Maurice V. Bell; Dana Bryant; Laura M. Harrison; David K. Grandy (Psychopharmacology, 2000)

Effects of pH and Dose on Nasal Absorption of Scopolamine Hydrobromide in Human Subjects - Shamim Ahmed; Anthony P. Sileno; Jorge C. deMeireles; Ramneik Dua; Harish K. Pimplaskar; Wei J. Xia; John Marinaro; Edward Langenback; Frank J. Matos; Lakshmi Putcha; Vincent D. Romeo; Charan R. Behl (Pharmaceutical Research, 2000)

Colon cancer screening, lifestyle, and risk of colon cancer - Martha L. Slattery; Sandra L. Edwards; Khe Ni Ma; Gary D. Friedman (Cancer Causes & Control, 2000)

Vasodilator effects of KRN2391, levcromakalim and 3-morpholino-sydnonimin in human pial and omental arteries - Jesper Petersson; Torsten Ryman; Edward D. Högestätt (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Has the Attraction of Predatory Coccinellids to Cornicle Droplets Constrained Aphid Alarm Signaling Behavior? - Edward B. Mondor; Bernard D. Roitberg (Journal of Insect Behavior, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

Surface pollen‐vegetation relationships on the Atlantic seaboard: South Uist, Scotland - Barbara A. Brayshay; David D. Gilbertson; Martin Kent*; Kevin J. Edwards; Peter Wathern; Ruth E. Weaver (Journal of Biogeography, 2000)
Studies of modern pollen rain from remote islands have raised a number of interesting issues concerning the spatial precision of present‐day pollen spectra in relation to their parent plant community types. This paper examines the relationships and degree of correlation between a sequence of contemporary vegetation types, environments and their associated surface pollen spectra from a transect across the island of South Uist in the Outer Hebrides of Scotland. Paired data on both contemporary vegetation and associated surface pollen assemblages have been collected and analysed using methods of numerical classification and ordination. In general terms, the modern pollen rain on South Uist reflects the major changes in vegetation pattern and the major community types fairly closely. The major boundary between the alkaline machair sand dune communities and the various acidic upland vegetation types is particularly clear. However, both variability in the vegetation and the effects of the strong prevailing westerly and south‐westerly winds tend to blur the boundaries of the various communities within each of these larger categories. On average 86.6% of the palynomorphs come from in‐community quadrat sources, while only 1.3% are from off‐island sources. The limited present‐day tree distribution on the transect is discussed in the context of the more widespread distribution of arboreal pollen. Overall, there is a strong numerical correspondence between vegetation, pollen and environmental variables. The various problems inherent in examining surface pollen spectra are reviewed.

The structure and function of orchid pollinaria - S. D. Johnson; T. J. Edwards (Plant Systematics and Evolution, 2000)

Relationships between sclerophylly, leaf biomechanical properties and leaf anatomy in some Australian heath and forest species - Cheryl Edwards; Gordon D. Sanson; Nuvan Aranwela; Jennifer Read (Plant Biosystems, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Photoenhanced toxicity of a weathered oil onCeriodaphnia dubia reproduction - Robin D. Calfee; Edward E. Little; Laverne Cleveland; Mace G. Barron (Environmental Science and Pollution Research, 1999)

Formulation and Physical Characterization of Large Porous Particles for Inhalation - Rita Vanbever; Jeffrey D. Mintzes; Jue Wang; Jacquelyn Nice; Donghao Chen; Richard Batycky; Robert Langer; David A. Edwards (Pharmaceutical Research, 1999)

Partition Constants and Adsorption/Desorption Hysteresis for Volatile Organic Compounds on Soil from a Louisiana Superfund Site - Kalliat T. Valsaraj; Raghava R. Kommalapati; Edward D. Robertson; W. D. Constant (Environmental Monitoring and Assessment, 1999)

Correspondence between Ontogenetic Shifts in Morphology and Habitat Use in Minnow Phoxinus Phoxinus - Predrag D. Simonović; Paul Garner; Edward A. Eastwood; Vladimír Kováč; Gordon H. Copp (Environmental Biology of Fishes, 1999)

Mazeno Pass Pluton and Jutial Pluton, Pakistan Himalaya: age and implications for entrapment mechanisms of two granites in the Himalaya - D. A. Schneider; M. A. Edwards; P. K. Zeitler; C. D. Coath (Contributions to Mineralogy and Petrology, 1999)

Hormone replacement therapy and improved survival among postmenopausal women diagnosed with colon cancer (USA) - Martha L. Slattery; Kristin Anderson; Wade Samowitz; Sandra L. Edwards; Karen Curtin; Bette Caan; John D. Potter (Cancer Causes & Control, 1999)

MHC characterization of ALR and ALS mice: respective similarities to the NOD and NON strains - Robert T. Graser; Clayton E. Mathews; Edward H. Leiter; D. V. Serreze (Immunogenetics, 1999)

RAPD divergence caused by microsite edaphic selection in wild barley - Edward D. Owuor; Tzion Fahima; Alex Beharav; Abraham Korol; Eviatar Nevo (Genetica, 1999)

Choosing a Forest Vision - Donald W. Floyd; Kelsey Alexander; Charles Burley; Arthur W. Cooper; Arthur DuFault; Ross W. Gorte; Sharon G. Haines; Bruce B. Hronek; Chadwick D. Oliver; Edward W. Shepard (Journal of Forestry, 1999)
It is unlikely, given the often-contentious history of the national forests, that incremental change in their administration can resolve fundamental differences in values. So concludes a task force appointed by the Society of American Foresters (SAF) to review federal forest management; its analysis and recommendations have been published in Forest of Discord: Options for Governing Our National Forests and Federal Public Lands. Whereas the Committee of Scientists was asked to stay within the framework of current laws and regulations, the SAF analysts were not so constrained. The following excerpts from Forest of Discord summarize the reasons that fundamental legislative and regulatory change is warranted and consider the purpose of having national forests and public lands.

Assessing Trace Element Uptake by Vegetation on a Coal Fly Ash Landfill - Peter B. Woodbury; Gail Rubin; D. C. McCune; Leonard H. Weinstein; Edward F. Neuhauser (Water, Air, & Soil Pollution, 1999)

Servicizing the Chemical Supply Chain - Edward D. Reiskin; Allen L. White; Jill Kauffman Johnson; Thomas J. Votta (Journal of Industrial Ecology, 1999)
Summary Servicizing—the transformation from product‐to service‐based enterprise—is a major force in changing how firms manage material input, throughput, and output. Redefinition of the firm as a service provider instead of a product manufacturer means that function, not form, is the source of added value delivered to the customer. To realize the dematerialization benefits of such a transformation requires a fundamental realignment of the supplier‐customer relationship. Instead of the traditional incentives to maximize the volume of physical product sold, servicizing requires a partnership wherein the financial rewards of reduced material consumption are shared between supplier and customer. We illustrate this partnership concept with the example of chemical management services (CMS), an approach that is gaining momentum in the automobile and electronics sector. Compensation and gain‐sharing based on chemical efficiency and chemical use reduction, often tied to fixed price mechanisms, lie at the core of the CMS model. Diffusion of the servicizing model holds much promise for driving dematerialization while reducing the environmental burden of product manufacturers.

Seasonal Sulfate Deposition and Export Patterns for a Small Appalachian Watershed - Pamela J. Edwards; James D. Gregory; H. Lee Allen (Water, Air, & Soil Pollution, 1999)

Climate and environment during the Younger Dryas (GS-1) as reflected by composite stable isotope records of lacustrine carbonates at Torreberga, southern Sweden - Dan Hammarlund; Thomas W. D. Edwards; Svante Björck; Bjørn Buchardt; Barbara Wohlfarth (Journal of Quaternary Science, 1999)

Climate and environment during the Younger Dryas (GS-1) as reflected by composite stable isotope records of lacustrine carbonates at Torreberga, southern Sweden - Dan Hammarlund; Thomas W. D. Edwards; Svante Björck; Bjørn Buchardt; Barbara Wohlfarth (Journal of Quaternary Science, 1999)

The biosynthetic relationship between littorine and hyoscyamine in transformed roots of Datura stramonium - I. Zabetakis; R. Edwards; John T. G. Hamilton; D. O'Hagan (Plant Cell Reports, 1998)

Review Geographic differences in host specialization between the symbiotic water mites Unionicola formosa and Unionicola foili (Acari: Unionicolidae) - Dale D. Edwards; Regan Bogardus; Nicholaus Wilhite (Experimental and Applied Acarology, 1998)

Isolation and characterization of an Arabidopsis thaliana C-8,7 sterol isomerase: functional and structural similarities to mammalian C-8,7 sterol isomerase/emopamil-binding protein - Robert J. Grebenok; Thomas E. Ohnmeiss; Alvin Yamamoto; Edward D. Huntley; David W. Galbraith; Dean Della Penna (Plant Molecular Biology, 1998)

Genes regulating copper metabolism - Edward D. Harris; Yongchang Qian; M.C.M. Reddy (Molecular and Cellular Biochemistry, 1998)

Taurine indirectly increases [Ca]i by inducing Ca2+ influx through the Na+-Ca2+ exchanger - Ghassan Bkaily; Doris Jaalouk; Sawsan Sader; Hadia Shbaklo; Pierre Pothier; Danielle Jacques; Pedro D'Orléans-Juste; Edward J. Cragoe; forename Bose (Molecular and Cellular Biochemistry, 1998)

Relic permafrost structures in the Gobi of Mongolia: age and significance - Lewis A. Owen; Ben Richards; Edward J. Rhodes; W. Dickson Cunningham; Brian F. Windley; J. Badamgarav; D. Dorjnamjaa (Journal of Quaternary Science, 1998)

The effects of ultraviolet‐B radiation on freshwater invertebrates: Experiments with asolar simulator - Robin D. Hurtubise; John E. Havel; Edward E. Little (Limnology and Oceanography, 1998)
There is concern that decreases in stratospheric ozone will lead to hazardous levels of ultraviolet‐B (UV‐B) radiation at the Earth's surface. In clear water, UV‐B may penetrate to significant depths. The purpose of the current study was to compare the sensitivity of freshwater invertebrates to UV‐B. We used a solar simulator, calibrated to match local ambient solar radiation, to expose five species of freshwater invertebrates to enhanced levels of UV‐B radiation. UV‐B measurements in a eutrophic pond revealed that 10% of the irradiance penetrated to 30‐cm depth and 1% to 57‐cm depth. The irradiance at the upper 5–20 cm was comparable to levels used in the simulator. Median lethal dose (LD50) values were determined for the cladocerans Ceriodaphnia reticulata , Scapholeberis kingii (two induced color morphs), and Daphnia magna ; the ostracod Cyprinotus incongruens ; and the amphipod Hyalella azteca . Among the species, 96‐h LD50 estimates were quite variable, ranging from 4.2 to 84.0 µW cm −2 . These estimates indicated S. kingii to be highly sensitive and H. azteca , C. reticulata , and D. magna to be moderately sensitive, whereas the ostracod C. incongruens was very tolerant to UV‐B radiation. Overall, this study suggests that, in shallow ponds without physical refuges, UV‐B radiation would have the strongest effects upon cladocerans and amphipods occurring in the water column, whereas ostracods would be better protected.

Effect of environmental temperature on the interactive developmental toxicity of radiofrequency radiation and 2-methoxyethanol in rats - B. K. Nelson; D. L. Conover; E. F. Krieg Jr; D. L. Snyder; R. M. Edwards (International Archives of Occupational and Environmental Health, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Characterising food‐webs in two New Zealand streams - N. G. Jaarsma; S. M. de Boer; C. R. Townsend; R. M. Thompson; E. D. Edwards (New Zealand Journal of Marine and Freshwater Research, 1998)
The food‐web communities of two stony tributaries of the Taieri River in New Zealand were documented. We placed heavy emphasis on algal and macroinvertebrate taxonomy, identifying most taxa to species or morpho‐species level. Food‐web attributes were derived from symmetrical matrices using an Excel macro. The values of the food‐web attributes are generally consistent with generalities that have previously been reported in food‐web studies, although some hypothesisied relationships between connectance and food‐web size did not hold. The patterns detected were robust to the inclusion or exclusion of species that were identified in gut contents but not in field samples. The attributes strongly reflected the trophic status of the streams. Dempsters Creek was classified as autotrophic (based on high primary production and a high ratio of production to respiration) and displayed a larger food‐web size and longer food‐chains than those seen in Healy Creek, which was classified as hetero‐trophic (lower primary production and production to respiration ratio). The importance of dynamic environmental attributes such as production and disturbance in structuring food‐webs is emphasised in this study.

Sequence of a Menkes-type Cu-transporting ATPase from Rat C6 Glioma Cells: Comparison of the rat protein with other mammalian Cu-transporting ATPases - Yongchang Qian; Evelyn Tiffany-Castiglioni; Edward D. Harris (Molecular and Cellular Biochemistry, 1998)

A cluster of stearoyl CoA desaturase genes, Scd1 and Scd2, on mouse Chromosome 19 - D. E. Tabor; Y. -R. Xia; M. Mehrabian; P. A. Edwards; A. J. Lusis (Mammalian Genome, 1998)

Digital analysis of multispectral airborne imagery of coral reefs - P. J. Mumby; E. P. Green; C. D. Clark; A. J. Edwards (Coral Reefs, 1998)

Combined stimulation of the glycine and polyamine sites of the NMDA receptor attenuates NMDA blockade-induced learning deficits of rats in a 14-unit T-maze - Robert C. Meyer; Jennifer Knox; Darren A. Purwin; Edward L. Spangler; D. K. Ingram (Psychopharmacology, 1998)

Coral reef habitat mapping: how much detail can remote sensing provide? - P. J. Mumby; E. P. Green; A. J. Edwards; C. D. Clark (Marine Biology, 1997)

The Pharmacokinetics and Electroencephalogram Response of Remifentanil Alone and in Combination with Esmolol in the Rat - Sam H. Haidar; J. Edward Moreton; Zhongming Liang; John R Hoke; Keith T. Muir; Natalie D. Eddington (Pharmaceutical Research, 1997)

Mapping to Chromosomes 1 and 12 of mouse homologs of human protein tyrosine phosphatase, receptor-type, related genes encoding pancreatic beta cell autoantigens - Edward H. Leiter; Hideki Tsumura; David V. Serreze; Harold D. Chapman; Daniel U. Rabin; Michael S. Lan; Abner L. Notkins (Mammalian Genome, 1997)

Population genetic response to microsite ecological stress in wild barley, Hordeum spontaneum - Edward D. Owuor; Tzion Fahima; Avigdor Beiles; Abraham Korol; Eviatar Nevo (Molecular Ecology, 1997)
Genetic diversity was studied in six subpopulations (a total of 60 individuals) of wild barley, Hordeum spontaneum , the progenitor of cultivated barley, sampled from six stations located along a transect of 300 m across the two opposing slopes of ‘Evolution Canyon’, a Mediterranean microsite at Lower Nahal Oren, Mt Carmel. The two opposing slopes are separated by between 100 and 400 m and designated SFS (South‐Facing Slope) and NFS (North‐Facing Slope) with each having three equidistant test stations. The SFS, which receives up to 300% more solar radiation, is drier, ecologically more heterogeneous, fluctuating, and more stressful than the NFS. Analysis of 12 RAPD primers, representing a total of 51 putative loci, revealed a significant inter‐ and intraslope variation in RAPD band polymorphism. A significantly higher proportion of polymorphic RAPD loci was found amongst the subpopulations on the SFS (mean P = 0.909) than on the NFS (mean P = 0.682), on the basis of the presence and absence of 22 strong bands. Polymorphism generally increased upwards from the bottom to the top of the SFS (0.636, 0.773, 0.955) and NFS (0.409, 0.500, 0.545), respectively. Gametic phase disequilibria estimates, D, revealed SFS and NFS unique predominant combinations which sharply differentiated the two slopes and indicated that there is differential interslope selection favouring slope‐specific multilocus combinations of alleles, or blocks of genes over tens to hundreds of meters. This suggests that selection overrides migration. RAPD polymorphism appears to parallel allozyme diversity which is climatically adaptive and driven by natural selection in the same subpopulations at the microsite.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Minimum sample sizes for identifying chromosomal fragile sites from individuals: Monte Carlo estimation - I. F. Greenbaum; J. K. Fulton; Edward D. White; P. Fred Dahm (Human Genetics, 1997)

Hydrologic control on the oxygen-isotope relation between sediment cellulose and lake water, western Taimyr Peninsula, Russia: Implications for the use of surface-sediment calibrations in paleolimnology - Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 1997)

Self-learning fuzzy control of atracurium-induced neuromuscular block during surgery - D. G. Mason; J. J. Ross; N. D. Edwards; D. A. Linkens; C. S. Reilly (Medical & Biological Engineering & Computing, 1997)

Short communicationMeasurement of cell surface hydrophobicity of Aeromonas salmonicida - D Deere; J Porter; R W Pickup; C Edwards (Journal of Fish Diseases, 1997)

GDNF improves survival and reduces apoptosis in human embryonic dopaminergic neurons in vitro - Edward D. Clarkson; W. Michael Zawada; Curt R. Freed (Cell and Tissue Research, 1997)

Lead transport in IEC-6 intestinal epithelial cells - Christopher M. Dekaney; Edward D. Harris; Gerald R. Bratton; Laurie A. Jaeger (Biological Trace Element Research, 1997)

The amino acid sequence of the light chain of Acanthamoeba myosin IC - ZHEN-YUAN WANG; JUN SAKAI; PAUL T. MATSUDAIRA; IVAN C. BAINES; JAMES R. SELLERS; JOHN A. HAMMER III; EDWARD D. KORN (Journal of Muscle Research and Cell Motility, 1997)

Establishment of serial persistent infections with bovine viral diarrhoea virus in cattle and sheep and changes in epitope expression related to host species - D. Paton; M. Gunn; J. Sands; F. Yappl; T. Drew; S. Vilcek; S. Edwards (Archives of Virology, 1997)

Hormone replacement therapy, reproductive history, and colon cancer: a multicenter, case-control study in the United States - Ellen Kampman; John D. Potter; Martha L. Slattery; Bette J. Caan; Sandra Edwards (Cancer Causes & Control, 1997)

Spatial variability in the naphthalene mineralization response to oxygen, nitrate, and orthophosphate amendments in MGP aquifer sediments - Neal D. Durant; Constance A.A. Jonkers; Edward J. Bouwer (Biodegradation, 1997)

Book review - Edward D. Harris (In Vitro Cellular & Developmental Biology - Animal, 1997)

Relation between delayed impairment of cerebral energy metabolism and infarction following transient focal hypoxia-ischaemia in the developing brain - R. M. Blumberg; E. B. Cady; J. S. Wigglesworth; J. E. McKenzie; A. D. Edwards (Experimental Brain Research, 1997)

A computer-controlled aortic and mitral valve occluder - Steven B. Solomon; Srdjan D. Nikolic; Robert W. M. Frater; Edward L. Yellin (Annals of Biomedical Engineering, 1997)

AN AIR TRANSPORT CLIMATOLOGY FOR SUBTROPICAL SOUTHERN AFRICA - P. D. TYSON; M. GARSTANG; R. SWAP; P. KÂLLBERG; M. EDWARDS (International Journal of Climatology, 1996)

AN AIR TRANSPORT CLIMATOLOGY FOR SUBTROPICAL SOUTHERN AFRICA - P. D. TYSON; M. GARSTANG; R. SWAP; P. KÂLLBERG; M. EDWARDS (International Journal of Climatology, 1996)

Elevated serum silicon levels in women with silicone gel breast implants - Suzanne S. Teuber; Robert L. Saunders; Georges M. Halpern; Robert F. Brucker; Victor Conte; Brian D. Goldman; Edward E. Winger; W. Graham Wood; M. Eric Gershwin (Biological Trace Element Research, 1995)

Potato leafroll virus spread in differentially resistant potato cultivars under varying aphid densities - Christina D. DiFonzo; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1995)

Border disease virus: delineation by monoclonal antibodies - D. J. Paton; J. J. Sands; S. Edwards (Archives of Virology, 1994)

Expression and characterisation of equine herpesvirus 1 glycoprotein H using a recombinant baculovirus - E. M. McGowan; M. B. Hayden; S. J. Edwards; D. Pye; D. N. Love; J. M. Whalley (Archives of Virology, 1994)

Cloning of erect, thornless, non-browsed nitrogen fixing trees of Haiti's principal fuelwood species (Prosopis juliflora) - Timothy wojtusik; Peter Felker; Edward J. Russell; Michael D. Benge (Agroforestry Systems, 1993)

Lead exposure from conventional and cottage lead smelting in Jamaica - Thomas D. Matte; J. Peter Figueroa; Stephanie Ostrowski; Gregory Burr; Linnette Jackson-Hunt; Edward L. Baker (Archives of Environmental Contamination and Toxicology, 1991)

Progress in Seed Production Technology - Edward D. Jones (American Journal of Potato Research, 1991)

Behavioral indicators of sublethal toxicity in rainbow trout - Edward E. Little; Richard D. Archeski; Boris A. Flerov; Vera I. Kozlovskaya (Archives of Environmental Contamination and Toxicology, 1990)

The effects of ochratoxin A on postimplantation rat embryos in culture - K. Mayura; John F. Edwards; Elizabeth A. Maull; Timothy D. Phillips (Archives of Environmental Contamination and Toxicology, 1989)

Delayed spatial alternation deficits resulting from perinatal PCB exposure in monkeys - Edward D. Levin; Susan L. Schantz; Robert E. Bowman (Archives of Toxicology, 1988)

Long-term effects of lactational zinc deficiency on bone mineral composition in rats fed a commercially modified Luecke diet - Curtiss D. Hunt; Edward S. Halas; Marilou J. Eberhardt (Biological Trace Element Research, 1988)

A current assessment ofin vitro culture and other rapid multiplication methods in North America and Europe - Edward D. Jones (American Journal of Potato Research, 1988)

Comparison of three potato leafroll virus antisera and a single Beet western yellows virus antiserum for luteovirus detection in potato - Dale J. Gallenberg; Thomas A. Zitter; Edward D. Jones (American Journal of Potato Research, 1987)

Life members announced - Paul J. Eastman; Raymon E. Webb; Edward F. Johnston; Franklin E. Manzer; Edward D. Jones (American Journal of Potato Research, 1984)

Evolutionary relationships of superoxide dismutases and glutamine synthetases from marine species of Alteromonas, Oceanospirillum, Pseudomonas and Deleya - Edward F. DeLong; Linda Baumann; Ron D. Bowditch; Paul Baumann (Archives of Microbiology, 1984)

Life Members announced - Robert Thornton; Edward D. Jones; Melvin Rominsky (American Journal of Potato Research, 1983)

Identification and quantification of water-soluble hydrocarbons generated by two-cycle outboard motors - W. Edward Montz; Robert L. Puyear; James D. Brammer (Archives of Environmental Contamination and Toxicology, 1982)

The genetics and biochemistry of urease in Ustilago violacea - Michael L. Baird; Edward D. Garber (Biochemical Genetics, 1981)

An assessment of growth yields and energy coupling inDesulfovibrio - Edward L. Magee; Burt D. Ensley; Larry L. Barton (Archives of Microbiology, 1978)

Minutes Meeting of The Potato Pathology Section business meeting, Stevens Point, Wisconsin July 27, 1976 - Edward D. Jones (American Journal of Potato Research, 1978)

Minutes Potato Pathology Section of The Potato Association of America 1977 Winter meeting, Bloomington, Minnesota February 16, 1977 - Edward D. Jones (American Journal of Potato Research, 1978)

Potassium hydroxide for peeling potatoes - P. Muneta; Wu-Wei Shen; S. Jennings; D. Everson; L. Edwards (American Journal of Potato Research, 1977)

Fourth Annual Seed Potato Certification Conference - Edward D. Jones (American Journal of Potato Research, 1971)

Frank L. Clark honored - Edward D. Jones (American Journal of Potato Research, 1970)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

Potato virus-S in oregon - Edward K. Vaughan; D. H. M. van Slogteren (American Journal of Potato Research, 1956)